Administering analgesia sublingually is a suitable option for children with acute abdominal pain in the emergency department. - Cozzi, Giorgio; Zanchi, Chiara; Chiaretti, Antonio; Tipo, Vincenzo; Cernich, Marta; D'Anna, Carolina; Fantacci, Claudia; Conversano, Ester; Zanon, Davide; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2019)
AIM: Acute abdominal pain is a frequent complaint in children attending emergency departments. The aim of this study was to investigate the pain score reductions when children with acute abdominal pain received medication sublingually. METHODS: We carried out a multicentre randomised controlled trial in three children's hospitals in Italy between March 2015 and June 2017. Children from four to 18 years of age with acute abdominal pain were recruited if their self-reported pain was at least six on a scale from 0-10. The children were randomised to receive ketorolac 0.5 mg/kg (n = 70) or tramadol 2 mg/kg (n = 70) sublingually or a melt in the mouth powder of 20 mg/kg paracetamol (n = 70). The main study outcome was the pain scores for the three drugs after two hours. RESULTS: The 210 children (58.6% girls) had a median age of 12 years with an interquartile range of 9-14.3. The median pain scores at two hours were not significantly different between ketorolac 2.0 (interquartile ranges, IQR 0.0-4.3) and tramadol 3.0 (IQR 1.0-5.0) vs paracetamol 3.0 (IQR 0.8-5.0). The median pain reductions were all 5.0 points. CONCLUSION: Delivering analgesia sublingually was a suitable option for pain relief in children with acute abdominal pain in the emergency department.

Antibodies reacting to mimotopes of Simian virus 40 large T antigen, the viral oncoprotein, in sera from children. - Mazzoni, Elisa; Frontini, Francesca; Rotondo, John Charles; Zanotta, Nunzia; Fioravanti, Arianna; Minelli, Francesca; Torreggiani, Elena; Campisciano, Giuseppina; Marcuzzi, Annalisa; Guerra, Giovanni; Tommasini, Alberto; Touzé, Antoine; et al. (J Cell Physiol, 2019)
Recent data indicate that the Simian virus 40 (SV40) infection appears to be transmitted in humans independently from early SV40-contaminated antipolio vaccines. Serum antibodies against SV40 large T antigen (Tag) were analyzed in children/adolescents and young adults. To investigate antibodies reacting to SV40 Tag antigens, serum samples ( n = 812) from children and young adults were analyzed by indirect ELISAs using specific SV40 Tag mimotopes. Mimotopes were synthetic peptides corresponding to SV40 Tag epitopes. In sera ( n = 412) from healthy children up to 17 years old, IgG antibodies against SV40 Tag mimotopes reached an overall prevalence of 15%. IgM antibodies against SV40 Tag were detected in sera of children 6-8 months old confirming and extending the knowledge that SV40 seroconversion occurs early in life. In children/adolescents affected by different diseases ( n = 180) SV40 Tag had a prevalence of 18%, being the difference no significant compared to healthy subjects ( n = 220; 16%) of the same age. Our immunological data indicate that SV40 circulates in children and young adults, both in healthy conditions and affected by distinct diseases. The IgM detection in sera from healthy children suggests that the SV40 infection/seroconversion occurs early in life (>6 months). Our immunological data support the hypothesis that SV40, or a closely related still unknown polyomavirus, infects humans. The SV40 seroprevalence is lower than common polyomaviruses, such as BKPyV and JCPyV, and other new human polyomaviruses. In addition, our immunological surveillance indicates a lack of association between different diseases, considered herein, and SV40.

Causes of Treatment Failure in Children With Inflammatory Bowel Disease Treated With Infliximab: A Pharmacokinetic Study. - Naviglio, Samuele; Lacorte, Doriana; Lucafò, Marianna; Cifù, Adriana; Favretto, Diego; Cuzzoni, Eva; Silvestri, Tania; Pozzi Mucelli, Martina; Radillo, Oriano; Decorti, Giuliana; Fabris, Martina; Bramuzzo, Matteo; et al. (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Anti-tumor necrosis factor antibodies have led to a revolution in the treatment of inflammatory bowel diseases (IBD); however, a sizable proportion of patients does not respond to therapy. There is increasing evidence suggesting that treatment failure may be classified as mechanistic (pharmacodynamic), pharmacokinetic, or immune-mediated. Data regarding the contribution of these factors in children with IBD treated with infliximab (IFX) are still incomplete. The aim was to assess the causes of treatment failure in a prospective cohort of pediatric patients treated with IFX. METHODS: This observational study considered 49 pediatric (median age 14.4) IBD patients (34 Crohn disease, 15 ulcerative colitis) treated with IFX. Serum samples were collected at 6, 14, 22 and 54 weeks, before IFX infusions. IFX and anti-infliximab antibodies (AIA) were measured using enzyme linked immunosorbent assays. Disease activity was determined by Pediatric Crohn's Disease Activity Index or Pediatric Ulcerative Colitis Activity Index. RESULTS: Clinical remission, defined as a clinical score <10, was obtained by 76.3% of patients at week 14 and by 73.9% at week 54. Median trough IFX concentration was higher at all time points in patients achieving sustained clinical remission. IFX levels during maintenance correlated also with C-reactive protein, albumin, and fecal calprotectin. After multivariate analysis, IFX concentration at week 14 >3.11 μg/mL emerged as the strongest predictor of sustained clinical remission. AIA concentrations were correlated inversely with IFX concentrations and directly with adverse reactions. CONCLUSIONS: Most cases of therapeutic failure were associated with low serum drug levels. IFX trough levels at the end of induction are associated with sustained long-term response.

First urinary tract infections in children: the role of the risk factors proposed by the Italian recommendations. - Alberici, I; La Manna, A; Pennesi, M; Starc, M; Scozzola, F; Nicolini, G; Toffolo, A; Marra, G; Chimenz, R; Sica, F; Maringhini, S; Monasta, L; et al. (Acta Paediatr, 2019)
AIM: In 2009, the Italian society for paediatric nephrology suggested the need for cystography, following a first febrile urinary tract infection (UTI), only in children at high risk for dilating vesicoureteral reflux or in the event of a second infection. The aim of this study was to evaluate the adequacy of the risk factors proposed by the Italian guidelines. METHODS: Children aged 2-36 months, managed by 10 Italian hospitals between 2009 and 2013, with a first febrile UTI were retrospectively evaluated. RESULTS: Four hundred and fourteen children were included: 51% female, mean age eight months. Escherichia coli was responsible of 84% UTIs. 269 children (65%) presented at least one risk factor, thus were further investigated: 44% had a reflux. The presence of a pathogen other than E. coli significantly predicted high-grade reflux, both in the univariate (Odd Ratio 2.52, 95% Confidence Interval 1.32-4.81, p < 0.005) and multivariate analysis (OR 2.74, 95% CI: 1.39-5.41, p: 0.003). 26/145 children (18%) with no risk factors experienced a second UTI, which prompted the execution of cystography, showing a dilating reflux in 11. CONCLUSION: Among the risk factors proposed by the Italian guidelines, only the presence of a pathogen other than E. coli significantly predicted reflux. Cystography can be postponed in children with no risk factors.

Four-miRNA Signature to Identify Asbestos-Related Lung Malignancies. - Santarelli, Lory; Gaetani, Simona; Monaco, Federica; Bracci, Massimo; Valentino, Matteo; Amati, Monica; Rubini, Corrado; Sabbatini, Armando; Pasquini, Ernesto; Zanotta, Nunzia; Comar, Manola; Neuzil, Jiri; et al. (Cancer Epidemiol Biomarkers Prev, 2019)
BACKGROUND: Altered miRNA expression is an early event upon exposure to occupational/environmental carcinogens; thus, identification of a novel asbestos-related profile of miRNAs able to distinguish asbestos-induced cancer from cancer with different etiology can be useful for diagnosis. We therefore performed a study to identify miRNAs associated with asbestos-induced malignancies. METHODS: Four groups of patients were included in the study, including patients with asbestos-related (NSCLC) and asbestos-unrelated non-small cell lung cancer (NSCLC) or with malignant pleural mesothelioma (MPM), and disease-free subjects (CTRL). The selected miRNAs were evaluated in asbestos-exposed population. RESULTS: Four serum miRNAs, that is miR-126, miR-205, miR-222, and miR-520g, were found to be implicated in asbestos-related malignant diseases. Notably, increased expression of miR-126 and miR-222 were found in asbestos-exposed subjects, and both miRNAs are involved in major pathways linked to cancer development. Epigenetic changes and cancer-stroma cross-talk could induce repression of miR-126 to facilitate tumor formation, angiogenesis, and invasion. CONCLUSIONS: This study indicates that miRNAs are potentially involved in asbestos-related malignancies, and their expression outlines mechanism(s) whereby miRNAs may be involved in an asbestos-induced pathogenesis. IMPACT: The discovery of a miRNA panel for asbestos-related malignancies would impact on occupational compensation and may be utilized for screening asbestos-exposed populations.

Gadolinium tissue deposition in the periodontal ligament of mice with reduced renal function exposed to Gd-based contrast agents. - Delfino, Riccarda; Biasotto, Matteo; Candido, Riccardo; Altissimo, Matteo; Stebel, Marco; Salomè, Murielle; van Elteren, Johannes T; Vogel Mikuš, Katarina; Zennaro, Cristina; Šala, Martin; Addobbati, Riccardo; Tromba, Giuliana; et al. (Toxicol Lett, 2019)
Gadolinium deposition in tissue is linked to nephrogenic systemic fibrosis (NSF): a rare disorder occurring in patients with severe chronic kidney disease and associated with administration of Gd-based contrast agents (GBCAs) for Magnetic Resonance Imaging (MRI). It is suggested that the GBCAs prolonged permanence in blood in these patients may result in a Gd precipitation in peripheral or central organs, where it initiates a fibrotic process. In this study we investigated new sites of retention/precipitation of Gd in a mouse model of renal disease (5/6 nephrectomy) receiving two doses (closely after each other) of a linear GBCA. Two commercial GBCAs (Omniscan® and Magnevist®) were administered at doses slightly higher than those used in clinical practice (0.7 mmol/kg body weight, each). The animals were sacrificed one month after the last administration and the explanted organs (kidney, liver, femur, dorsal skin, teeth) were analysed by X-ray fluorescence (XRF) at two synchrotron facilities. The XRF analysis with a millimetre-sized beam at the SYRMEP beamline (Elettra, Italy) produced no detectable levels of Gd in the examined tissues, with the notable exception of the incisors of the nephrectomised mice. The XRF analyses at sub-micron resolution performed at ID21 (ESRF, France) allowed to clearly localize Gd in the periodontal ligaments of teeth both from Omniscan® and Magnevist® treated nephrectomised mice. The latter results were further confirmed by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The study prompts that prolonged permanence of GBCAs in blood may result in Gd retention in this particular muscular tissue, opening possibilities for diagnostic applications at this level when investigating Gd-related toxicities.
Keywords: Animals; Contrast Media; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gadolinium; Gadolinium DTPA; Magnetic Resonance Imaging; Mice; Nephrogenic Fibrosing Dermopathy; Periodontal Ligament; Renal Insufficiency; Tissue Distribution

Idiopathic neutropenia of infancy: Data from the Italian Neutropenia Registry. - Farruggia, Piero; Fioredda, Francesca; Puccio, Giuseppe; Onofrillo, Daniela; Russo, Giovanna; Barone, Angelica; Bonanomi, Sonia; Boscarol, Gianluca; Finocchi, Andrea; Ghilardi, Roberta; Giordano, Paola; Ladogana, Saverio; et al. (Am J Hematol, 2019)
Autoimmune neutropenia of infancy (AIN) is characterized by low risk of severe infection, tendency to spontaneously resolve and typically onset at ≤4-5 years of age; it is due to auto-antibodies whose detection is often difficult. In case of negativity of 4 antineutrophils autoantibody tests, after having excluded ethnic, postinfection, drug induced, or congenital neutropenia, according to the Italian guidelines the patients will be defined as affected by "idiopathic neutropenia" (IN). We describe the characteristics of 85 IN patients enrolled in the Italian neutropenia registry: they were compared with 336 children affected by AIN. The 2 groups were clinically very similar and the main differences were detection age (later in IN), length of disease (longer in IN) and, among recovered patients, age of spontaneous recovery: the median age at resolution was 2.13 years in AINs and 3.03 years in INs (P = .00002). At bivariate analysis among AIN patients earlier detection age (P = .00013), male sex (P = .000748), absence of leucopenia (P = .0045), and absence of monocytosis (P = .0419) were significantly associated with earlier recovery; in the IN group only detection age (P = .013) and absence of monocytosis (P = .0333) were significant. At multivariate analysis detection age and absence of monocytosis were independently significant (P = 6.7e-05 and 4.4e-03, respectively) in the AIN group, whereas in the IN group only detection age stayed significant (P = .013).

Prevalence and phenotype of the c.1529C>T SPG7 variant in adult-onset cerebellar ataxia in Italy. - Mancini, C; Giorgio, E; Rubegni, A; Pradotto, L; Bagnoli, S; Rubino, E; Prontera, P; Cavalieri, S; Di Gregorio, E; Ferrero, M; Pozzi, E; Riberi, E; et al. (Eur J Neurol, 2019)
BACKGROUND AND PURPOSE: Hereditary ataxias are heterogeneous groups of neurodegenerative disorders, characterized by cerebellar syndromes associated with dysarthria, oculomotor and corticospinal signs, neuropathy and cognitive impairment. Recent reports have suggested mutations in the SPG7 gene, causing the most common form of autosomal recessive spastic paraplegia (MIM#607259), as a main cause of ataxias. The majority of described patients were homozygotes or compound heterozygotes for the c.1529C>T (p.Ala510Val) change. We screened a cohort of 895 Italian patients with ataxia for p.Ala510Val in order to define the prevalence and genotype-phenotype correlation of this variant. METHODS: We set up a rapid assay for c.1529C>T using restriction enzyme analysis after polymerase chain reaction amplification. We confirmed the diagnosis with Sanger sequencing. RESULTS: We identified eight homozygotes and 13 compound heterozygotes, including two novel variants affecting splicing. Mutated patients showed a pure cerebellar ataxia at onset, evolving in mild spastic ataxia (alternatively) associated with dysarthria (~80% of patients), urinary urgency (~30%) and pyramidal signs (~70%). Comparing homozygotes and compound heterozygotes, we noted a difference in age at onset and Scale for the Assessment and Rating of Ataxia score between the two groups, supporting an earlier and more severe phenotype in compound heterozygotes versus homozygotes. CONCLUSIONS: The SPG7 c.1529C>T (p.Ala510Val) mutants accounted for 2.3% of cerebellar ataxia cases in Italy, suggesting that this variant should be considered as a priority test in the presence of late-onset pure ataxia. Moreover, the heterozygous/homozygous genotype appeared to predict the onset of clinical manifestation and disease progression.

Retrospective study showed that palpitations with tachycardia on admission to a paediatric emergency department were related to cardiac arrhythmias. - Bobbo, Marco; Amoroso, Stefano; Tamaro, Gianluca; Gesuete, Valentina; D'agata Mottolese, Biancamaria; Barbi, Egidio; Ventura, Alessandro (Acta Paediatr, 2019)
AIM: This retrospective study reviewed the prevalence and long-term prognosis of children aged 0-18 with palpitations who were admitted to the emergency department (ED) of an Italian paediatric hospital. METHODS: We examined all admissions to the ED of the IRCCS Burlo Garofolo between January 2009 and December 2015 by selecting triage diagnoses of palpitations. The hospital discharge cards were reviewed to assess vital parameters, physical examinations, diagnostic tests, cardiology consultations and final diagnoses. RESULTS: Of the 142 803 patients who attended our ED for any reason, 96 (0.07%) complained of palpitations. Despite this low prevalence, it was noteworthy that 13.5% had a real underlying arrhythmic cause and needed medical assistance. Over half (52.1%) were women and the mean age was 12.7 years. At the long-term follow-up, at a mean of 47 ± 23 months, 53.8% of patients with a cardiac arrhythmia had received medical therapy and 46.1% had undergone trans-catheter ablation for supraventricular tachycardia. A heart rate above 146 beats per minute or palpitations for more than an hour was statistically related to a cardiac arrhythmia. CONCLUSION: Palpitations were an infrequent cause of admission to our ED, but 13.5% who displayed them had an underlying cardiac arrhythmia.

Activation of hepatic stem cells compartment during hepatocarcinogenesis in a HBsAg HBV-transgenic mouse model. - Anfuso, Beatrice; El-Khobar, Korri E; Ie, Susan I; Avellini, Claudio; Radillo, Oriano; Raseni, Alan; Tiribelli, Claudio; Sukowati, Caecilia H C (Sci Rep, 2018)
Chronic infection of Hepatitis B Virus (HBV) is one of the highest risk factors of hepatocellular carcinoma (HCC). The accumulation of HBV surface antigen (HBsAg) into hepatocytes induces inflammation and oxidative stress, impairing their replicative ability and allowing the activation of the hepatic stem cells (SC) compartment. This study aimed to understand the involvement of SC during hepatocarcinogenesis in HBsAg-related liver damage, from early injury until HCC. HBsAg-transgenic (TG) and wild type (WT) mouse were followed at several stages of the liver damage: inflammation, early hepatocytes damage, dysplasia, and HCC. Serum transaminases, liver histology, and diagnostic data were collected. The expressions of SC and cancer stem cells (CSC) markers was analyzed by RT-qPCR, immunohistochemistry and Western blot. Starting from 3 months, TG animals showed a progressive liver damage characterized by transaminases increase. The up-regulations of SCs markers Cd34 and Sca-1 started from the beginning of the inflammatory stage while progressive increase of Krt19 and Sox9 and CSCs markers Epcam and Cd133 from early hepatic injury. The expressions of Cd133, Cd34, and Afp were significantly higher in HCC compared to paired non-HCC tissue, in contrast to Epcam and Krt19. Western blot and IHC confirmed the positivity of Cd34 and Cd133 in small cells subpopulation.

Alendronate treatment induces IL-1B expression and apoptosis in glioblastoma cell line. - Tricarico, Paola Maura; Epate, Angeladine; Celsi, Fulvio; Crovella, Sergio (Inflammopharmacology, 2018)
Alendronate (ALD), one among the nitrogen-containing bisphosphonates (NBPs), is currently used for the treatment of many pathological conditions. Unfortunately, although generally tolerated, NBPs treatment has been associated with central nervous system (CNS) adverse outcomes, such as amnesia, hallucinations and visual disturbances. So, we analyzed the effect of ALD treatment in glial cells, the main sources of cholesterol for neurons and principal cells involved in the immunological defense of the brain. We treated a glial cell line (U87-MG) with increasing doses of ALD (0.1, 1, 10, 25, 50 μM) for 48 h, aimed at evaluating the influence of this drug treatment on IL-1B expression, NLRP3 and CASP1 expression, mitochondrial activity and apoptotic cell death. We observed that ALD treatment, at the higher concentrations, induced a significant increase of IL-1B, NLRP3, CASP1 expression, provoked apoptosis and also mitochondrial damage in U87-MG. Considering the reported CNS adverse outcomes of NBPs treatment, our results confirm ALD side-effects on glial cell model.
Keywords: Alendronate; Apoptosis; Brain; Cell Line, Tumor; Diphosphonates; Glioblastoma; Humans; Interleukin-1beta; Neuroglia

Antibody response to polyomavirus primary infection: high seroprevalence of Merkel cell polyomavirus and lymphoid tissue involvement. - Cason, Carolina; Monasta, Lorenzo; Zanotta, Nunzia; Campisciano, Giuseppina; Maestri, Iva; Tommasino, Massimo; Pawlita, Michael; Villani, Sonia; Comar, Manola; Delbue, Serena (J Neurovirol, 2018)
Human polyomaviruses (HPyVs) asymptomatically infect the human population establishing latency in the host, and their seroprevalence can reach 90% in healthy adults. Few studies have focused on the pediatric population, and there are no reports regarding the seroprevalence of all the newly isolated HPyVs among Italian children. Therefore, we investigated the frequency of serum antibodies against 12 PyVs in 182 immunocompetent children from Northeast Italy, by means of a multiplex antibody detection system. Additionally, secondary lymphoid tissues were collected to analyze the presence of HPyV DNA sequences using a specific real-time PCRs or PCRs. Almost 100% of subjects were seropositive for at least one PyV. Seropositivity ranged from 3% for antibodies against simian virus 40 (SV40) in children from 0 to 3 years, to 91% for antibodies against WU polyomavirus (WUPyV) and HPyV10 in children from 8 to 17 years. The mean number of PyV for which children were seropositive increased with the increasing of age: 4 standard deviations (SD) 1.8 in the 0-3-year group, 5 (SD 1.9) in the 4-7-year group, and 6 (SD 2.2) in the 8-17-year group. JC polyomavirus (JCPyV) DNA was detected in 1% of the adenoids, WUPyV in 12% of the tonsils, and 28% of the adenoids, and Merkel cell polyomavirus (MCPyV) was present in 6 and 2% of the tonsils and adenoids, respectively. Our study gives new insights on the serological evidence of exposure to PyVs during childhood, and on their possible respiratory route of transmission.

Are aortic coarctation and rheumatoid arthritis different models of aortic stiffness? Data from an echocardiographic study. - Faganello, Giorgio; Cioffi, Giovanni; Rossini, Maurizio; Ognibeni, Federica; Giollo, Alessandro; Fisicaro, Maurizio; Russo, Giulia; Di Nora, Concetta; Doimo, Sara; Tarantini, Luigi; Mazzone, Carmine; Cherubini, Antonella; et al. (Cardiovasc Ultrasound, 2018)
BACKGROUND: Patients who underwent a successful repair of the aortic coarctation (CoA) show high risk for cardiovascular (CV) events. Mechanical and structural abnormalities in the ascending aorta (Ao) might have a role in the prognosis of CoA patients. We analyzed the elastic properties of Ao measured as aortic stiffness index (AoSI) in CoA patients in the long-term period and we compared AoSI with a cohort of 38 patients with rheumatoid arthritis (RA) and 38 non-RA matched controls. METHODS: Data from 19 CoA patients were analyzed 28 ± 13 years after surgery. Abnormally high AoSI was diagnosed if AoSI > 6.07% (95th percentile of the AoSI detected in our reference healthy population). AoSI was assessed at the level of the aortic root by two-dimensional guided M-mode evaluation. RESULTS: CoA patients showed more than two-fold higher AoSI compared to RA and controls (9.8 ± 12.6 vs 4.8 ± 2.5% and 3.1 ± 2.0%, respectively; all p < 0.05 and in 5 of 19 patients with CoA (26%) AoSI was exceptionally high. The 5 patients with abnormally high AoSI were older with higher BP, LV mass and prevalence of LV diastolic dysfunction. Multiple linear regression analysis revealed that AoSI was independently related to the presence of LV hypertrophy and higher LV relative wall thickness. CONCLUSIONS: CoA patients have higher AoSI levels than RA patients and non-RA matched controls. AoSI levels are abnormally high in a small sub-group of CoA patients who show a very high-risk clinical profile for adverse CV events.
Keywords: Aorta; Aortic Coarctation; Arthritis, Rheumatoid; Humans; Prognosis; Vascular Stiffness

Cell-autonomous and cell non-autonomous downregulation of tumor suppressor DAB2IP by microRNA-149-3p promotes aggressiveness of cancer cells. - Bellazzo, Arianna; Di Minin, Giulio; Valentino, Elena; Sicari, Daria; Torre, Denis; Marchionni, Luigi; Serpi, Federica; Stadler, Michael B; Taverna, Daniela; Zuccolotto, Gaia; Montagner, Isabella Monia; Rosato, Antonio; et al. (Cell Death Differ, 2018)
The tumor suppressor DAB2IP contributes to modulate the network of information established between cancer cells and tumor microenvironment. Epigenetic and post-transcriptional inactivation of this protein is commonly observed in multiple human malignancies, and can potentially favor progression of tumors driven by a variety of genetic mutations. Performing a high-throughput screening of a large collection of human microRNA mimics, we identified miR-149-3p as a negative post-transcriptional modulator of DAB2IP. By efficiently downregulating DAB2IP, this miRNA enhances cancer cell motility and invasiveness, facilitating activation of NF-kB signaling and promoting expression of pro-inflammatory and pro-angiogenic factors. In addition, we found that miR-149-3p secreted by prostate cancer cells induces DAB2IP downregulation in recipient vascular endothelial cells, stimulating their proliferation and motility, thus potentially remodeling the tumor microenvironment. Finally, we found that inhibition of endogenous miR-149-3p restores DAB2IP activity and efficiently reduces tumor growth and dissemination of malignant cells. These observations suggest that miR-149-3p can promote cancer progression via coordinated inhibition of DAB2IP in tumor cells and in stromal cells.

Cerebrospinal Fluid Cytokine Expression Profile in Multiple Sclerosis and Chronic Inflammatory Demyelinating Polyneuropathy. - Bonin, Serena; Zanotta, Nunzia; Sartori, Arianna; Bratina, Alessio; Manganotti, Paolo; Trevisan, Giusto; Comar, Manola (Immunol Invest, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) analysis in patients with particular neurologic disorders is a powerful tool to evaluate specific central nervous system inflammatory markers for diagnostic needs, because CSF represents the specific immune micro-environment to the central nervous system. METHODS: CSF samples from 49 patients with multiple sclerosis (MS), chronic inflammatory demyelinating polyneuropathy (CIDP), and non-inflammatory neurologic disorders (NIND) as controls were submitted to protein expression profiles of 47 inflammatory biomarkers by multiplex Luminex bead assay to investigate possible differences in the inflammatory process for MS and CIDP. RESULTS: Our results showed differences in CSF cytokine levels in MS and CIDP; in particular, IL12 (p40) was significantly highly expressed in MS in comparison with CIDP and NIND, while SDF-1α and SCGF-β were significantly highly expressed in CIDP cohort when compared to MS and NIND. IL-9, IL-13, and IL-17 had higher expression levels in NIND if compared with the other groups. CONCLUSIONS: Our study showed that, despite some common pathogenic mechanisms, central and peripheral nervous system demyelinating diseases, such as MS and CIDP, differ in some specific inflammatory soluble proteins in CSF, underlining differences in the immune response involved in those autoimmune diseases.
Keywords: Adult; Aged; Biomarkers; Central Nervous System; Diagnosis, Differential; Female; Hematopoietic Cell Growth Factors; Humans; Interleukin-12; Lectins, C-Type; Male; Middle Aged; Multiple Sclerosis; Peripheral Nervous System; Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; Proteins

Cervical-length measurement in mid-gestation to predict spontaneous preterm birth in asymptomatic triplet pregnancy. - Fichera, A; Pagani, G; Stagnati, V; Cascella, S; Faiola, S; Gaini, C; Lanna, M; Pasquini, L; Raffaelli, R; Stampalija, T; Tommasini, A; Prefumo, F (Ultrasound Obstet Gynecol, 2018)
OBJECTIVE: To assess the predictive value of sonographic cervical-length (CL) measurement in mid-gestation for spontaneous preterm birth (PTB) in asymptomatic triplet pregnancy. METHODS: This was a retrospective study of asymptomatic triplet pregnancies followed at five Italian tertiary referral centers, between 2002 and 2015. CL was measured transvaginally between 18 and 24 weeks' gestation. Pregnancies with medically indicated PTB were excluded. Demographic and pregnancy characteristics of pregnancies complicated by PTB were analyzed and the distributions of CL measurements in these patients were calculated. Logistic regression analysis was performed to assess the association between CL and PTB, adjusted for confounders. Performance of CL measurement in prediction of PTB < 28, < 30 and < 32 weeks of gestation was assessed. RESULTS: A total of 120 triplet pregnancies were included in the final analysis. Median CL was 35 (interquartile range (IQR), 29-40) mm measured at a median gestational age of 20 + 2 (IQR, 20 + 0 to 23 + 4) weeks. Overall, 23 (19.2%), 17 (14.2%) and eight (6.7%) patients had a CL < 25, < 20 and < 15 mm, respectively. Spontaneous PTB < 32 weeks occurred in 41 (34.2%) cases, < 30 weeks in 23 (19.2%) and < 28 weeks in 12 (10%) cases. CL < 15 mm was significantly more frequent in the group of patients who delivered < 28 (P = 0.03) and < 30 (P = 0.01) weeks' gestation, compared with those who delivered after 28 and after 30 weeks, respectively, while CL < 20 mm was more common in triplet pregnancies with delivery < 32 weeks compared with those delivered ≥ 32 weeks (P = 0.03). Logistic regression analysis was possible only for PTB < 32 weeks due to the small number of cases that delivered < 30 and < 28 weeks. After adjustment for confounders, CL was not significantly associated with PTB < 32 weeks (adjusted odds ratio, 0.97; 95% CI, 0.94-1.01). CL measurement had an area under the receiver-operating characteristics curve of 0.41 (95% CI, 0.20-0.62), 0.41 (95% CI, 0.26-0.56) and 0.42 (95% CI, 0.31-0.54) for the prediction of spontaneous PTB < 28, < 30 and < 32 weeks, respectively. CONCLUSION: CL assessed in mid-gestation is a poor predictor of PTB < 28, < 30 and < 32 weeks' gestation in asymptomatic triplet pregnancy. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cervical Length Measurement; Female; Gestational Age; Humans; Infant, Newborn; Logistic Models; Predictive Value of Tests; Pregnancy; Pregnancy, Triplet; Premature Birth; Retrospective Studies

Characterization of multi-locus imprinting disturbances and underlying genetic defects in patients with chromosome 11p15.5 related imprinting disorders. - Fontana, L; Bedeschi, M F; Maitz, S; Cereda, A; Faré, C; Motta, S; Seresini, A; D'Ursi, P; Orro, A; Pecile, V; Calvello, M; Selicorni, A; et al. (Epigenetics, 2018)
The identification of multilocus imprinting disturbances (MLID) appears fundamental to uncover molecular pathways underlying imprinting disorders (IDs) and to complete clinical diagnosis of patients. However, MLID genetic associated mechanisms remain largely unknown. To characterize MLID in Beckwith-Wiedemann (BWS) and Silver-Russell (SRS) syndromes, we profiled by MassARRAY the methylation of 12 imprinted differentially methylated regions (iDMRs) in 21 BWS and 7 SRS patients with chromosome 11p15.5 epimutations. MLID was identified in 50% of BWS and 29% of SRS patients as a maternal hypomethylation syndrome. By next-generation sequencing, we searched for putative MLID-causative mutations in genes involved in methylation establishment/maintenance and found two novel missense mutations possibly causative of MLID: one in NLRP2, affecting ADP binding and protein activity, and one in ZFP42, likely leading to loss of DNA binding specificity. Both variants were paternally inherited. In silico protein modelling allowed to define the functional effect of these mutations. We found that MLID is very frequent in BWS/SRS. In addition, since MLID-BWS patients in our cohort show a peculiar pattern of BWS-associated clinical signs, MLID test could be important for a comprehensive clinical assessment. Finally, we highlighted the possible involvement of ZFP42 variants in MLID development and confirmed NLRP2 as causative locus in BWS-MLID.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Beckwith-Wiedemann Syndrome; Child; Child, Preschool; Chromosomes, Human, Pair 15; DNA Methylation; Female; Genomic Imprinting; Humans; Infant; Kruppel-Like Transcription Factors; Male; Mutation, Missense; Silver-Russell Syndrome; Young Adult

A Child with Diminished Linear Growth and Waddling Gait. - Tamaro, Gianluca; Pederiva, Federica; Dibello, Daniela; Gregori, Massimo; Carbone, Marco; Pantaleoni, Francesca; Dentici, Maria Lisa; Niceta, Marcello; Barbi, Egidio (J Pediatr, 2018)
Keywords: Abnormalities, Multiple; Child; Dwarfism; Female; Gait; Humans; Osteochondrodysplasias; Radiography

The Complex Interplay between Lipids, Immune System and Interleukins in Cardio-Metabolic Diseases. - Bernardi, Stella; Marcuzzi, Annalisa; Piscianz, Elisa; Tommasini, Alberto; Fabris, Bruno (Int J Mol Sci, 2018)
Lipids and inflammation regulate each other. Early studies on this topic focused on the systemic effects that the acute inflammatory response-and interleukins-had on lipid metabolism. Today, in the era of the obesity epidemic, whose primary complications are cardio-metabolic diseases, attention has moved to the effects that the nutritional environment and lipid derangements have on peripheral tissues, where lipotoxicity leads to organ damage through an imbalance of chronic inflammatory responses. After an overview of the effects that acute inflammation has on the systemic lipid metabolism, this review will describe the lipid-induced immune responses that take place in peripheral tissues and lead to chronic cardio-metabolic diseases. Moreover, the anti-inflammatory effects of lipid lowering drugs, as well as the possibility of using anti-inflammatory agents against cardio-metabolic diseases, will be discussed.
Keywords: Anti-Inflammatory Agents; Cardiovascular Diseases; Humans; Hypolipidemic Agents; Immune System; Inflammation; Interleukins; Lipid Metabolism; Lipids; Metabolic Diseases

Cooking influence in tolerance acquisition in egg-induced acute food protein enterocolitis syndrome. - Miceli Sopo, S; Romano, A; Bersani, G; Fantacci, C; Badina, L; Longo, G; Monti, G; Viola, S; Tripodi, S; Barilaro, G; Iacono, I D; Caffarelli, C; et al. (Allergol Immunopathol (Madr), 2018)
BACKGROUND: Few studies on the age of resolution of Food Protein Induced Enterocolitis Syndrome (FPIES) induced by solid foods are available. In particular, for FPIES induced by egg, the mean age of tolerance acquisition reported in the literature ranges from 42 to 63 months. OBJECTIVE: We have assessed whether the age of tolerance acquisition in acute egg FPIES varies depending on whether the egg is cooked or raw. METHODS: We conducted a retrospective and multicentric study of children with diagnosis of acute egg FPIES seen in 10 Italian allergy units between July 2003 and October 2017. The collected data regarded sex, presence of other allergic diseases, age of onset of symptoms, kind and severity of symptoms, cooking technique of the ingested egg, outcome of the allergy test, age of tolerance acquisition. RESULTS: Sixty-one children with acute egg FPIES were enrolled, 34 (56%) males and 27 (44%) females. Tolerance to cooked egg has been demonstrated by 47/61 (77%) children at a mean age of 30.2 months. For 32 of them, tolerance to raw egg has been demonstrated at a mean age of 43.9 months. No episodes of severe adverse reaction after baked egg ingestion have been recorded. CONCLUSIONS: It is possible to perform an OFC with baked egg, to verify the possible acquisition of tolerance, at about 30 months of life in children with acute egg FPIES.

Cx26 partial loss causes accelerated presbycusis by redox imbalance and dysregulation of Nfr2 pathway. - Fetoni, Anna Rita; Zorzi, Veronica; Paciello, Fabiola; Ziraldo, Gaia; Peres, Chiara; Raspa, Marcello; Scavizzi, Ferdinando; Salvatore, Anna Maria; Crispino, Giulia; Tognola, Gabriella; Gentile, Giulia; Spampinato, Antonio Gianmaria; et al. (Redox Biol, 2018)
Mutations in GJB2, the gene that encodes connexin 26 (Cx26), are the most common cause of sensorineural hearing impairment. The truncating variant 35delG, which determines a complete loss of Cx26 protein function, is the prevalent GJB2 mutation in several populations. Here, we generated and analyzed Gjb2 mice as a model of heterozygous human carriers of 35delG. Compared to control mice, auditory brainstem responses (ABRs) and distortion product otoacoustic emissions (DPOAEs) worsened over time more rapidly in Gjb2 mice, indicating they were affected by accelerated age-related hearing loss (ARHL), or presbycusis. We linked causally the auditory phenotype of Gjb2 mice to apoptosis and oxidative damage in the cochlear duct, reduced release of glutathione from connexin hemichannels, decreased nutrient delivery to the sensory epithelium via cochlear gap junctions and deregulated expression of genes that are under transcriptional control of the nuclear factor erythroid 2-related factor 2 (Nrf2), a pivotal regulator of tolerance to redox stress. Moreover, a statistically significant genome-wide association with two genes (PRKCE and TGFB1) related to the Nrf2 pathway (p-value < 4 × 10) was detected in a very large cohort of 4091 individuals, originating from Europe, Caucasus and Central Asia, with hearing phenotype (including 1076 presbycusis patients and 1290 healthy matched controls). We conclude that (i) elements of the Nrf2 pathway are essential for hearing maintenance and (ii) their dysfunction may play an important role in the etiopathogenesis of human presbycusis.
Keywords: Animals; Apoptosis; Connexin 26; Female; Gene Deletion; Male; Mice; Mice, Inbred C57BL; NF-E2-Related Factor 2; Oxidation-Reduction; Presbycusis; Signal Transduction

De novo unbalanced translocations have a complex history/aetiology. - Bonaglia, Maria Clara; Kurtas, Nehir Edibe; Errichiello, Edoardo; Bertuzzo, Sara; Beri, Silvana; Mehrjouy, Mana M; Provenzano, Aldesia; Vergani, Debora; Pecile, Vanna; Novara, Francesca; Reho, Paolo; Di Giacomo, Marilena Carmela; et al. (Hum Genet, 2018)
We investigated 52 cases of de novo unbalanced translocations, consisting in a terminally deleted or inverted-duplicated deleted (inv-dup del) 46th chromosome to which the distal portion of another chromosome or its opposite end was transposed. Array CGH, whole-genome sequencing, qPCR, FISH, and trio genotyping were applied. A biparental origin of the deletion and duplication was detected in 6 cases, whereas in 46, both imbalances have the same parental origin. Moreover, the duplicated region was of maternal origin in more than half of the cases, with 25% of them showing two maternal and one paternal haplotype. In all these cases, maternal age was increased. These findings indicate that the primary driver for the occurrence of the de novo unbalanced translocations is a maternal meiotic non-disjunction, followed by partial trisomy rescue of the supernumerary chromosome present in the trisomic zygote. In contrast, asymmetric breakage of a dicentric chromosome, originated either at the meiosis or postzygotically, in which the two resulting chromosomes, one being deleted and the other one inv-dup del, are repaired by telomere capture, appears at the basis of all inv-dup del translocations. Notably, this mechanism also fits with the origin of some simple translocations in which the duplicated region was of paternal origin. In all cases, the signature at the translocation junctions was that of non-homologous end joining (NHEJ) rather than non-allelic homologous recombination (NAHR). Our data imply that there is no risk of recurrence in the following pregnancies for any of the de novo unbalanced translocations we discuss here.
Keywords: DNA End-Joining Repair; Female; Humans; Male; Meiosis; Recombinational DNA Repair; Translocation, Genetic

Does the Application of Heat Gel Pack After Eutectic Mixture of Local Anesthetic Cream Improve Venipuncture or Intravenous Cannulation Success Rate in Children? A Randomized Control Trial. - Schreiber, Silvana; Cozzi, Giorgio; Patti, Giuseppa; Taddio, Andrea; Montico, Marcella; Pierobon, Chiara; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVE: Needle-related procedures are the most common sources of pain for children in the hospital setting. The most used topical anesthetic, eutectic mixture of local anesthetic (EMLA) cream, may cause transient vasoconstriction. It has been postulated that this vasoconstriction may decrease vein visualization. The application of heat gel pack after removal of EMLA cream in the site of venipuncture counteracts the vasoconstriction, improving vein visualization. We assessed using a prospective randomized controlled trial whether the application of heat gel pack increases the needle procedure success rate. The primary study outcome was procedural success rate at the first attempt. METHODS: The study enrolled 400 children, 200 of whom applied heat gel pack after removing EMLA (treatment group) and 200 did not (control group). Procedural success rate at the first attempt, vein perception before procedure, procedural pain, and adverse events were recorded in both groups. RESULTS: Eighty-eight percent of the procedures were successful at the first attempt in the treatment group and 89% in the control group (P = 0.876). Vein perception was not significantly different in the 2 groups (P = 0.081). Pain score after the procedure was similar in the 2 groups. CONCLUSIONS: This study shows that the application of heat gel pack after removal of EMLA cream does not improve venipuncture or intravenous cannulation success rate.
Keywords: Anesthetics, Local; Child; Child, Preschool; Female; Hot Temperature; Humans; Lidocaine; Lidocaine, Prilocaine Drug Combination; Male; Pain; Pain Management; Phlebotomy; Prilocaine; Prospective Studies

Emergency extracorporeal shockwave lithotripsy as opposed to delayed shockwave lithotripsy for the treatment of acute renal colic due to obstructive ureteral stone: a prospective randomized trial. - Bucci, Stefano; Umari, Paolo; Rizzo, Michele; Pavan, Nicola; Liguori, Giovanni; Barbone, Fabio; Trombetta, Carlo (Minerva Urol Nefrol, 2018)
BACKGROUND: The aim of this study was to assess the efficacy of emergency extracorporeal shockwave lithotripsy (eSWL) as first-line treatment in patients with acute colic due to obstructive ureteral stone. METHODS: Seventy-four patients were randomized to emergency SWL within 12 hours (eSWL group) and deferred SWL later than 3 days (dSWL group). Follow-up included ultrasound, KUB (kidney-ureter-bladder) radiography and CT (computed tomography) scan at 24 hours, 7 days, 1 and 3 months from the treatment. When necessary, repeated SWL (re-SWL) or ureteroscopy (auxiliary-URS) was performed. Preoperative and postoperative data were compared and stone free rates (SFR) and efficiency quotients (EQ) were evaluated. Analyses were performed using SAS software. RESULTS: Complete data of 70 patients were collected. 36 underwent eSWL and 34 dSWL. The mean patient age was 48.7. Mean stone size was 9.8 mm (CI 95%: 8.9-10.8). 25 (35.7%) were proximal and 45 (64.3%) distal. Mean SWL energy was 19.2 kV (CI 95%: 18.5-19.9) and mean number of shocks was 2657 (CI 95%: 2513-2802). eSWL patients needs less auxiliary-URS than dSWL patients (13.9% vs. 44.1%, P=0.039) and less re-SWL sessions (8.3% vs. 32.4%, P=0.093). SFR at 24 hours was 52.8% and 11.8% (P<0.001) and the EQ at 3 months was 79.1% and 57.5% in the eSWL and dSWL group respectively. Patients from the dSWL group spent more time in the hospital (2.21 vs. 1.36 days, P=0.046) and complication rates between the two groups were similar. CONCLUSIONS: eSWL is a safe procedure and delivers high SFR even within 24 hours especially for <10 mm stones. It is able to reduce the number of auxiliary procedures and hospitalization.
Keywords: Aged; Calculi; Emergency Medical Services; Female; Humans; Length of Stay; Lithotripsy; Male; Middle Aged; Prospective Studies; Renal Colic; Time-to-Treatment; Tomography, X-Ray Computed; Ureteral Obstruction

Exome-chip meta-analysis identifies novel loci associated with cardiac conduction, including ADAMTS6. - Prins, Bram P; Mead, Timothy J; Brody, Jennifer A; Sveinbjornsson, Gardar; Ntalla, Ioanna; Bihlmeyer, Nathan A; van den Berg, Marten; Bork-Jensen, Jette; Cappellani, Stefania; Van Duijvenboden, Stefan; Klena, Nikolai T; Gabriel, George C; et al. (Genome Biol, 2018)
BACKGROUND: Genome-wide association studies conducted on QRS duration, an electrocardiographic measurement associated with heart failure and sudden cardiac death, have led to novel biological insights into cardiac function. However, the variants identified fall predominantly in non-coding regions and their underlying mechanisms remain unclear. RESULTS: Here, we identify putative functional coding variation associated with changes in the QRS interval duration by combining Illumina HumanExome BeadChip genotype data from 77,898 participants of European ancestry and 7695 of African descent in our discovery cohort, followed by replication in 111,874 individuals of European ancestry from the UK Biobank and deCODE cohorts. We identify ten novel loci, seven within coding regions, including ADAMTS6, significantly associated with QRS duration in gene-based analyses. ADAMTS6 encodes a secreted metalloprotease of currently unknown function. In vitro validation analysis shows that the QRS-associated variants lead to impaired ADAMTS6 secretion and loss-of function analysis in mice demonstrates a previously unappreciated role for ADAMTS6 in connexin 43 gap junction expression, which is essential for myocardial conduction. CONCLUSIONS: Our approach identifies novel coding and non-coding variants underlying ventricular depolarization and provides a possible mechanism for the ADAMTS6-associated conduction changes.
Keywords: ADAMTS Proteins; African Continental Ancestry Group; Animals; Connexin 43; Electrocardiography; European Continental Ancestry Group; Exome; Female; Gene Expression; Gene Expression Profiling; Genetic Loci; Genome-Wide Association Study; Heart Conduction System; Humans; Male; Mice; Middle Aged; Myocardium; Open Reading Frames; Polymorphism, Single Nucleotide; Whole Exome Sequencing

Fecal Calprotectin to Detect Inflammatory Bowel Disease in Juvenile Idiopathic Arthritis. - Ferrara, Giovanna; Pastore, Serena; Sancin, Lara; Torelli, Lucio; Radillo, Oriano; Bramuzzo, Matteo; Bibalo, Chiara; Tommasini, Alberto; Ventura, Alessandro; Taddio, Andrea (J Rheumatol, 2018)
OBJECTIVE: This study aimed to test fecal calprotectin (FC) as a screening tool to identify inflammatory bowel disease (IBD) among patients with juvenile idiopathic arthritis (JIA). METHODS: FC level < 100 g/kg was considered normal. Patients with 2 consecutive FC dosage ≥ 100 g/kg underwent endoscopic evaluation. RESULTS: There were 113 patients with JIA enrolled. FC was raised in 7 patients out of 113. All patients had IBD. In 3/7 patients, high FC levels were the only sign consistent with IBD. CONCLUSION: FC is a useful, economical, and noninvasive diagnostic tool to identify JIA patients with underlying IBD.

Flares After Withdrawal of Biologic Therapies in Juvenile Idiopathic Arthritis: Clinical and Laboratory Correlates of Remission Duration. - Simonini, Gabriele; Ferrara, Giovanna; Pontikaki, Irene; Scoccimarro, Erika; Giani, Teresa; Taddio, Andrea; Meroni, Pier Luigi; Cimaz, Rolando (Arthritis Care Res (Hoboken), 2018)
OBJECTIVE: To assess the time in remission after discontinuing biologic therapy in patients with juvenile idiopathic arthritis (JIA). METHODS: We enrolled 135 patients followed in 3 tertiary-care centers. The primary outcome was to assess, once remission was achieved, the time in remission up to the first flare after discontinuing treatment. Mann-Whitney U test, Wilcoxon's signed rank test for paired samples, chi-square tests, and Fisher's exact test were used to compare data. Pearson's and Spearman's correlation tests were used to determine correlation coefficients for different variables. To identify predictors of outcome, Cox regression model and Kaplan-Meier curves were constructed, each one at the mean of entered covariates. RESULTS: The majority of enrolled patients flared after stopping treatment with biologics (102 of 135, 75.6%) after a median followup time in remission off therapy of 6 months (range 3-109 months). A higher probability of maintaining remission after discontinuing treatment was present in systemic-onset disease compared to the rest of the JIA patients (Mantel-Cox χ = 8.31, P < 0.004). In analysis limited to children with JIA with polyarticular and oligoarticular disease, patients who received biologics >2 years after achieving remission had a higher probability of maintaining such remission off therapy (mean ± SD 18.64 ± 3.3 months versus 11.51 ± 2.7 months [P < 0.009]; Mantel-Cox χ = 9.06, P < 0.002). No other clinical variable was significantly associated with a long-lasting remission. CONCLUSION: Children with oligoarticular and polyarticular JIA who stop treatment before 2 years from remission have a higher chance of relapsing after biologic withdrawal.

Fractional CO laser for genitourinary syndrome of menopause in breast cancer survivors: clinical, immunological, and microbiological aspects. - Becorpi, Angelamaria; Campisciano, Giuseppina; Zanotta, Nunzia; Tredici, Zelinda; Guaschino, Secondo; Petraglia, Felice; Pieralli, Annalisa; Sisti, Giovanni; De Seta, Francesco; Comar, Manola (Lasers Med Sci, 2018)
The composition of vaginal microbiome in menopause and cancer survivor women changes dramatically leading to genitourinary syndrome of menopause (GSM) in up to 70% of patients. Recent reports suggest that laser therapy may be valuable as a not hormonal therapeutic modality. The aim of the present study was to evaluate the effects of fractional CO laser treatment on the vaginal secretory pathway of a large panel of immune mediators, usually implicated in tissue remodeling and inflammation, and on microbiome composition in postmenopausal breast cancer survivors. The Ion Torrent PGM platform and the Luminex Bio-Plex platform were used for microbiome and immune factor analysis. The significant reduction of clinical symptoms and the non-significant changes in vaginal microbiome support the efficacy and safety of laser treatment. Moreover, the high remodeling status in vaginal epithelium is demonstrated by the significant changes in inflammatory and modulatory cytokine patterns. Laser therapy can be used for the treatment of GSM symptoms and does not show any adverse effects. However, further studies will be needed to clarify its long-term efficacy and other effects.
Keywords: Breast Neoplasms; Cancer Survivors; Cytokines; Dyspareunia; Female; Humans; Lasers, Gas; Menopause; Microbiota; Middle Aged; Prospective Studies; Syndrome; Vagina; Vaginal Diseases

Gene discovery and polygenic prediction from a genome-wide association study of educational attainment in 1.1 million individuals. - Lee, James J; Wedow, Robbee; Okbay, Aysu; Kong, Edward; Maghzian, Omeed; Zacher, Meghan; Nguyen-Viet, Tuan Anh; Bowers, Peter; Sidorenko, Julia; Karlsson Linnér, Richard; Fontana, Mark Alan; Kundu, Tushar; et al. (Nat Genet, 2018)
Here we conducted a large-scale genetic association analysis of educational attainment in a sample of approximately 1.1 million individuals and identify 1,271 independent genome-wide-significant SNPs. For the SNPs taken together, we found evidence of heterogeneous effects across environments. The SNPs implicate genes involved in brain-development processes and neuron-to-neuron communication. In a separate analysis of the X chromosome, we identify 10 independent genome-wide-significant SNPs and estimate a SNP heritability of around 0.3% in both men and women, consistent with partial dosage compensation. A joint (multi-phenotype) analysis of educational attainment and three related cognitive phenotypes generates polygenic scores that explain 11-13% of the variance in educational attainment and 7-10% of the variance in cognitive performance. This prediction accuracy substantially increases the utility of polygenic scores as tools in research.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

Genetic profile of patients with early onset inflammatory bowel disease. - Girardelli, Martina; Basaldella, Federica; Paolera, Sara Della; Vuch, Josef; Tommasini, Alberto; Martelossi, Stefano; Crovella, Sergio; Bianco, Anna Monica (Gene, 2018)
Inflammatory Bowel disease (IBD) is a widespread pathological condition with clinical heterogeneity and with different levels of severity. Although IBD usually occurs in young adults, onset in childhood and infancy are described in patients within the 10th and second year of age. By genome-wide association studies and meta-analysis, several genetic loci have been identified associated with an increased risk of developing IBD in Western populations with variants that may alter the normal mucosal immunity in the gastrointestinal tract. The clinical complexity and the heterogeneity of the IBD phenotype probably reflect the presence of genetic heterogeneity where different genes or combinations of them may be involved, together with environmental factors. We hypothesized that patients with early onset IBD could have either more severe genetic variants in genes associated with IBD or multiple variants in different genes. Under the multifactorial diseases is crucial to consider the small contribution of a single variant in all not only to other small variations in the same gene but also in different genes belonging to the same pathway. We performed direct gene sequencing looking for 94 variations in NOD2, ATG16L1, IL23R, IL10R, IL10 and XIAP genes previously shown as correlated with IBD both in multifactorial and in Mendelian models. All variants identified are known in literature as being associated with IBD except for three variants in the genes NOD2, IL10 and IL10RB that even though present in online databases have never been involved in association studies on IBD patients. Moreover, we coupled genetic variants identification with an accurate "in silico" analysis to verify their predictive impact on the protein structure and function. The in-silico prediction of these variants results as benign therefore even if they exhibit a very low frequency in control population being benign, they cannot be considered pathogenic as monogenic disease but fall within the multifactorial range. The variants identified in our study partially reflect the association data described in the literature but there are no significant differences with the onset of disease (VEO vs EO-IBD).
Keywords: Age of Onset; Autophagy-Related Proteins; Child; Child, Preschool; Computer Simulation; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Infant; Inflammatory Bowel Diseases; Interleukin-10; Male; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Receptors, Interleukin; Receptors, Interleukin-10; Sequence Analysis, DNA; X-Linked Inhibitor of Apoptosis Protein

A genetic variant of NLRP1 gene is associated with asbestos body burden in patients with malignant pleural mesothelioma. - Crovella, S; Moura, R R; Cappellani, S; Celsi, F; Trevisan, E; Schneider, M; Brollo, A; Nicastro, E M; Vita, F; Finotto, L; Zabucchi, G; Borelli, V (J Toxicol Environ Health A, 2018)
The presence of asbestos bodies (ABs) in lung parenchyma is considered a histopathologic hallmark of past exposure to asbestos fibers, of which there was a population of longer fibers. The mechanisms underlying AB formation are complex, involving inflammatory responses and iron (Fe) metabolism. Thus, the responsiveness to AB formation is variable, with some individuals appearing to be poor AB formers. The aim of this study was to disclose the possible role of genetic variants of genes encoding inflammasome and iron metabolism proteins in the ability to form ABs in a population of 81 individuals from North East Italy, who died after having developed malignant pleural mesothelioma (MPM). This study included 86 genetic variants distributed in 10 genes involved in Fe metabolism and 7 genetic variants in two genes encoding for inflammasome molecules. Genotypes/haplotypes were compared according to the number of lung ABs. Data showed that the NLRP1 rs12150220 missense variant (H155L) was significantly correlated with numbers of ABs in MPM patients. Specifically, a low number of ABs was detected in individuals carrying the NLRP1 rs12150220 A/T genotype. Our findings suggest that the NLRP1 inflammasome might contribute in the development of lung ABs. It is postulated that the NLRP1 missense variant may be considered as one of the possible host genetic factors contributing to individual variability in coating efficiency, which needs to be taken when assessing occupational exposure to asbestos.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error. - Tedja, Milly S; Wojciechowski, Robert; Hysi, Pirro G; Eriksson, Nicholas; Furlotte, Nicholas A; Verhoeven, Virginie J M; Iglesias, Adriana I; Meester-Smoor, Magda A; Tompson, Stuart W; Fan, Qiao; Khawaja, Anthony P; Cheng, Ching-Yu; et al. (Nat Genet, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study of corneal astigmatism: The CREAM Consortium. - Shah, Rupal L; Li, Qing; Zhao, Wanting; Tedja, Milly S; Tideman, J Willem L; Khawaja, Anthony P; Fan, Qiao; Yazar, Seyhan; Williams, Katie M; Verhoeven, Virginie J M; Xie, Jing; Wang, Ya Xing; et al. (Mol Vis, 2018)
Purpose: To identify genes and genetic markers associated with corneal astigmatism. Methods: A meta-analysis of genome-wide association studies (GWASs) of corneal astigmatism undertaken for 14 European ancestry (n=22,250) and 8 Asian ancestry (n=9,120) cohorts was performed by the Consortium for Refractive Error and Myopia. Cases were defined as having >0.75 diopters of corneal astigmatism. Subsequent gene-based and gene-set analyses of the meta-analyzed results of European ancestry cohorts were performed using VEGAS2 and MAGMA software. Additionally, estimates of single nucleotide polymorphism (SNP)-based heritability for corneal and refractive astigmatism and the spherical equivalent were calculated for Europeans using LD score regression. Results: The meta-analysis of all cohorts identified a genome-wide significant locus near the platelet-derived growth factor receptor alpha () gene: top SNP: rs7673984, odds ratio=1.12 (95% CI:1.08-1.16), p=5.55×10. No other genome-wide significant loci were identified in the combined analysis or European/Asian ancestry-specific analyses. Gene-based analysis identified three novel candidate genes for corneal astigmatism in Europeans-claudin-7 (), acid phosphatase 2, lysosomal (), and TNF alpha-induced protein 8 like 3 (). Conclusions: In addition to replicating a previously identified genome-wide significant locus for corneal astigmatism near the gene, gene-based analysis identified three novel candidate genes, , , and , that warrant further investigation to understand their role in the pathogenesis of corneal astigmatism. The much lower number of genetic variants and genes demonstrating an association with corneal astigmatism compared to published spherical equivalent GWAS analyses suggest a greater influence of rare genetic variants, non-additive genetic effects, or environmental factors in the development of astigmatism.
Keywords: Acid Phosphatase; Asian Continental Ancestry Group; Astigmatism; Claudins; Cohort Studies; Cornea; Corneal Diseases; European Continental Ancestry Group; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Odds Ratio; Polymorphism, Single Nucleotide; Receptor, Platelet-Derived Growth Factor alpha; Software

Influence of polymerization time on properties of dual-curing cements in combination with high translucency monolithic zirconia. - Alovisi, Mario; Scotti, Nicola; Comba, Allegra; Manzon, Elena; Farina, Elena; Pasqualini, Damiano; Michelotto Tempesta, Riccardo; Breschi, Lorenzo; Cadenaro, Milena (J Prosthodont Res, 2018)
PURPOSE: The aim of this in vitro study was to assess conversion degree (DC), micro-hardness (MH) and bond strength of two dual-curing resin cements employed under translucent monolithic zirconia irradiated with different time protocols. METHODS: 84 square shaped samples of 1mm thickness were prepared from high translucency zirconia blocks and divided into two groups (n=24) according to the cement employed: (1) Rely-X Ultimate; (2) Panavia SA. Each group was further divided into 3 subgroups (n=8) according to the irradiation time: (a) no light; (b) 20s; (c) 120s. Light curing was performed 60s after the sample was placed on the diamond support of a FT-IR spectrophotometer with a high power multiLED lamp. Final DC% were calculated after 10min. After 24h, Vickers Test on the cement layer was performed. The same protocol was used to lute composite cylinders in order to evaluate microshear bond-strength test. ANOVA and Bonferroni tests were performed to find differences between MH and bond-strength to zirconia, while for DC% the Scheirer-Ray-Hare two-way test was used. RESULTS: The two cements reached higher DC% in subgroup (b) and (c). As concern MH, statistics showed an increase in curing time was able to improve MH significantly. Bond-strength was not affected by irradiation time only for Panavia SA. CONCLUSIONS: The first null hypothesis has to be rejected since DC% and MH of the dual-cements tested were influenced by the curing time. The second null hypothesis is partially rejected since the bond strength was influenced by the curing time only for Rely-X Ultimate.
Keywords: Composite Resins; Dental Bonding; Dental Cements; Hardness; Lansoprazole; Materials Testing; Polymerization; Resins, Synthetic; Spectrophotometry; Time Factors; Zirconium

Intranasal dexmedetomidine, as midazolam-sparing drug, for MRI in preterm neonates. - Bua, Jenny; Massaro, Marta; Cossovel, Francesca; Monasta, Lorenzo; Brovedani, Pierpaolo; Cozzi, Giorgio; Barbi, Egidio; Demarini, Sergio; Travan, Laura (Paediatr Anaesth, 2018)

Joint Data Analysis in Nutritional Epidemiology: Identification of Observational Studies and Minimal Requirements. - Pinart, Mariona; Nimptsch, Katharina; Bouwman, Jildau; Dragsted, Lars O; Yang, Chen; De Cock, Nathalie; Lachat, Carl; Perozzi, Giuditta; Canali, Raffaella; Lombardo, Rosario; D'Archivio, Massimo; Guillaume, Michèle; et al. (J Nutr, 2018)
Background: Joint data analysis from multiple nutrition studies may improve the ability to answer complex questions regarding the role of nutritional status and diet in health and disease. Objective: The objective was to identify nutritional observational studies from partners participating in the European Nutritional Phenotype Assessment and Data Sharing Initiative (ENPADASI) Consortium, as well as minimal requirements for joint data analysis. Methods: A predefined template containing information on study design, exposure measurements (dietary intake, alcohol and tobacco consumption, physical activity, sedentary behavior, anthropometric measures, and sociodemographic and health status), main health-related outcomes, and laboratory measurements (traditional and omics biomarkers) was developed and circulated to those European research groups participating in the ENPADASI under the strategic research area of "diet-related chronic diseases." Information about raw data disposition and metadata sharing was requested. A set of minimal requirements was abstracted from the gathered information. Results: Studies (12 cohort, 12 cross-sectional, and 2 case-control) were identified. Two studies recruited children only and the rest recruited adults. All studies included dietary intake data. Twenty studies collected blood samples. Data on traditional biomarkers were available for 20 studies, of which 17 measured lipoproteins, glucose, and insulin and 13 measured inflammatory biomarkers. Metabolomics, proteomics, and genomics or transcriptomics data were available in 5, 3, and 12 studies, respectively. Although the study authors were willing to share metadata, most refused, were hesitant, or had legal or ethical issues related to sharing raw data. Forty-one descriptors of minimal requirements for the study data were identified to facilitate data integration. Conclusions: Combining study data sets will enable sufficiently powered, refined investigations to increase the knowledge and understanding of the relation between food, nutrition, and human health. Furthermore, the minimal requirements for study data may encourage more efficient secondary usage of existing data and provide sufficient information for researchers to draft future multicenter research proposals in nutrition.
Keywords: Adult; Biomarkers; Blood Glucose; Case-Control Studies; Child; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Diet; Epidemiology; Europe; Genomics; Health Status; Humans; Inflammation; Insulin; Life Style; Lipoproteins; Longitudinal Studies; Metabolomics; Nutritional Status; Observational Studies as Topic; Statistics as Topic

A Klinefelter boy with congenital adrenal hyperplasia: too much or too little androgens? - Zanella, Giada; Tornese, Gianluca; Mascheroni, Elisabetta; Faleschini, Elena; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: The simultaneous occurrence of Klinefelter Syndrome (KS) and Congenital Adrenal Hyperplasia (CAH) is an exceptional event: there are just three case reports (two children and a 51 years old man) describing males affected by both KS and 21OHD (21-hydroxylase deficiency) CAH, the first causing androgen deficiency, the latter leading to androgen excess. CASE REPORT: We report the 4th case of association of KS and CAH in a young man with CAH with good androgen control and with normal secondary sex characteristics, whose Klinefelter syndrome was diagnosed because of reduced testicular volume. He was the first reported case of association of KS and CAH who started androgen replacement therapy in the pubertal age and whose pubertal development was described and followed up step by step. CONCLUSION: In a boy with CAH and small testicular volume, it's important to consider that hypogonadism may be masked by the adrenal androgens excess and a karyotype should be performed once testicular adrenal rests have been ruled out.
Keywords: Adolescent; Adrenal Hyperplasia, Congenital; Androgens; Follow-Up Studies; Hormone Replacement Therapy; Humans; Klinefelter Syndrome; Male; Rare Diseases; Risk Assessment; Testis

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).
Keywords: Blood Pressure; Cohort Studies; Continental Population Groups; Diastole; Epistasis, Genetic; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Smoking; Systole

Long term outcome of eight patients with type 1 Leukocyte Adhesion Deficiency (LAD-1): Not only infections, but high risk of autoimmune complications. - De Rose, Domenico Umberto; Giliani, Silvia; Notarangelo, Lucia Dora; Lougaris, Vassilios; Lanfranchi, Arnalda; Moratto, Daniele; Martire, Baldassarre; Specchia, Fernando; Tommasini, Alberto; Plebani, Alessandro; Badolato, Raffaele (Clin Immunol, 2018)
Leukocyte Adhesion Deficiency type 1 (LAD-1) is a rare primary immunodeficiency due to mutations in the gene encoding for the common β-chain of the β2 integrin family (CD18). Herein, we describe clinical manifestations and long-term complications of eight LAD-1 patients. Four LAD-1 patients were treated with hematopoietic stem cell transplantation (HSCT), while the remaining four, including two with moderate LAD-1 deficiency, received continuous antibiotic prophylaxis. Untreated patients presented numerous infections and autoimmune manifestations. In particular, two of them developed renal and intestinal autoimmune diseases, despite the expression of Beta-2 integrin was partially conserved. Other two LAD-1 patients developed type 1 diabetes and autoimmune cytopenia after HSCT, suggesting that HSCT is effective for preventing infections in LAD-1, but does not prevent the risk of the autoimmune complications.

Lopinavir/Ritonavir Treatment Induces Oxidative Stress and Caspaseindependent Apoptosis in Human Glioblastoma U-87 MG Cell Line. - Gratton, Rossella; Tricarico, Paola Maura; Guimarães, Rafael Lima; Celsi, Fulvio; Crovella, Sergio (Curr HIV Res, 2018)
BACKGROUND: Lopinavir and Ritonavir (LPV/r) treatment is widely used to prevent HIV mother-to-child transmission. Nevertheless, studies related to the impact of these compounds on patients, in particular in the foetus and newborns, are strictly required due to the controversial findings reported in the literature concerning possible neurologic side effects following the administration of these drugs. OBJECTIVES: In our study, we evaluated the impact of LPV/r treatment on the human glioblastoma U- 87 MG cell line. METHODS: In order to evaluate the influence of Lopinavir and Ritonavir in terms of oxidative stress (ROS production), mitochondrial morphology and apoptotic cell death, the latter either in the presence or in the absence of caspase-3 and -9 inhibitors, we treated U-87 MG with increasing doses (0.1-1-10-25-50 µM) of Lopinavir and Ritonavir for 24h, either in single formulation or in combination. ROS production was measured by flow cytometry using H2DCFDA dye, mitochondrial morphology was evaluated using MitoRed dye and apoptotic cell death was monitored by flow cytometry using Annexin V-FITC and Propidium Iodide. RESULTS: We observed that co-treatment with Lopinavir and Ritonavir (25 and 50 µM) promoted a significant increase in ROS production, caused mitochondrial network damage and induced apoptosis in a caspase-independent manner. CONCLUSION: Based on our findings, concordant with others reported in the literature, we hypothesize that LPV/r treatment could not be entirely free from side effects, being aware of the need of validation in in vivo models, necessary to confirm our results.

Low-dose sirolimus in two cousins with autoimmune lymphoproliferative syndrome-associated infection. - Nocerino, Agostino; Valencic, Erica; Loganes, Claudia; Pelos, Giorgio; Tommasini, Alberto (Pediatr Int, 2018)
Keywords: Anti-Bacterial Agents; Autoimmune Lymphoproliferative Syndrome; Child; Child, Preschool; Dose-Response Relationship, Drug; Female; Humans; Immunosuppressive Agents; Infant; Male; Otitis Media; Pneumonia, Bacterial; Sirolimus

MKRN3 levels in girls with central precocious puberty and correlation with sexual hormone levels: a pilot study. - Grandone, Anna; Cirillo, Grazia; Sasso, Marcella; Capristo, Carlo; Tornese, Gianluca; Marzuillo, Pierluigi; Luongo, Caterina; Rosaria Umano, Giuseppina; Festa, Adalgisa; Coppola, Ruggero; Miraglia Del Giudice, Emanuele; Perrone, Laura (Endocrine, 2018)
PURPOSE: Recently, mutations of makorin RING-finger protein 3 (MKRN3) have been described in familial central precocious puberty. Serum levels of this protein decline before the pubertal onset in healthy girls and boys. The aim of the study is to investigate MKRN3 circulating levels in patients with central precocious puberty. METHODS: We performed an observational cross-sectional study. We enrolled 17 patients with central precocious puberty aged 7 years (range: 2-8 years) and breast development onset <8 years; 17 prepubertal control age-matched patients aged 6.3 years (2-8.2); and 10 pubertal stage-matched control patients aged 11.4 years (9-14). Serum values of MKRN3, gonadotropins, (17)estradiol and Anti-Müllerian Hormone were evaluated and the MKRN3 genotyped in central precocious puberty patients. RESULTS: No MKRN3 mutation was found among central precocious puberty patients. MKRN3 levels were lower in patients with central precocious puberty compared to prepubertal age-matched ones (p: 0.0004) and comparable to those matched for pubertal stage. MKRN3 levels were inversely correlated to Body Mass Index Standard Deviations (r:-0.35; p:0.02), Luteinizing Hormone (r:-0.35; p:0.03), FSH (r:-0.37; p:0.02), and (17)estradiol (r: -0.36; p:0.02). CONCLUSIONS: We showed that girls with central precocious puberty had lower peripheral levels of MKRN3 compared to age-matched pairs and that they negatively correlated to gonadotropins, estrogen, and BMI. Our findings support the MKRN3 involvement in central precocious puberty also in absence of deleterious mutations, although our sample size is small. In addition our data suggest the role of MKRN3 in the complex mechanism controlling puberty onset and its interaction with other factors affecting puberty such as nutrition.
Keywords: Adolescent; Adolescent Nutritional Physiological Phenomena; Anti-Mullerian Hormone; Case-Control Studies; Child; Child Nutritional Physiological Phenomena; Child, Preschool; Cross-Sectional Studies; Female; Follicle Stimulating Hormone; Gonadotropin-Releasing Hormone; Humans; Luteinizing Hormone; Pilot Projects; Puberty, Precocious; Ribonucleoproteins; Sexual Maturation

MKRN3 Levels in Girls with Central Precocious Puberty during GnRHa Treatment: A Longitudinal Study. - Grandone, Anna; Cirillo, Grazia; Sasso, Marcella; Tornese, Gianluca; Luongo, Caterina; Festa, Adalgisa; Marzuillo, Pierluigi; Miraglia Del Giudice, Emanuele (Horm Res Paediatr, 2018)
BACKGROUND: Recently, mutations of makorin RING finger protein 3 (MKRN3) have been identified in familial central precocious puberty (CPP). Serum levels of this protein decline before the pubertal onset in healthy girls and boys and are lower in patients with CPP compared to prepubertal matched pairs. The aim of our study was to investigate longitudinal changes in circulating MKRN3 levels in patients with CPP before and during GnRH analogs (GnRHa) treatment. METHODS: We performed a longitudinal prospective study. We enrolled 15 patients with CPP aged 7.2 years (range: 2-8) with age at breast development onset < 8 years and 12 control girls matched for the time from puberty onset (mean age 11.8 ± 1.2 years). Serum values of MKRN3, gonadotropins, and 17β-estradiol were evaluated before and during treatment with GnRHa (at 6 and 12 months). The MKRN3 gene was genotyped in CPP patients. In the girls from the control group, only basal levels were analyzed. RESULTS: No MKRN3 mutations were found among CPP patients. MKRN3 levels declined significantly from baseline to 6 months of GnRHa treatment (p = 0.0007) and from 6 to 12 months of treatment (p = 0.003); MKRN3 levels at 6 months were significantly lower than in the control girls (p < 0.0001). CONCLUSIONS: We showed that girls with CPP had a decline in peripheral levels of MKRN3 during GnRHa treatment. Our data suggest a suppression of MKRN3 by continuous pharmacological administration of GnRHa.
Keywords: Brain Diseases; Case-Control Studies; Child; Child, Preschool; Female; Follicle Stimulating Hormone; Genotype; Gonadotropin-Releasing Hormone; Humans; Longitudinal Studies; Luteinizing Hormone; Male; Puberty, Precocious; Ribonucleoproteins

Neuronal Dysfunction Associated with Cholesterol Deregulation. - Marcuzzi, Annalisa; Loganes, Claudia; Valencic, Erica; Piscianz, Elisa; Monasta, Lorenzo; Bilel, Sabrine; Bortul, Roberta; Celeghini, Claudio; Zweyer, Marina; Tommasini, Alberto (Int J Mol Sci, 2018)
Cholesterol metabolism is crucial for cells and, in particular, its biosynthesis in the central nervous system occurs in situ, and its deregulation involves morphological changes that cause functional variations and trigger programmed cell death. The pathogenesis of rare diseases, such as Mevalonate Kinase Deficiency or Smith⁻Lemli⁻Opitz Syndrome, arises due to enzymatic defects in the cholesterol metabolic pathways, resulting in a shortage of downstream products. The most severe clinical manifestations of these diseases appear as neurological defects. Expanding the knowledge of this biological mechanism will be useful for identifying potential targets and preventing neuronal damage. Several studies have demonstrated that deregulation of the cholesterol pathway induces mitochondrial dysfunction as the result of respiratory chain damage. We set out to determine whether mitochondrial damage may be prevented by using protective mitochondria-targeted compounds, such as MitoQ, in a neuronal cell line treated with a statin to induce a biochemical block of the cholesterol pathway. Evidence from the literature suggests that mitochondria play a crucial role in the apoptotic mechanism secondary to blocking the cholesterol pathway. Our study shows that MitoQ, administered as a preventive agent, could counteract the cell damage induced by statins in the early stages, but its protective role fades over time.
Keywords: Anticholesteremic Agents; Cell Line, Tumor; Cholesterol; Electron Transport; Humans; Lovastatin; Mitochondria; Neurons; Neuroprotective Agents; Organophosphorus Compounds; Ubiquinone

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Pathological Significance and Prognostic Value of Surfactant Protein D in Cancer. - Mangogna, Alessandro; Belmonte, Beatrice; Agostinis, Chiara; Ricci, Giuseppe; Gulino, Alessandro; Ferrara, Ines; Zanconati, Fabrizio; Tripodo, Claudio; Romano, Federico; Kishore, Uday; Bulla, Roberta (Front Immunol, 2018)
Surfactant protein D (SP-D) is a pattern recognition molecule belonging to the Collectin (collagen-containing C-type lectin) family that has pulmonary as well as extra-pulmonary existence. In the lungs, it is a well-established opsonin that can agglutinate a range of microbes, and enhance their clearance phagocytosis and super-oxidative burst. It can interfere with allergen-IgE interaction and suppress basophil and mast cell activation. However, it is now becoming evident that SP-D is likely to be an innate immune surveillance molecule against tumor development. SP-D has been shown to induce apoptosis in sensitized eosinophils derived from allergic patients and a leukemic cell line p53 pathway. Recently, SP-D has been shown to suppress lung cancer progression interference with the epidermal growth factor signaling. In addition, a truncated form of recombinant human SP-D has been reported to induce apoptosis in pancreatic adenocarcinoma Fas-mediated pathway in a p53-independent manner. To further establish a correlation between SP-D presence/levels and normal and cancer tissues, we performed a bioinformatics analysis, using Oncomine dataset and the survival analysis platforms Kaplan-Meier plotter, to assess if SP-D can serve as a potential prognostic marker for human lung cancer, in addition to human gastric, breast, and ovarian cancers. We also analyzed immunohistochemically the presence of SP-D in normal and tumor human tissues. We conclude that (1) in the lung, gastric, and breast cancers, there is a lower expression of SP-D than normal tissues; (2) in ovarian cancer, there is a higher expression of SP-D than normal tissue; and (3) in lung cancer, the presence of SP-D could be associated with a favorable prognosis. On the contrary, at non-pulmonary sites such as gastric, breast, and ovarian cancers, the presence of SP-D could be associated with unfavorable prognosis. Correlation between the levels of SP-D and overall survival requires further investigation. Our analysis involves a large number of dataset; therefore, any trend observed is reliable. Despite apparent complexity within the results, it is evident that cancer tissues that produce less levels of SP-D compared to their normal tissue counterparts are probably less susceptible to SP-D-mediated immune surveillance mechanisms infiltrating immune cells.

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.
Keywords: Atrial Function; Atrioventricular Node; Electrocardiography; Electrophysiological Phenomena; Female; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Mutation, Missense; Risk Factors

Red Flags in Torticollis: A Historical Cohort Study. - Starc, Meta; Norbedo, Stefania; Tubaro, Martina; Ronfani, Luca; Bassanese, Giulia; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVE: This study aimed to assess the spectrum of pathologies responsible for torticollis in children presenting to the emergency department and to evaluate the associated symptoms to determine clinical red flags for hospitalization. METHODS: This was a historical retrospective cohort study. Medical records of children evaluated in our emergency department for torticollis from 2008 to 2013 were reviewed. RESULTS: Among 392 identified patients, 61% had postural torticollis,19.4% infection related, 16.3% traumatic, and 3.5% other. Twenty-five patients (6.4%) were hospitalized. Four variables were strongly and independently related to the severe outcome: fever, sore throat, headache, and age. CONCLUSIONS: The association of 2 or 3 of these 4 features carried a risk of 32% and 58%, respectively, of having a severe illness.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Emergency Service, Hospital; Female; Hospitalization; Humans; Male; Retrospective Studies; Torticollis

Report on an international workshop on kangaroo mother care: lessons learned and a vision for the future. - Cattaneo, Adriano; Amani, Adidja; Charpak, Nathalie; De Leon-Mendoza, Socorro; Moxon, Sarah; Nimbalkar, Somashekhar; Tamburlini, Giorgio; Villegas, Julieta; Bergh, Anne-Marie (BMC Pregnancy Childbirth, 2018)
BACKGROUND: Globally, complications of prematurity are the leading cause of death in children under five. Preterm infants who survive their first month of life are at greater risk for various diseases and impairments in infancy, childhood and later life, representing a heavy social and economic burden for families, communities and health and social systems. Kangaroo mother care (KMC) is recommended as a beneficial and effective intervention for improving short- and long-term preterm birth outcomes in low- and high-income settings. Nevertheless, KMC is not as widely used as it should be. The International Network on KMC runs biennial workshops and congresses to help improve the coverage and quality of KMC worldwide. This paper reports the results of the two-day workshop held in November 2016, where 92 participants from 33 countries shared experiences in a series of round tables, group work sessions and plenaries. FINDINGS: Barriers to and enablers of KMC are discussed with regard to parents, health workers and the health system. Key factors for effective implementation and uptake relate to appropriate training for health staff, adherence to protocols and the creation of a welcoming environment for families. Recommendations for planning for national programmes are made according to a six-stage change model. Resources and the cost of making progress are discussed in terms of investment, maintenance, and acceleration and scaling-up costs. KMC training requirements are presented according to three levels of care. To ensure quality KMC, key requisites are proposed for the different KMC components and for sensitive communication with caregivers. The group attending to the monitoring and evaluation of KMC at a national and subnational level highlight the lack of standard indicator definitions. Key priorities for investment include health services research, harmonisation of indicators, development of a costing tool, programming and scaling up, and the follow-up of preterm infants. CONCLUSION: It is hoped that this report will help to further scale-up and sustain KMC through a systematic approach that includes raising commitment, identifying key strategies to address the main barriers and using existing facilitators, ensuring training and quality, agreeing on indicators for monitoring and evaluation, and advancing implementation research.
Keywords: Education; Education, Nonprofessional; Female; Government Programs; Health Plan Implementation; Humans; Infant; Infant Mortality; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; International Cooperation; Kangaroo-Mother Care Method; Male

Role of the Long Non-Coding RNA Growth Arrest-Specific 5 in Glucocorticoid Response in Children with Inflammatory Bowel Disease. - Lucafò, Marianna; Di Silvestre, Alessia; Romano, Maurizio; Avian, Alice; Antonelli, Roberta; Martelossi, Stefano; Naviglio, Samuele; Tommasini, Alberto; Stocco, Gabriele; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Basic Clin Pharmacol Toxicol, 2018)
Glucocorticoids (GCs) are widely employed in inflammatory, autoimmune and neoplastic diseases, and, despite the introduction of novel therapies, remain the first-line treatment for inducing remission in inflammatory bowel disease (IBD). Given the high incidence of suboptimal response, associated with a significant number of side-effects, that are particularly severe in paediatric patients, the identification of subjects that are most likely to respond poorly to GCs is extremely important. Recent evidence suggests that the long non-coding RNA (lncRNA) GAS5 could be a potential marker of GC resistance. To address this issue, we evaluated the association between the lncRNA GAS5 and the efficacy of steroids, in terms of inhibition of proliferation, in two cell lines derived from colon and ovarian cancers, to confirm the sensitivity and specificity of these lncRNAs. These cells showed a different sensitivity to GCs and revealed differential expression of GAS5 after treatment. GAS5 was up-regulated in GC-resistant cells and accumulated more in the cytoplasm compared to the nucleus in response to the drug. The functions of GAS5 were assessed by silencing, and we found that GAS5 knock-down reduced the proliferation during GC treatment. Furthermore, for the first time, we measured GAS5 levels in 19 paediatric IBD patients at diagnosis and after the first cycle of GCs, and we demonstrated an up-regulation of the lncRNA in patients with unfavourable steroid response. Our preliminary results indicate that GAS5 could be considered a novel pharmacogenomic marker useful for the personalization of GC therapy.
Keywords: Biomarkers; Cell Line, Tumor; Cell Proliferation; Child; Drug Resistance; Female; Gene Knockdown Techniques; Glucocorticoids; Humans; Inflammatory Bowel Diseases; Male; Patient Selection; Pharmacogenomic Testing; Precision Medicine; RNA, Long Noncoding; RNA, Small Interfering; Treatment Outcome; Up-Regulation

Secondary prevention of early-onset sepsis: a less invasive Italian approach for managing neonates at risk. - Berardi, Alberto; Tzialla, Chryssoula; Travan, Laura; Bua, Jenny; Santori, Daniele; Azzalli, Milena; Spada, Caterina; Lucaccioni, Laura (Ital J Pediatr, 2018)
Strategies to prevent early-onset sepsis (EOS) have led to a substantial decline in many countries. However, one of the most controversial topics in neonatology is the management of asymptomatic full-term and late preterm neonates at risk for EOS, and guidelines lack substantial consensus regarding this issue. A strategy for managing neonates, entirely based on serial physical examinations, has been developed in two Italian regions. This strategy seems safe, while reducing laboratory tests and unnecessary antibiotics. In the current commentary we provide area-based data concerning the prevention of EOS in 2 northern Italian regions, and we detail the results of their strategy for managing healthy-appearing newborns at risk for EOS.

Serum Stem Cell Growth Factor Beta for the Prediction of Therapy Response in Hepatocellular Carcinoma. - Sukowati, Caecilia H C; Patti, Riccardo; Pascut, Devis; Ladju, Rusdina B; Tarchi, Paola; Zanotta, Nunzia; Comar, Manola; Tiribelli, Claudio; Crocè, Lory S (Biomed Res Int, 2018)
Introduction: Chronic inflammatory response is one of major contributors in the development of hepatocellular carcinoma (HCC). Inflammatory molecules, such as cytokines and growth factors in the circulation, can be useful in the diagnosis and prognosis of the patients. The stem cell growth factor beta (SCGF), a newly found protein, is a secreted sulfated glycoprotein and it functions as a growth factor for primitive hematopoietic progenitor cells. The level of SCGF had been reported to be elevated in several cancer types. However, there is very few or even no information on this protein in the study of HCC, even more in clinical studies. Methods: A multiplex immunoassay panel of 48 cytokines and growth factors were utilized to screen 68 sera from 29 HCC patients at pretreatment (T0), 1 month (T1), and 6 months (T6) after treatment by either radiofrequency ablation (RF) or transarterial chemoembolization (TACE). Treatment response was evaluated according to mRECIST criteria. Results: Immunoassay screening showed that the levels of IL-17, CTACK, TNF, IL-2R, IL-8, and SCGF were different in Complete Responders (CR) and Nonresponders (NR) groups. At T0 and T1, the SCGF level was significantly the highest in NR (23.8 and 40.7 ng/mL, respectively), followed by early recurrence (25.4 and 25.0 ng/mL), and CR (6.7 and 5.3 ng/mL), independently from HCV, stages, and treatment type. Low basal SCGF level was associated with longer disease-free survival compared to high SCGF. Conclusion: In this study, for the first time, we demonstrate that the high level of serum SCGF at pre- and posttreatment is associated with HCC nonresponsiveness.
Keywords: Aged; Carcinoma, Hepatocellular; Chemoembolization, Therapeutic; Female; Hematopoietic Cell Growth Factors; Humans; Liver Neoplasms; Male; Middle Aged; Neoplasm Recurrence, Local; Retrospective Studies; Stem Cells; Treatment Outcome

Theophylline as a precision therapy in a young girl with PIK3R1 immunodeficiency. - Valencic, Erica; Grasso, Antonio Giacomo; Conversano, Ester; Lucafò, Marianna; Piscianz, Elisa; Gregori, Massimo; Conti, Francesca; Cancrini, Caterina; Tommasini, Alberto (J Allergy Clin Immunol Pract, 2018)

An unusual unilateral breast enlargement in a prepubertal girl. - Pavan, Matteo; Faleschini, Elena; Tornese, Gianluca; Zandonà, Lorenzo; Ventura, Alessandro (Arch Dis Child, 2018)

1000 Genomes-based meta-analysis identifies 10 novel loci for kidney function. - Gorski, Mathias; van der Most, Peter J; Teumer, Alexander; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Nolte, Ilja M; Cocca, Massimiliano; Taliun, Daniel; Gomez, Felicia; Li, Yong; Tayo, Bamidele; et al. (Sci Rep, 2017)
HapMap imputed genome-wide association studies (GWAS) have revealed >50 loci at which common variants with minor allele frequency >5% are associated with kidney function. GWAS using more complete reference sets for imputation, such as those from The 1000 Genomes project, promise to identify novel loci that have been missed by previous efforts. To investigate the value of such a more complete variant catalog, we conducted a GWAS meta-analysis of kidney function based on the estimated glomerular filtration rate (eGFR) in 110,517 European ancestry participants using 1000 Genomes imputed data. We identified 10 novel loci with p-value < 5 × 10 previously missed by HapMap-based GWAS. Six of these loci (HOXD8, ARL15, PIK3R1, EYA4, ASTN2, and EPB41L3) are tagged by common SNPs unique to the 1000 Genomes reference panel. Using pathway analysis, we identified 39 significant (FDR < 0.05) genes and 127 significantly (FDR < 0.05) enriched gene sets, which were missed by our previous analyses. Among those, the 10 identified novel genes are part of pathways of kidney development, carbohydrate metabolism, cardiac septum development and glucose metabolism. These results highlight the utility of re-imputing from denser reference panels, until whole-genome sequencing becomes feasible in large samples.
Keywords: Computational Biology; Gene Frequency; Genetic Loci; Genome, Human; Genome-Wide Association Study; Genotyping Techniques; Humans; Kidney; Polymorphism, Single Nucleotide

46,XY ovotesticular disorders of sex development: A therapeutic challenge. - Scarpa, Maria-Grazia; Grazia, Massimo Di; Tornese, Gianluca (Pediatr Rep, 2017)

ADA2 deficiency (DADA2) as an unrecognised cause of early onset polyarteritis nodosa and stroke: a multicentre national study. - Caorsi, Roberta; Penco, Federica; Grossi, Alice; Insalaco, Antonella; Omenetti, Alessia; Alessio, Maria; Conti, Giovanni; Marchetti, Federico; Picco, Paolo; Tommasini, Alberto; Martino, Silvana; Malattia, Clara; et al. (Ann Rheum Dis, 2017)
OBJECTIVES: To analyse the prevalence of mutations in patients diagnosed with early onset livedo reticularis and/or haemorrhagic/ischaemic strokes in the context of inflammation or polyarteritis nodosa (PAN). Forty-eight patients from 43 families were included in the study. METHODS: Direct sequencing of was performed by Sanger analysis. Adenosine deaminase 2 (ADA2) enzymatic activity was analysed in monocyte isolated from patients and healthy controls incubated with adenosine and with or without an ADA1 inhibitor. RESULTS: Biallelic homozygous or compound heterozygous mutations were detected in 15/48 patients. A heterozygous disease-associated mutation (p.G47V) was observed in two affected brothers. The mean age of onset of the genetically positive patients was 24 months (6 months to 7 years). Ten patients displayed one or more cerebral strokes during their disease course. Low immunoglobulin levels were detected in six patients. Thalidomide and anti-TNF (tumour necrosis factor) blockers were the most effective drugs. Patients without mutations had a later age at disease onset, a lower prevalence of neurological and skin manifestations; one of these patients displayed all the clinical features of adenosine deaminase 2deficiency (DADA2) and a defective enzymatic activity suggesting the presence of a missed mutation or a synthesis defect. CONCLUSIONS: DADA2 accounts for paediatric patients diagnosed with PAN-like disease and strokes and might explain an unrecognised condition in patients followed by adult rheumatologist. Timely diagnosis and treatment with anti-TNF agents are crucial for the prevention of severe complications of the disease. Functional assay to measure ADA2 activity should complement genetic testing in patients with non-confirming genotypes.
Keywords: Adenosine Deaminase; Adolescent; Age of Onset; Case-Control Studies; Child; Child, Preschool; DNA Mutational Analysis; Female; Heterozygote; Homozygote; Humans; Immunoglobulins; Immunosuppressive Agents; Infant; Intercellular Signaling Peptides and Proteins; Italy; Livedo Reticularis; Male; Pedigree; Polyarteritis Nodosa; Stroke; Thalidomide; Tumor Necrosis Factor-alpha; Young Adult

Alternative functions of the complement protein C1q at embryo implantation site. - Agostinis, Chiara; Tedesco, Francesco; Bulla, Roberta (J Reprod Immunol, 2017)
Complement component C1q is one of the recognition molecules of the complement system which can serve several functions unrelated to complement activation. This molecule is produced at foeto-maternal interface by macrophages as wells as by decidual endothelial cells and invading trophoblast. Foetal trophoblast cells migrating through the decidua in the early stages of pregnancy synthesize and express C1q on their surface, which is actively involved in promoting trophoblast endovascular and interstitial invasion of the decidua. These functions are mediated by two cell surface receptors, gC1qR and α4β1 integrin, which promote trophoblast adhesion and migration through the activation of ERK1/2 MAPKs. C1q mice manifest increased frequency of foetal resorption, reduced foetal weight, and smaller litter size when compared to their wild-type counterparts, suggesting that defective local production of C1q may be involved in pregnancy disorders, such as pre-eclampsia. C1q acts also as a strong angiogenic factor and promotes neovascularization. These studies suggest novel and unexpected roles of this complement component in physiological and pathological pregnancies.
Keywords: Animals; Complement C1q; Decidua; Embryo Implantation; Extracellular Signal-Regulated MAP Kinases; Female; Humans; Integrin alpha4beta1; Mice; Mice, Knockout; Neovascularization, Physiologic; Pre-Eclampsia; Pregnancy; Trophoblasts; Vascular Remodeling

Amniocentesis and chorionic villus sampling in HIV-infected pregnant women: a multicentre case series. - Floridia, M; Masuelli, G; Meloni, A; Cetin, I; Tamburrini, E; Cavaliere, A F; Dalzero, S; Sansone, M; Alberico, S; Guerra, B; Spinillo, A; Chiadò Fiorio Tin, M; et al. (BJOG, 2017)
OBJECTIVES: To assess in pregnant women with HIV the rates of amniocentesis and chorionic villus sampling (CVS), and the outcomes associated with such procedures. DESIGN: Observational study. Data from the Italian National Program on Surveillance on Antiretroviral Treatment in Pregnancy were used. SETTING: University and hospital clinics. POPULATION: Pregnant women with HIV. METHODS: Temporal trends were analysed by analysis of variance and by the Chi-square test for trend. Quantitative variables were compared by Student's t-test and categorical data by the Chi-square test, with odds ratios and 95% confidence intervals calculated. MAIN OUTCOME MEASURES: Rate of invasive testing, intrauterine death, HIV transmission. RESULTS: Between 2001 and 2015, among 2065 pregnancies in women with HIV, 113 (5.5%) had invasive tests performed. The procedures were conducted under antiretroviral treatment in 99 cases (87.6%), with a significant increase over time in the proportion of tests performed under highly active antiretroviral therapy (HAART) (100% in 2011-2015). Three intrauterine deaths were observed (2.6%), and 14 pregnancies were terminated because of fetal anomalies. Among 96 live newborns, eight had no information available on HIV status. Among the remaining 88 cases with either amniocentesis (n = 75), CVS (n = 12), or both (n = 1), two HIV transmissions occurred (2.3%). No HIV transmission occurred among the women who were on HAART at the time of invasive testing, and none after 2005. CONCLUSIONS: The findings reinforce the assumption that invasive prenatal testing does not increase the risk of HIV vertical transmission among pregnant women under suppressive antiretroviral treatment. TWEETABLE ABSTRACT: No HIV transmission occurred among women who underwent amniocentesis or CVS under effective anti-HIV regimens.
Keywords: Adult; Amniocentesis; Analysis of Variance; Anti-Retroviral Agents; Chi-Square Distribution; Chorionic Villi Sampling; Female; Fetal Death; HIV Infections; Humans; Infectious Disease Transmission, Vertical; Odds Ratio; Pregnancy; Pregnancy Complications, Infectious

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Antiretroviral Treatment in HIV-1-Positive Mothers: Neurological Implications in Virus-Free Children. - Coelho, Antônio Victor Campos; Tricarico, Paola Maura; Celsi, Fulvio; Crovella, Sergio (Int J Mol Sci, 2017)
Since the worldwide introduction of antiretroviral therapy (ART) in human immunodeficiency virus type 1, HIV-1-positive mothers, together with HIV-1 testing prior to pregnancy, caesarian birth and breastfeeding cessation with replacement feeding, a reduction of HIV-1 mother-to-child transmission (MTCT) has been observed in the last few years. As such, an increasing number of children are being exposed in utero to ART. Several questions have arisen concerning the neurological effects of ART exposure in utero, considering the potential effect of antiretroviral drugs on the central nervous system, a structure which is in continuous development in the fetus and characterized by great plasticity. This review aims at discussing the possible neurological impairment of children exposed to ART in utero, focusing attention on the drugs commonly used for HIV-1 MTCT prevention, clinical reports of ART neurotoxicity in children born to HIV-1-positive mothers, and neurologic effects of protease inhibitors (PIs), especially ritonavir-"boosted" lopinavir (LPV/r) in cell and animal central nervous system models evaluating the potential neurotoxic effect of ART. Finally, we present the findings of a meta-analysis to assess the effects on the neurodevelopment of children exposed to ART in utero.
Keywords: Animals; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Disease Management; Disease Models, Animal; Epigenesis, Genetic; Female; HIV Infections; HIV-1; Humans; Infectious Disease Transmission, Vertical; Maternal Exposure; Meta-Analysis as Topic; Mothers; Neurodevelopmental Disorders; Pregnancy; Prenatal Exposure Delayed Effects

Association between thyroid hormones and TRAIL. - Bernardi, Stella; Bossi, Fleur; Toffoli, Barbara; Giudici, Fabiola; Bramante, Alessandra; Furlanis, Giulia; Stenner, Elisabetta; Secchiero, Paola; Zauli, Giorgio; Carretta, Renzo; Fabris, Bruno (Clin Biochem, 2017)
INTRODUCTION: Recent studies suggest that a circulating protein called TRAIL (TNF-related apoptosis-inducing ligand) might have a role in the regulation of body weight and metabolism. Interestingly, thyroid hormones seem to increase TRAIL tissue expression. This study aimed at evaluating whether overt thyroid disorders affected circulating TRAIL levels. METHODS: TRAIL circulating levels were measured in euthyroid, hyperthyroid, and hypothyroid patients before and after thyroid function normalization. Univariate and multivariate analyses were performed to evaluate the correlation between thyroid hormones and TRAIL. Then, the stimulatory effect of both triiodothyronine (T3) and thyroxine (T4) on TRAIL was evaluated in vitro on peripheral blood mononuclear cells. RESULTS: Circulating levels of TRAIL significantly increased in hyperthyroid and decreased in hypothyroid patients as compared to controls. Once thyroid function was restored, TRAIL levels normalized. There was an independent association between TRAIL and both fT3 and fT4. Consistent with these findings, T3 and T4 stimulated TRAIL release in vitro. CONCLUSION: Here we show that thyroid hormones are associated with TRAIL expression in vivo and stimulate TRAIL expression in vitro. Given the overlap between the metabolic effects of thyroid hormones and TRAIL, this work sheds light on the possibility that TRAIL might be one of the molecules mediating thyroid hormones peripheral effects.
Keywords: Aged; Female; Gene Expression Regulation; Humans; Hyperthyroidism; Hypothyroidism; Leukocytes, Mononuclear; Male; Middle Aged; Thyroxine; TNF-Related Apoptosis-Inducing Ligand; Triiodothyronine

Autoimmune neutropenia of childhood secondary to other autoimmune disorders: Data from the Italian neutropenia registry. - Farruggia, Piero; Puccio, Giuseppe; Fioredda, Francesca; Lanza, Tiziana; Porretti, Laura; Ramenghi, Ugo; Barone, Angelica; Bonanomi, Sonia; Finocchi, Andrea; Ghilardi, Roberta; Ladogana, Saverio; Marra, Nicoletta; et al. (Am J Hematol, 2017)
Keywords: Autoimmune Diseases; Child; Disease Susceptibility; Female; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; Italy; Male; Neutropenia; Prevalence; Registries

Cardiac output decreases and systemic vascular resistance increases in newborns placed in the left-lateral position. - Paviotti, G; Todero, S; Demarini, S (J Perinatol, 2017)
OBJECTIVE: The objective of the study was to study the effect of short-term left-lateral position on cardiovascular parameters in hemodynamically stable newborns. STUDY DESIGN: Cardiac output (CO), stroke volume (SV), systemic vascular resistance index (SVRI) and heart rate (HR) were measured by electric velocimetry in hemodynamically stable newborns without respiratory support in the supine, left-lateral and back-to-supine positions, each kept for 10 min. RESULTS: Thirty-two newborns were enrolled, birth weight 2134 (1818 to 2460) g, gestational age 34.5±2.4 weeks. CO and SV decreased significantly from supine to left-lateral position (CO supine: 193.4 (168.0 to 229.6) ml kgmin; CO left-lateral: 172.0 (154.9 to 201.6) ml kgmin, P<0.0001; SV supine: 3.0 (2.7 to 4.0) ml; SV left-lateral: 2.7 (2.4 to 3.2) ml, P<0.0004). Conversely, SVRI increased in left-lateral position: SVRI supine: 18865±9244 dyns cm m; SVRI left-lateral: 21203±10059 dyns cm m, P<0.0001). All variables returned to the initial value when infants were back in the supine position. HR and blood pressure did not change. CONCLUSION: In stable infants, CO and SV decrease and SVRI increases, in left-lateral position.
Keywords: Blood Pressure; Cardiac Output; Female; Gestational Age; Heart Rate; Humans; Infant, Low Birth Weight; Infant, Newborn; Infant, Premature; Italy; Male; Posture; Stroke Volume; Vascular Resistance

CCR5Δ32 and the genetic susceptibility to rheumatoid arthritis in admixed populations: a multicentre study. - Toson, Bruno; Dos Santos, Eduardo José; Adelino, José Eduardo; Sandrin-Garcia, Paula; Crovella, Sergio; Louzada-Júnior, Paulo; Oliveira, Renê Donizete Ribeiro; Pedroza, Larysse Santa Rosa Aquino; de Fátima Lobato Cunha Sauma, Maria; de Lima, Clayton Pereira Silva; Barbosa, Fabiola Brasil; Brenol, Claiton Viegas; et al. (Rheumatology (Oxford), 2017)
Keywords: Arthritis, Rheumatoid; Brazil; Case-Control Studies; Consanguinity; Gene Frequency; Genetic Predisposition to Disease; Humans; Polymorphism, Single Nucleotide; Receptors, CCR5

Child and Adolescent Health From 1990 to 2015: Findings From the Global Burden of Diseases, Injuries, and Risk Factors 2015 Study. - Kassebaum, Nicholas; Kyu, Hmwe Hmwe; Zoeckler, Leo; Olsen, Helen Elizabeth; Thomas, Katie; Pinho, Christine; Bhutta, Zulfiqar A; Dandona, Lalit; Ferrari, Alize; Ghiwot, Tsegaye Tewelde; Hay, Simon I; Kinfu, Yohannes; et al. (JAMA Pediatr, 2017)
Importance: Comprehensive and timely monitoring of disease burden in all age groups, including children and adolescents, is essential for improving population health. Objective: To quantify and describe levels and trends of mortality and nonfatal health outcomes among children and adolescents from 1990 to 2015 to provide a framework for policy discussion. Evidence Review: Cause-specific mortality and nonfatal health outcomes were analyzed for 195 countries and territories by age group, sex, and year from 1990 to 2015 using standardized approaches for data processing and statistical modeling, with subsequent analysis of the findings to describe levels and trends across geography and time among children and adolescents 19 years or younger. A composite indicator of income, education, and fertility was developed (Socio-demographic Index [SDI]) for each geographic unit and year, which evaluates the historical association between SDI and health loss. Findings: Global child and adolescent mortality decreased from 14.18 million (95% uncertainty interval [UI], 14.09 million to 14.28 million) deaths in 1990 to 7.26 million (95% UI, 7.14 million to 7.39 million) deaths in 2015, but progress has been unevenly distributed. Countries with a lower SDI had a larger proportion of mortality burden (75%) in 2015 than was the case in 1990 (61%). Most deaths in 2015 occurred in South Asia and sub-Saharan Africa. Global trends were driven by reductions in mortality owing to infectious, nutritional, and neonatal disorders, which in the aggregate led to a relative increase in the importance of noncommunicable diseases and injuries in explaining global disease burden. The absolute burden of disability in children and adolescents increased 4.3% (95% UI, 3.1%-5.6%) from 1990 to 2015, with much of the increase owing to population growth and improved survival for children and adolescents to older ages. Other than infectious conditions, many top causes of disability are associated with long-term sequelae of conditions present at birth (eg, neonatal disorders, congenital birth defects, and hemoglobinopathies) and complications of a variety of infections and nutritional deficiencies. Anemia, developmental intellectual disability, hearing loss, epilepsy, and vision loss are important contributors to childhood disability that can arise from multiple causes. Maternal and reproductive health remains a key cause of disease burden in adolescent females, especially in lower-SDI countries. In low-SDI countries, mortality is the primary driver of health loss for children and adolescents, whereas disability predominates in higher-SDI locations; the specific pattern of epidemiological transition varies across diseases and injuries. Conclusions and Relevance: Consistent international attention and investment have led to sustained improvements in causes of health loss among children and adolescents in many countries, although progress has been uneven. The persistence of infectious diseases in some countries, coupled with ongoing epidemiologic transition to injuries and noncommunicable diseases, require all countries to carefully evaluate and implement appropriate strategies to maximize the health of their children and adolescents and for the international community to carefully consider which elements of child and adolescent health should be monitored.
Keywords: Adolescent; Adolescent Health; Age Factors; Cause of Death; Child; Child Health; Child Mortality; Disabled Children; Female; Global Burden of Disease; Global Health; Humans; Male; Pregnancy; Pregnancy Complications; Risk Factors; Sex Factors; Wounds and Injuries

Circulating osteoprotegerin is associated with chronic kidney disease in hypertensive patients. - Bernardi, Stella; Toffoli, Barbara; Bossi, Fleur; Candido, Riccardo; Stenner, Elisabetta; Carretta, Renzo; Barbone, Fabio; Fabris, Bruno (BMC Nephrol, 2017)
BACKGROUND: Osteoprotegerin (OPG) is a glycoprotein that plays an important regulatory role in the skeletal, vascular, and immune system. It has been shown that OPG predicts chronic kidney disease (CKD) in diabetic patients. We hypothesized that OPG could be a risk marker of CKD development also in non-diabetic hypertensive patients. METHODS: A case-control study was carried out to measure circulating OPG levels in 42 hypertensive patients with CKD and in 141 hypertensive patients without CKD. A potential relationship between OPG and the presence of CKD was investigated and a receiver-operating characteristic (ROC) curve was designed thereafter to identify a cut-off value of OPG that best explained the presence of CKD. Secondly, to evaluate whether OPG increase could affect the kidney, 18 C57BL/6J mice were randomized to be treated with saline or recombinant OPG every 3 weeks for 12 weeks. RESULTS: Circulating OPG levels were significantly higher in hypertensive patients with CKD, and there was a significant inverse association between OPG and renal function, that was independent from other variables. ROC analysis showed that OPG levels had a high statistically predictive value on CKD in hypertensive patients, which was greater than that of hypertension. The OPG best cut-off value associated with CKD was 1109.19 ng/L. In the experimental study, OPG delivery significantly increased the gene expression of pro-inflammatory and pro-fibrotic mediators, as well as the glomerular nitrosylation of proteins. CONCLUSIONS: This study shows that OPG is associated with CKD in hypertensive patients, where it might have a higher predictive value than that of hypertension for CKD development. Secondly, we found that OPG delivery significantly increased the expression of molecular pathways involved in kidney damage. Further longitudinal studies are needed not only to evaluate whether OPG predicts CKD development but also to clarify whether OPG should be considered a risk factor for CKD.
Keywords: Aged; Animals; Biomarkers; Case-Control Studies; Female; Follow-Up Studies; Humans; Hypertension; Male; Mice; Mice, Inbred C57BL; Middle Aged; Osteoprotegerin; Random Allocation; Renal Insufficiency, Chronic

[Clinical and molecular study in a family with autosomal dominant hypohidrotic ectodermal dysplasia]. - Callea, Michele; Cammarata-Scalisi, Francisco; Willoughby, Colin E; Giglio, Sabrina R; Sani, Ilaria; Bargiacchi, Sara; Traficante, Giovanna; Bellacchio, Emanuele; Tadini, Gianluca; Yavuz, Izzet; Galeotti, Angela; Clarich, Gabriella (Arch Argent Pediatr, 2017)
Hypohidrotic ectodermal dysplasia (HED) is a rare disease characterized by deficiency in development of structure derived from the ectoderm and is caused by mutations in the genes EDA, EDAR, or EDARADD. Phenotypes caused by mutations in these three may exhibit similar clinical features, explained by a common signaling pathway. Mutations in EDA gene cause X linked HED, which is the most common form. Mutations in EDAR and EDARADD genes cause autosomal dominant and recessive form of HED. The most striking clinical findings in HED are hypodontia, hypotrichosis and hypohidrosis that can lead to episodes of hyperthermia. We report on clinical findings in a child with HED with autosomal dominant inheritance pattern with a heterozygous mutation c.1072C>T (p.Arg358X) in the EDAR gene. A review of the literature with regard to other cases presenting the same mutation has been carried out and discussed.
Keywords: Child, Preschool; Ectodermal Dysplasia 1, Anhidrotic; Edar Receptor; Humans; Male; Mutation; Pedigree

Common variants in CLDN14 are associated with differential excretion of magnesium over calcium in urine. - Corre, Tanguy; Olinger, Eric; Harris, Sarah E; Traglia, Michela; Ulivi, Sheila; Lenarduzzi, Stefania; Belge, Hendrica; Youhanna, Sonia; Tokonami, Natsuko; Bonny, Olivier; Houillier, Pascal; Polasek, Ozren; et al. (Pflugers Arch, 2017)
The nature and importance of genetic factors regulating the differential handling of Ca and Mg by the renal tubule in the general population are poorly defined. We conducted a genome-wide meta-analysis of urinary magnesium-to-calcium ratio to identify associated common genetic variants. We included 9320 adults of European descent from four genetic isolates and three urban cohorts. Urinary magnesium and calcium concentrations were measured centrally in spot urine, and each study conducted linear regression analysis of urinary magnesium-to-calcium ratio on ~2.5 million single-nucleotide polymorphisms (SNPs) using an additive model. We investigated, in mouse, the renal expression profile of the top candidate gene and its variation upon changes in dietary magnesium. The genome-wide analysis evidenced a top locus (rs172639, p = 1.7 × 10), encompassing CLDN14, the gene coding for claudin-14, that was genome-wide significant when using urinary magnesium-to-calcium ratio, but not either one taken separately. In mouse, claudin-14 is expressed in the distal nephron segments specifically handling magnesium, and its expression is regulated by chronic changes in dietary magnesium content. A genome-wide approach identified common variants in the CLDN14 gene exerting a robust influence on the differential excretion of Mg over Ca in urine. These data highlight the power of urinary electrolyte ratios to unravel genetic determinants of renal tubular function. Coupled with mouse experiments, these results support a major role for claudin-14, a gene associated with kidney stones, in the differential paracellular handling of divalent cations by the renal tubule.
Keywords: Animals; Calcium; Claudins; Humans; Kidney Tubules; Magnesium; Polymorphism, Single Nucleotide; Urine

Complement Protein C1q Binds to Hyaluronic Acid in the Malignant Pleural Mesothelioma Microenvironment and Promotes Tumor Growth. - Agostinis, Chiara; Vidergar, Romana; Belmonte, Beatrice; Mangogna, Alessandro; Amadio, Leonardo; Geri, Pietro; Borelli, Violetta; Zanconati, Fabrizio; Tedesco, Francesco; Confalonieri, Marco; Tripodo, Claudio; Kishore, Uday; et al. (Front Immunol, 2017)
C1q is the first recognition subcomponent of the complement classical pathway, which acts toward the clearance of pathogens and apoptotic cells. C1q is also known to modulate a range of functions of immune and non-immune cells, and has been shown to be involved in placental development and sensorial synaptic pruning. We have recently shown that C1q can promote tumor by encouraging their adhesion, migration, and proliferation in addition to angiogenesis and metastasis. In this study, we have examined the role of human C1q in the microenvironment of malignant pleural mesothelioma (MPM), a rare form of cancer commonly associated with exposure to asbestos. We found that C1q was highly expressed in all MPM histotypes, particularly in epithelioid rather than in sarcomatoid histotype. C1q avidly bound high and low molecular weight hyaluronic acid (HA) its globular domain. C1q bound to HA was able to induce adhesion and proliferation of mesothelioma cells (MES) enhancement of ERK1/2, SAPK/JNK, and p38 phosphorylation; however, it did not activate the complement cascade. Consistent with the modular organization of the globular domain, we demonstrated that C1q may bind to HA through ghA module, whereas it may interact with human MES through the ghC. In conclusion, C1q highly expressed in MPM binds to HA and enhances the tumor growth promoting cell adhesion and proliferation. These data can help develop novel diagnostic markers and molecular targets for MPM.

A complete duplication of X chromosome resulting in a tricentric isochromosome originated by centromere repositioning. - Villa, N; Conconi, D; Benussi, D Gambel; Tornese, G; Crosti, F; Sala, E; Dalprà, L; Pecile, V (Mol Cytogenet, 2017)
BACKGROUND: Neocentromeres are rare and considered chromosomal aberrations, because a non-centromeric region evolves in an active centromere by mutation. The literature reported several structural anomalies of X chromosome and they influence the female reproductive capacity or are associated to Turner syndrome in the presence of monosomy X cell line. CASE PRESENTATION: We report a case of chromosome X complex rearrangement found in a prenatal diagnosis. The fetal karyotype showed a mosaicism with a 45,X cell line and a 46 chromosomes second line with a big marker, instead of a sex chromosome. The marker morphology and fluorescence in situ hybridization (FISH) characterization allowed us to identify a tricentric X chromosome constituted by two complete X chromosome fused at the p arms telomere and an active neocentromere in the middle, at the union of the two Xp arms, where usually are the telomeric regions. FISH also showed the presence of a paracentric inversion of both Xp arms. Furthermore, fragility figures were found in 56% of metaphases from peripheral blood lymphocytes culture at birth: a shorter marker chromosome and an apparently acentric fragment frequently lost. CONCLUSIONS: At our knowledge, this is the first isochromosome of an entire non-acrocentric chromosome. The neocentromere is constituted by canonical sequences but localized in an unusual position and the original centromeres are inactivated. We speculated that marker chromosome was the result of a double rearrangement: firstly, a paracentric inversion which involved the Xp arm, shifting a part of the centromere at the p end and subsequently a duplication of the entire X chromosome, which gave rise to an isochromosome. It is possible to suppose that the first event could be a result of a non-allelic homologous recombination mediated by inverted low-copy repeats. As expected, our case shows a Turner phenotype with mild facial features and no major skeletal deformity, normal psychomotor development and a spontaneous development of puberty and menarche, although with irregular menses since the last follow-up.

Cubosomes for in vivo fluorescence lifetime imaging. - Biffi, Stefania; Andolfi, Laura; Caltagirone, Claudia; Garrovo, Chiara; Falchi, Angela M; Lippolis, Vito; Lorenzon, Andrea; Macor, Paolo; Meli, Valeria; Monduzzi, Maura; Obiols-Rabasa, Marc; Petrizza, Luca; et al. (Nanotechnology, 2017)
Herein we provided the first proof of principle for in vivo fluorescence optical imaging application using monoolein-based cubosomes in a healthy mouse animal model. This formulation, administered at a non-cytotoxic concentration, was capable of providing both exogenous contrast for NIR fluorescence imaging with very high efficiency and chemospecific information upon lifetime analysis. Time-resolved measurements of fluorescence after the intravenous injection of cubosomes revealed that the dye rapidly accumulated mainly in the liver, while lifetimes profiles obtained in vivo allowed for discriminating between free dye or dye embedded within the cubosome nanostructure after injection.
Keywords: Animals; Carbocyanines; Cell Survival; Drug Compounding; Erythrocytes; Female; Fluorescent Dyes; Glycerides; Humans; Injections, Intravenous; Liposomes; Liver; Mice; Mice, Inbred BALB C; Nanoparticles; NIH 3T3 Cells; Optical Imaging; Particle Size; Spectroscopy, Near-Infrared; Time-Lapse Imaging

Curcumin Anti-Apoptotic Action in a Model of Intestinal Epithelial Inflammatory Damage. - Loganes, Claudia; Lega, Sara; Bramuzzo, Matteo; Vecchi Brumatti, Liza; Piscianz, Elisa; Valencic, Erica; Tommasini, Alberto; Marcuzzi, Annalisa (Nutrients, 2017)
The purpose of this study is to determine if a preventive treatment with curcumin can protect intestinal epithelial cells from inflammatory damage induced by IFNγ. To achieve this goal we have used a human intestinal epithelial cell line (HT29) treated with IFNγ to undergo apoptotic changes that can reproduce the damage of intestinal epithelia exposed to inflammatory cytokines. In this model, we measured the effect of curcumin (curcuminoid from ) added as a pre-treatment at different time intervals before stimulation with IFNγ. Curcumin administration to HT29 culture before the inflammatory stimulus IFNγ reduced the cell apoptosis rate. This effect gradually declined with the reduction of the curcumin pre-incubation time. This anti-apoptotic action by curcumin pre-treatment was paralleled by a reduction of secreted IL7 in the HT29 culture media, while there was no relevant change in the other cytokine levels. Even though curcumin pre-administration did not impact the activation of the NF-κB pathway, a slight effect on the phosphorylation of proteins in this inflammatory signaling pathway was observed. In conclusion, curcumin pre-treatment can protect intestinal cells from inflammatory damage. These results can be the basis for studying the preventive role of curcumin in inflammatory bowel diseases.
Keywords: Anti-Inflammatory Agents, Non-Steroidal; Apoptosis; Cell Survival; Curcuma; Curcumin; Cytokines; Epithelial Cells; HT29 Cells; Humans; Inflammation; Interferon-gamma; Interleukin-7; Intestinal Mucosa; NF-kappa B; Phosphorylation; Signal Transduction

CYP3A genes and the association between prenatal methylmercury exposure and neurodevelopment. - Llop, Sabrina; Tran, Van; Ballester, Ferran; Barbone, Fabio; Sofianou-Katsoulis, Aikaterini; Sunyer, Jordi; Engström, Karin; Alhamdow, Ayman; Love, Tanzy M; Watson, Gene E; Bustamante, Mariona; Murcia, Mario; et al. (Environ Int, 2017)
BACKGROUND: Results on the association between prenatal exposure to methylmercury (MeHg) and child neuropsychological development are heterogeneous. Underlying genetic differences across study populations could contribute to this varied response to MeHg. Studies in Drosophila have identified the cytochrome p450 3A (CYP3A) family as candidate MeHg susceptibility genes. OBJECTIVES: We evaluated whether genetic variation in CYP3A genes influences the association between prenatal exposure to MeHg and child neuropsychological development. METHODS: The study population included 2639 children from three birth cohort studies: two subcohorts in Seychelles (SCDS) (n=1160, 20 and 30months of age, studied during the years 2001-2012), two subcohorts from Spain (INMA) (n=625, 14months of age, 2003-2009), and two subcohorts from Italy and Greece (PHIME) (n=854, 18months of age, 2006-2011). Total mercury, as a surrogate of MeHg, was analyzed in maternal hair and/or cord blood samples. Neuropsychological development was evaluated using Bayley Scales of Infant Development (BSID). Three functional polymorphisms in the CYP3A family were analyzed: rs2257401 (CYP3A7), rs776746 (CYP3A5), and rs2740574 (CYP3A4). RESULTS: There was no association between CYP3A polymorphisms and cord mercury concentrations. The scores for the BSID mental scale improved with increasing cord blood mercury concentrations for carriers of the most active alleles (β[95% CI]:=2.9[1.53,4.27] for CYP3A7 rs2257401 GG+GC, 2.51[1.04,3.98] for CYP3A5 rs776746 AA+AG and 2.31[0.12,4.50] for CYP3A4 rs2740574 GG+AG). This association was near the null for CYP3A7 CC, CYP3A5 GG and CYP3A4 AA genotypes. The interaction between the CYP3A genes and total mercury was significant (p<0.05) in European cohorts only. CONCLUSIONS: Our results suggest that the polymorphisms in CYP3A genes may modify the response to dietary MeHg exposure during early life development.
Keywords: Adult; Child Development; Child, Preschool; Cohort Studies; Cytochrome P-450 CYP3A; Female; Fetal Blood; Genotype; Greece; Humans; Infant; Italy; Male; Mercury; Methylmercury Compounds; Neurodevelopmental Disorders; Neuropsychological Tests; Polymorphism, Genetic; Pregnancy; Prenatal Exposure Delayed Effects; Seychelles; Spain

Describing Kawasaki shock syndrome: results from a retrospective study and literature review. - Taddio, Andrea; Rossi, Eleonora Dei; Monasta, Lorenzo; Pastore, Serena; Tommasini, Alberto; Lepore, Loredana; Bronzetti, Gabriele; Marrani, Edoardo; Mottolese, Biancamaria D'Agata; Simonini, Gabriele; Cimaz, Rolando; Ventura, Alessandro (Clin Rheumatol, 2017)
Kawasaki shock syndrome (KSS) is a rare manifestation of Kawasaki disease (KD) characterized by systolic hypotension or clinical signs of poor perfusion. The objectives of the study are to describe the main clinical presentation, echocardiographic, and laboratory findings, as well as the treatment options and clinical outcomes of KSS patients when compared with KD patients. This is a retrospective study. All children referred to two pediatric rheumatology units from January 1, 2012, to December 31, 2014, were enrolled. Patients were divided into patients with or without KSS. We compared the two groups according to the following variables: sex, age, type of KD (classic, with less frequent manifestations, or incomplete), clinical manifestations, cardiac involvement, laboratory findings, therapy administered, response to treatment, and outcome. Eighty-four patients with KD were enrolled. Of these, five (6 %) met the criteria for KSS. Patients with KSS had higher values of C-reactive protein (p = 0.005), lower hemoglobin levels (p = 0.003); more frequent hyponatremia (p = 0.004), hypoalbuminemia (p = 0.004), and coagulopathy (p = 0.003); and increase in cardiac troponins (p = 0.000). Among the KSS patients, three had a coronary artery involvement, but none developed a permanent aneurysm. Intravenous immunoglobulin resistance was more frequent in the KSS group, although not significantly so (3/5, 60 % vs. 23/79, 30 %, P = NS). None of the five cases was fatal, and all recovered without sequelae. KSS patients are more likely to have higher rates of cardiac involvement. However, most cardiovascular abnormalities resolved promptly with therapy.
Keywords: C-Reactive Protein; Child; Child, Preschool; Echocardiography; Female; Heart Failure; Hemoglobins; Humans; Immunoglobulins, Intravenous; Male; Mucocutaneous Lymph Node Syndrome; Retrospective Studies; Shock; Syndrome

Enrichment of low-frequency functional variants revealed by whole-genome sequencing of multiple isolated European populations. - Xue, Yali; Mezzavilla, Massimo; Haber, Marc; McCarthy, Shane; Chen, Yuan; Narasimhan, Vagheesh; Gilly, Arthur; Ayub, Qasim; Colonna, Vincenza; Southam, Lorraine; Finan, Christopher; Massaia, Andrea; et al. (Nat Commun, 2017)
The genetic features of isolated populations can boost power in complex-trait association studies, and an in-depth understanding of how their genetic variation has been shaped by their demographic history can help leverage these advantageous characteristics. Here, we perform a comprehensive investigation using 3,059 newly generated low-depth whole-genome sequences from eight European isolates and two matched general populations, together with published data from the 1000 Genomes Project and UK10K. Sequencing data give deeper and richer insights into population demography and genetic characteristics than genotype-chip data, distinguishing related populations more effectively and allowing their functional variants to be studied more fully. We demonstrate relaxation of purifying selection in the isolates, leading to enrichment of rare and low-frequency functional variants, using novel statistics, DVxy and SVxy. We also develop an isolation-index (Isx) that predicts the overall level of such key genetic characteristics and can thus help guide population choice in future complex-trait association studies.
Keywords: European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Humans; Polymorphism, Single Nucleotide; Whole Genome Sequencing

Essure Permanent Birth Control, Effectiveness and Safety: An Italian 11-Year Survey. - Franchini, Mario; Zizolfi, Brunella; Coppola, Carmela; Bergamini, Valentino; Bonin, Cecilia; Borsellino, Giovanni; Busato, Enrico; Calabrese, Stefania; Calzolari, Stefano; Fantin, Gian Piero; Giarrè, Giovanna; Litta, Piero; et al. (J Minim Invasive Gynecol, 2017)
STUDY OBJECTIVE: To describe safety, tolerability, and effectiveness results through a minimum 2-year follow-up of patients who underwent permanent sterilization with the Essure insert. DESIGN: A retrospective multicenter study (Canadian Task Force classification II2). SETTING: Seven general hospitals and 4 clinical teaching centers in Italy. PATIENTS: A total of 1968 women, mean age 39.5 years (range, 23-48 years) who underwent office hysteroscopic sterilization using the Essure insert between April 1, 2003, and December 30, 2014. INTERVENTION: The women underwent office hysteroscopic bilateral Essure insert placement, with satisfactory device location and tube occlusion based on hysterosalpingography or hysterosalpingo-contrast sonography (HyCoSy). MEASUREMENTS AND MAIN RESULTS: Placement rate, successful bilateral tubal occlusion, perioperative adverse events, early postoperative (during the first 3 months of follow-up), and late complications were evaluated. Satisfactory insertion was accomplished in 97.2% of women and, in 4, perforation and 1 expulsion were detected during hysterosalpingography. Three unintended pregnancies occurred before the 3-month confirmation test. Two pregnancies were reported among women relying on the Essure inserts. Postprocedure pain was minimal and brief; in 9 women, pelvic pain became intractable, necessitating removal of the devices via laparoscopy. On telephone interviews, overall satisfaction was rated as "very satisfied" by the majority of women (97.6%), and no long-term adverse events were reported. CONCLUSION: The findings from this extended Italian survey further support the effectiveness, tolerability, and satisfaction of Essure hysteroscopic sterilization when motivated women are selected and well informed of the potential risks of the device. Moreover, the results do not demonstrate an increased incidence of complications and pregnancies associated with long-term Essure use. Patients with a known hypersensitivity to nickel may be less suitable candidates for the Essure insert.
Keywords: Adult; Fallopian Tubes; Female; Follow-Up Studies; Humans; Hypersensitivity; Hysterosalpingography; Hysteroscopy; Italy; Laparoscopy; Middle Aged; Nickel; Pain; Pregnancy; Pregnancy, Unplanned; Retrospective Studies; Sterilization, Reproductive; Sterilization, Tubal; Surveys and Questionnaires; Young Adult

Factors Influencing the Phenotypic Characterization of the Oral Marker, PROP. - Tepper, Beverly J; Melis, Melania; Koelliker, Yvonne; Gasparini, Paolo; Ahijevych, Karen L; Tomassini Barbarossa, Iole (Nutrients, 2017)
In the last several decades, the genetic ability to taste the bitter compound, 6--propyltiouracil (PROP) has attracted considerable attention as a model for understanding individual differences in taste perception, and as an oral marker for food preferences and eating behavior that ultimately impacts nutritional status and health. However, some studies do not support this role. This review describes common factors that can influence the characterization of this phenotype including: (1) changes in taste sensitivity with increasing age; (2) gender differences in taste perception; and (3) effects of smoking and obesity. We suggest that attention to these factors during PROP screening could strengthen the associations between this phenotype and a variety of health outcomes ranging from variation in body composition to oral health and cancer risk.
Keywords: Food Preferences; Genetic Variation; Humans; Propylthiouracil; Taste Perception; Taste Threshold

Fetal monitoring indications for delivery and 2-year outcome in 310 infants with fetal growth restriction delivered before 32 weeks' gestation in the TRUFFLE study. - Visser, G H A; Bilardo, C M; Derks, J B; Ferrazzi, E; Fratelli, N; Frusca, T; Ganzevoort, W; Lees, C C; Napolitano, R; Todros, T; Wolf, H; Hecher, K (Ultrasound Obstet Gynecol, 2017)
OBJECTIVE: In the TRUFFLE (Trial of Randomized Umbilical and Fetal Flow in Europe) study on the outcome of early fetal growth restriction, women were allocated to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate (FHR) short-term variation (STV) on cardiotocography (CTG); (2) early changes in fetal ductus venosus (DV) waveform (DV-p95); and (3) late changes in fetal DV waveform (DV-no-A). However, many infants per monitoring protocol were delivered because of safety-net criteria, for maternal or other fetal indications, or after 32 weeks of gestation when the protocol was no longer applied. The objective of the present posthoc subanalysis was to investigate the indications for delivery in relation to 2-year outcome in infants delivered before 32 weeks to further refine management proposals. METHODS: We included all 310 cases of the TRUFFLE study with known outcome at 2 years' corrected age and seven fetal deaths, excluding seven cases with inevitable perinatal death. Data were analyzed according to the allocated fetal monitoring strategy in combination with the indication for delivery. RESULTS: Overall, only 32% of liveborn infants were delivered according to the specified monitoring parameter for indication for delivery; 38% were delivered because of safety-net criteria, 15% for other fetal reasons and 15% for maternal reasons. In the CTG-STV group, 51% of infants were delivered because of reduced STV. In the DV-p95 group, 34% of infants were delivered because of abnormal DV and, in the DV-no-A group, only 10% of infants were delivered accordingly. The majority of infants in the DV groups were delivered for the safety-net criterion of spontaneous decelerations in FHR. Two-year intact survival was highest in the DV groups combined compared with the CTG-STV group (P = 0.05 for live births only, P = 0.21 including fetal death), with no difference between DV groups. A poorer outcome in the CTG-STV group was restricted to infants delivered because of FHR decelerations in the safety-net subgroup. Infants delivered because of maternal reasons had the highest birth weight and a non-significantly higher intact survival. CONCLUSIONS: In this subanalysis of infants delivered before 32 weeks, the majority were delivered for reasons other than the allocated monitoring strategy indication. Since, in the DV group, CTG-STV criteria were used as a safety net but in the CTG-STV group, no DV safety-net criteria were applied, we speculate that the slightly poorer outcome in the CTG-STV group might be explained by the absence of DV data. The optimal timing of delivery of fetuses with early intrauterine growth restriction may therefore be best determined by monitoring them longitudinally, with both DV and CTG monitoring. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Cardiotocography; Delivery, Obstetric; Female; Fetal Growth Retardation; Fetal Monitoring; Fetus; Gestational Age; Humans; Infant, Newborn; Male; Netherlands; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal; Umbilical Arteries

Genome-wide association analysis identifies novel blood pressure loci and offers biological insights into cardiovascular risk. - Warren, Helen R; Evangelou, Evangelos; Cabrera, Claudia P; Gao, He; Ren, Meixia; Mifsud, Borbala; Ntalla, Ioanna; Surendran, Praveen; Liu, Chunyu; Cook, James P; Kraja, Aldi T; Drenos, Fotios; et al. (Nat Genet, 2017)
Elevated blood pressure is the leading heritable risk factor for cardiovascular disease worldwide. We report genetic association of blood pressure (systolic, diastolic, pulse pressure) among UK Biobank participants of European ancestry with independent replication in other cohorts, and robust validation of 107 independent loci. We also identify new independent variants at 11 previously reported blood pressure loci. In combination with results from a range of in silico functional analyses and wet bench experiments, our findings highlight new biological pathways for blood pressure regulation enriched for genes expressed in vascular tissues and identify potential therapeutic targets for hypertension. Results from genetic risk score models raise the possibility of a precision medicine approach through early lifestyle intervention to offset the impact of blood pressure-raising genetic variants on future cardiovascular disease risk.
Keywords: Adult; Blood Pressure; Cardiovascular Diseases; European Continental Ancestry Group; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Higher growth, fat and fat-free masses correlate with larger cerebellar volumes in preterm infants at term. - Paviotti, Giulia; De Cunto, Angela; Zennaro, Floriana; Boz, Giulia; Travan, Laura; Cont, Gabriele; Bua, Jenny; Demarini, Sergio (Acta Paediatr, 2017)
AIM: Smaller cerebellar volumes in very low-birthweight (VLBW) infants at term have been related to adverse cognitive outcomes, and this study evaluated whether these volumes were associated with a growth in body composition during hospital stays. METHODS: We prospectively recruited 42 VLBW infants from an Italian neonatal unit between January 2013 and August 2015. Cerebellar volumes and body composition were measured by magnetic resonance imaging (MRI) and air-displacement plethysmography, respectively, at 40 weeks of gestational age and anthropometric and nutritional data were collected. We also included 20 term-born controls. RESULTS: The mean gestational age and birthweight of the VLBW infants were 29.4 (±1.9) weeks and 1120 (±290) g. There was a positive correlation between cerebellar volumes and daily weight gain from birth to term (R = 0.26, p = 0.001), weight (R = 0.25, p = 0.001), length (R = 0.16, p = 0.01), fat mass (R = 0.15, p = 0.01) and fat-free mass at term (R = 0.20, p = 0.003). In multiple regression analysis, daily weight gain, mechanical ventilation and postconceptional age at MRI were independently associated with cerebellar volumes. Anthropometric data and cerebellar volumes were similar between VLBW and control infants. CONCLUSION: Higher growth, higher fat mass and fat-free mass were associated with larger cerebellar volumes in VLBW infants at term.
Keywords: Body Composition; Cerebellum; Child Development; Female; Humans; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Male; Nutritional Status; Organ Size; Prospective Studies; Regression Analysis

How to monitor pregnancies complicated by fetal growth restriction and delivery before 32 weeks: post-hoc analysis of TRUFFLE study. - Ganzevoort, W; Mensing Van Charante, N; Thilaganathan, B; Prefumo, F; Arabin, B; Bilardo, C M; Brezinka, C; Derks, J B; Diemert, A; Duvekot, J J; Ferrazzi, E; Frusca, T; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: In the recent TRUFFLE study, it appeared that, in pregnancies complicated by fetal growth restriction (FGR) between 26 and 32 weeks' gestation, monitoring of the fetal ductus venosus (DV) waveform combined with computed cardiotocography (CTG) to determine timing of delivery increased the chance of infant survival without neurological impairment. However, concerns with the interpretation were raised, as DV monitoring appeared to be associated with a non-significant increase in fetal death, and some infants were delivered after 32 weeks, at which time the study protocol no longer applied. This secondary sensitivity analysis of the TRUFFLE study focuses on women who delivered before 32 completed weeks' gestation and analyzes in detail the cases of fetal death. METHODS: Monitoring data of 317 pregnancies with FGR that delivered before 32 weeks were analyzed, excluding those with absent outcome data or inevitable perinatal death. Women were allocated randomly to one of three groups of indication for delivery according to the following monitoring strategies: (1) reduced fetal heart rate short-term variation (STV) on CTG; (2) early changes in fetal DV waveform; and (3) late changes in fetal DV waveform. Primary outcome was 2-year survival without neurological impairment. The association of the last monitoring data before delivery and infant outcome was assessed by multivariable analysis. RESULTS: Two-year survival without neurological impairment occurred more often in the two DV groups (both 83%) than in the CTG-STV group (77%), however, the difference was not statistically significant (P = 0.21). Among the surviving infants in the DV groups, 93% were free of neurological impairment vs 85% of surviving infants in the CTG-STV group (P = 0.049). All fetal deaths (n = 7) occurred in the groups with DV monitoring. Of the monitoring parameters obtained shortly before fetal death in these seven cases, an abnormal CTG was observed in only one case. Multivariable regression analysis of factors at study entry demonstrated that a later gestational age, higher estimated fetal weight-to-50 percentile ratio and lower umbilical artery pulsatility index (PI)/fetal middle cerebral artery-PI ratio were significantly associated with normal outcome. Allocation to DV monitoring had a smaller effect on outcome, but remained in the model (P < 0.1). Abnormal fetal arterial Doppler before delivery was significantly associated with adverse outcome in the CTG-STV group. In contrast, abnormal DV flow was the only monitoring parameter associated with adverse outcome in the DV groups, while fetal arterial Doppler, STV below the cut-off used in the CTG-STV group and recurrent decelerations in fetal heart rate were not. CONCLUSIONS: In accordance with the findings of the TRUFFLE study on monitoring and intervention management of very preterm FGR, we found that the proportion of infants surviving without neuroimpairment was not significantly different when the decision for delivery was based on changes in DV waveform vs reduced STV on CTG. The uneven distribution of fetal deaths towards the DV groups was probably a chance effect, and neurological outcome was better among surviving children in these groups. Before 32 weeks, delaying delivery until abnormalities in DV-PI or STV and/or recurrent decelerations in fetal heat rate occur, as defined by the study protocol, is likely to be safe and possibly benefits long-term outcome. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Central Nervous System Diseases; Child, Preschool; Female; Fetal Growth Retardation; Fetal Membranes, Premature Rupture; Gestational Age; Heart Rate, Fetal; Humans; Infant; Infant, Extremely Premature; Male; Middle Cerebral Artery; Pregnancy; Pulsatile Flow; Survival Analysis; Treatment Outcome; Ultrasonography, Prenatal; Uterine Artery

Impaired fasting glucose and impaired glucose tolerance in children and adolescents with overweight/obesity. - Di Bonito, P; Pacifico, L; Chiesa, C; Valerio, G; Miraglia Del Giudice, E; Maffeis, C; Morandi, A; Invitti, C; Licenziati, M R; Loche, S; Tornese, G; Franco, F; et al. (J Endocrinol Invest, 2017)
OBJECTIVE: To investigate in a large sample of overweight/obese (OW/OB) children and adolescents the prevalence of prediabetic phenotypes such as impaired fasting glucose (IFG) and impaired glucose tolerance (IGT), and to assess their association with cardiometabolic risk (CMR) factors including hepatic steatosis (HS). METHODS: Population data were obtained from the CARdiometabolic risk factors in children and adolescents in ITALY study. Between 2003 and 2013, 3088 youths (972 children and 2116 adolescents) received oral glucose tolerance test (OGTT) and were included in the study. In 798 individuals, abdominal ultrasound for identification of HS was available. RESULTS: The prevalence of IFG (3.2 vs. 3.3%) and IGT (4.6 vs. 5.0%) was similar between children and adolescents. Children with isolated IGT had a 2-11 fold increased risk of high LDL-C, non-HDL-C, Tg/HDL-C ratio, and low insulin sensitivity, when compared to those with normal glucose tolerance (NGT). No significant association of IFG with any CMR factor was found in children. Among adolescents, IGT subjects, and to a lesser extent those with IFG, showed a worse CMR profile compared to NGT subgroup. In the overall sample, IGT phenotype showed a twofold increased risk of HS compared to NGT subgroup. CONCLUSIONS: Our study shows an unexpected similar prevalence of IFG and IGT between children and adolescents with overweight/obesity. The IGT phenotype was associated with a worse CMR profile in both children and adolescents. Phenotyping prediabetes conditions by OGTT should be done as part of prediction and prevention of cardiometabolic diseases in OW/OB youth since early childhood.
Keywords: Adolescent; Blood Glucose; Case-Control Studies; Child; Fasting; Female; Glucose Intolerance; Glucose Tolerance Test; Humans; Insulin; Insulin Resistance; Italy; Male; Obesity; Overweight; Prediabetic State; Prevalence

Improving the quality of hospital care for children by supportive supervision: a cluster randomized trial, Kyrgyzstan. - Lazzerini, Marzia; Shukurova, Venera; Davletbaeva, Marina; Monolbaev, Kubanychbek; Kulichenko, Tatiana; Akoev, Yuri; Bakradze, Maya; Margieva, Tea; Mityushino, Ilya; Namazova-Baranova, Leyla; Boronbayeva, Elnura; Kuttumuratova, Aigul; et al. (Bull World Health Organ, 2017)
OBJECTIVE: To determine whether periodic supportive supervision after a training course improved the quality of paediatric hospital care in Kyrgyzstan, where inappropriate care was common but in-hospital postnatal mortality was low. METHODS: In a cluster, randomized, parallel-group trial, 10 public hospitals were allocated to a 4-day World Health Organization (WHO) course on hospital care for children followed by periodic supportive supervision by paediatricians for 1 year, while 10 hospitals had no intervention. We assessed prospectively 10 key indicators of inappropriate paediatric case management, as indicated by WHO guidelines. The primary indicator was the combination of the three indicators: unnecessary hospitalization, increased iatrogenic risk and unnecessary painful procedures. An independent team evaluated the overall quality of care. FINDINGS: We prospectively reviewed the medical records of 4626 hospitalized children aged 2 to 60 months. In the intervention hospitals, the mean proportion of the primary indicator decreased from 46.9% (95% confidence interval, CI: 24.2 to 68.9) at baseline to 6.8% (95% CI: 1.1 to 12.1) at 1 year, but was unchanged in the control group (45.5%, 95% CI: 25.2 to 67.9, to 64.7%, 95% CI: 43.3 to 86.1). At 1 year, the risk ratio for the primary indicator in the intervention versus the control group was 0.09 (95% CI: 0.06 to 0.13). The proportions of the other nine indicators also decreased in the intervention group ( < 0.0001 for all). Overall quality of care improved significantly in intervention hospitals. CONCLUSION: Periodic supportive supervision for 1 year after a training course improved both adherence to WHO guidelines on hospital care for children and the overall quality of paediatric care.
Keywords: Child; Child Care; Cluster Analysis; Hospitalization; Hospitals, Public; Humans; Kyrgyzstan; Medical Audit; Pediatricians; Professional Role; Prospective Studies; Quality Improvement

Influence of vaginal lactoferrin administration on amniotic fluid cytokines and its role against inflammatory complications of pregnancy. - Maritati, Martina; Comar, Manola; Zanotta, Nunzia; Seraceni, Silva; Trentini, Alessandro; Corazza, Fabrizio; Vesce, Fortunato; Contini, Carlo (J Inflamm (Lond), 2017)
BACKGROUND: An altered amniotic cytokine profile has been reported in inflammatory pregnancy complications with a leading role for IL-6, a marker of the foetal systemic inflammatory response. Up to this date there is no exhaustive information neither on the foetal cytokine balance nor on the best method for its modulation. We aimed to evaluate the influence of vaginal lactoferrin administration on amniotic fluid concentration of 47 cytokines, chemokines and growth factors. METHODS: Sixty women undergoing genetic amniocentesis were enrolled in an open-label clinical trial. 300 mg of vaginal lactoferrin (Florence, Italy) were randomly administered to obtain 3 groups: A, 20 untreated patients; B and C (20 patients in each) respectively treated 4 and 12 h before amniocentesis. Cytokines, chemokines and growth factors concentrations were quantified by a magnetic bead Luminex multiplex immunoassays panel technology. Data analysis was performed with the software Stata (v. 13.1) and GraphPad Prism (v. 5). Group comparisons were performed using Kruskal-Wallis followed by Mann-Whitney U tests, with Bonferroni correction for multiple comparisons. A  < 0.05 was considered significant. RESULTS: Among the 47 tested mediators, 24 (51.06%) were influenced by lactoferrin. 11 (23.4%), showed a highly significant difference (p <0.001); among these IL-9, IL-15, IFN-γ, IP-10, TNF-α, IL-1α and MCP-3 underwent a down-regulation, while IL-17 and FGF-basic, G-CSF, GM-CSF an up-regulation. Difference between group C and both B and A was small for IL-15, IP-10, IL-1α, MCP-3, while it was negligible for IL-9, IFN-γ and TNF-α. IL-17 and the 3 growth factors were strongly enhanced in B and C groups. IL-17, FGF-basic and GM-CSF showed increasing concentrations in both B and C groups, while G-CSF resulted up-regulated only in group C. Significance was intermediate ( < 0.01) for the down regulated IL-2RA, IL-12p40 and IFNα2 (6.38%) while it was small for 10 mediators (21.27%) 7 of which (IL-2, IL-4, eotaxin, PDGF-BB, RANTES, IL-18 and MIF) down-regulated and 3 (MCP-1, IL-3, and SDF-1α) up-regulated. CONCLUSION: Lactoferrin down-regulates 17 pro-inflammatory amniotic mediators while up-regulating 7 anti-inflammatory amniotic mediators, 5 of which definitively belonging to an anti-inflammatory profile. These findings open to clinical investigation on its use against inflammatory complications of pregnancy.

The Italian Society for Pediatric Nephrology (SINePe) consensus document on the management of nephrotic syndrome in children: Part I - Diagnosis and treatment of the first episode and the first relapse. - Pasini, Andrea; Benetti, Elisa; Conti, Giovanni; Ghio, Luciana; Lepore, Marta; Massella, Laura; Molino, Daniela; Peruzzi, Licia; Emma, Francesco; Fede, Carmelo; Trivelli, Antonella; Maringhini, Silvio; et al. (Ital J Pediatr, 2017)
This consensus document is aimed at providing an updated, multidisciplinary overview on the diagnosis and treatment of pediatric nephrotic syndrome (NS) at first presentation. It is the first consensus document of its kind to be produced by all the pediatric nephrology centres in Italy, in line with what is already present in other countries such as France, Germany and the USA. It is based on the current knowledge surrounding the symptomatic and steroid treatment of NS, with a view to providing the basis for a separate consensus document on the treatment of relapses. NS is one of the most common pediatric glomerular diseases, with an incidence of around 2-7 cases per 100000 children per year. Corticosteroids are the mainstay of treatment, but the optimal therapeutic regimen for managing childhood idiopathic NS is still under debate. In Italy, shared treatment guidelines were lacking and, consequently, the choice of steroid regimen was based on the clinical expertise of each individual unit. On the basis of the 2015 Cochrane systematic review, KDIGO Guidelines and more recent data from the literature, this working group, with the contribution of all the pediatric nephrology centres in Italy and on the behalf of the Italian Society of Pediatric Nephrology, has produced a shared steroid protocol that will be useful for National Health System hospitals and pediatricians. Investigations at initial presentation and the principal causes of NS to be screened are suggested. In the early phase of the disease, symptomatic treatment is also important as many severe complications can occur which are either directly related to the pathophysiology of the underlying NS or to the steroid treatment itself. To date, very few studies have been published on the prophylaxis and treatment of these early complications, while recommendations are either lacking or conflicting. This consensus provides indications for the prevention, early recognition and treatment of these complications (management of edema and hypovolemia, therapy and prophylaxis of infections and thromboembolic events). Finally, recommendations about the clinical definition of steroid resistance and its initial diagnostic management, as well as indications for renal biopsy are provided.
Keywords: Adrenal Cortex Hormones; Child; Child, Preschool; Consensus; Dose-Response Relationship, Drug; Drug Administration Schedule; Female; Humans; Italy; Male; Nephrotic Syndrome; Practice Guidelines as Topic; Prognosis; Recurrence; Retreatment; Societies, Medical; Survival Rate; Treatment Outcome

Lack of Prenylated Proteins, Autophagy Impairment and Apoptosis in SH-SY5Y Neuronal Cell Model of Mevalonate Kinase Deficiency. - Tricarico, Paola Maura; Romeo, Alessandra; Gratton, Rossella; Crovella, Sergio; Celsi, Fulvio (Cell Physiol Biochem, 2017)
BACKGROUND/AIMS: Mevalonate Kinase Deficiency (MKD), is a hereditary disease due to mutations in mevalonate kinase gene (MVK). MKD has heterogeneous clinical phenotypes: the correlation between MVK mutations and MKD clinical phenotype is still to be fully elucidated. Deficiency of prenylated proteins has been hypothesized as possible MKD pathogenic mechanism. Based on this hypothesis and considering that neurologic impairment characterizes Mevalonic Aciduria (MA), the most severe form of MKD, we studied the effects of I268T and N301T MVK mutations on protein prenylation, autophagy and programmed cell death in SH-SY5Y neuroblastoma cell lines. METHODS: SH-SY5Y cells were transiently transfected, with the pCMV-6 plasmid containing MVK wild type and the two mutated sequences. Protein prenylation levels were evaluated using GFP-RhoA-F to assess farnesylation, and GFP-RhoA to evaluate geranylgeranylation; autophagy was measured by evaluating LC3 and p62 protein levels, while Annexin V-FITC and Propidium Iodide staining allowed apoptosis detection. RESULTS: MVK mutants' over-expression causes decreased levels of farnesylation and geranylgeranylation, and also increased LC3 lipidation in SH-SY5Y, with concomitant p62 accumulation. Treatment with bafilomycin A1 (an inhibitor of vacuolar H+-ATPase, a late autophagy inhibitor) further increase LC3-II and p62 levels, suggesting that degradation of autophagolysosome could be impaired. SH-SY5Y, with both MVK mutants, showed apoptosis increase; the presence of N301T associated with augmented cell death. CONCLUSIONS: We hypothesize that mevalonate pathway impairment causes alteration of farnesylation and geranylgeranylation proteins and alteration of the autophagic flux; these changes can induce apoptosis, possibly more relevant in the presence of N301T mutation.
Keywords: Animals; Apoptosis; Autophagy; Cell Line, Tumor; Macrolides; Mevalonate Kinase Deficiency; Microtubule-Associated Proteins; Models, Biological; Mutation; Phosphotransferases (Alcohol Group Acceptor); Protein Prenylation; Rats

Longitudinal study of computerized cardiotocography in early fetal growth restriction. - Wolf, H; Arabin, B; Lees, C C; Oepkes, D; Prefumo, F; Thilaganathan, B; Todros, T; Visser, G H A; Bilardo, C M; Derks, J B; Diemert, A; Duvekot, J J; et al. (Ultrasound Obstet Gynecol, 2017)
OBJECTIVES: To explore whether, in early fetal growth restriction (FGR), the longitudinal pattern of fetal heart rate (FHR) short-term variation (STV) can be used to identify imminent fetal distress and whether abnormalities of FHR recordings are associated with 2-year infant outcome. METHODS: The original TRUFFLE study assessed whether, in early FGR, delivery based on ductus venosus (DV) Doppler pulsatility index (PI), in combination with safety-net criteria of very low STV on cardiotocography (CTG) and/or recurrent FHR decelerations, could improve 2-year infant survival without neurological impairment in comparison with delivery based on CTG monitoring only. This was a secondary analysis of women who delivered before 32 weeks and had consecutive STV data recorded > 3 days before delivery and known infant outcome at 2 years of age. Women who received corticosteroids within 3 days of delivery were excluded. Individual regression line algorithms of all STV values, except the last one before delivery, were calculated. Life tables and Cox regression analysis were used to calculate the daily risk for low STV or very low STV and/or FHR decelerations (below DV group safety-net criteria) and to assess which parameters were associated with this risk. Furthermore, it was assessed whether STV pattern, last STV value or recurrent FHR decelerations were associated with 2-year infant outcome. RESULTS: One hundred and forty-nine women from the original TRUFFLE study met the inclusion criteria. Using the individual STV regression lines, prediction of a last STV below the cut-off used by the CTG monitoring group had sensitivity of 42% and specificity of 91%. For each day after study inclusion, the median risk for low STV (CTG group cut-off) was 4% (interquartile range (IQR), 2-7%) and for very low STV and/or recurrent FHR decelerations (below DV group safety-net criteria) was 5% (IQR, 4-7%). Measures of STV pattern, fetal Doppler (arterial or venous), birth-weight multiples of the median and gestational age did not usefully improve daily risk prediction. There was no association of STV regression coefficients, a low last STV and/or recurrent FHR decelerations with short- or long-term infant outcomes. CONCLUSION: The TRUFFLE study showed that a strategy of DV monitoring with safety-net criteria of very low STV and/or recurrent FHR decelerations for delivery indication could increase 2-year infant survival without neurological impairment. This post-hoc analysis demonstrates that, in early FGR, the daily risk of abnormal CTG, as defined by the DV group safety-net criteria, is 5%, and that prediction is not possible. This supports the rationale for CTG monitoring more often than daily in these high-risk fetuses. Low STV and/or recurrent FHR decelerations were not associated with adverse infant outcome and it appears safe to delay intervention until such abnormalities occur, as long as DV-PI is within normal range. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: Adult; Cardiotocography; Child, Preschool; Female; Fetal Growth Retardation; Fetal Heart; Heart Rate, Fetal; Humans; Infant; Infant, Newborn; Longitudinal Studies; Middle Cerebral Artery; Pregnancy; Pregnancy Outcome; Pulsatile Flow; Survival Analysis; Ultrasonography, Prenatal

MCM8 and MCM9 Nucleotide Variants in Women With Primary Ovarian Insufficiency. - Desai, Swapna; Wood-Trageser, Michelle; Matic, Jelena; Chipkin, Jaqueline; Jiang, Huaiyang; Bachelot, Anne; Dulon, Jerome; Sala, Cinzia; Barbieri, Caterina; Cocca, Massimiliano; Toniolo, Daniela; Touraine, Philippe; et al. (J Clin Endocrinol Metab, 2017)
Objective: To assess the frequency of variants, including biallelic pathogenic variants, in minichromosome maintenance 8 (MCM8) and minichromosome maintenance 9 (MCM9), other genes related to MCM8-MCM9, and DNA damage repair (DDR) pathway in participants with primary ovarian insufficiency (POI). Design: MCM8, MCM9, and genes encoding DDR proteins that have been implicated in reproductive aging were sequenced among POI participants. Setting: Academic research institution. Participants: All were diagnosed with POI prior to age 40 years and presented with elevated follicle-stimulating hormone levels. Interventions: None. Main Outcome Measures: We identified nucleotide variants in MCM8, MCM9, and genes thought to be involved in the DNA damage response pathway and/or implicated in reproductive aging. Results: MCM8 was sequenced in 155 POI participants, whereas MCM9 was sequenced in 151 participants. Three of 155 (2%) participants carried possibly damaging heterozygous variants in MCM8, whereas 7 of 151 (5%) individuals carried possibly damaging heterozygous variants in MCM9. One participant carried a novel homozygous variant, c.1651C>T, p.Gln551*, in MCM9, which is predicted to introduce a premature stop codon in exon 9. Biallelic damaging heterozygous variants in both MCM8 and MCM9 were identified in 1 participant. Of a total of 10 participants carrying damaging heterozygous variants in either MCM8 or MCM9, 2 individuals carried heterozygous damaging variants in genes associated with either MCM8 or MCM9 or the DDR pathway. Conclusions: We identified a significant number of potentially damaging and novel variants in MCM8 and MCM9 among participants with POI and examined multiallelic association with variants in DDR and MCM8-MCM9 interactome genes.
Keywords: Adult; Aging; DNA Damage; DNA Repair; Female; Humans; Minichromosome Maintenance Proteins; Primary Ovarian Insufficiency; Sequence Analysis, DNA

Metastatic neuroblastoma in infants: are survival rates excellent only within the stringent framework of clinical trials? - Di Cataldo, A; Agodi, A; Balaguer, J; Garaventa, A; Barchitta, M; Segura, V; Bianchi, M; Castel, V; Castellano, A; Cesaro, S; Couselo, J M; Cruz, O; et al. (Clin Transl Oncol, 2017)
INTRODUCTION: SIOPEN INES protocol yielded excellent 5-year survival rates for MYCN-non-amplified metastatic neuroblastoma. Patients deemed ineligible due to lack or delay of MYCN status or late registration were treated, but not included in the study. Our goal was to analyse survival at 10 years among the whole population. MATERIALS AND METHODS: Italian and Spanish metastatic INES patients' data are reported. SPSS 20.0 was used for statistical analysis. RESULTS: Among 98 infants, 27 had events and 19 died, while 79 were disease free. Five- and 10-year event-free survival (EFS) were 73 and 70 %, and overall survival (OS) was 81 and 74 %, respectively. MYCN status was significant for EFS, but not for OS in multivariate analysis. CONCLUSIONS: The survival rates of patients who complied with all the inclusion criteria for INES trials are higher compared to those that included also not registered patients. Five-year EFS and OS for INES 99.2 were 87.8 and 95.7 %, while our stage 4s population obtained 78 and 87 %. Concerning 99.3, 5-year EFS and OS were 86.7 and 95.6 %, while for stage 4 we registered 61 and 68 %. MYCN amplification had a strong impact on prognosis and therefore we consider it unacceptable that many patients were not studied for MYCN and probably inadequately treated. Ten-year survival rates were shown to decrease: EFS from 73 to 70 % and OS from 81 to 74 %, indicating a risk of late events, particularly in stage 4s. Population-based registries like European ENCCA WP 11-task 11 will possibly clarify these data.
Keywords: Biomarkers, Tumor; Child; Child, Preschool; Clinical Trials as Topic; Combined Modality Therapy; Female; Follow-Up Studies; Gene Amplification; Humans; Infant; Infant, Newborn; Male; N-Myc Proto-Oncogene Protein; Neoplasm Staging; Neuroblastoma; Prognosis; Survival Rate

Is middle cerebral artery Doppler related to neonatal and 2-year infant outcome in early fetal growth restriction? - Stampalija, Tamara; Arabin, Birgit; Wolf, Hans; Bilardo, Caterina M; Lees, Christoph (Am J Obstet Gynecol, 2017)
BACKGROUND: Reduced fetal middle cerebral artery Doppler impedance is associated with hypoxemia in fetal growth restriction. It remains unclear as to whether this finding could be useful in timing delivery, especially in the third trimester. In this regard there is a paucity of evidence from prospective studies. OBJECTIVES: The aim of this study was to determine whether there is an association between middle cerebral artery Doppler impedance and its ratio with the umbilical artery in relation to neonatal and 2 year infant outcome in early fetal growth restriction (26-31 weeks of gestation). Additionally we sought to explore which ratio is more informative for clinical use. STUDY DESIGN: This is a secondary analysis from the Trial of Randomized Umbilical and Fetal Flow in Europe, a prospective, multicenter, randomized management study on different antenatal monitoring strategies (ductus venosus Doppler changes and computerized cardiotocography short-term variation) in fetal growth restriction diagnosed between 26 and 31 weeks. We analyzed women with middle cerebral artery Doppler measurement at study entry and within 1 week before delivery and with complete postnatal follow-up (374 of 503). The primary outcome was survival without neurodevelopmental impairment at 2 years corrected for prematurity. Neonatal outcome was defined as survival until first discharge home without severe neonatal morbidity. Z-scores were calculated for middle cerebral artery pulsatility index and both umbilicocerebral and cerebroplacental ratios. Odds ratios of Doppler parameter Z-scores for neonatal and 2 year infant outcome were calculated by multivariable logistic regression analysis adjusted for gestational age and birthweight p50 ratio. RESULTS: Higher middle cerebral artery pulsatility index at inclusion but not within 1 week before delivery was associated with neonatal survival without severe morbidity (odds ratio, 1.24; 95% confidence interval, 1.02-1.52). Middle cerebral artery pulsatility index Z-score and umbilicocerebral ratio Z-score at inclusion were associated with 2 year survival with normal neurodevelopmental outcome (odds ratio, 1.33; 95% confidence interval, 1.03-1.72, and odds ratio, 0.88; 95% confidence interval, 0.78-0.99, respectively) as were gestation at delivery and birthweight p50 ratio (odds ratio, 1.41; 95% confidence interval, 1.20-1.66, and odds ratio, 1.86; 95% confidence interval, 1.33-2.60, respectively). When comparing cerebroplacental ratio against umbilicocerebral ratio, the incremental range of the cerebroplacental ratio tended toward zero, whereas the umbilicocerebral ratio tended toward infinity as the values became more abnormal. CONCLUSION: In a monitoring protocol based on ductus venosus and cardiotocography in early fetal growth restriction (26-31 weeks of gestation), the impact of middle cerebral artery Doppler and its ratios on outcome is modest and less marked than birthweight and delivery gestation. It is unlikely that middle cerebral artery Doppler and its ratios are informative in optimizing the timing of delivery in fetal growth restriction before 32 weeks of gestation. The umbilicocerebral ratio allows for a better differentiation in the abnormal range than the cerebroplacental ratio.
Keywords: Birth Weight; Child Development; Child, Preschool; Delivery, Obstetric; Female; Fetal Growth Retardation; Gestational Age; Humans; Middle Cerebral Artery; Pregnancy; Prospective Studies; Pulsatile Flow; Ultrasonography, Doppler; Ultrasonography, Prenatal; Umbilical Arteries

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

Pediatric gastrointestinal bleeding: Perspectives from the Italian Society of Pediatric Gastroenterology. - Romano, Claudio; Oliva, Salvatore; Martellossi, Stefano; Miele, Erasmo; Arrigo, Serena; Graziani, Maria Giovanna; Cardile, Sabrina; Gaiani, Federica; de'Angelis, Gian Luigi; Torroni, Filippo (World J Gastroenterol, 2017)
There are many causes of gastrointestinal bleeding (GIB) in children, and this condition is not rare, having a reported incidence of 6.4%. Causes vary with age, but show considerable overlap; moreover, while many of the causes in the pediatric population are similar to those in adults, some lesions are unique to children. The diagnostic approach for pediatric GIB includes definition of the etiology, localization of the bleeding site and determination of the severity of bleeding; timely and accurate diagnosis is necessary to reduce morbidity and mortality. To assist medical care providers in the evaluation and management of children with GIB, the "Gastro-Ped Bleed Team" of the Italian Society of Pediatric Gastroenterology, Hepatology and Nutrition (SIGENP) carried out a systematic search on MEDLINE PubMed (http://www.ncbi.nlm.nih.gov/pubmed/) to identify all articles published in English from January 1990 to 2016; the following key words were used to conduct the electronic search: "upper GIB" and "pediatric" [all fields]; "lower GIB" and "pediatric" [all fields]; "obscure GIB" and "pediatric" [all fields]; "GIB" and "endoscopy" [all fields]; "GIB" and "therapy" [all fields]. The identified publications included articles describing randomized controlled trials, reviews, case reports, cohort studies, case-control studies and observational studies. References from the pertinent articles were also reviewed. This paper expresses a position statement of SIGENP that can have an immediate impact on clinical practice and for which sufficient evidence is not available in literature. The experts participating in this effort were selected according to their expertise and professional qualifications.
Keywords: Adolescent; Child; Child, Preschool; Diagnostic Imaging; Endoscopy; Gastroenterology; Gastrointestinal Diseases; Gastrointestinal Hemorrhage; Hemodynamics; Humans; Infant; Infant, Newborn; Italy; Pediatrics; Recurrence; Societies, Medical

Pediatric Ovarian Torsion and its Recurrence: A Multicenter Study. - Bertozzi, Mirko; Esposito, Ciro; Vella, Claudio; Briganti, Vito; Zampieri, Nicola; Codrich, Daniela; Ubertazzi, Michele; Trucchi, Alessandro; Magrini, Elisa; Battaglia, Sonia; Bini, Vittorio; Conighi, Maria Luisa; et al. (J Pediatr Adolesc Gynecol, 2017)
STUDY OBJECTIVE: To report results of a retrospective multicentric Italian survey concerning the management of pediatric ovarian torsion (OT) and its recurrence. DESIGN: Multicenter retrospective cohort study. SETTING: Italian Units of Pediatric Surgery. PARTICIPANTS: Participants were female aged 1-14 years of age with surgically diagnosed OT between 2004 and 2014. INTERVENTIONS: Adnexal detorsion, adnexectomy, mass excision using laparoscopy or laparotomy. Different kinds of oophoropexy (OPY) for OT or recurrence, respectively. MAIN OUTCOME MEASURES: A total of 124 questionnaires were returned and analyzed to understand the current management of pediatric OT and its recurrence. The questionnaires concerned patient age, presence of menarche, OT site, presence and type of mass, performed procedure, OPY technique adopted, intra- and postoperative complications, recurrence and site, procedure performed for recurrence, OPY technique for recurrence, and 1 year follow-up of detorsed ovaries. RESULTS: Mean age at surgery was 9.79 ± 3.54 years. Performed procedures were open adnexectomy (52 of 125; 41.6%), laparoscopic adnexectomy (25 of 125; 20%), open detorsion (10 of 125; 8%), and laparoscopic detorsion (38 of 125; 30.4%). Recurrence occurred in 15 of 125 cases (12%) and resulted as significant (P = .012) if associated with a normal ovary at the first episode of torsion. Recurrence occurred only in 1 of 19 cases after OPY (5.2%). Ultrasonographic results of detorsed ovaries were not significant whether an OPY was performed or not (P = 1.00). CONCLUSION: Unfortunately, oophorectomy and open technique are still widely adopted even if not advised. Recurrence is not rare and the risk is greater in patients without ovarian masses. OPY does not adversely affect ultrasonographic results at 1 year. When possible OPY should be performed at the first episode of OT.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Female; Humans; Infant; Italy; Laparoscopy; Laparotomy; Menarche; Ovarian Diseases; Ovariectomy; Postoperative Complications; Recurrence; Retrospective Studies; Surveys and Questionnaires; Torsion Abnormality

Phenotypic expression of 19q13.32 microdeletions: Report of a new patient and review of the literature. - Travan, Laura; Naviglio, Samuele; De Cunto, Angela; Pellegrin, Andrea; Pecile, Vanna; Spinelli, Alessandro Mauro; Cappellani, Stefania; Faletra, Flavio (Am J Med Genet A, 2017)
The phenotypic manifestations of microdeletions in the 19q13.32 region are still poorly known. In this paper we report a patient who presented with hypotonia, developmental delay, facial dysmorphism, micrognathia, kyphoscoliosis, and buried penis. Chromosomal microarray revealed an interstitial 327 kb de novo microdeletion in the 19q13.32 region comprising eight genes (ARGHAP35, NPAS1, TMEM160, ZC3H4, SAE1, BBC3, MIR3190, and MIR3191). Previously reported cases of microdeletions in the 19q13.32 region were reviewed and compared to our patient, highlighting the common features of a possible 19q13.32 microdeletion syndrome.

Predictors of Relapse after Discontinuing Systemic Treatment in Childhood Autoimmune Chronic Uveitis. - Simonini, Gabriele; Bracaglia, Claudia; Cattalini, Marco; Taddio, Andrea; Brambilla, Alice; de Libero, Cinzia; Pires Marafon, Denise; Caputo, Roberto; Cimaz, Rolando (J Rheumatol, 2017)
OBJECTIVE: To identify clinical predictors of relapse in childhood autoimmune chronic uveitis after stopping systemic treatment. METHODS: A retrospective, multicenter, cohort study. RESULTS: Ninety-four children in remission, receiving no treatments and with at least a 6-month followup, were enrolled. A higher probability of maintaining remission after discontinuing treatment was shown in idiopathic compared with juvenile idiopathic arthritis uveitis (Mantel-Cox chi-square = 23.21) if inactivity had been obtained within 6 months from starting systemic treatment (Mantel-Cox chi-square = 24.17) and by antitumor necrosis factor-α treatment (Mantel-Cox chi-square = 6.43). CONCLUSION: Type of disease, time, and type of systemic therapy to achieve inactivity predict different duration of uveitis remission after treatment withdrawal.
Keywords: Adolescent; Antirheumatic Agents; Autoimmune Diseases; Child; Child, Preschool; Female; Humans; Male; Predictive Value of Tests; Recurrence; Retrospective Studies; Treatment Outcome; Uveitis; Withholding Treatment

Pregnant with HIV before age 25: data from a large national study in Italy, 2001-2016. - Floridia, M; Masuelli, G; Tamburrini, E; Cetin, I; Liuzzi, G; Martinelli, P; Guaraldi, G; Spinillo, A; Vimercati, A; Maso, G; Pinnetti, C; Frisina, V; et al. (Epidemiol Infect, 2017)
Young pregnant women with HIV may be at significant risk of unplanned pregnancy, lower treatment coverage, and other adverse pregnancy outcomes. In a large cohort of pregnant women with HIV in Italy, among 2979 pregnancies followed in 2001-2016, 9·0% were in women <25 years, with a significant increase over time (2001-2005: 7·0%; 2006-2010: 9·1%; 2011-2016: 12·2%, P < 0·001). Younger women had a lower rate of planned pregnancy (23·2% vs. 37·7%, odds ratio (OR) 0·50, 95% confidence interval (CI) 0·36-0·69), were more frequently diagnosed with HIV in pregnancy (46·5% vs. 20·9%, OR 3·29, 95% CI 2·54-4·25), and, if already diagnosed with HIV before pregnancy, were less frequently on antiretroviral treatment at conception (<25 years: 56·3%; ⩾25 years: 69·0%, OR 0·58, 95% CI 0·41-0·81). During pregnancy, treatment coverage was almost universal in both age groups (98·5% vs. 99·3%), with no differences in rate of HIV viral suppression at third trimester and adverse pregnancy outcomes. The data show that young women represent a growing proportion of pregnant women with HIV, and are significantly more likely to have unplanned pregnancy, undiagnosed HIV infection, and lower treatment coverage at conception. During pregnancy, antiretroviral treatment, HIV suppression, and pregnancy outcomes are similar compared with older women. Earlier intervention strategies may provide additional benefits in the quality of care for women with HIV.
Keywords: Adolescent; Cohort Studies; Female; HIV Infections; Humans; Italy; Odds Ratio; Pregnancy; Young Adult

A premenarcheal girl with urogenital bleeding. - Lora, Angela; Scrimin, Federica; Taddio, Andrea; Ventura, Alessandro; Barbi, Egidio (Arch Dis Child, 2017)

Presentation of acute suppurative parotitis in a newborn with incessant crying. - Velkoski, Angelika; Amoroso, Stefano; Brovedani, Pierpaolo; Cont, Gabriele; Trappan, Antonella; Travan, Laura (Arch Dis Child Fetal Neonatal Ed, 2017)
Keywords: Acute Disease; Anti-Bacterial Agents; Crying; Female; Humans; Infant, Newborn; Parotitis; Staphylococcal Infections; Staphylococcus aureus

Qualitative questionnaire on the psychosocial wellbeing of mothers of children with BEEC. - Di Grazia, Massimo; Pellizzoni, Sandra; Tonegatti, Luca Giacomo; Rigamonti, Waifro (J Pediatr Urol, 2017)
INTRODUCTION: The bladder exstrophy-epispadias complex (BEEC) represents a spectrum of malformations that affect the anatomical and functional structure of the urogenital system. The parents of patients affected by this condition are subject to particularly stressful situations, such as worrying about their child's health, long hospital stays, concerns about the health and constant need for personal care for their children, that can profoundly compromise the quality of family life. OBJECTIVE: The objective of this explorative qualitative study is to evaluate the social situation and the psychological strategies implemented by the mothers of children between 6 and 10 years of age who are affected by BEEC. STUDY DESIGN: Fourteen mothers of children aged 6-10 years and affected by BEEC (9 boys and 5 girls) were interviewed. Data on the mothers' experiences were collected through semi-structured interviews (Table). RESULTS: The qualitative analysis of the interviews showed that participants described experiences that were characterised by emotions such as fear and anger. Each mother had implemented a different and, sometimes, dysfunctional strategy in order to cope with the complex situation of the son/daughter. The aspects that most clearly emerged from mothers' descriptions were (1) the traumatic situation at the birth of the baby, (2) the sense of embarrassment concerning the pathological condition as the child was growing and the consequent sense of isolation of the mother, and (3) the fluctuation of feelings towards the multidisciplinary staff, which was sometimes seen as an important source of help and some other times as too destabilising and not helpful at all. DISCUSSION: The study provided some insight into the psychological and social conditions experienced by mothers of children with BEEC, which could serve as a basis for developing multidisciplinary teams with greater awareness about families living with this condition and better timing in addressing their needs. CONCLUSIONS: Mothers of children with BEEC show emotional and social difficulties. This is a crucial aspect to consider when planning a multidisciplinary approach to the treatment/therapy, especially considering that children examined in this study are approaching adolescence.
Keywords: Adaptation, Psychological; Adolescent; Bladder Exstrophy; Child; Epispadias; Female; Humans; Long-Term Care; Male; Mother-Child Relations; Mothers; Qualitative Research; Quality of Life; Stress, Psychological; Surveys and Questionnaires; Treatment Outcome

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Rate, correlates and outcomes of repeat pregnancy in HIV-infected women. - Floridia, M; Tamburrini, E; Masuelli, G; Martinelli, P; Spinillo, A; Liuzzi, G; Vimercati, A; Alberico, S; Maccabruni, A; Pinnetti, C; Frisina, V; Dalzero, S; et al. (HIV Med, 2017)
OBJECTIVES: The aim of the study was to assess the rate, determinants, and outcomes of repeat pregnancies in women with HIV infection. METHODS: Data from a national study of pregnant women with HIV infection were used. Main outcomes were preterm delivery, low birth weight, CD4 cell count and HIV plasma viral load. RESULTS: The rate of repeat pregnancy among 3007 women was 16.2%. Women with a repeat pregnancy were on average younger than those with a single pregnancy (median age 30 vs. 33 years, respectively), more recently diagnosed with HIV infection (median time since diagnosis 25 vs. 51 months, respectively), and more frequently of foreign origin [odds ratio (OR) 1.36; 95% confidence interval (CI) 1.10-1.68], diagnosed with HIV infection in the current pregnancy (OR: 1.69; 95% CI: 1.35-2.11), and at their first pregnancy (OR: 1.33; 95% CI: 1.06-1.66). In women with sequential pregnancies, compared with the first pregnancy, several outcomes showed a significant improvement in the second pregnancy, with a higher rate of antiretroviral treatment at conception (39.0 vs. 65.4%, respectively), better median maternal weight at the start of pregnancy (60 vs. 61 kg, respectively), a higher rate of end-of-pregnancy undetectable HIV RNA (60.7 vs. 71.6%, respectively), a higher median birth weight (2815 vs. 2885 g, respectively), lower rates of preterm delivery (23.0 vs. 17.7%, respectively) and of low birth weight (23.4 vs. 15.4%, respectively), and a higher median CD4 cell count (+47 cells/μL), with almost no clinical progression to Centers for Disease Control and Prevention stage C (CDC-C) HIV disease (0.3%). The second pregnancy was significantly more likely to end in voluntary termination than the first pregnancy (11.4 vs. 6.1%, respectively). CONCLUSIONS: Younger and foreign women were more likely to have a repeat pregnancy; in women with sequential pregnancies, the second pregnancy was characterized by a significant improvement in several outcomes, suggesting that women with HIV infection who desire multiple children may proceed safely and confidently with subsequent pregnancies.
Keywords: Adult; Anti-HIV Agents; CD4 Lymphocyte Count; Emigrants and Immigrants; Female; HIV Infections; HIV-1; Humans; Infant, Low Birth Weight; Pregnancy; Premature Birth; Viral Load

Retrospective study on the incidence and outcome of proven and probable invasive fungal infections in high-risk pediatric onco-hematological patients. - Cesaro, Simone; Tridello, Gloria; Castagnola, Elio; Calore, Elisabetta; Carraro, Francesca; Mariotti, Ilaria; Colombini, Antonella; Perruccio, Katia; Decembrino, Nunzia; Russo, Giovanna; Maximova, Natalia; Baretta, Valentina; et al. (Eur J Haematol, 2017)
BACKGROUND: Invasive fungal infection (IFI) is a cause of morbidity, mortality and increased health costs in children undergoing chemotherapy or hematopoietic stem cell transplant (HSCT). METHODS: Multicenter, retrospective study to assess the incidence, outcome of proven and probable IFI (PP-IFI) in children treated for acute leukemia, non-Hodgkin lymphoma or who underwent HSCT from 2006 to 2012. RESULTS: Over the 7-year period, 127 PP-IFI were diagnosed in 123 patients, median age of 9.7 years. The 1-year cumulative incidence was 2.5% (CI 1.8-3.7) after frontline chemotherapy, 9.4% (CI 5.8-15.0) after relapse, and 5.3% (CI 3.9-7.1) after HSCT. Severe neutropenia was present in 98 (77%) patients. Culture-proven agents were Candida spp., mostly non-albicans, 28, mold 23, whereas three proven IFI were identified by histopathology. Favorable response to treatment within 3 months from diagnosis was observed in 77 (89%). The overall ninety-day probability of survival was 68% (CI 59-76). CONCLUSIONS: About two-thirds of pediatric patients with PP-IFI survived, regardless of whether the infection occurred after frontline chemotherapy, reinduction chemotherapy for disease relapse, or after HSCT. Further prospective studies are needed to define the impact of antifungal prophylaxis and early combination therapy on short-term overall survival.
Keywords: Adolescent; Antifungal Agents; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Drug Therapy, Combination; Female; Hematologic Neoplasms; Hematopoietic Stem Cell Transplantation; Humans; Incidence; Male; Mycoses; Patient Outcome Assessment; Retrospective Studies; Survival Analysis; Treatment Outcome

Shifts of subgingival bacterial population after nonsurgical and pharmacological therapy of localized aggressive periodontitis, followed for 1 year by Ion Torrent PGM platform. - Campisciano, Giuseppina; Toschetti, Annamaria; Comar, Manola; Taranto, Rosanna Di; Berton, Federico; Stacchi, Claudio (Eur J Dent, 2017)
The possibility of targeting the hypervariable region V3 of the 16S rRNA gene using Ion Torrent Personal Genome Machine (PGM) could provide a complete analysis of subgingival plaque samples, potentially able to identify microbiological species missed by culture-based methods. A 16-year-old female smoker patient, affected by localized aggressive periodontitis, underwent a full-mouth disinfection protocol and was inserted in a 3-month recall program. Microbiological samples were collected at baseline and at 30, 100, 365 days follow-up and analyzed by Ion Torrent PGM. , , , and were the most represented pathogens at baseline. Nonsurgical treatment and systemic antibiotics drastically lowered the anaerobic species, and their presence remained limited after 100 days, while a consistent recolonization by anaerobic bacteria was detected at 365 days. The patient showed a general improvement of periodontal conditions. Differently from polymerase chain reaction and other microarray techniques, Ion Torrent performs a quantitative analysis of the microbiota, irrespective of the searched species. An accurate definition of the shifts of the bacterial community might help periodontal researchers for a better understanding of the impact of different treatment approaches or in intercepting nonresponsive conditions.

Synthesis of Lipophilic Core-Shell FeO@SiO@Au Nanoparticles and Polymeric Entrapment into Nanomicelles: A Novel Nanosystem for in Vivo Active Targeting and Magnetic Resonance-Photoacoustic Dual Imaging. - Monaco, Ilaria; Arena, Francesca; Biffi, Stefania; Locatelli, Erica; Bortot, Barbara; La Cava, Francesca; Marini, Giada Maria; Severini, Giovanni Maria; Terreno, Enzo; Comes Franchini, Mauro (Bioconjug Chem, 2017)
In this work, iron/silica/gold core-shell nanoparticles (FeO@SiO@Au NPs) characterized by magnetic and optical properties have been synthesized to obtain a promising theranostic platform. To improve their biocompatibility, the obtained multilayer nanoparticles have been entrapped in polymeric micelles, decorated with folic acid moieties, and tested in vivo for photoacoustic and magnetic resonance imaging detection of ovarian cancer.
Keywords: Animals; Cell Proliferation; Female; Ferric Compounds; Folic Acid; Gold; Humans; Image Processing, Computer-Assisted; Magnetic Resonance Imaging; Magnetite Nanoparticles; Mice; Mice, Inbred BALB C; Mice, Nude; Micelles; Multimodal Imaging; Ovarian Neoplasms; Photoacoustic Techniques; Polymers; Silicon Dioxide; Tumor Cells, Cultured; Xenograft Model Antitumor Assays

An Update on the Pathogenesis and Treatment of Chronic Recurrent Multifocal Osteomyelitis in Children. - Taddio, Andrea; Zennaro, Floriana; Pastore, Serena; Cimaz, Rolando (Paediatr Drugs, 2017)
Chronic recurrent multifocal osteomyelitis (CRMO), also known as chronic non-bacterial osteomyelitis (CNO), is a rare inflammatory disorder that primarily affects children. It is characterized by pain, local bone expansion, and radiological findings suggestive of osteomyelitis, usually at multiple sites. CRMO predominantly affects the metaphyses of long bones, but involvement of the clavicle or mandible are suggestive of the diagnosis. CRMO is a diagnosis of exclusion, and its pathogenesis remains unknown. Differential diagnosis includes infection, malignancies, benign bone tumors, metabolic disorders, and other autoinflammatory disorders. Biopsy of the bone lesion is not often required but could be necessary in unclear cases, especially for differentiation from bone neoplasia. Non-steroidal anti-inflammatory drugs (NSAIDs) are the first-line treatment. Alternative therapies have been used, including corticosteroids, methotrexate, bisphosphonates, and tumor necrosis factor (TNF)-α inhibitors. No guidelines have been established regarding diagnosis and treatment options. This manuscript gives an overview of the most recent findings on the pathogenesis of CRMO and clinical approaches for patients with the condition.
Keywords: Adrenal Cortex Hormones; Anti-Inflammatory Agents, Non-Steroidal; Child; Chronic Disease; Diagnosis, Differential; Humans; Osteomyelitis; Recurrence; Tumor Necrosis Factor-alpha

Whole-Genome Sequencing Coupled to Imputation Discovers Genetic Signals for Anthropometric Traits. - Tachmazidou, Ioanna; Süveges, Dániel; Min, Josine L; Ritchie, Graham R S; Steinberg, Julia; Walter, Klaudia; Iotchkova, Valentina; Schwartzentruber, Jeremy; Huang, Jie; Memari, Yasin; McCarthy, Shane; Crawford, Andrew A; et al. (Am J Hum Genet, 2017)
Deep sequence-based imputation can enhance the discovery power of genome-wide association studies by assessing previously unexplored variation across the common- and low-frequency spectra. We applied a hybrid whole-genome sequencing (WGS) and deep imputation approach to examine the broader allelic architecture of 12 anthropometric traits associated with height, body mass, and fat distribution in up to 267,616 individuals. We report 106 genome-wide significant signals that have not been previously identified, including 9 low-frequency variants pointing to functional candidates. Of the 106 signals, 6 are in genomic regions that have not been implicated with related traits before, 28 are independent signals at previously reported regions, and 72 represent previously reported signals for a different anthropometric trait. 71% of signals reside within genes and fine mapping resolves 23 signals to one or two likely causal variants. We confirm genetic overlap between human monogenic and polygenic anthropometric traits and find signal enrichment in cis expression QTLs in relevant tissues. Our results highlight the potential of WGS strategies to enhance biologically relevant discoveries across the frequency spectrum.
Keywords: Anthropometry; Body Height; Cohort Studies; Databases, Genetic; DNA Methylation; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipodystrophy; Male; Meta-Analysis as Topic; Obesity; Physical Chromosome Mapping; Quantitative Trait Loci; Sequence Analysis, DNA; Sex Characteristics; Syndrome; United Kingdom

Zika virus induces inflammasome activation in the glial cell line U87-MG. - Tricarico, Paola Maura; Caracciolo, Ilaria; Crovella, Sergio; D'Agaro, Pierlanfranco (Biochem Biophys Res Commun, 2017)
In the last years, neurological complications related to Zika virus (ZIKV) infection have emerged as an important threat to public health worldwide. ZIKV infection has been associated to neurological disorders such as congenital microcephaly in newborns and Guillain-Barré syndrome, myelopathy and encephalitis in adults. ZIKV is characterized by neurotropism and neurovirulence. Several studies have identified microglial nodules, gliosis, neuronal and glial cells degeneration and necrosis in the brain of ZIKV infected infants, suggesting that ZIKV could play a role in these neurological disorders through neuroinflammation and microglial activation. Little information is available about neuroinflammation and ZIKV-related neurological disorders. Therefore, we investigated if ZIKV is able to infect a glial cell line (U87-MG) and how the glial cell line responds to this infection in terms of inflammation (IL-1β, NLRP-3 and CASP-1), oxidative stress (SOD2 and HemeOX) and cell death. We observed a significant increase of ZIKV load in both cells and supernatants after 72 h, compared to 48 h of infection. We found that ZIKV infection induces an increase of IL-1β, NLRP-3 and CASP-1 genes expression. Significant increase of IL-1β and unchanged pro-IL-1β protein levels have also been detected. Moreover, we observed SOD2 and HemeOX increased gene expression mainly after 72 h post ZIKV infection. Subsequently, we found a decrease of U87-MG cell viability, after both 48 h and 72 h of ZIKV infection. Our results show that U87-MG cells are susceptible to ZIKV infection. ZIKV is able to successfully replicate in infected cells causing oxidative stress, NLRP3 inflammasome activation and subsequent release of mature IL-1β; this process culminates in cell death. Thus, considering the central role of neuroinflammation in neurological disorders, it is important to comprehend every aspect of this mechanism in order to better understand the pathogenesis of ZIKV infection and to identify possible strategies to fight the virus by rescuing cell death.
Keywords: Apoptosis; Cell Line; Cytokines; Humans; Immunity, Innate; Inflammasomes; Inflammation Mediators; Neuroglia; Oxidative Stress; Virus Replication; Zika Virus

Action of methotrexate and tofacitinib on directly stimulated and bystander-activated lymphocytes. - Piscianz, Elisa; Candilera, Vanessa; Valencic, Erica; Loganes, Claudia; Paron, Greta; De Iudicibus, Sara; Decorti, Giuliana; Tommasini, Alberto (Mol Med Rep, 2016)
Chronic inflammation associated with autoimmune activation is characteristic of rheumatic diseases from childhood to adulthood. In recent decades, significant improvements in the treatment of these types of disease have been achieved using disease modifying anti-rheumatic drugs (DMARDs), such as methotrexate (MTX) and, more recently, using biologic inhibitors. The recent introduction of kinase inhibitors (for example, tofacitinib; Tofa) further increases the available ARDs. However, there are patients that do not respond to any treatment strategies, for whom combination therapies are proposed. The data regarding the combined action of different drugs is lacking and the knowledge of the mechanisms of ARDs and their actions upon pathogenic lymphocytes, which are hypothesized to sustain disease, is poor. An in vitro model of inflammation was developed in the current study, in which stimulated and unstimulated lymphocytes were cultured together, but tracked separately, to investigate the action of MTX and Tofa on the two populations. By analysing lymphocyte proliferation and activation, and cytokine secretion in the culture supernatants, it was established that, due to the presence of activated cells, unstimulated cells underwent a bystander activation that was modulated by the ARDs. Additionally, varying administration schedules were demonstrated to affect lymphocytes differently in vitro, either directly or via bystander activation. Furthermore, MTX and Tofa exerted different effects; while MTX showed an antiproliferative effect, Tofa marginally effected activation, although only a slight antiproliferative action, which could be potentiated by sequential treatment with MTX. Thus, it was hypothesized that these differences may be exploited in sequential therapeutic strategies, to maximize the anti‑rheumatic effect. These findings are notable and must be accounted for, as bystander‑activated cells in vivo could contribute to the spread of autoimmune activation and disease progression.

Acute lobar nephritis in children: Not so easy to recognize and manage. - Bibalo, Cristina; Apicella, Andrea; Guastalla, Veronica; Marzuillo, Pierluigi; Zennaro, Floriana; Tringali, Carmela; Taddio, Andrea; Germani, Claudio; Barbi, Egidio (World J Clin Pediatr, 2016)
Acute lobar nephritis (ALN) is a localized non-liquefactive inflammatory renal bacterial infection, which typically involves one or more lobes. ALN is considered to be a midpoint in the spectrum of upper urinary tract infection, a spectrum ranging from uncomplicated pyelonephritis to intrarenal abscess. This condition may be difficult to recognize due to the lack of specific symptoms and laboratory findings. Therefore the disease is probably underdiagnosed. Computed tomography scanning represents the diagnostic gold standard for ALN, but magnetic resonance imagine could be considered in order to limit irradiation. The diagnosis is relevant since initial intravenous antibiotic therapy and overall length of treatment should not be shorter than 3 wk. We review the literature and analyze the ALN clinical presentation starting from four cases with the aim to give to the clinicians the elements to suspect and recognize the ALN in children.

An Animal Model for the Juvenile Non-Alcoholic Fatty Liver Disease and Non-Alcoholic Steatohepatitis. - Marin, Veronica; Rosso, Natalia; Dal Ben, Matteo; Raseni, Alan; Boschelle, Manuela; Degrassi, Cristina; Nemeckova, Ivana; Nachtigal, Petr; Avellini, Claudio; Tiribelli, Claudio; Gazzin, Silvia (PLoS One, 2016)
Non Alcoholic Fatty Liver Disease (NAFLD) and Non-Alcoholic Steatohepatitis (NASH) are the hepatic manifestations of the metabolic syndrome; worrisome is the booming increase in pediatric age. To recreate the full spectrum of juvenile liver pathology and investigate the gender impact, male and female C57Bl/6 mice were fed with high fat diet plus fructose in the drinking water (HFHC) immediately after weaning (equal to 3-years old human), and disease progression followed for 16 weeks, until adults (equal to 30-years old human). 100% of subjects of both genders on HFHC diet developed steatosis in 4weeks, and some degree of fibrosis in 8weeks, with the 86% of males and 15% of females presenting a stage 2 fibrosis at 16weeks. Despite a similar final liver damage both groups, a sex difference in the pathology progression was observed. Alterations in glucose homeostasis, dyslipidemia, hepatomegaly and obese phenotype were evident from the very beginning in males with an increased hepatic inflammatory activity. Conversely, such alterations were present in females only at the end of the HFHC diet (with the exception of insulin resistance and the hepatic inflammatory state). Interestingly, only females showed an altered hepatic redox state. This juvenile model appears a good platform to unravel the underlying gender dependent mechanisms in the progression from NAFLD to NASH, and to characterize novel therapeutic approaches.

Anti-ApoA-1 IgG serum levels predict worse poststroke outcomes. - Carbone, Federico; Satta, Nathalie; Montecucco, Fabrizio; Virzi, Julien; Burger, Fabienne; Roth, Aline; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; et al. (Eur J Clin Invest, 2016)
BACKGROUND: Autoantibodies to apolipoprotein A-1 (anti-ApoA-1 IgG) were shown to predict major adverse cardiovascular events and promote atherogenesis. However, their potential relationship with clinical disability and ischaemic lesion volume after acute ischaemic stroke (AIS) remains unexplored. MATERIALS AND METHODS: We included n = 76 patients admitted for AIS and we investigated whether baseline serum anti-ApoA-1 IgG levels could predict (i) AIS-induced clinical disability [assessed by the modified Rankin Scale (mRS)], and (ii) AIS-related ischaemic lesion volume [assessed by Computed Tomography (CT)]. We also evaluated the possible pro-apoptotic and pro-necrotic effects of anti-ApoA-1 IgG on human astrocytoma cell line (U251) using flow cytometry. RESULTS: High levels of anti-ApoA-1 IgG were retrieved in 15·8% (12/76) of patients. Increased baseline levels of anti-ApoA-1 IgG were independently correlated with worse mRS [β = 0·364; P = 0·002; adjusted odds ratio (OR): 1·05 (95% CI 1·01-1·09); P = 0·017] and CT-assessed ischaemic lesion volume [β = 0·333; P < 0·001; adjusted OR: 1·06 (95% CI 1·01-1·12); P = 0·048] at 3 months. No difference in baseline clinical, biochemical and radiological characteristics was observed between patients with high vs. low levels of anti-ApoA-1 IgG. Incubating human astrocytoma cells with anti-ApoA-1 IgG dose dependently induced necrosis and apoptosis of U251 cells in vitro. CONCLUSION: Anti-ApoA-1 IgG serum levels at AIS onset are associated with poorer clinical recovery and worse brain lesion volume 3 months after AIS. These observations could be partly explained by the deleterious effect of anti-ApoA-1 IgG on human brain cell survival in vitro and may have clinical implication in the prediction of poor outcome in AIS.

Association of the HLA-G 3'UTR polymorphisms with colorectal cancer in Italy: a first insight. - Garziera, M; Catamo, E; Crovella, S; Montico, M; Cecchin, E; Lonardi, S; Mini, E; Nobili, S; Romanato, L; Toffoli, G (Int J Immunogenet, 2016)
This study aimed to explore functional and regulatory polymorphisms and haplotypes at the HLA-G 3'UTR region in colorectal cancer development. The presence of nonpolymorphic variants was also evaluated. Three-hundred and eight patients with colorectal cancer and 294 healthy controls were analysed at the germinal level. We found an association with increased risk of colorectal cancer for +2960 14-bp INDEL, +3196 C>G SNPs and UTR-2 haplotype, and a 'protective' role for +3003 T>C, +3010 C>G polymorphisms and UTR-4 haplotype. We detected in 3 distinct patients, a novel nucleotide change (+3037 C>A) and 2 already described rare variants, +3032 G/C (EUR MAF = 0.1%) and +3092 G/T (EUR MAF = 0%). This is the first study showing associations between different polymorphisms in the HLA-G 3'UTR and colorectal cancer susceptibility.

C1q acts in the tumour microenvironment as a cancer-promoting factor independently of complement activation. - Bulla, Roberta; Tripodo, Claudio; Rami, Damiano; Ling, Guang Sheng; Agostinis, Chiara; Guarnotta, Carla; Zorzet, Sonia; Durigutto, Paolo; Botto, Marina; Tedesco, Francesco (Nat Commun, 2016)
Complement C1q is the activator of the classical pathway. However, it is now recognized that C1q can exert functions unrelated to complement activation. Here we show that C1q, but not C4, is expressed in the stroma and vascular endothelium of several human malignant tumours. Compared with wild-type (WT) or C3- or C5-deficient mice, C1q-deficient (C1qa(-/-)) mice bearing a syngeneic B16 melanoma exhibit a slower tumour growth and prolonged survival. This effect is not attributable to differences in the tumour-infiltrating immune cells. Tumours developing in WT mice display early deposition of C1q, higher vascular density and an increase in the number of lung metastases compared with C1qa(-/-) mice. Bone marrow (BM) chimeras between C1qa(-/-) and WT mice identify non-BM-derived cells as the main local source of C1q that can promote cancer cell adhesion, migration and proliferation. Together these findings support a role for locally synthesized C1q in promoting tumour growth.
Keywords: Animals; Apoptosis; Cell Line, Tumor; Cell Movement; Cell Proliferation; Complement Activation; Complement C1q; Complement C3; Complement C5; Humans; Mice; Mice, Inbred C57BL; Mice, Knockout; Neoplasms

Candidate Soluble Immune Mediators in Young Women with High-Risk Human Papillomavirus Infection: High Expression of Chemokines Promoting Angiogenesis and Cell Proliferation. - Zanotta, Nunzia; Tornesello, Maria Lina; Annunziata, Clorinda; Stellato, Giovanni; Buonaguro, Franco Maria; Comar, Manola (PLoS One, 2016)
BACKGROUND: The causal interpretation of cervical immune response to Human Papillomavirus (HPV) infection is complex and poorly characterized mainly due to the delicate balance that exists between viral infection, increase of inflammatory cytokines and host risk factors. This study aims to explore the significance of cervical immune mediators associated to cell survival, angiogenesis and interaction with immune response, in predicting the risk to develop HPV-related intraepithelial lesions. METHODS: A panel of 48 cytokines and growth factors were explored in a selected cohort of 168 immunocompetent women including 88 diagnosed with low (LSIL) or high (HSIL) squamous intraepithelial lesions of the cervix and 80 with normal cervical cytology (NIL). HPV genotyping was performed by Linear Array HPV test and the soluble concentration of 48 immune molecules was analyzed using the Bio-Plex platform. RESULTS: The prevalence of single HR-HPV infection was 30% in NIL and 100% in LSIL and HSIL women. The expression of 13 cytokines, including interleukins IL-6, IL-3, IL-12p40, IL-12p70, IL-16, IL-18, LIF, of chemokines CCL7 (MCP-3), CXCL9 (MIG), CXCL12 (SDF-1α) and of the tropic factors VEGF, G-CSF, M-CSF were significantly associated with the presence of infection, with levels being higher in women with precancerous lesions compared to NIL HPV negative women. Only the growth factor GM-CSF was positively associated with the cytological abnormalities. CONCLUSIONS: The ability of HR-HPV to escape from innate immune recognition and to orchestrate the production of specific inflammatory and growth factors, involved in early inflammatory response and in the cell-proliferating phase of intraepithelial damage, was documented in women before the development of cervical lesions.
Keywords: Adult; Cell Survival; Cervix Uteri; Chemokines; Cohort Studies; Female; Humans; Neovascularization, Pathologic; Papillomaviridae; Papillomavirus Infections

Carbamazepine-induced thrombocytopenic purpura in a child: Insights from a genomic analysis. - Abate, Maria Valentina; Stocco, Gabriele; Devescovi, Raffaella; Carrozzi, Marco; Pierobon, Chiara; Valencic, Erica; Lucafò, Marianna; Di Silvestre, Alessia; d'Adamo, Pio; Tommasini, Alberto; Decorti, Giuliana; Ventura, Alessandro (Blood Cells Mol Dis, 2016)

A Child with Severe Developmental Delay and Growth Retardation. - Rossetto, Elena; Matarazzo, Lorenza; Maschio, Massimo; Taddio, Andrea; Costa, Paola; Ventura, Alessandro (J Pediatr, 2016)

Chronic nonbacterial osteomyelitis may be associated with renal disease and bisphosphonates are a good option for the majority of patients. - Pastore, Serena; Ferrara, Giovanna; Monasta, Lorenzo; Meini, Antonella; Cattalini, Marco; Martino, Silvana; Alessio, Maria; La Torre, Francesco; Teruzzi, Barbara; Gerloni, Valeria; Breda, Luciana; Taddio, Andrea; et al. (Acta Paediatr, 2016)
AIM: The aim of this Italian study was to describe the clinical features, treatment options and outcomes of a cohort of patients with chronic nonbacterial osteomyelitis (CNO). METHODS: This was a retrospective cohort study. Laboratory data, diagnostic imaging, histological features and clinical course are reported. RESULTS: We enrolled 47 patients diagnosed with CNO. Bone pain was the leading symptom, and multifocal disease was present in 87% of the patients. The majority of the bone lesions were located in the appendicular skeleton (58%). Extraosseous manifestations were present in 34% of the patients, and renal involvement was detected in four patients. Inflammatory indices were increased in 80%, and bone x-rays were negative in 15% of the patients. Nonsteroidal anti-inflammatory drugs (NSAIDs) were the first therapy for all patients, achieving clinical remission in 27%. A good response to NSAIDs was significantly associated with a better prognosis. Bisphosphonates were used in 26 patients, with remission in 73%. Only six patients (13%), all with spine involvement, developed sequelae. CONCLUSION: We found a possible association between CNO and renal disease. Bisphosphonates were more likely to lead to clinical remission when NSAIDs and corticosteroids had failed. Vertebral localisation was the only risk factor for potential sequelae.

Clinical Characteristics of Patients Carrying the Q703K Variant of the NLRP3 Gene: A 10-year Multicentric National Study. - Naselli, Aldo; Penco, Federica; Cantarini, Luca; Insalaco, Antonella; Alessio, Mariolina; Tommasini, Alberto; Maggio, Cristina; Obici, Laura; Gallizi, Romina; Cimmino, Marco; Signa, Sara; Lucherini, Orso Maria; et al. (J Rheumatol, 2016)
OBJECTIVE: The aim of our study was to analyze the clinical and functional effect of the p.Q703K (p. Q705K, c. 2107C>A) variant of the NLRP3 gene in a population of patients screened for suspected cryopyrin-associated periodic syndrome (CAPS). METHODS: Since 2002, 580 patients underwent molecular analysis for NLRP3. Data on clinical presentation, response to treatment, and longterm followup were collected using a uniform questionnaire. The pattern of cytokine secretion after lipopolysaccharide stimulation from isolated monocytes was analyzed in 3 patients carrying the p.Q703K variant and 1 patient with a chronic infantile neurologic, cutaneous, articular syndrome phenotype carrying both the p.M406I and p.Q703K, and compared with 7 patients with CAPS with sure pathogenic variants and 6 healthy controls. RESULTS: The p.Q703K variant was found in 57 screened patients with an overall allelic frequency of 5%. The frequency in normal controls was 5.5%. Clinical data at the moment of molecular analysis and at followup were available in 36 patients. Two patients displayed additional mutations of NLRP3. The mean followup was 2.5 years. Thirteen patients (39%) had a final diagnosis different from the original suspicion of CAPS. The remaining 21 patients displayed a mild phenotype mainly characterized by recurrent episodes of urticarial rash and arthralgia. Only 8 patients were treated with anti-interleukin (IL)-1 treatment, with a complete response in 5 patients. The pattern of secretion of IL-1β and other cytokines (IL-6 and IL-1 receptor antagonist) in patients did not display the aberrancies observed in patients with CAPS and was similar to that observed in healthy controls. CONCLUSION: The present study confirms the weak clinical and functional effect of the p.Q703K variant.

Clinical Spectrum of PRKAG2 Syndrome. - Porto, Andrea Giuseppe; Brun, Francesca; Severini, Giovanni Maria; Losurdo, Pasquale; Fabris, Enrico; Taylor, Matthew R G; Mestroni, Luisa; Sinagra, Gianfranco (Circ Arrhythm Electrophysiol, 2016)
Keywords: AMP-Activated Protein Kinases; DNA; Heart Conduction System; Humans; Mutation; Wolff-Parkinson-White Syndrome

Cross-sectional study of coeliac autoimmunity in a population of Vietnamese children. - Zanella, Sara; De Leo, Luigina; Nguyen-Ngoc-Quynh, Le; Nguyen-Duy, Bo; Not, Tarcisio; Tran-Thi-Chi, Mai; Phung-Duc, Son; Le-Thanh, Hai; Malaventura, Cristina; Vatta, Serena; Ziberna, Fabiana; Mazzocco, Martina; et al. (BMJ Open, 2016)
OBJECTIVE: The prevalence of coeliac disease (CD) in Vietnam is unknown. To fill this void, we assessed the prevalence of serological markers of CD autoimmunity in a population of children in Hanoi. SETTING: The outpatient blood drawing laboratory of the largest paediatric hospital in North Vietnam was used for the study, which was part of an international project of collaboration between Italy and Vietnam. PARTICIPANTS: Children having blood drawn for any reason were included. Exclusion criteria were age younger than 2 years, acquired or congenital immune deficiency and inadequate sample. A total of 1961 children (96%) were enrolled (838 females, 1123 males, median age 5.3 years). OUTCOMES: Primary outcome was the prevalence of positive autoimmunity to both IgA antitransglutaminase antibodies (anti-tTG) assessed with an ELISA test and antiendomysial antibodies (EMA). Secondary outcome was the prevalence of CD predisposing human leucocyte antigens (HLA) (HLA DQ2/8) in the positive children and in a random group of samples negative for IgA anti-tTG. RESULTS: The IgA anti-tTG test was positive in 21/1961 (1%; 95% CI 0.61% to 1.53%); however, EMA antibodies were negative in all. HLA DQ2/8 was present in 7/21 (33%; 95% CI 14.5% to 56.9%) of the anti-tTG-positive children and in 72/275 (26%; 95% CI 21% to 32%) of those who were negative. CONCLUSIONS: Coeliac autoimmunity is rare in Vietnam, although prevalence of HLA DQ2/8 is similar to that of other countries. We hypothesise that the scarce exposure to gluten could be responsible for these findings.

Differential expression of GAS5 in rapamycin-induced reversion of glucocorticoid resistance. - Lucafò, Marianna; Bravin, Vanessa; Tommasini, Alberto; Martelossi, Stefano; Rabach, Ingrid; Ventura, Alessandro; Decorti, Giuliana; De Iudicibus, Sara (Clin Exp Pharmacol Physiol, 2016)
This study evaluates the association between the long noncoding RNA GAS5 levels and the anti-proliferative effect of the glucocorticoid (GC) methylprednisolone (MP) alone and in combination with rapamycin in peripheral blood mononuclear cells (PBMCs) obtained from healthy donors. The effect of MP, rapamycin, and MP plus rapamycin was determined in 17 healthy donors by labelling metabolically active cells with [methyl-3H] thymidine and the expression levels of GAS5 gene were evaluated by real-time RT-PCR TaqMan analysis. We confirmed a role for GAS5 in modulating GC response: poor responders presented higher levels of GAS5 in comparison with good responders. Interestingly, when PBMCs were treated with the combination of rapamycin plus MP, the high levels of GAS5 observed for each drug in the MP poor responders group decreased in comparison with rapamycin (P value = 0.0134) or MP alone (P value = 0.0193). GAS5 is involved in GC resistance and co-treatment of rapamycin with GCs restores GC effectiveness in poor responders through the downregulation of the long noncoding RNA. GAS5 could be considered a biomarker to personalize therapy and a novel therapeutic target useful for the development of new pharmacological approaches to restore GC sensitivity.

EPG5-related Vici syndrome: a paradigm of neurodevelopmental disorders with defective autophagy. - Byrne, Susan; Jansen, Lara; U-King-Im, Jean-Marie; Siddiqui, Ata; Lidov, Hart G W; Bodi, Istvan; Smith, Luke; Mein, Rachael; Cullup, Thomas; Dionisi-Vici, Carlo; Al-Gazali, Lihadh; Al-Owain, Mohammed; et al. (Brain, 2016)
Vici syndrome is a progressive neurodevelopmental multisystem disorder due to recessive mutations in the key autophagy gene EPG5. We report genetic, clinical, neuroradiological, and neuropathological features of 50 children from 30 families, as well as the neuronal phenotype of EPG5 knock-down in Drosophila melanogaster. We identified 39 different EPG5 mutations, most of them truncating and predicted to result in reduced EPG5 protein. Most mutations were private, but three recurrent mutations (p.Met2242Cysfs*5, p.Arg417*, and p.Gln336Arg) indicated possible founder effects. Presentation was mainly neonatal, with marked hypotonia and feeding difficulties. In addition to the five principal features (callosal agenesis, cataracts, hypopigmentation, cardiomyopathy, and immune dysfunction), we identified three equally consistent features (profound developmental delay, progressive microcephaly, and failure to thrive). The manifestation of all eight of these features has a specificity of 97%, and a sensitivity of 89% for the presence of an EPG5 mutation and will allow informed decisions about genetic testing. Clinical progression was relentless and many children died in infancy. Survival analysis demonstrated a median survival time of 24 months (95% confidence interval 0-49 months), with only a 10th of patients surviving to 5 years of age. Survival outcomes were significantly better in patients with compound heterozygous mutations (P = 0.046), as well as in patients with the recurrent p.Gln336Arg mutation. Acquired microcephaly and regression of skills in long-term survivors suggests a neurodegenerative component superimposed on the principal neurodevelopmental defect. Two-thirds of patients had a severe seizure disorder, placing EPG5 within the rapidly expanding group of genes associated with early-onset epileptic encephalopathies. Consistent neuroradiological features comprised structural abnormalities, in particular callosal agenesis and pontine hypoplasia, delayed myelination and, less frequently, thalamic signal intensity changes evolving over time. Typical muscle biopsy features included fibre size variability, central/internal nuclei, abnormal glycogen storage, presence of autophagic vacuoles and secondary mitochondrial abnormalities. Nerve biopsy performed in one case revealed subtotal absence of myelinated axons. Post-mortem examinations in three patients confirmed neurodevelopmental and neurodegenerative features and multisystem involvement. Finally, downregulation of epg5 (CG14299) in Drosophila resulted in autophagic abnormalities and progressive neurodegeneration. We conclude that EPG5-related Vici syndrome defines a novel group of neurodevelopmental disorders that should be considered in patients with suggestive features in whom mitochondrial, glycogen, or lysosomal storage disorders have been excluded. Neurological progression over time indicates an intriguing link between neurodevelopment and neurodegeneration, also supported by neurodegenerative features in epg5-deficient Drosophila, and recent implication of other autophagy regulators in late-onset neurodegenerative disease.
Keywords: Agenesis of Corpus Callosum; Animals; Autophagy; Cataract; Child, Preschool; Cross-Sectional Studies; Drosophila melanogaster; Female; Hippocampus; Humans; Male; Mutation; Neurodevelopmental Disorders; Proteins; Retrospective Studies

Evidence for three genetic loci involved in both anorexia nervosa risk and variation of body mass index. - Hinney, A; Kesselmeier, M; Jall, S; Volckmar, A-L; Föcker, M; Antel, J; Heid, I M; Winkler, T W; Grant, S F A; Guo, Y; Bergen, A W; Kaye, W; et al. (Mol Psychiatry, 2016)
The maintenance of normal body weight is disrupted in patients with anorexia nervosa (AN) for prolonged periods of time. Prior to the onset of AN, premorbid body mass index (BMI) spans the entire range from underweight to obese. After recovery, patients have reduced rates of overweight and obesity. As such, loci involved in body weight regulation may also be relevant for AN and vice versa. Our primary analysis comprised a cross-trait analysis of the 1000 single-nucleotide polymorphisms (SNPs) with the lowest P-values in a genome-wide association meta-analysis (GWAMA) of AN (GCAN) for evidence of association in the largest published GWAMA for BMI (GIANT). Subsequently we performed sex-stratified analyses for these 1000 SNPs. Functional ex vivo studies on four genes ensued. Lastly, a look-up of GWAMA-derived BMI-related loci was performed in the AN GWAMA. We detected significant associations (P-values <5 × 10(-5), Bonferroni-corrected P<0.05) for nine SNP alleles at three independent loci. Interestingly, all AN susceptibility alleles were consistently associated with increased BMI. None of the genes (chr. 10: CTBP2, chr. 19: CCNE1, chr. 2: CARF and NBEAL1; the latter is a region with high linkage disequilibrium) nearest to these SNPs has previously been associated with AN or obesity. Sex-stratified analyses revealed that the strongest BMI signal originated predominantly from females (chr. 10 rs1561589; Poverall: 2.47 × 10(-06)/Pfemales: 3.45 × 10(-07)/Pmales: 0.043). Functional ex vivo studies in mice revealed reduced hypothalamic expression of Ctbp2 and Nbeal1 after fasting. Hypothalamic expression of Ctbp2 was increased in diet-induced obese (DIO) mice as compared with age-matched lean controls. We observed no evidence for associations for the look-up of BMI-related loci in the AN GWAMA. A cross-trait analysis of AN and BMI loci revealed variants at three chromosomal loci with potential joint impact. The chromosome 10 locus is particularly promising given that the association with obesity was primarily driven by females. In addition, the detected altered hypothalamic expression patterns of Ctbp2 and Nbeal1 as a result of fasting and DIO implicate these genes in weight regulation.Molecular Psychiatry advance online publication, 17 May 2016; doi:10.1038/mp.2016.71.

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

A Genome-Wide Association Study in isolated populations reveals new genes associated to common food likings. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia; Toniolo, Daniela; Gasparini, Paolo (Rev Endocr Metab Disord, 2016)
Food preferences are the first factor driving food choice and thus nutrition. They involve numerous different senses such as taste and olfaction as well as various other factors such as personal experiences and hedonistic aspects. Although it is clear that several of these have a genetic basis, up to now studies have focused mostly on the effects of polymorphisms of taste receptor genes. Therefore, we have carried out one of the first large scale (4611 individuals) GWAS on food likings assessed for 20 specific food likings belonging to 4 different categories (vegetables, fatty, dairy and bitter). A two-step meta-analysis using three different isolated populations from Italy for the discovery step and two populations from The Netherlands and Central Asia for replication, revealed 15 independent genome-wide significant loci (p < 5 × 10(-8)) for 12 different foods. None of the identified genes coded for either taste or olfactory receptors suggesting that genetics impacts in determining food likings in a much broader way than simple differences in taste perception. These results represent a further step in uncovering the genes that underlie liking of common foods that in the end will greatly help understanding the genetics of human nutrition in general.

Giant Cerebellar Lesion in a Patient With Purulent Ear Drainage. - Mandalà, Marco; Muzzi, Enrico; Trabalzini, Franco (JAMA Otolaryngol Head Neck Surg, 2016)

Global diversity in the TAS2R38 bitter taste receptor: revisiting a classic evolutionary PROPosal. - Risso, Davide S; Mezzavilla, Massimo; Pagani, Luca; Robino, Antonietta; Morini, Gabriella; Tofanelli, Sergio; Carrai, Maura; Campa, Daniele; Barale, Roberto; Caradonna, Fabio; Gasparini, Paolo; Luiselli, Donata; et al. (Sci Rep, 2016)
The ability to taste phenylthiocarbamide (PTC) and 6-n-propylthiouracil (PROP) is a polymorphic trait mediated by the TAS2R38 bitter taste receptor gene. It has long been hypothesized that global genetic diversity at this locus evolved under pervasive pressures from balancing natural selection. However, recent high-resolution population genetic studies of TAS2Rs suggest that demographic events have played a critical role in the evolution of these genes. We here utilized the largest TAS2R38 database yet analyzed, consisting of 5,589 individuals from 105 populations, to examine natural selection, haplotype frequencies and linkage disequilibrium to estimate the effects of both selection and demography on contemporary patterns of variation at this locus. We found signs of an ancient balancing selection acting on this gene but no post Out-Of-Africa departures from neutrality, implying that the current observed patterns of variation can be predominantly explained by demographic, rather than selective events. In addition, we found signatures of ancient selective forces acting on different African TAS2R38 haplotypes. Collectively our results provide evidence for a relaxation of recent selective forces acting on this gene and a revised hypothesis for the origins of the present-day worldwide distribution of TAS2R38 haplotypes.

The Great Pretender: Pediatric Wandering Spleen: Two Case Reports and Review of the Literature. - Radillo, Lucia; Taddio, Andrea; Ghirardo, Sergio; Bramuzzo, Matteo; Pederiva, Federica; Maschio, Massimo; Barbi, Egidio (Pediatr Emerg Care, 2016)
Wandering spleen is a rare condition, typically not only due to embryological defects of the splenic ligaments, but also secondary to trauma and splenomegaly. The most common presentation is acute abdomen with a mobile abdominal mass or recurrent abdominal pain. However, the spleen may be temporary in its normal position, and patients could be asymptomatic. A familiarity, if present, strengthens the diagnostic suspect.Abdominal ultrasonography and computed tomography are the examination of choice, and the management is surgical.

Histopathological data of iron and calcium in the mouse lung after asbestos exposure. - Trevisan, Elisa; Zabucchi, Giuliano; Pascolo, Lorella; Pascotto, Ernesto; Casarsa, Claudia; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; Zweyer, Marina; Borelli, Violetta (Data Brief, 2016)
This data article contains data related to the research article entitled, "Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice" [1]. Asbestos fibers disrupt iron homeostasis in the human and mouse lung, leading to the deposition of iron (Fe) onto longer asbestos fibers which forms asbestos bodies (AB) [2]. Similar to Fe, calcium (Ca) is also deposited in the coats of the AB. This article presents data on iron and calcium in the mouse lung after asbestos exposure detected by histochemical evaluation.

The Importance of Mortality Risk Assessment: Validation of the Pediatric Index of Mortality 3 Score. - Wolfler, Andrea; Osello, Raffaella; Gualino, Jenny; Calderini, Edoardo; Vigna, Gianluca; Santuz, Pierantonio; Amigoni, Angela; Savron, Fabio; Caramelli, Fabio; Rossetti, Emanuele; Cecchetti, Corrado; Corbari, Maurizio; et al. (Pediatr Crit Care Med, 2016)
OBJECTIVE: To evaluate the performance of the newest version of the Pediatric Index of Mortality 3 score and compare it with the Pediatric Index of Mortality 2 in a multicenter national cohort of children admitted to PICU. DESIGN: Retrospective, prospective cohort study. SETTING: Seventeen Italian PICUs. PATIENTS: All children 0 to 15 years old admitted in PICU from January 2010 to October 2014. INTERVENTIONS: None. MEASUREMENT AND MAIN RESULTS: Eleven thousand one hundred nine children were enrolled in the study. The mean Pediatric Index of Mortality 2 and 3 values of 4.9 and 3.9, respectively, differed significantly (p < 0.05). Overall mortality rate was 3.9%, and the standardized mortality ratio was 0.80 for Pediatric Index of Mortality 2 and 0.98 for Pediatric Index of Mortality 3 (p < 0.05). The area under the curve of the receiver operating characteristic curves was similar for Pediatric Index of Mortality 2 and Pediatric Index of Mortality 3. The Hosmer-Lemeshow test was not significant for Pediatric Index of Mortality 3 (p = 0.21) but was highly significant for Pediatric Index of Mortality 2 (p < 0.001), which overestimated death mainly in high-risk categories. CONCLUSIONS: Mortality indices require validation in each country where it is used. The new Pediatric Index of Mortality 3 score performed well in an Italian population. Both calibration and discrimination were appropriate, and the score more accurately predicted the mortality risk than Pediatric Index of Mortality 2.

The incidence rate and prevalence of pediatric type 1 diabetes mellitus (age 0-18) in the Italian region Friuli Venezia Giulia: population-based estimates through the analysis of health administrative databases. - Valent, Francesca; Candido, Riccardo; Faleschini, Elena; Tonutti, Laura; Tortul, Carla; Zanatta, Manuela; Zanette, Giorgio; Zanier, Loris (Acta Diabetol, 2016)
AIMS: The main objective of this study was to estimate the incidence rate and prevalence of pediatric type 1 diabetes mellitus (T1DM; population 0-18 years of age) in the northeastern Italian region Friuli Venezia Giulia and to characterize the subjects affected by the disease. METHODS: This was a retrospective population-based study conducted through the individual-level linkage of several health administrative databases of the Friuli Venezia Giulia region. The incidence rate and prevalence were calculated in the population 0-18 years of age. Using the Mid-p exact method, 95 % confidence intervals for rates were calculated. RESULTS: The incidence rate of pediatric T1DM in the years 2010-2013 was 15.8 new cases/100,000 person-years, peaking in the age class 10-14 years. The rate has increased substantially as compared with the previous regional estimate that dated back to 1993. We observed a seasonal pattern both in the date of birth of the incident cases and in the date of onset of the disease. In the region in 2013, there were 294 prevalent cases (15.1/10,000 inhabitants). Most of them had at least one glycated hemoglobin test in the year. More than 15 % had co-existing autoimmune comorbidities. CONCLUSIONS: The incidence rate of pediatric T1DM in Friuli Venezia Giulia has increased in the last years, and the disease is a relevant public health issue in the region.

Iron signature in asbestos-induced malignant pleural mesothelioma: A population-based autopsy study. - Crovella, Sergio; Bianco, Anna Monica; Vuch, Joseph; Zupin, Luisa; Moura, Ronald Rodrigues; Trevisan, Elisa; Schneider, Manuela; Brollo, Alessandro; Nicastro, Enza Maria; Cosenzi, Alessandro; Zabucchi, Giuliano; Borelli, Violetta (J Toxicol Environ Health A, 2016)
Malignant pleural mesothelioma (MPM) is an aggressive cancer with poor prognosis. The development of MPM is frequently linked to inhalation of asbestos fibers. A genetic component of susceptibility to this disease is suggested by the observation that some individuals develop MPM following lower doses of asbestos exposure, whereas others exposed to higher quantities do not seem to be affected. This hypothesis is supported also by frequent reports of MPM familial clustering. Despite the widely recognized role of iron (Fe) in cellular asbestos-induced pulmonary toxicity, the role of the related gene polymorphisms in the etiology of MPM has apparently not been evaluated. Eighty-six single-nucleotide polymorphisms (SNPs) of 10 Fe-metabolism genes were examined by exploiting formalin-fixed paraffin-embedded postmortem samples from 77 patients who died due to MPM (designated AEM) and compared with 48 who were exposed to asbestos but from died in old age of cause other than asbestos (designated AENM). All subjects showed objective signs of asbestos exposure. Three SNPs, localized in the ferritin heavy polypeptide, transferrin, and hephaestin genes, whose frequencies were distributed differently in AEM and AENM populations, were identified. For ferritin and transferrin the C/C and the G/G genotypes, respectively, representing intronic polymorphisms, were significantly associated with protection against MPM and need to be considered as possible genetic markers of protection. Similarly, the C/C hephaestin SNP, a missense variation of this multicopper ferroxidase encoding gene, may be related, also functionally, with protection against MPM. In conclusion, it is proposed that three Fe metabolism-associated genes, significantly associated with protection against development of MPM, may serve as protective markers for this aggressive tumor.
Keywords: Adult; Aged; Asbestos; Autopsy; Case-Control Studies; Female; Ferritins; Gene Frequency; Genetic Markers; Humans; Iron; Lung Neoplasms; Male; Membrane Proteins; Mesothelioma; Middle Aged; Mutation, Missense; Polymorphism, Single Nucleotide; Transferrin; Young Adult

Isolated hypoplasia of abdominal wall muscles associated with fetal ascites. - Travan, Laura; Naviglio, Samuele; Cont, Gabriele; Brovedani, Pierpaolo; Davanzo, Riccardo; Demarini, Sergio (Congenit Anom (Kyoto), 2016)
We report the case of an infant born after parvovirus B19-induced fetal hydrops, who presented at birth with bilateral abdominal wall laxity, which was more evident on the flanks. Imaging exams revealed congenital hypoplasia of oblique abdominal muscles not associated with other anatomical abnormalities except for small liver calcifications. We review the medical literature and identify similar cases associated with fetal ascites. We propose that isolated hypoplasia of abdominal wall muscles can be associated with fetal ascites from various causes, and represents a separate condition from prune belly syndrome.

A minor trauma revealing linear morphoea in a 4-year-old female. - Pastore, Serena; Contorno, Sarah; Caddeo, Giulia; Calligaris, Lorenzo; Taddio, Andrea (Arch Dis Child, 2016)

A multi-method approach to the molecular diagnosis of overt and borderline 11p15.5 defects underlying Silver-Russell and Beckwith-Wiedemann syndromes. - Russo, Silvia; Calzari, Luciano; Mussa, Alessandro; Mainini, Ester; Cassina, Matteo; Di Candia, Stefania; Clementi, Maurizio; Guzzetti, Sara; Tabano, Silvia; Miozzo, Monica; Sirchia, Silvia; Finelli, Palma; et al. (Clin Epigenetics, 2016)
BACKGROUND: Multiple (epi)genetic defects affecting the expression of the imprinted genes within the 11p15.5 chromosomal region underlie Silver-Russell (SRS) and Beckwith-Wiedemann (BWS) syndromes. The molecular diagnosis of these opposite growth disorders requires a multi-approach flowchart to disclose known primary and secondary (epi)genetic alterations; however, up to 20 and 30 % of clinically diagnosed BWS and SRS cases remain without molecular diagnosis. The complex structure of the 11p15 region with variable CpG methylation and low-rate mosaicism may account for missed diagnoses. Here, we demonstrate the relevance of complementary techniques for the assessment of different CpGs and the importance of testing multiple tissues to increase the SRS and BWS detection rate. RESULTS: Molecular testing of 147 and 450 clinically diagnosed SRS and BWS cases provided diagnosis in 34 SRS and 185 BWS patients, with 9 SRS and 21 BWS cases remaining undiagnosed and herein referred to as "borderline." A flowchart including complementary techniques and, when applicable, the analysis of buccal swabs, allowed confirmation of the molecular diagnosis in all borderline cases. Comparison of methylation levels by methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) in borderline and control cases defined an interval of H19/IGF2:IG-DMR loss of methylation that was distinct between "easy to diagnose" and "borderline" cases, which were characterized by values ≤mean -3 standard deviations (SDs) compared to controls. Values ≥mean +1 SD at H19/IGF2: IG-DMR were assigned to borderline hypermethylated BWS cases and those ≤mean -2 SD at KCNQ1OT1: TSS-DMR to hypomethylated BWS cases; these were supported by quantitative pyrosequencing or Southern blot analysis. Six BWS cases suspected to carry mosaic paternal uniparental disomy of chromosome 11 were confirmed by SNP array, which detected mosaicism till 10 %. Regarding the clinical presentation, borderline SRS were representative of the syndromic phenotype, with exception of one patient, whereas BWS cases showed low frequency of the most common features except hemihyperplasia. CONCLUSIONS: A conclusive molecular diagnosis was reached in borderline methylation cases, increasing the detection rate by 6 % for SRS and 5 % for BWS cases. The introduction of complementary techniques and additional tissue analyses into routine diagnostic work-up should facilitate the identification of cases undiagnosed because of mosaicism, a distinctive feature of epigenetic disorders.
Keywords: Beckwith-Wiedemann Syndrome; Blotting, Southern; Child; Child, Preschool; Chromosomes, Human, Pair 11; CpG Islands; DNA Methylation; Epigenesis, Genetic; Female; Humans; Infant; Male; Mosaicism; Multiplex Polymerase Chain Reaction; Oligonucleotide Array Sequence Analysis; Silver-Russell Syndrome

Nationwide study of headache pain in Italy shows that pain assessment is still inadequate in paediatric emergency care. - Benini, Franca; Piga, Simone; Zangardi, Tiziana; Messi, Gianni; Tomasello, Caterina; Pirozzi, Nicola; Cuttini, Marina (Acta Paediatr, 2016)
AIM: Italian national guidelines on pain management were published in 2010, but there is little information on how effective pain management is in paediatric emergency care, with other countries reporting poor levels. Using headache as an indicator, we described pain assessment in Italian emergency departments and identified predictors of algometric scale use. METHODS: All Italian paediatric and maternal and child hospitals participated, plus four general hospitals. Data on all children aged 4-14 years admitted during a one-month period with headache as their chief complaint were abstracted from clinical records. Multivariable analyses identified predictors of algometric assessment, taking into account the cluster study design. RESULTS: We studied 470 admissions. During triage, pain was assessed using a standardised scale (41.5%), informally (15.5%) or was not recorded (42.9%). Only 32.1% of the children received analgesia in the emergency department. The odds ratios for predictors of algometric assessment were non-Italian nationality (3.6), prehospital medication (1.8), admission to a research hospital (7.3) and a more favourable nurses-to-admissions ratio of 10.8 for the highest versus lowest tertile. CONCLUSION: Despite national guidelines, paediatric pain assessment in Italian emergency care was suboptimal. Hospital variables appeared to be stronger predictors of adequate assessment than patient characteristics.

Nonmuscle Myosin Heavy Chain IIA Mutation Predicts Severity and Progression of Sensorineural Hearing Loss in Patients With MYH9-Related Disease. - Verver, Eva J J; Topsakal, Vedat; Kunst, Henricus P M; Huygen, Patrick L M; Heller, Paula G; Pujol-Moix, Núria; Savoia, Anna; Benazzo, Marco; Fierro, Tiziana; Grolman, Wilko; Gresele, Paolo; Pecci, Alessandro (Ear Hear, 2016)
OBJECTIVES: MYH9-related disease (MYH9-RD) is an autosomal- dominant disorder deriving from mutations in MYH9, the gene for the nonmuscle myosin heavy chain (NMMHC)-IIA. MYH9-RD has a complex phenotype including congenital features, such as thrombocytopenia, and noncongenital manifestations, namely sensorineural hearing loss (SNHL), nephropathy, cataract, and liver abnormalities. The disease is caused by a limited number of mutations affecting different regions of the NMMHC-IIA protein. SNHL is the most frequent noncongenital manifestation of MYH9-RD. However, only scarce and anecdotal information is currently available about the clinical and audiometric features of SNHL of MYH9-RD subjects. The objective of this study was to investigate the severity and propensity for progression of SNHL in a large series of MYH9-RD patients in relation to the causative NMMHC-IIA mutations. DESIGN: This study included the consecutive patients diagnosed with MYH9-RD between July 2007 and March 2012 at four participating institutions. A total of 115 audiograms were analyzed from 63 patients belonging to 45 unrelated families with different NMMHC-IIA mutations. Cross-sectional analyses of audiograms were performed. Regression analysis was performed, and age-related typical audiograms (ARTAs) were derived to characterize the type of SNHL associated with different mutations. RESULTS: Severity of SNHL appeared to depend on the specific NMMHC-IIA mutation. Patients carrying substitutions at the residue R702 located in the short functional SH1 helix had the most severe degree of SNHL, whereas patients with the p.E1841K substitution in the coiled-coil region or mutations at the nonhelical tailpiece presented a mild degree of SNHL even at advanced age. The authors also disclosed the effects of different amino acid changes at the same residue: for instance, individuals with the p.R702C mutation had more severe SNHL than those with the p.R702H mutation, and the p.R1165L substitution was associated with a higher degree of hearing loss than the p.R1165C. In general, mild SNHL was associated with a fairly flat audiogram configuration, whereas severe SNHL correlated with downsloping configurations. ARTA plots showed that the most progressive type of SNHL was associated with the p.R702C, the p.R702H, and the p.R1165L substitutions, whereas the p.R1165C mutation correlated with a milder, nonprogressive type of SNHL than the p.R1165L. ARTA for the p.E1841K mutation demonstrated a mild degree of SNHL with only mild progression, whereas the ARTA for the mutations at the nonhelical tailpiece did not show any substantial progression. CONCLUSIONS: These data provide useful tools to predict the progression and the expected degree of severity of SNHL in individual MYH9-RD patients, which is especially relevant in young patients. Consequences in clinical practice are important not only for appropriate patient counseling but also for development of customized, genotype-driven clinical management. The authors recently reported that cochlear implantation has a good outcome in MYH9-RD patients; thus, stricter follow-up and earlier intervention are recommended for patients with unfavorable genotypes.

The prognostic value of biological markers in paediatric Hodgkin lymphoma. - Farruggia, Piero; Puccio, Giuseppe; Sala, Alessandra; Todesco, Alessandra; Buffardi, Salvatore; Garaventa, Alberto; Bottigliero, Gaetano; Bianchi, Maurizio; Zecca, Marco; Locatelli, Franco; Pession, Andrea; Pillon, Marta; et al. (Eur J Cancer, 2016)
BACKGROUND: Many biological and inflammatory markers have been proposed as having a prognostic value at diagnosis of Hodgkin lymphoma (HL), but very few have been validated in paediatric patients. We explored the significance of these markers in a large population of 769 affected children. PATIENTS AND METHODS: By using the database of patients enrolled in A.I.E.O.P. (Associazione Italiana di Emato-Oncologia Pediatrica) trial LH2004 for paediatric HL, we identified 769 consecutive patients treated with curative intent from 1st June 2004 to 1st April 2014 with ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine), or hybrid COPP/ABV (cyclophosphamide, vincristine, prednisone, procarbazine, doxorubicin, bleomycin and vinblastine) regimens. RESULTS: On multivariate analysis with categorical forms, the 5-year freedom from progression survival was significantly lower in patients with stage IV or elevated value of platelets, eosinophils and ferritin at diagnosis. Furthermore, stage IV and eosinophils seem to maintain their predictive value independently of interim (after IV cycles of chemotherapy) positron emission tomography. CONCLUSION: Using the combination of four simple markers such as stage IV and elevated levels of platelets, ferritin and eosinophils, it is possible to classify the patients into subgroups with very different outcomes.
Keywords: Adolescent; Age Factors; Antineoplastic Combined Chemotherapy Protocols; Biomarkers, Tumor; Blood Platelets; Child; Child, Preschool; Databases, Factual; Disease Progression; Disease-Free Survival; Eosinophils; Female; Ferritins; Hodgkin Disease; Humans; Infant; Infant, Newborn; Italy; Kaplan-Meier Estimate; Leukocyte Count; Male; Multivariate Analysis; Neoplasm Staging; Platelet Count; Predictive Value of Tests; Proportional Hazards Models; Retrospective Studies; Risk Factors; Time Factors; Treatment Outcome

Putative modifier genes in mevalonate kinase deficiency. - Marcuzzi, Annalisa; Vozzi, Diego; Girardelli, Martina; Tricarico, Paola Maura; Knowles, Alessandra; Crovella, Sergio; Vuch, Josef; Tommasini, Alberto; Piscianz, Elisa; Bianco, Anna Monica (Mol Med Rep, 2016)
Mevalonate kinase deficiency (MKD) is an autosomal recessive auto‑inflammatory disease, caused by impairment of the mevalonate pathway. Although the molecular mechanism remains to be elucidated, there is clinical evidence suggesting that other regulatory genes may be involved in determining the phenotype. The identification of novel target genes may explain non‑homogeneous genotype‑phenotype correlations, and provide evidence in support of the hypothesis that novel regulatory genes predispose or amplify deregulation of the mevalonate pathway in this orphan disease. In the present study, DNA samples were obtained from five patients with MKD, which were then analyzed using whole exome sequencing. A missense variation in the PEX11γ gene was observed in homozygosis in P2, possibly correlating with visual blurring. The UNG rare gene variant was detected in homozygosis in P5, without correlating with a specific clinical phenotype. A number of other variants were found in the five analyzed DNA samples from the MKD patients, however no correlation with the phenotype was established. The results of the presents study suggested that further analysis, using next generation sequencing approaches, is required on a larger sample size of patients with MKD, who share the same MVK mutations and exhibit 'extreme' clinical phenotypes. As MVK mutations may be associated with MKD, the identification of specific modifier genes may assist in providing an earlier diagnosis.

A quasi randomized-controlled trial to evaluate the effectiveness of clowntherapy on children's anxiety and pain levels in emergency department. - Felluga, Margherita; Rabach, Ingrid; Minute, Marta; Montico, Marcella; Giorgi, Rita; Lonciari, Isabella; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2016)
UNLABELLED: The aim of the study is to investigate if the presence of medical clowns during painful procedures in the emergency department (ED) affects children's anxiety and pain. Forty children (4-11 years) admitted to the ED with the need of painful procedures were prospectively enrolled. They were randomly assigned to the clown group, where children interacted with clowns or to the control group in which they were entertained by parents and ED nurses. The children's anxiety was assessed by the Children's Anxiety and Pain Scales; pain was evaluated with the Numerical Rating Scale and Wong-Backer Scale, according to the children's age. Staff and clown's opinions were evaluated by means of dedicated questionnaires. Children's anxiety levels in the clown group were significantly lower than those compared with the control group, while children's pain levels did not change between the two groups. CONCLUSION: The presence of clowns in the ED before and during painful procedures was effective in reducing children's anxiety. WHAT IS KNOWN: • Anxiety and fear caused by medical procedures exacerbate children's pain and may interfere with the procedure. • To reduce anxiety, fear, and pain and to facilitate patient's evaluation, different non-pharmacological approaches have been proposed and positive effects of laughter and humor have been reported. What is New: • The presence of clowns in the waiting room and in the ED during medical evaluation and painful procedures helps to reduce children's anxiety.

Recent advances in the use of Anti-TNFα therapy for the treatment of juvenile idiopathic arthritis. - Taddio, Andrea; Cattalini, Marco; Simonini, Gabriele; Cimaz, Rolando (Expert Rev Clin Immunol, 2016)
Juvenile Idiopathic Arthritis (JIA) encompasses a group of diseases of unknown etiology having in common arthritis in at least 1 joint that persists for 6 weeks and begins before 16 years of age, with other conditions excluded. With a prevalence of 1 per 1,000 children in the USA, JIA is the most common pediatric rheumatic illness and a major cause of acquired childhood disability. During the last 20 years, the advent of host immune response modifiers known as biologic agents, in particular the anti-TNFα agents (etanercept, infliximab, adalimumab), which directly inhibit the action of pro-inflammatory mediators, has revolutionized the treatment and the expected outcome of JIA. This article highlights treatment indications of anti-TNFα drugs and their more frequent side effects in JIA patients.

A reference panel of 64,976 haplotypes for genotype imputation. - McCarthy, Shane; Das, Sayantan; Kretzschmar, Warren; Delaneau, Olivier; Wood, Andrew R; Teumer, Alexander; Kang, Hyun Min; Fuchsberger, Christian; Danecek, Petr; Sharp, Kevin; Luo, Yang; Sidore, Carlo; et al. (Nat Genet, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.

Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice. - Pascolo, Lorella; Zabucchi, Giuliano; Gianoncelli, Alessandra; Kourousias, George; Trevisan, Elisa; Pascotto, Ernesto; Casarsa, Claudia; Ryan, Chris; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; et al. (Toxicol Lett, 2016)
Human exposure to asbestos can cause a wide variety of lung diseases that are still a current major health concern, even if asbestos has been banned in many countries. It has been shown in many studies that asbestos fibers, ingested by alveolar macrophages, disrupt lung iron homeostasis by sequestering iron. Calcium can also be deposited on the fibers. The pathways along which iron and above all calcium interact with fibers are still unknown. Our aim was that of investigating if the iron accumulation induced by the inhaled asbestos fibers also involves calcium ions accumulation. Lung sections of asbestos-exposed mice were analyzed using an extremely sensitive procedure available at the synchrotron facilities, that provides morphological and chemical information based on X-ray fluorescence microspectroscopy (μ-XRF). In this study we show that (1) where conventional histochemical procedures revealed only weak deposits of iron and calcium, μ-XRF analysis is able to detect significant deposits of both iron and calcium on the inhaled asbestos fibers; (2) the extent of the deposition of these ions is proportionally directly related and (3) iron and calcium deposition on inhaled asbestos fibers is concomitant with the appearance of inflammatory and hyperplastic reactions.

Torticollis as the Presenting Sign of Cervical Spondylodiscitis. - Pizzol, Antonio; Bramuzzo, Matteo; Pillon, Roberto; Taddio, Andrea; Barbi, Egidio (Pediatr Emerg Care, 2016)
Acquired torticollis is a common clinical finding in children evaluated in the pediatric emergency department. It may be the presentation symptom of different illnesses, such as trauma, muscle contraction, infections, or malignancies, and an accurate differential diagnosis is required to correctly identify the cause and choose the right treatment. Spondylodiscitis is a low-grade bacterial infection that involves intervertebral disks and the adjacent vertebral bodies. Spondylodiscitis of the cervical spine is unusual and may be a rare cause of torticollis. We report the case of a 4-year-old male patient admitted to the emergency department for a 5-day history of painful torticollis. Blood tests showed an elevated erythrocyte sedimentation rate. The radiograph of the cervical spine showed a thin fifth cervical soma. The magnetic resonance imaging of cervical spine showed the alteration of cervical vertebral bodies and intervertebral disks, suggesting the diagnosis of cervical spondylodiscitis. The patient recovered after endovenous antibiotic treatment. We suggest that cervical spondylodiscitis should be suspected and investigated by means of an magnetic resonance imaging in every case of unexplained torticollis with persisting symptoms.

Understanding the role of personality and alexithymia in food preferences and PROP taste perception. - Robino, Antonietta; Mezzavilla, Massimo; Pirastu, Nicola; La Bianca, Martina; Gasparini, Paolo; Carlino, Davide; Tepper, Beverly J (Physiol Behav, 2016)
Taste perception and food preferences are influenced by a variety of factors, including personality characteristics. The aims of this study were to examine the role of personality characteristics, such as alexithymia (a personality construct characterized by inability to identify, describe, and work with one's own feelings), in: 1) taste responses to the bitter genetic taste-marker PROP and 2) food liking. We studied 649 healthy subjects residing in six genetically-isolated villages of Northeast Italy. Data on PROP taste responsiveness, food liking, personality characteristics and TAS2R28 genotypes were collected. Results showed that PROP non-tasters had higher alexithymia scores than PROP tasters. Moreover, the presence of alexithymia in heterozygous individuals for the rs1726886 polymorphism of the TAS2R38 gene was associated with a reduction in the perceived intensity of PROP. Finally, higher alexithymia scores were associated with liking of alcohol, sweets and fats/meats whereas lower alexithymia scores were related to liking of vegetables, condiments and strong cheeses, Measures of temperament, character, anxiety and depression were also related to food liking. Our findings suggest that: 1) alexithymia, in addition to the TAS2R38 polymorphism, may play a role in responsiveness to the aversive and bitter taste of PROP; and 2) alexithymia, in combination with other personality traits, may provide important insights for better understanding food liking.

Alendronate, a double-edged sword acting in the mevalonate pathway. - Tricarico, Paola Maura; Girardelli, Martina; Kleiner, Giulio; Knowles, Alessandra; Valencic, Erica; Crovella, Sergio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Aminobisphosphonate aledronate is a compound commonly used clinically for the treatment of osteoporosis and other bone diseases, as a result of it preventing bone resorption. However, in previous years it has also been used to obtain cellular and animal models of a rare genetic disorder termed Mevalonate Kinase Deficiency (MKD). MKD is caused by mutations affecting the mevalonate kinase enzyme, in the cholesterol pathway and alendronate can be used to biochemically mimic the genetic defect as it inhibits farnesyl pyrophosphate synthase in the same pathway. Despite evidence in favor of the inhibition exerted on the mevalonate pathway, there is at least one clinical case of MKD in which alendronate improved not only skeletal and bone fractures, as expected, but also MKD clinical features. Based on this finding, the present study assessed the anti‑inflammatory properties of this aminobisphosphonate in vitro. No anti‑inflammatory effects of alendronate were observed in the in vitro experiments. Since MKD lacks specific treatments, these results may assist scientists and physicians in making the decision as to the most suitable choice of therapeutic compounds for this neglected disease.

Altered germinal center reaction and abnormal B cell peripheral maturation in PI3KR1-mutated patients presenting with HIGM-like phenotype. - Lougaris, Vassilios; Faletra, Flavio; Lanzi, Gaetana; Vozzi, Diego; Marcuzzi, Annalisa; Valencic, Erica; Piscianz, Elisa; Bianco, AnnaMonica; Girardelli, Martina; Baronio, Manuela; Loganes, Claudia; Fasth, Anders; et al. (Clin Immunol, 2015)
Keywords: B-Lymphocytes; Child, Preschool; Female; Germinal Center; Humans; Hyper-IgM Immunodeficiency Syndrome; Infant; Male; Mutation; Phenotype; Phosphatidylinositol 3-Kinases; RNA Splice Sites; Sequence Analysis, DNA

Analgesia by cooling vibration during venipuncture in children with cognitive impairment. - Schreiber, Silvana; Cozzi, Giorgio; Rutigliano, Rosaria; Assandro, Paola; Tubaro, Martina; Cortellazzo Wiel, Luisa; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2015)
AIM: Children with cognitive impairment experience pain more frequently than healthy children and are more likely to require venipuncture or intravenous cannulation for various procedures. They are frequently unable to report pain and often receive poor pain assessment and management. This study assessed the effectiveness of physical analgesia during vascular access in children with cognitive impairments. METHODS: We conducted a prospective randomised controlled study at a tertiary-level children's hospital in Italy from April to May 2015 to assess whether a cooling vibration device called Buzzy decreased pain during venipuncture and intravenous cannulation in children with cognitive impairment. None of the children had verbal skills and the main cognitive impairments were cerebral palsy, epileptic encephalopathy and genetic syndromes. RESULTS: We tested 70 children with a median age of nine years: 34 in the Buzzy group and 36 in the no-intervention group. Parents were trained in the use of the Noncommunicating Children's Pain Checklist - postoperative version scale, and they reported no or mild procedural pain in 32 cases (91.4%) in the Buzzy group and in 22 cases (61.1%) in the no-intervention group (p = 0.003). CONCLUSION: Cooling vibration analgesia during vascular access reduced pain in children with cognitive impairment.

Are all cases of paediatric essential thrombocythaemia really myeloproliferative neoplasms? Analysis of a large cohort. - Randi, Maria L; Geranio, Giulia; Bertozzi, Irene; Micalizzi, Concetta; Ramenghi, Ugo; Tucci, Fabio; Notarangelo, Lucia D; Ladogana, Saverio; Menna, Giuseppe; Giordano, Paola; Consarino, Caterina; Farruggia, Piero; et al. (Br J Haematol, 2015)
Sporadic essential thrombocythaemia (ET) is rare in paediatrics, and the diagnostic and clinical approach to paediatric cases cannot be simply copied from experience with adults. Here, we assessed 89 children with a clinical diagnosis of ET and found that 23 patients (25·8%) had a clonal disease. The JAK2 V617F mutation was identified in 14 children, 1 child had the MPL W515L mutation, and 6 had CALR mutations. The monoclonal X-chromosome inactivation pattern was seen in six patients (two with JAK2 V617F and two with CALR mutations). The other 66 patients (74·2%) had persistent thrombocytosis with no clonality. There were no clinical or haematological differences between the clonal and non-clonal patients. The relative proportion of ET-specific mutations in the clonal children was much the same as in adults. The higher prevalence of non-clonal cases suggests that some patients may not have myeloproliferative neoplasms, with significant implications for their treatment.
Keywords: Adolescent; Adult; Amino Acid Substitution; Child; Child, Preschool; Cohort Studies; Female; Hematologic Neoplasms; Humans; Infant; Janus Kinase 2; Male; Mutation, Missense; Neoplasm Proteins; Thrombocythemia, Essential

Bedside diagnosis of two major clinical phenotypes of hypertensive disorders of pregnancy. - Ferrazzi, E; Zullino, S; Stampalija, T; Vener, C; Cavoretto, P; Gervasi, M T; Vergani, P; Mecacci, F; Marozio, L; Oggè, G; Algeri, P; Ruffatti, A; et al. (Ultrasound Obstet Gynecol, 2015)
OBJECTIVE: We hypothesized that fetal abdominal circumference (AC) and Uterine Doppler Pulsatility Index (UtA-PI) could select two homogenous subgroups of women affected by hypertensive disorders of pregnancy (HDP), characterized by the coexistence of maternal hypertension with and without IUGR. METHODS: This is a multicentre study that studied cases affected by HDP in whom fetal AC and UtA-PI had been measured at admission to feto Maternal Medicine Units. Maternal characteristics, pregnancy complications and outcome were recorded. These data allowed us to model the characteristics of fetal growth in cases affected by HDP, and to design a composite index for risk factors of maternal metabolic syndrome (rfMMS) and composite index of severity for maternal organ and/or function damage (OFD). RESULTS: Measurements of fetal AC and UtA-PI allowed us to define a group of HDP with AGA fetuses (HDP-AGAf) diagnosed by normal fetal AC and a UtA-PI (#205), and a group of HDP with IUGR fetuses (HDP-IUGR) diagnosed by fetal AC <5(th) centile and UtA-PI >95(th) centile (#124). Curves fitted to birth-weight of the two groups were significantly different, and gestational age at admission for HDP, <34 or ≥34, had no effect on their models. When birth-weight was expressed as standard deviation score (SDS) of local reference charts, the average SDS (±standard error) corresponded to the 6(th) and 48(th) centile respectively. The risk of developing HDP-AGAf was significantly associated with risk factors for maternal metabolic syndrome (OR= 2.79;CI 1.57-4.97), independently of gestational age. The same risk factors yielded a non significant ORs of developing late onset HDP. Women with HDP-IUGR proved to be associated with the worst clinical outcomes. CONCLUSIONS: This study adds genuine new data based on simple prenatal bedside examinations, that might help to differentiate HDP with IUGR, from HDP with AGA fetuses, associated with different fetal growth patterns and different risk factors, not affected by gestational age at onset of the disease.

Brain-derived neurotrophic factor serum levels in genetically isolated populations: gender-specific association with anxiety disorder subtypes but not with anxiety levels or Val66Met polymorphism. - Carlino, Davide; Francavilla, Ruggiero; Baj, Gabriele; Kulak, Karolina; d'Adamo, Pio; Ulivi, Sheila; Cappellani, Stefania; Gasparini, Paolo; Tongiorgi, Enrico (PeerJ, 2015)
Anxiety disorders (ADs) are disabling chronic disorders with exaggerated behavioral response to threats. This study was aimed at testing the hypothesis that ADs may be associated with reduced neurotrophic activity, particularly of Brain-derived neurotrophic factor (BDNF), and determining possible effects of genetics on serum BDNF concentrations. In 672 adult subjects from six isolated villages in North-Eastern Italy with high inbreeding, we determined serum BDNF levels and identified subjects with different ADs subtypes such as Social and Specific Phobias (PHSOC, PHSP), Generalized Anxiety Disorder (GAD), and Panic Disorder (PAD). Analysis of the population as a whole or individual village showed no significant correlation between serum BDNF levels and Val66Met polymorphism and no association with anxiety levels. Stratification of subjects highlighted a significant decrease in serum BDNF in females with GAD and males with PHSP. This study indicates low heritability and absence of any impact of the Val66Met polymorphism on circulating concentrations of BDNF. Our results show that BDNF is not a general biomarker of anxiety but serum BDNF levels correlate in a gender-specific manner with ADs subtypes.

A case of Rubinstein-Taybi syndrome associated with growth hormone deficiency in childhood. - Tornese, Gianluca; Marzuillo, Pierluigi; Pellegrin, Maria Chiara; Germani, Claudio; Faleschini, Elena; Zennaro, Floriana; Grandone, Anna; Miraglia Del Giudice, Emanuele; Perrone, Laura; Ventura, Alessandro (Clin Endocrinol (Oxf), 2015)

Central venous access devices in pediatric malignancies: a position paper of Italian Association of Pediatric Hematology and Oncology. - Crocoli, Alessandro; Tornesello, Assunta; Pittiruti, Mauro; Barone, Angelica; Muggeo, Paola; Inserra, Alessandro; Molinari, Angelo Claudio; Grillenzoni, Valeria; Durante, Viviana; Cicalese, Maria Pia; Zanazzo, Giulio Andrea; Cesaro, Simone (J Vasc Access, 2015)
INTRODUCTION: Treatment of pediatric malignancies is becoming progressively more complex, implying the adoption of multimodal therapies. A reliable, long-lasting venous access represents one of the critical requirements for the success of those treatments. Recent technical innovations-such as minimally invasive procedures for placement, new devices and novel materials-have rapidly spread for clinical use in adult patients, but are still not consistently used in the pediatric population. METHODS: The Supportive Therapy Working Group of Italian Association of Hematology and Oncology (AIEOP) reviewed medical literature focusing on new aspects of central venous access devices (VADs) in pediatric patients affected by oncohematological diseases. RESULTS: Appropriate recommendations for clinical use in these patients have been discussed and formulated. CONCLUSIONS: The importance of the correct choice, management and use of VADs in pediatric oncohematological patients is a necessary prerequisite for an adequate standard of care, also considering the increased chances of cure and the longer life expectancy of those patients with modern therapies.

Cerebral oxygenation with different nasal continuous positive airway pressure levels in preterm infants. - Bembich, Stefano; Travan, Laura; Cont, Gabriele; Bua, Jenny; Strajn, Tamara; Demarini, Sergio (Arch Dis Child Fetal Neonatal Ed, 2015)
OBJECTIVES: This study evaluates the effect of varying nasal continuous positive airway pressure (NCPAP) level on cerebral blood flow (CBF) and oxygenation in preterm infants. METHODS: Oxy-haemoglobin (HbO2) and total haemoglobin (HbTot), as CBF estimates, and the ratio between HbO2 and HbTot (HbO2/HbTot), as cerebral oxygenation estimate, were assessed by near-infrared spectroscopy in 26 stable preterm newborns at a postmenstrual age between 26 and 33 weeks. Baseline HbO2, HbTot and HbO2/HbTot values were initially collected with NCPAP at 5 cm H2O and then compared with values obtained with NCPAP levels at both 3 and 8 cm H2O. RESULTS: Compared with 5 cm H2O, cerebral HbO2, HbTot and HbO2/HbTot remained unchanged both after increasing (to 8 cm H2O) and decreasing (to 3 cm H2O) the NCPAP level. This result was observed both in regional areas (24 sites) and in the overall monitored area (frontal and parietal cortex). Compared with 8 cm H2O, peripheral oxygen saturation significantly decreased at 3 cm H2O (p=0.021). Heart rate did not change. CONCLUSIONS: No differences in CBF and cerebral oxygenation were observed with NCPAP levels in the range 3-8 cm H2O despite a decrease in peripheral oxygenation with 3 cm H2O.
Keywords: Cerebrovascular Circulation; Continuous Positive Airway Pressure; Female; Hemoglobins; Humans; Infant, Newborn; Infant, Premature; Intensive Care, Neonatal; Male; Nasal Cavity; Oxygen; Oxygen Consumption; Oxyhemoglobins; Spectroscopy, Near-Infrared

Combined circulating epigenetic markers to improve mesothelin performance in the diagnosis of malignant mesothelioma. - Santarelli, Lory; Staffolani, Sara; Strafella, Elisabetta; Nocchi, Linda; Manzella, Nicola; Grossi, Paola; Bracci, Massimo; Pignotti, Elettra; Alleva, Renata; Borghi, Battista; Pompili, Cecilia; Sabbatini, Armando; et al. (Lung Cancer, 2015)
OBJECTIVES: Malignant mesothelioma (MM) is a highly aggressive tumor with poor prognosis. A major challenge is the development and application of early and highly reliable diagnostic marker(s). Serum biomarkers, such as 'soluble mesothelin-related proteins' (SMRPs), is the most studied and frequently used in MM. However, the low sensitivity of SMRPs for early MM limits its value; therefore, additional biomarkers are required. In this study, two epigenetically regulated markers in MM (microRNA-126, miR-126, and methylated thrombomodulin promoter, Met-TM) were combined with SMRPs and evaluated as a potential strategy to detect MM at an early stage. MATERIALS AND METHODS: A total of 188 subjects, including 45 MM patients, 99 asbestos-exposed subjects, and 44 healthy controls were prospectively enrolled, serum samples collected, and serum levels of SMRPs, miR-126 and Met-TM evaluated. Logistic regression analysis was performed to evaluate the diagnostic value of the three biomarkers. Using this approach, the performance of the '3-biomarker classifier' was tested by calculating the overall probability score of the MM and control samples, respectively, and the ROC curve was generated. RESULTS AND CONCLUSION: The combination of the three biomarkers was the best predictor to differentiate MM patients from asbestos-exposed subjects and healthy controls. The accuracy and cancer specificity was confirmed in a second validation cohort and lung cancer population. We propose that the combination of the two epigenetic biomarkers with SMRPs as a diagnosis for early MM overcomes the limitations of using SMRPs alone.

Complete remission of VZV reactivation treated with valganciclovir in a patient with total lymphocyte depletion and acute kidney injury after allogeneic bone marrow transplantation. - Maximova, Natalia; Antonio, Pizzol; Marilena, Granzotto; Rovere, Francesca; Tamaro, Paolo (APMIS, 2015)
Varicella zoster virus (VZV), a threat for hematopoietic stem cell transplantation (HSCT) recipients, is still one of the most common viral pathogens that affect these patients with a reported incidence ranging between 17% and 50% in the post transplantation period. Valganciclovir (V-GCV), a valine ester pro-drug of GCV orally administrable, has recently shown great activity against CMV infections, but there are no reports of its clinical efficacy against VZV. We here report a case history of a patient with positive serologic test for VZV, who underwent allogeneic HSCT and developed an atypical varicella-like illness. First-line therapy with foscarnet had to be discontinued due rapid development of renal impairment (creatinine: 2.60 mg/dL, urea: 130.6 mg/dL) and therefore was switched to V-GCV. The renal impairment and skin lesions of the patient fully recovered after few days of therapy, even though the patient had complete lymphocyte depletion. This is the first case of a patient with chickenpox-like illness treated successfully with V-GCV.
Keywords: Acute Kidney Injury; Adolescent; Bone Marrow Transplantation; Fatal Outcome; Female; Ganciclovir; Herpes Zoster; Herpesvirus 3, Human; Humans; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Viral Load

Delayed reactivation of chronic infantile neurologic, cutaneous, articular syndrome (CINCA) in a patient with somatic mosaicism of CIAS1/NLRP3 gene after withdrawal of anti-IL-1 beta therapy. - Paloni, Giulia; Pastore, Serena; Tommasini, Alberto; Lepore, Loredana; Taddio, Andrea (Clin Exp Rheumatol, 2015)
Keywords: Antibodies, Monoclonal; Carrier Proteins; Cryopyrin-Associated Periodic Syndromes; Drug Administration Schedule; Female; Genetic Predisposition to Disease; Humans; Immunosuppressive Agents; Interleukin 1 Receptor Antagonist Protein; Interleukin-1beta; Mosaicism; Phenotype; Recurrence; Remission Induction; Time Factors; Treatment Outcome; Young Adult

Design, Synthesis, and Biological Characterization of Novel Mitochondria Targeted Dichloroacetate-Loaded Compounds with Antileukemic Activity. - Trapella, Claudio; Voltan, Rebecca; Melloni, Elisabetta; Tisato, Veronica; Celeghini, Claudio; Bianco, Sara; Fantinati, Anna; Salvadori, Severo; Guerrini, Remo; Secchiero, Paola; Zauli, Giorgio (J Med Chem, 2015)
The mitochondrial kinase inhibitor dichloroacetate (DCA) has recently received attention in oncology due to its ability to target glycolysis. However, DCA molecule exhibits poor bioavailability and cellular uptake with limited ability to reach its target mitochondria. To overcome these biases, we have synthesized novel DCA-loaded compounds. The selection of the most promising therapeutic molecule was evaluated by combining in vitro assays, to test the antitumoral potential on leukemic cells, and a preliminary characterization of the molecule stability in vivo, in mice. Among the newly synthesized compounds, we have selected the multiple DCA-loaded compound 10, characterized by a tertiary amine scaffold, because it exhibited enhanced (>30-fold) in vitro antitumor activity with respect to DCA and increased in vivo stability. On the basis of these results, we believe that compound 10 should be considered for further preclinical evaluations for the treatment of cancers and/or other diseases characterized by altered metabolic origin.

The diagnostic challenge of very early-onset enterocolitis in an infant with XIAP deficiency. - Girardelli, Martina; Arrigo, Serena; Barabino, Arrigo; Loganes, Claudia; Morreale, Giuseppe; Crovella, Sergio; Tommasini, Alberto; Bianco, Anna Monica (BMC Pediatr, 2015)
BACKGROUND: Aggressive course and resistance to treatments usually characterize very early onset inflammatory bowel disease (VEO-IBD). Some VEO-IBD cases are due to monogenic immune defects and can benefit from hematopoietic stem cell transplantation (HSCT). CASE PRESENTATION: We describe a Caucasian male baby who presented in the first months of life macrophage activation syndrome, followed by intractable colitis, recurrent episodes of fever and mild splenomegaly. After several immunological, genetic and clinical investigations, subsequently a therapeutic attempt with colectomy, analysis of VEO-IBD-associated genes, revealed a causative mutation in XIAP. The genetic diagnosis of a primary immune deficiency allowed curing the boy with hematopoietic stem cell transplantation. CONCLUSION: Our report, together with novel findings from recent literature, should contribute to increase awareness of monogenic immune defects as a cause of VEO-IBD. Comprehensive genetic analysis can allow a prompt diagnosis, resulting in the choice of effective treatments and sparing useless and damaging procedures.

Different presentations of mevalonate kinase deficiency: a case series. - De Pieri, Carlo; Taddio, Andrea; Insalaco, Antonella; Barbi, Egidio; Lepore, Loredana; Ventura, Alessandro; Tommasini, Alberto (Clin Exp Rheumatol, 2015)
OBJECTIVES: We aimed to raise awareness among paediatricians and physicians about this often misunderstood condition. METHODS: We discussed the clinical profiles associated with late or wrong diagnosis of mevalonate kinase deficency (MKD) in a single centre case series. RESULTS: We analysed the most common challenges and pitfalls that a clinician might face during the diagnostic process. Five main clinical profiles were characterised. CONCLUSIONS: We propose a new perspective on MKD, suggesting that the presentation of this disease can vary from patient to patient.
Keywords: Age Factors; Bacterial Infections; Child; Child, Preschool; Diagnosis, Differential; Diagnostic Errors; Female; Genetic Predisposition to Disease; Humans; Infant; Inflammatory Bowel Diseases; Male; Mevalonate Kinase Deficiency; Phenotype; Predictive Value of Tests; Recurrence; Risk Factors; Sepsis; Vasculitis; Young Adult

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Does Teno Torque Virus Induce Autoimmunity After Hematopoietic Stem Cell Transplantation? A Case Report. - Maximova, Natalia; Pizzol, Antonio; Ferrara, Giovanna; Maestro, Alessandra; Tamaro, Paolo (J Pediatr Hematol Oncol, 2015)
Teno Torque virus, member of the family of Anelloviridae, has been associated with many autoimmune diseases such as idiopathic hepatitis, systemic lupus erythematosus, and multiple sclerosis. Its viral load tends to be higher in the bone marrow and in tissues with high turnover rate. We report here a case of an 11-month-old infant affected by acute myeloid leukemia who underwent hematopoietic stem cell transplantation, and after 6 months had autoimmune hepatitis and atopic dermatitis. Extremely high-cytokine IP-10 and eotaxin levels were found in her sera, and serological tests and RT-PCR for viruses showed positive results exclusively for Teno Torque virus.
Keywords: Autoimmune Diseases; Autoimmunity; Dermatitis, Atopic; DNA Virus Infections; DNA, Viral; Female; Hematopoietic Stem Cell Transplantation; Hepatitis; Humans; Infant; Leukemia, Myeloid, Acute; Prognosis; Torque teno virus; Viral Load

Failure of interferon-γ pre-treated mesenchymal stem cell treatment in a patient with Crohn's disease. - Taddio, Andrea; Tommasini, Alberto; Valencic, Erica; Biagi, Ettore; Decorti, Giuliana; De Iudicibus, Sara; Cuzzoni, Eva; Gaipa, Giuseppe; Badolato, Raffaela; Prandini, Alberto; Biondi, Andrea; Ventura, Alessandro (World J Gastroenterol, 2015)
Mesenchymal stem cells (MSC) are cells of stromal origin which exhibit unlimited self-renewal capacity and pluripotency in vitro. It has recently been observed that MSC may also exert a profound immunosuppressive and anti-inflammatory effect both in vitro and in vivo with consequent potential use in autoimmune disorders. We present the case of a patient suffering from childhood-onset, multidrug resistant and steroid-dependent Crohn's disease who underwent systemic infusions of MSC, which led to a temporary reduction in CCR4, CCR7 and CXCR4 expression by T-cells, and a temporary decrease in switched memory B-cells, In addition, following MSC infusion, lower doses of steroids were needed to inhibit proliferation of the patient's peripheral blood mononuclear cells. Despite these changes, no significant clinical benefit was observed, and the patient required rescue therapy with infliximab and subsequent autologous hematopoietic stem cell transplantation. The results of biological and in vitro observations after MSC use and the clinical effects of infusion are discussed, and a brief description is provided of previous data on MSC-based therapy in autoimmune disorders.

Fever tree revisited: From malaria to autoinflammatory diseases. - Pastore, Serena; Vuch, Josef; Bianco, Anna Monica; Taddio, Andrea; Tommasini, Alberto (World J Clin Pediatr, 2015)
Over the centuries the idea of recurrent fevers has mainly been associated with malaria, but many other fevers, such as typhoid and diphtheria were cause for concern. It is only in recent times, with the more severe forms of fever from infectious origin becoming less frequent or a cause for worry that we started noticing recurrent fevers without any clear infectious cause, being described as having a pathogenesis of autoinflammatory nature. The use of molecular examinations in many cases can allow a diagnosis where the cause is monogenic. In other cases, however the pathogenesis is likely to be multifactorial and the diagnostic-therapeutic approach is strictly clinical. The old fever tree paradigm developed to describe fevers caused by malaria has been revisited here to describe today's periodic fevers from the periodic fever adenitis pharyngitis aphthae syndrome to the more rare autoinflammatory diseases. This model may allow us to place cases that are yet to be identified which are likely to be of multifactorial origin.

Ficolin Gene Polymorphisms in Systemic Lupus Erythematosus and Rheumatoid Arthritis. - Addobbati, Catarina; De Azevêdo Silva, Jaqueline; A C Tavares, Nathália; Monticielo, Odirlei; M Xavier, Ricardo; T Brenol, João Carlos; Crovella, Sergio; B Chies, José Artur; Sandrin-Garcia, Paula (Ann Hum Genet, 2015)
Systemic lupus erythemathosus (SLE) and rheumatoid arthritis (RA) are complex autoimmune diseases characterized by an immune balance breakdown and by chronic inflammation. Several findings link SLE and RA development with the complement system and ficolin components have emerged as candidates for disease development. Since genetic association studies with ficolin genes in SLE and RA have not yet been conducted in a Brazilian population, the aim of this study was to determine whether polymorphisms of ficolin-1(FCN1) and ficolin-2 (FCN2) genes are associated with SLE and RA susceptibility as well as disease manifestation. Two SNPs within FCN1 (rs2989727 and 1071583) and three in FCN2 (rs17514136, rs3124954, and rs7851696) were studied in 208 SLE and184 RA patients as well as 264 healthy individuals in a Southeast Brazilian population. For SLE patients, the FCN2 rs17514136 SNP was associated with a more severe disease (SLICC) (p = 0.0067). Furthermore, an association between the occurrence of nephritis and the T/T genotype for FCN2 rs3124954 SNP (p = 0.047, OR = 3.17, 95%CI = 1.34-7.5) was observed. No association was observed between the studied polymorphisms and RA development. Thus, our data support involvement of the FCN2 gene in the SLE phenotype.

Functionalized synchrotron in-line phase-contrast computed tomography: a novel approach for simultaneous quantification of structural alterations and localization of barium-labelled alveolar macrophages within mouse lung samples. - Dullin, Christian; dal Monego, Simeone; Larsson, Emanuel; Mohammadi, Sara; Krenkel, Martin; Garrovo, Chiara; Biffi, Stefania; Lorenzon, Andrea; Markus, Andrea; Napp, Joanna; Salditt, Tim; Accardo, Agostino; et al. (J Synchrotron Radiat, 2015)
Functionalized computed tomography (CT) in combination with labelled cells is virtually non-existent due to the limited sensitivity of X-ray-absorption-based imaging, but would be highly desirable to realise cell tracking studies in entire organisms. In this study we applied in-line free propagation X-ray phase-contrast CT (XPCT) in an allergic asthma mouse model to assess structural changes as well as the biodistribution of barium-labelled macrophages in lung tissue. Alveolar macrophages that were barium-sulfate-loaded and fluorescent-labelled were instilled intratracheally into asthmatic and control mice. Mice were sacrificed after 24 h, lungs were kept in situ, inflated with air and scanned utilizing XPCT at the SYRMEP beamline (Elettra Synchrotron Light Source, Italy). Single-distance phase retrieval was used to generate data sets with ten times greater contrast-to-noise ratio than absorption-based CT (in our setup), thus allowing to depict and quantify structural hallmarks of asthmatic lungs such as reduced air volume, obstruction of airways and increased soft-tissue content. Furthermore, we found a higher concentration as well as a specific accumulation of the barium-labelled macrophages in asthmatic lung tissue. It is believe that XPCT will be beneficial in preclinical asthma research for both the assessment of therapeutic response as well as the analysis of the role of the recruitment of macrophages to inflammatory sites.
Keywords: Algorithms; Allergens; Animals; Asthma; Barium Sulfate; Cell Line, Transformed; Cell Movement; Contrast Media; Disease Models, Animal; Female; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Lung; Macrophages, Alveolar; Mice; Mice, Inbred BALB C; Microscopy, Fluorescence; Ovalbumin; Synchrotrons; Tomography, X-Ray Computed

Genetic determinants for methotrexate response in juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Favretto, Diego; De Iudicibus, Sara; Taddio, Andrea; d'Adamo, Pio; Malusà, Noelia; Addobbati, Riccardo; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Front Pharmacol, 2015)
Juvenile idiopathic arthritis (JIAs) is the most common chronic rheumatic disease of childhood and is an important cause of disability. The folic acid analog methotrexate is the first choice disease-modifying anti-rheumatic drug in this disease, however, 35-45% of patients fail to respond. Molecular elements, such as variants in genes of pharmacological relevance, influencing response to methotrexate in JIA, would be important to individualize treatment strategies. Several studies have evaluated the effects of candidate genetic variants in the complex pathway of genes involved in methotrexate pharmacodynamics and pharmacokinetics, however, results are still contrasting and no definitive genetic marker of methotrexate response useful for the clinician to tailor therapy of children with JIA has been identified. Recently, genome-wide approaches have been applied, identifying new potential biological processes involved in methotrexate response in JIA such as TGF-beta signaling and calcium channels. If these genomic results are properly validated and integrated with innovative analyses comprising deep sequencing, epigenetics, and pharmacokinetics, they will greatly contribute to personalize therapy with methotrexate in children with JIA.

Genetic evidence for an origin of the Armenians from Bronze Age mixing of multiple populations. - Haber, Marc; Mezzavilla, Massimo; Xue, Yali; Comas, David; Gasparini, Paolo; Zalloua, Pierre; Tyler-Smith, Chris (Eur J Hum Genet, 2015)
The Armenians are a culturally isolated population who historically inhabited a region in the Near East bounded by the Mediterranean and Black seas and the Caucasus, but remain under-represented in genetic studies and have a complex history including a major geographic displacement during World War I. Here, we analyse genome-wide variation in 173 Armenians and compare them with 78 other worldwide populations. We find that Armenians form a distinctive cluster linking the Near East, Europe, and the Caucasus. We show that Armenian diversity can be explained by several mixtures of Eurasian populations that occurred between ~3000 and ~2000 bce, a period characterized by major population migrations after the domestication of the horse, appearance of chariots, and the rise of advanced civilizations in the Near East. However, genetic signals of population mixture cease after ~1200 bce when Bronze Age civilizations in the Eastern Mediterranean world suddenly and violently collapsed. Armenians have since remained isolated and genetic structure within the population developed ~500 years ago when Armenia was divided between the Ottomans and the Safavid Empire in Iran. Finally, we show that Armenians have higher genetic affinity to Neolithic Europeans than other present-day Near Easterners, and that 29% of Armenian ancestry may originate from an ancestral population that is best represented by Neolithic Europeans.European Journal of Human Genetics advance online publication, 21 October 2015; doi:10.1038/ejhg.2015.206.

Genetic profiling of autoinflammatory disorders in patients with periodic fever: a prospective study. - De Pieri, Carlo; Vuch, Josef; De Martino, Eleonora; Bianco, Anna M; Ronfani, Luca; Athanasakis, Emmanouil; Bortot, Barbara; Crovella, Sergio; Taddio, Andrea; Severini, Giovanni M; Tommasini, Alberto (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Periodic fever syndromes (PFS) are an emerging group of autoinflammatory disorders. Clinical overlap exists and multiple genetic analyses may be needed to assist diagnosis. We evaluated the diagnostic value of a 5-gene sequencing panel (5GP) in patients with undiagnosed PFS. METHODS: Simultaneous double strand Sanger sequencing of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12 genes was performed in 42 patients with unexplained PFS. Clinical features were correlated with genetic results. RESULTS: None of 42 patients analyzed displayed a causative genotype. However, single or multiple genetic variants of uncertain significance were detected in 24 subjects. Only in 5 subjects a definite diagnosis was made by taking into account both genetic and clinical data (2 TRAPS syndrome; 2 FMF; 1 FCAS). Statistical analysis showed that patients carrying genetic variants in one or more of the five selected genes displayed a significantly lower response to glucocorticoids compared with subjects who had completely negative genetic results. CONCLUSIONS: The sequencing of multiple genes is of little help in the diagnostics of PFS and can often lead to results of uncertain interpretation, thus the clinically driven sequencing of single genes should remain the recommended approach. However, the presence of single or multiple genetic variants of uncertain significance, even if not allowing any specific diagnosis, correlated with a poorer response to glucocorticoids, possibly indicating a multifactorial subgroup of PFS with differential response to pharmacological treatment.
Keywords: Adolescent; Carrier Proteins; Child; Cryopyrin-Associated Periodic Syndromes; Cytoskeletal Proteins; Familial Mediterranean Fever; Female; Fever; Gene Expression Profiling; Genotype; Hereditary Autoinflammatory Diseases; Humans; Intracellular Signaling Peptides and Proteins; Logistic Models; Male; Mutation; Phosphotransferases (Alcohol Group Acceptor); Prospective Studies; Receptors, Tumor Necrosis Factor, Type I; Syndrome

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

Genetics of inflammatory bowel disease from multifactorial to monogenic forms. - Bianco, Anna Monica; Girardelli, Martina; Tommasini, Alberto (World J Gastroenterol, 2015)
Inflammatory bowel disease (IBD) is a group of chronic multifactorial disorders. According to a recent study, the number of IBD association loci is increased to 201, of which 37 and 27 loci contribute specifically to the development of Crohn's disease and ulcerative colitis respectively. Some IBD associated genes are involved in innate immunity, in the autophagy and in the inflammatory response such as NOD2, ATG16L1 and IL23R, while other are implicated in immune mediated disease (STAT3) and in susceptibility to mycobacterium infection (IL12B). In case of early onset of IBD (VEO-IBD) within the 6(th) year of age, the disease may be caused by mutations in genes responsible for severe monogenic disorders such as the primary immunodeficiency diseases. In this review we discuss how these monogenic disorders through different immune mechanisms can similarly be responsible of VEO-IBD phenotype. Moreover we would highlight how the identification of pathogenic genes by Next Generation Sequencing technologies can allow to obtain a rapid diagnosis and to apply specific therapies.

Genome sequencing elucidates Sardinian genetic architecture and augments association analyses for lipid and blood inflammatory markers. - Sidore, Carlo; Busonero, Fabio; Maschio, Andrea; Porcu, Eleonora; Naitza, Silvia; Zoledziewska, Magdalena; Mulas, Antonella; Pistis, Giorgio; Steri, Maristella; Danjou, Fabrice; Kwong, Alan; Ortega Del Vecchyo, Vicente Diego; et al. (Nat Genet, 2015)
We report ∼17.6 million genetic variants from whole-genome sequencing of 2,120 Sardinians; 22% are absent from previous sequencing-based compilations and are enriched for predicted functional consequences. Furthermore, ∼76,000 variants common in our sample (frequency >5%) are rare elsewhere (<0.5% in the 1000 Genomes Project). We assessed the impact of these variants on circulating lipid levels and five inflammatory biomarkers. We observe 14 signals, including 2 major new loci, for lipid levels and 19 signals, including 2 new loci, for inflammatory markers. The new associations would have been missed in analyses based on 1000 Genomes Project data, underlining the advantages of large-scale sequencing in this founder population.

Genome-wide association analysis on five isolated populations identifies variants of the HLA-DOA gene associated with white wine liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; Amin, Najaf; Sala, Cinzia; Karssen, Lennart C; van Duijn, Cornelia M; Toniolo, Daniela; Gasparini, Paolo (Eur J Hum Genet, 2015)
Wine is the most popular alcoholic beverage around the world and because of its importance in society has been widely studied. Understanding what drives its flavor has been a quest for decades but much is still unknown and will be determined at least in part by individual taste preferences. Recently studies in the genetics of taste have uncovered the role of different genes in the determination of food preferences giving new insight on its physiology. In this context we have performed a genome-wide association study on red and white wine liking using three isolated populations collected in Italy, and replicated our results on two additional populations coming from the Netherland and Central Asia for a total of 3885 samples. We have found a significant association (P=2.1 × 10(-8)) between white wine liking and rs9276975:C>T a polymorphism in the HLA-DOA gene encoding a non-canonical MHC II molecule, which regulates other MHC II molecules. The same association was also found with red wine liking (P=8.3 × 10(-6)). Sex-separated analysis have also revealed that the effect of HLA-DOA is twice as large in women as compared to men suggesting an interaction between this polymorphism and gender. Our results are one of the first examples of genome-wide association between liking of a commonly consumed food and gene variants. Moreover, our results suggest a role of the MHC system in the determination of food preferences opening new insight in this field in general.

The Global Burden of Cancer 2013. - Fitzmaurice, Christina; Dicker, Daniel; Pain, Amanda; Hamavid, Hannah; Moradi-Lakeh, Maziar; MacIntyre, Michael F; Allen, Christine; Hansen, Gillian; Woodbrook, Rachel; Wolfe, Charles; Hamadeh, Randah R; Moore, Ami; et al. (JAMA Oncol, 2015)
IMPORTANCE: Cancer is among the leading causes of death worldwide. Current estimates of cancer burden in individual countries and regions are necessary to inform local cancer control strategies. OBJECTIVE: To estimate mortality, incidence, years lived with disability (YLDs), years of life lost (YLLs), and disability-adjusted life-years (DALYs) for 28 cancers in 188 countries by sex from 1990 to 2013. EVIDENCE REVIEW: The general methodology of the Global Burden of Disease (GBD) 2013 study was used. Cancer registries were the source for cancer incidence data as well as mortality incidence (MI) ratios. Sources for cause of death data include vital registration system data, verbal autopsy studies, and other sources. The MI ratios were used to transform incidence data to mortality estimates and cause of death estimates to incidence estimates. Cancer prevalence was estimated using MI ratios as surrogates for survival data; YLDs were calculated by multiplying prevalence estimates with disability weights, which were derived from population-based surveys; YLLs were computed by multiplying the number of estimated cancer deaths at each age with a reference life expectancy; and DALYs were calculated as the sum of YLDs and YLLs. FINDINGS: In 2013 there were 14.9 million incident cancer cases, 8.2 million deaths, and 196.3 million DALYs. Prostate cancer was the leading cause for cancer incidence (1.4 million) for men and breast cancer for women (1.8 million). Tracheal, bronchus, and lung (TBL) cancer was the leading cause for cancer death in men and women, with 1.6 million deaths. For men, TBL cancer was the leading cause of DALYs (24.9 million). For women, breast cancer was the leading cause of DALYs (13.1 million). Age-standardized incidence rates (ASIRs) per 100 000 and age-standardized death rates (ASDRs) per 100 000 for both sexes in 2013 were higher in developing vs developed countries for stomach cancer (ASIR, 17 vs 14; ASDR, 15 vs 11), liver cancer (ASIR, 15 vs 7; ASDR, 16 vs 7), esophageal cancer (ASIR, 9 vs 4; ASDR, 9 vs 4), cervical cancer (ASIR, 8 vs 5; ASDR, 4 vs 2), lip and oral cavity cancer (ASIR, 7 vs 6; ASDR, 2 vs 2), and nasopharyngeal cancer (ASIR, 1.5 vs 0.4; ASDR, 1.2 vs 0.3). Between 1990 and 2013, ASIRs for all cancers combined (except nonmelanoma skin cancer and Kaposi sarcoma) increased by more than 10% in 113 countries and decreased by more than 10% in 12 of 188 countries. CONCLUSIONS AND RELEVANCE: Cancer poses a major threat to public health worldwide, and incidence rates have increased in most countries since 1990. The trend is a particular threat to developing nations with health systems that are ill-equipped to deal with complex and expensive cancer treatments. The annual update on the Global Burden of Cancer will provide all stakeholders with timely estimates to guide policy efforts in cancer prevention, screening, treatment, and palliation.

Global, regional, and national comparative risk assessment of 79 behavioural, environmental and occupational, and metabolic risks or clusters of risks in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Forouzanfar, Mohammad H; Alexander, Lily; Anderson, H Ross; Bachman, Victoria F; Biryukov, Stan; Brauer, Michael; Burnett, Richard; Casey, Daniel; Coates, Matthew M; Cohen, Aaron; Delwiche, Kristen; Estep, Kara; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease, Injuries, and Risk Factor study 2013 (GBD 2013) is the first of a series of annual updates of the GBD. Risk factor quantification, particularly of modifiable risk factors, can help to identify emerging threats to population health and opportunities for prevention. The GBD 2013 provides a timely opportunity to update the comparative risk assessment with new data for exposure, relative risks, and evidence on the appropriate counterfactual risk distribution. METHODS: Attributable deaths, years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) have been estimated for 79 risks or clusters of risks using the GBD 2010 methods. Risk-outcome pairs meeting explicit evidence criteria were assessed for 188 countries for the period 1990-2013 by age and sex using three inputs: risk exposure, relative risks, and the theoretical minimum risk exposure level (TMREL). Risks are organised into a hierarchy with blocks of behavioural, environmental and occupational, and metabolic risks at the first level of the hierarchy. The next level in the hierarchy includes nine clusters of related risks and two individual risks, with more detail provided at levels 3 and 4 of the hierarchy. Compared with GBD 2010, six new risk factors have been added: handwashing practices, occupational exposure to trichloroethylene, childhood wasting, childhood stunting, unsafe sex, and low glomerular filtration rate. For most risks, data for exposure were synthesised with a Bayesian meta-regression method, DisMod-MR 2.0, or spatial-temporal Gaussian process regression. Relative risks were based on meta-regressions of published cohort and intervention studies. Attributable burden for clusters of risks and all risks combined took into account evidence on the mediation of some risks such as high body-mass index (BMI) through other risks such as high systolic blood pressure and high cholesterol. FINDINGS: All risks combined account for 57·2% (95% uncertainty interval [UI] 55·8-58·5) of deaths and 41·6% (40·1-43·0) of DALYs. Risks quantified account for 87·9% (86·5-89·3) of cardiovascular disease DALYs, ranging to a low of 0% for neonatal disorders and neglected tropical diseases and malaria. In terms of global DALYs in 2013, six risks or clusters of risks each caused more than 5% of DALYs: dietary risks accounting for 11·3 million deaths and 241·4 million DALYs, high systolic blood pressure for 10·4 million deaths and 208·1 million DALYs, child and maternal malnutrition for 1·7 million deaths and 176·9 million DALYs, tobacco smoke for 6·1 million deaths and 143·5 million DALYs, air pollution for 5·5 million deaths and 141·5 million DALYs, and high BMI for 4·4 million deaths and 134·0 million DALYs. Risk factor patterns vary across regions and countries and with time. In sub-Saharan Africa, the leading risk factors are child and maternal malnutrition, unsafe sex, and unsafe water, sanitation, and handwashing. In women, in nearly all countries in the Americas, north Africa, and the Middle East, and in many other high-income countries, high BMI is the leading risk factor, with high systolic blood pressure as the leading risk in most of Central and Eastern Europe and south and east Asia. For men, high systolic blood pressure or tobacco use are the leading risks in nearly all high-income countries, in north Africa and the Middle East, Europe, and Asia. For men and women, unsafe sex is the leading risk in a corridor from Kenya to South Africa. INTERPRETATION: Behavioural, environmental and occupational, and metabolic risks can explain half of global mortality and more than one-third of global DALYs providing many opportunities for prevention. Of the larger risks, the attributable burden of high BMI has increased in the past 23 years. In view of the prominence of behavioural risk factors, behavioural and social science research on interventions for these risks should be strengthened. Many prevention and primary care policy options are available now to act on key risks. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national disability-adjusted life years (DALYs) for 306 diseases and injuries and healthy life expectancy (HALE) for 188 countries, 1990-2013: quantifying the epidemiological transition. - Murray, Christopher J L; Barber, Ryan M; Foreman, Kyle J; Abbasoglu Ozgoren, Ayse; Abd-Allah, Foad; Abera, Semaw F; Aboyans, Victor; Abraham, Jerry P; Abubakar, Ibrahim; Abu-Raddad, Laith J; Abu-Rmeileh, Niveen M; Achoki, Tom; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease Study 2013 (GBD 2013) aims to bring together all available epidemiological data using a coherent measurement framework, standardised estimation methods, and transparent data sources to enable comparisons of health loss over time and across causes, age-sex groups, and countries. The GBD can be used to generate summary measures such as disability-adjusted life-years (DALYs) and healthy life expectancy (HALE) that make possible comparative assessments of broad epidemiological patterns across countries and time. These summary measures can also be used to quantify the component of variation in epidemiology that is related to sociodemographic development. METHODS: We used the published GBD 2013 data for age-specific mortality, years of life lost due to premature mortality (YLLs), and years lived with disability (YLDs) to calculate DALYs and HALE for 1990, 1995, 2000, 2005, 2010, and 2013 for 188 countries. We calculated HALE using the Sullivan method; 95% uncertainty intervals (UIs) represent uncertainty in age-specific death rates and YLDs per person for each country, age, sex, and year. We estimated DALYs for 306 causes for each country as the sum of YLLs and YLDs; 95% UIs represent uncertainty in YLL and YLD rates. We quantified patterns of the epidemiological transition with a composite indicator of sociodemographic status, which we constructed from income per person, average years of schooling after age 15 years, and the total fertility rate and mean age of the population. We applied hierarchical regression to DALY rates by cause across countries to decompose variance related to the sociodemographic status variable, country, and time. FINDINGS: Worldwide, from 1990 to 2013, life expectancy at birth rose by 6·2 years (95% UI 5·6-6·6), from 65·3 years (65·0-65·6) in 1990 to 71·5 years (71·0-71·9) in 2013, HALE at birth rose by 5·4 years (4·9-5·8), from 56·9 years (54·5-59·1) to 62·3 years (59·7-64·8), total DALYs fell by 3·6% (0·3-7·4), and age-standardised DALY rates per 100 000 people fell by 26·7% (24·6-29·1). For communicable, maternal, neonatal, and nutritional disorders, global DALY numbers, crude rates, and age-standardised rates have all declined between 1990 and 2013, whereas for non-communicable diseases, global DALYs have been increasing, DALY rates have remained nearly constant, and age-standardised DALY rates declined during the same period. From 2005 to 2013, the number of DALYs increased for most specific non-communicable diseases, including cardiovascular diseases and neoplasms, in addition to dengue, food-borne trematodes, and leishmaniasis; DALYs decreased for nearly all other causes. By 2013, the five leading causes of DALYs were ischaemic heart disease, lower respiratory infections, cerebrovascular disease, low back and neck pain, and road injuries. Sociodemographic status explained more than 50% of the variance between countries and over time for diarrhoea, lower respiratory infections, and other common infectious diseases; maternal disorders; neonatal disorders; nutritional deficiencies; other communicable, maternal, neonatal, and nutritional diseases; musculoskeletal disorders; and other non-communicable diseases. However, sociodemographic status explained less than 10% of the variance in DALY rates for cardiovascular diseases; chronic respiratory diseases; cirrhosis; diabetes, urogenital, blood, and endocrine diseases; unintentional injuries; and self-harm and interpersonal violence. Predictably, increased sociodemographic status was associated with a shift in burden from YLLs to YLDs, driven by declines in YLLs and increases in YLDs from musculoskeletal disorders, neurological disorders, and mental and substance use disorders. In most country-specific estimates, the increase in life expectancy was greater than that in HALE. Leading causes of DALYs are highly variable across countries. INTERPRETATION: Global health is improving. Population growth and ageing have driven up numbers of DALYs, but crude rates have remained relatively constant, showing that progress in health does not mean fewer demands on health systems. The notion of an epidemiological transition--in which increasing sociodemographic status brings structured change in disease burden--is useful, but there is tremendous variation in burden of disease that is not associated with sociodemographic status. This further underscores the need for country-specific assessments of DALYs and HALE to appropriately inform health policy decisions and attendant actions. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Chronic Disease; Communicable Diseases; Female; Global Health; Health Transition; Humans; Life Expectancy; Male; Middle Aged; Mortality, Premature; Quality-Adjusted Life Years; Socioeconomic Factors; Wounds and Injuries

GRID2 a novel gene possibly associated with mevalonate kinase deficiency. - Moura, Ronald; Tricarico, Paola Maura; Campos Coelho, Antonio Victor; Crovella, Sergio (Rheumatol Int, 2015)
Mevalonate kinase deficiency (MKD) is a rare autosomal disease caused by mutations in the mevalonate kinase gene (MVK). The genotype-phenotype correlation is sometimes problematic due to the great genetic and clinical heterogeneity; so we hypothesize that genes other than MVK are able to modulate MKD clinical phenotypes. This hypothesis was tested by analyzing the exome of 22 patients with MKD all carrying MVK gene mutations, and 20 patients with recurrent fevers (RF) not carrying MVK mutations. Our preliminary findings suggest a possible role of GRID2 in the susceptibility to develop MKD. GRID2 gene (4q22.2), encoding for human glutamate receptor delta-2, associated with MKD: The rs1450500 SNP was differently distributed in patients with MKD with respect to those with RF. Being aware of the small number of patients analyzed, we hypothesized a possible role for GRID2 as possible phenotype modifier in MKD patients, especially in those with severe phenotypes.

Identification of a novel frameshift mutation in the EDAR gene causing autosomal dominant hypohidrotic ectodermal dysplasia. - Callea, M; Willoughby, C E; Nieminen, P; Di Stazio, M; Bellacchio, E; Giglio, S; Sani, I; Vinciguerra, A; Maglione, M; Tadini, G; Clarich, G (J Eur Acad Dermatol Venereol, 2015)

Immunologic evidence of a strong association between non-Hodgkin lymphoma and simian virus 40. - Tognon, Mauro; Luppi, Mario; Corallini, Alfredo; Taronna, Angelo; Barozzi, Patrizia; Rotondo, John Charles; Comar, Manola; Casali, Maria Vittoria; Bovenzi, Massimo; D'Agostino, Antonio; Vinante, Fabrizio; Rigo, Antonella; et al. (Cancer, 2015)
BACKGROUND: Non-Hodgkin lymphoma (NHL), the most common cancer of the lymphatic system, is of unknown etiology. The identification of etiologic factors in the onset of NHL is a key event that could facilitate the prevention and cure of this malignancy. Simian virus 40 (SV40) has been considered an oncogenic agent in the onset/progression of NHL. METHODS: In this study, an indirect enzyme-linked immunosorbent assay with 2 synthetic peptides that mimic SV40 antigens of viral capsid proteins 1 to 3 was employed to detect specific antibodies against SV40. Serum samples were taken from 2 distinct cohorts of NHL-affected patients (NHL1 [n = 89] and NHL2 [n = 61]) along with controls represented by oncologic patients affected by breast cancer (BC; n = 78) and undifferentiated nasopharyngeal carcinoma (UNPC; n = 64) and 3 different cohorts of healthy subjects (HSs; HS1 [n = 130], HS2 [n = 83], and HS3 [n = 87]). RESULTS: Immunologic data indicated that in serum samples from NHL patients, antibodies against SV40 mimotopes were detectable with a prevalence of 40% in NHL1 patients and with a prevalence of 43% in NHL2 patients. In HSs of the same median age as NHL patients, the prevalence was 16% for the HS1 group (57 years) and 14% for the HS2 group (65 years). The difference was statistically significant (P < .0001 and P < .001). Interestingly, the difference between NHL1/NHL2 patients and BC patients (40%/43% vs 15%, P < .001) and between NHL1/NHL2 patients and UNPC patients (40%/43% vs 25%, P < .05) was significant. CONCLUSIONS: Our data indicate a strong association between NHL and SV40 and thus a need for innovative therapeutic approaches for this hematologic malignancy.
Keywords: Adult; Aged; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Lymphoma, Non-Hodgkin; Male; Middle Aged; Polyomavirus Infections; Seroepidemiologic Studies; Simian virus 40; Tumor Virus Infections

Impact of Surgery for Neonatal Gastrointestinal Diseases on Weight and Fat Mass. - De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (J Pediatr, 2015)
OBJECTIVE: To compare growth, fat mass (FM), and fat-free mass in surgical infants vs matched controls at similar postconceptional age (PCA). STUDY DESIGN: Anthropometric and body composition measurements by air-displacement plethysmography (PeaPod-Infant Body Composition System; LMI, Concord, California) were performed at the same PCA in 21 infants who received gastrointestinal surgery and in 21 controls matched for gestational age, birth weight, and sex. RESULTS: Despite similar anthropometry at birth, postsurgical infants were shorter (50.4 [4.7] cm vs 53.2 [4.1] cm, P = .001), lighter (3516 [743] g vs 3946 [874] g, P < .001), and had lower FM content (%FM 14.8 [4.7]% vs 20.2 [5.8]%, P < .0001) than their peers at similar PCA (43 [4] weeks). All surgical infants but 1 (20/21) received parenteral nutrition (PN). Mean PN duration was 40 (30) days. Five infants in the control group received PN because of prematurity for 15 (9-30) days. Nine infants in the surgical group and 1 in the control group had PN-associated cholestasis. CONCLUSIONS: Neonates having surgery for gastrointestinal diseases were shorter, had lower weight, and lower FM content than their peers, despite receiving more PN. Body composition evaluation and monitoring may help optimize growth in these newborns.

Impaired immune response to Candida albicans in cells from Fanconi anemia patients. - Parodi, Alessia; Kalli, Francesca; Svahn, Johanna; Stroppiana, Giorgia; De Rocco, Daniela; Terranova, Paola; Dufour, Carlo; Fenoglio, Daniela; Cappelli, Enrico (Cytokine, 2015)
Fanconi anemia (FA) is a genetic disorder characterized by bone marrow failure and cancer predisposition. Several studies show alterations of the immunological status of FA patients including defects in peripheral blood lymphocyte subsets, serum immunoglobulin levels, and inflammatory cytokines. However scanty information is available on the response of FA cells to specific infectious antigens. In this work we examined the response of FA cells to different immunological stimuli and found a defective response of IL-1β, TNF-α and IL-17 to Candida albicans stimulation thus pointing to a potentially impaired response to fungal infections of FA patients.
Keywords: Adolescent; Candida albicans; CD8-Positive T-Lymphocytes; Cell Proliferation; Cells, Cultured; Child; Child, Preschool; Cytokines; Fanconi Anemia; Humans; Immunity; Infant; Young Adult

Improved imputation of low-frequency and rare variants using the UK10K haplotype reference panel. - Huang, Jie; Howie, Bryan; McCarthy, Shane; Memari, Yasin; Walter, Klaudia; Min, Josine L; Danecek, Petr; Malerba, Giovanni; Trabetti, Elisabetta; Zheng, Hou-Feng; Gambaro, Giovanni; Richards, J Brent; et al. (Nat Commun, 2015)
Imputing genotypes from reference panels created by whole-genome sequencing (WGS) provides a cost-effective strategy for augmenting the single-nucleotide polymorphism (SNP) content of genome-wide arrays. The UK10K Cohorts project has generated a data set of 3,781 whole genomes sequenced at low depth (average 7x), aiming to exhaustively characterize genetic variation down to 0.1% minor allele frequency in the British population. Here we demonstrate the value of this resource for improving imputation accuracy at rare and low-frequency variants in both a UK and an Italian population. We show that large increases in imputation accuracy can be achieved by re-phasing WGS reference panels after initial genotype calling. We also present a method for combining WGS panels to improve variant coverage and downstream imputation accuracy, which we illustrate by integrating 7,562 WGS haplotypes from the UK10K project with 2,184 haplotypes from the 1000 Genomes Project. Finally, we introduce a novel approximation that maintains speed without sacrificing imputation accuracy for rare variants.

Insights from Cardiac Mechanics after Three Decades from Successfully Repaired Aortic Coarctation. - Faganello, Giorgio; Fisicaro, Maurizio; Russo, Giulia; Iorio, Anita; Mazzone, Carmine; Grande, Eliana; Humar, Franco; Cherubini, Antonella; Pandullo, Claudio; Barbati, Giulia; Tarantini, Luigi; Benettoni, Alessandra; et al. (Congenit Heart Dis, 2015)
BACKGROUND AND AIMS: Patients who underwent a successful repair of the aortic coarctation show chronic hyperdynamic state and normal left ventricular (LV) geometry; however, there are few data regarding the LV systolic function in the long term. Accordingly, we assessed LV systolic mechanics and factors associated with LV systolic dysfunction (LVSD) in patients with repaired CoA. METHODS: Clinical and echocardiographic data from 19 repaired CoA were analyzed 28 ± 13 years after surgery. Stress-corrected midwall shortening (sc-MS) and mitral annular peak systolic velocity (S') were analyzed as indexes of LV circumferential and longitudinal systolic function, respectively. Echocardiographic data of CoA patients were compared with 19 patients matched for age and hypertension and 38 healthy controls. Sc-MS was considered impaired if <89%, S' if <8.5 cm/s (10th percentiles of healthy controls, respectively). RESULTS: There were no statistical differences between study groups in LV volumes, mass and geometry. LV ejection fraction and Sc-MS were similar in all groups, however, CoA group had a significantly lower peak S' in comparison with matched and healthy controls (7.1 ± 1.3, 10.3 ± 1.9, and 11.1 ± 1.5, respectively; all P < 0.001). Prevalence of longitudinal LVSD defined as low S' was 84% in CoA, 13% in matched, and 5% in healthy control group (all P<0.05). Multivariate logistic regression analysis revealed that low peak S' was independently related to higher E/E' ratio and the presence of CoA. CONCLUSIONS: Patients who underwent a successful repair of CoA commonly show asymptomatic longitudinal LVSD associated with worse LV diastolic function in the long-term follow-up.

The Kalash genetic isolate: ancient divergence, drift, and selection. - Ayub, Qasim; Mezzavilla, Massimo; Pagani, Luca; Haber, Marc; Mohyuddin, Aisha; Khaliq, Shagufta; Mehdi, Syed Qasim; Tyler-Smith, Chris (Am J Hum Genet, 2015)
The Kalash represent an enigmatic isolated population of Indo-European speakers who have been living for centuries in the Hindu Kush mountain ranges of present-day Pakistan. Previous Y chromosome and mitochondrial DNA markers provided no support for their claimed Greek descent following Alexander III of Macedon's invasion of this region, and analysis of autosomal loci provided evidence of a strong genetic bottleneck. To understand their origins and demography further, we genotyped 23 unrelated Kalash samples on the Illumina HumanOmni2.5M-8 BeadChip and sequenced one male individual at high coverage on an Illumina HiSeq 2000. Comparison with published data from ancient hunter-gatherers and European farmers showed that the Kalash share genetic drift with the Paleolithic Siberian hunter-gatherers and might represent an extremely drifted ancient northern Eurasian population that also contributed to European and Near Eastern ancestry. Since the split from other South Asian populations, the Kalash have maintained a low long-term effective population size (2,319-2,603) and experienced no detectable gene flow from their geographic neighbors in Pakistan or from other extant Eurasian populations. The mean time of divergence between the Kalash and other populations currently residing in this region was estimated to be 11,800 (95% confidence interval = 10,600-12,600) years ago, and thus they represent present-day descendants of some of the earliest migrants into the Indian sub-continent from West Asia.
Keywords: Asia; Asian Continental Ancestry Group; Chromosomes, Human, Y; Demography; DNA, Mitochondrial; European Continental Ancestry Group; Genetic Drift; Genetics, Population; Haplotypes; History, Ancient; Humans; Male; Pakistan; Phylogeny

Kinetic Profiles of Inflammatory Mediators in the Conjunctival Sac Fluid of Patients upon Photorefractive Keratectomy. - Tisato, Veronica; Perri, Paolo; Rimondi, Erika; Melloni, Elisabetta; Lamberti, Giuseppe; Milani, Daniela; Secchiero, Paola; Zauli, Giorgio (Mediators Inflamm, 2015)
Photorefractive keratectomy (PRK) represents a therapeutic option to remodel corneal stroma and to compensate refractive errors, which involves inflammatory and/or regenerative processes. In this context, the modulation of cytokines/chemokines in the conjunctival sac fluid and their role in the maintenance of the corneal microenvironment during the healing process upon refractive procedures has not been deeply investigated. In this study, serial samples of conjunctival sac fluid of patients (n = 25) undergoing PRK were harvested before and at different time points after surgery. The levels of 29 cytokines/chemokines/growth factors involved in inflammatory/immune processes were measured with a multiplex array system. The results have firstly highlighted the different pattern of cytokine expression between the microenvironment at the anterior surface of the eye and the systemic circulation. More importantly, the kinetic of modulation of cytokines/chemokines at the conjunctival level following PRK revealed that while the majority of cytokines/chemokines showed a significant decrease, MCP-1 emerged in light of its pronounced and significant increase soon after PRK and during the follow-up. This methodological approach has highlighted the role of MCP-1 in the healing process following PRK and has shown a potential for the identification of expression/modulation of soluble factors for biomarker profiling in ocular surface diseases.

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.

Leptin/adiponectin ratio predicts poststroke neurological outcome. - Carbone, Federico; Burger, Fabienne; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; Bertolotto, Maria; Dallegri, Franco; Mach, François; Fainardi, Enrico; et al. (Eur J Clin Invest, 2015)
BACKGROUND AND AIMS: Different adipokines have been associated with atherosclerotic plaque rupture and cardiovascular events, such as acute ischaemic stroke (AIS). However, the potential role of these molecules in postischaemic brain injury remains largely unknown. METHODS AND METHODS: We performed a substudy analysis on nonobese patients with first atherothrombotic stroke (n = 35) from a recently published prospective cohort. Primary endpoint was to investigate the predictive value of serum leptin/adiponectin ratio on neurological recovery at 90 days after AIS. The secondary endpoint was the predictive value of serum adipokine levels of clinical and radiological outcomes at a shorter follow-up (at days 1 and 7 after AIS). The radiological evaluation included ischaemic lesion volume and haemorrhagic transformation (HT). The clinical examination was based on National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS). RESULTS: At day 1 after AIS, serum leptin and leptin/adiponectin ratio were increased and inversely correlated with both radiological and clinical parameters at all follow-up time points. Once identified the best cut-off points by receiver operating characteristic (ROC) analysis, risk analysis showed that higher circulating leptin improved neurological recovery at day 90. In addition, leptin/adiponectin ratio maintained statistical significance after adjustment for age, gender and thrombolysis, also predicting the occurrence of HT in the first 7 days after AIS (adjusted OR 0·15 [95% CI 0·03-0·83); P = 0·030]). CONCLUSIONS: Higher leptin/adiponectin ratio at day 1 predicted better neurological outcomes in patients with atherothrombotic AIS and might be potentially useful as a prognostic biomarker of the disease.

Long noncoding RNA GAS5: a novel marker involved in glucocorticoid response. - Lucafo, M; De Iudicibus, S; Di Silvestre, A; Pelin, M; Candussio, L; Martelossi, S; Tommasini, A; Piscianz, E; Ventura, A; Decorti, G (Curr Mol Med, 2015)
Glucocorticoids (GCs) exert their effects through regulation of gene expression after activation in the cytoplasm of the glucocorticoid receptor (GR) encoded by NR3C1 gene. A negative feedback mechanism resulting in GR autoregulation has been demonstrated through the binding of the activated receptor to intragenic sequences called GRE-like elements, contained in GR gene. The long noncoding RNA growth arrest-specific transcript 5 (GAS5) interacts with the activated GR suppressing its transcriptional activity. The aim of this study was to evaluate the possible role of GAS5 and NR3C1 gene expression in the antiproliferative effect of methylprednisolone in peripheral blood mononuclear cells and to correlate the expression with individual sensitivity to GCs. Subjects being poor responders to GCs presented higher levels of GAS5 and NR3C1 in comparison with good responders. We suggest that abnormal levels of GAS5 may alter GC effectiveness, probably interfering with the mechanism of GR autoregulation.
Keywords: Adult; Cell Proliferation; Female; Gene Expression Regulation; Glucocorticoids; Humans; Leukocytes, Mononuclear; Male; Methylprednisolone; Middle Aged; Receptors, Glucocorticoid; RNA, Long Noncoding; Transcription, Genetic

Making patient centered care a reality: a survey of patient educational programs in Italian Cancer Research and Care Institutes. - Cipolat Mis, C; Truccolo, I; Ravaioli, V; Cocchi, S; Gangeri, L; Mosconi, P; Drace, C; Pomicino, L; Paradiso, A; De Paoli, P (BMC Health Serv Res, 2015)
BACKGROUND: Educational intervention represents an essential element of care for cancer patients; while several single institutions develop their own patient education (PE) programs on cancer, little information is available on the effective existence of PE programs at the level of research and care institutes. In Italy such institutes--Istituti di Ricovero e Cura a Carattere Scientifico--are appointed by the Ministry of Health, and 11 (Cancer Research & Care Istitute-CRCI) of the 48 are specific for cancer on the basis of specific requirements regarding cancer care, research and education. Therefore, they represent an ideal and homogeneous model through which to investigate PE policies and activities throughout the country. The objective of this study was to assess PE activities in Italian CRCI. METHODS: We carried out a survey on PE strategies and services through a questionnaire. Four key points were investigated: a) PE as a cancer care priority, b) activities that are routinely part of PE, c) real involvement of the patients, and d) involvement of healthcare workers in PE activities. RESULTS: Most CRCI (85%) completed the survey. All reported having ongoing PE activities, and 4 of the 11 considered PE an institutional activity. More than 90% of CRCI organize classes and prepare PE handouts, while other PE activities (e.g., Cancer Information Services, mutual support groups) are less frequently part of institutional PE programs. Patients are frequently involved in the organization and preparation of educational activities on the basis of their own needs. Various PE activities are carried out for caregivers in 8 (73%) out of 11 institutes. Finally, health care workers have an active role in the organization of PE programs, although nurses take part in these activities in only half of CRCI and pharmacists are seldom included. CONCLUSIONS: The information arising from our research constitutes a necessary framework to identify areas of development and to design new strategies and standards to disseminate the culture of PE. This may ultimately help and stimulate the establishment of institutional integrated PE programs, including policies and interventions that can benefit a significant proportion of cancer patients.

Making the first days of life safer: preventing sudden unexpected postnatal collapse while promoting breastfeeding. - Davanzo, Riccardo; De Cunto, Angela; Paviotti, Giulia; Travan, Laura; Inglese, Stefania; Brovedani, Pierpaolo; Crocetta, Anna; Calligaris, Chiara; Corubolo, Elisa; Dussich, Valentina; Verardi, Giuseppa; Causin, Enrica; et al. (J Hum Lact, 2015)
Early and prolonged skin-to-skin contact (SSC) after birth between a mother and her newborn has been shown to generate beneficial effects on the mother-infant relationship and breastfeeding. Close mother-infant body contact immediately after birth positively enhances exclusive breastfeeding during the hospital stay, with a dose-response relationship. Skin-to-skin contact may ease the infant's transition to extra-uterine life and helps regulate the infant's body temperature and nursing behavior. However, reports of sudden unexpected postnatal collapse (SUPC) soon after birth, in healthy term neonates, in association with SSC, have raised concerns about the safety of this practice. Based on available evidence, we developed a surveillance protocol in the delivery room and postnatal ward of the Institute for Maternal and Child Health of Trieste (Italy). The aim of our protocol is (a) to promote safe mother and infant bonding and (b) to establish successful breastfeeding, without increasing the risk of SUPC. As there is no known effective intervention to prevent SUPC, our protocol has been conceived as a potential best practice.

Mature and immature teratoma: A report from the second Italian pediatric study. - Terenziani, Monica; D'Angelo, Paolo; Inserra, Alessandro; Boldrini, Renata; Bisogno, Gianni; Babbo, Gian Luca; Conte, Massimo; Dall' Igna, Patrizia; De Pasquale, Maria Debora; Indolfi, Paolo; Piva, Luigi; Riccipetitoni, Giovanna; et al. (Pediatr Blood Cancer, 2015)
BACKGROUND: Teratomas demonstrate a benign clinical behavior, however they may recur with malignant components or as teratoma, and in a small group of patients prognosis could be fatal. After the first Italian study, we collected cases of teratoma, alongside the protocol for malignant germ cell tumors. PROCEDURE: Patients with teratoma were collected from 2004 to 2014. Teratomas were classified according to the WHO classifications, as mature and immature. Patients with pathological aFP and/or bHCG, and those with a malignant germ cell component were not included. RESULTS: The study enrolled 219 patients (150 mature, 69 immature teratomas) with a median age at diagnosis of 42 months. The primary sites involved were: 118 gonadal and 101 extragonadal teratomas. Two females with ovarian teratoma had a positive family history. Complete and incomplete surgeries were performed in 85% and 9% of cases. Seventeen events occurred: six females had a second metachronous tumor (5 contralateral ovarian teratoma, 1 adrenal neuroblastoma) and 11 teratomas relapsed/progressed (3 mature, 8 immature teratomas). Two patients died, one of progressive immature teratoma and one of surgical complications. At a median follow up of 68 months, the event-free, relapse-free, and overall survival rates were 90.6%, 94.3%, 98.6%, respectively. CONCLUSIONS: Teratomas show a good prognosis, especially the mature ones: surgery and follow-up remain the standard approach. Incomplete surgery in immature teratoma is the group at greatest risk of relapse. Bilateral ovarian tumors are a possibility, and the rare family predisposition to ovarian mature teratoma warrants further analyses.
Keywords: Adolescent; Adult; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Incidence; Infant; Infant, Newborn; Italy; Male; Neoplasm Grading; Neoplasm Recurrence, Local; Neoplasm Staging; Neoplasms, Second Primary; Neuroblastoma; Ovarian Neoplasms; Prognosis; Prospective Studies; Survival Rate; Teratoma; Testicular Neoplasms; Young Adult

The mediating role of interpersonal conflict at work in the relationship between negative affectivity and biomarkers of stress. - Girardi, Damiano; Falco, Alessandra; De Carlo, Alessandro; Benevene, Paula; Comar, Manola; Tongiorgi, Enrico; Bartolucci, Giovanni Battista (J Behav Med, 2015)
This study examined the association between interpersonal conflict at work (ICW) and serum levels of three possible biomarkers of stress, namely the pro-inflammatory cytokines Interleukin 1 beta (IL-1β), Interleukin 12 (IL-12), and Interleukin 17 (IL-17). Additionally, this study investigated the role of negative affectivity (NA) in the relationship between ICW and the pro-inflammatory cytokines. Data from 121 employees in an Italian healthcare organization were analyzed using structural equation modeling. Results showed that ICW was positively associated with IL-1β, IL-12, and IL-17, after controlling for the effect of gender. Moreover, ICW completely mediated the relationship between NA and the pro-inflammatory cytokines IL-1β, IL-12, and IL-17. This mediating effect was significant after controlling for the effect of gender. Overall, this study suggests that work-related stress may be associated with biomarkers of inflammation, and that negative affectivity may influence the stress process affecting the exposure to psychosocial stressors.

Mevalonate Pathway Blockade, Mitochondrial Dysfunction and Autophagy: A Possible Link. - Tricarico, Paola Maura; Crovella, Sergio; Celsi, Fulvio (Int J Mol Sci, 2015)
The mevalonate pathway, crucial for cholesterol synthesis, plays a key role in multiple cellular processes. Deregulation of this pathway is also correlated with diminished protein prenylation, an important post-translational modification necessary to localize certain proteins, such as small GTPases, to membranes. Mevalonate pathway blockade has been linked to mitochondrial dysfunction: especially involving lower mitochondrial membrane potential and increased release of pro-apoptotic factors in cytosol. Furthermore a severe reduction of protein prenylation has also been associated with defective autophagy, possibly causing inflammasome activation and subsequent cell death. So, it is tempting to hypothesize a mechanism in which defective autophagy fails to remove damaged mitochondria, resulting in increased cell death. This mechanism could play a significant role in Mevalonate Kinase Deficiency, an autoinflammatory disease characterized by a defect in Mevalonate Kinase, a key enzyme of the mevalonate pathway. Patients carrying mutations in the MVK gene, encoding this enzyme, show increased inflammation and lower protein prenylation levels. This review aims at analysing the correlation between mevalonate pathway defects, mitochondrial dysfunction and defective autophagy, as well as inflammation, using Mevalonate Kinase Deficiency as a model to clarify the current pathogenetic hypothesis as the basis of the disease.

Microglia activation and interaction with neuronal cells in a biochemical model of mevalonate kinase deficiency. - Tricarico, Paola Maura; Piscianz, Elisa; Monasta, Lorenzo; Kleiner, Giulio; Crovella, Sergio; Marcuzzi, Annalisa (Apoptosis, 2015)
Mevalonate kinase deficiency is a rare disease whose worst manifestation, characterised by severe neurologic impairment, is called mevalonic aciduria. The progressive neuronal loss associated to cell death can be studied in vitro with a simplified model based on a biochemical block of the mevalonate pathway and a subsequent inflammatory trigger. The aim of this study was to evaluate the effect of the mevalonate blocking on glial cells (BV-2) and the following effects on neuronal cells (SH-SY5Y) when the two populations were cultured together. To better understand the cross-talk between glial and neuronal cells, as it happens in vivo, BV-2 and SH-SY5Y were co-cultured in different experimental settings (alone, transwell, direct contact); the effect of mevalonate pathway biochemical block by Lovastatin, followed by LPS inflammatory trigger, were evaluated by analysing programmed cell death and mitochondrial membrane potential, cytokines' release and cells' morphology modifications. In this experimental condition, glial cells underwent an evident activation, confirmed by elevated pro-inflammatory cytokines release, typical of these disorders, and a modification in morphology. Moreover, the activation induced an increase in apoptosis. When glial cells were co-cultured with neurons, their activation caused an increase of programmed cell death also in neuronal cells, but only if the two populations were cultured in direct contact. Our findings, being aware of the limitations related to the cell models used, represent a preliminary step towards understanding the pathological and neuroinflammatory mechanisms occurring in mevalonate kinase diseases. Contact co-culture between neuronal and microglial cells seems to be a good model to study mevalonic aciduria in vitro, and to contribute to the identification of potential drugs able to block microglial activation for this orphan disease. In fact, in such a pathological condition, we demonstrated that microglial cells are activated and contribute to neuronal cell death. We can thus hypothesise that the use of microglial activation blockers could prevent this additional neuronal death.

Modulation of genetic associations with serum urate levels by body-mass-index in humans. - Huffman, Jennifer E; Albrecht, Eva; Teumer, Alexander; Mangino, Massimo; Kapur, Karen; Johnson, Toby; Kutalik, Zoltán; Pirastu, Nicola; Pistis, Giorgio; Lopez, Lorna M; Haller, Toomas; Salo, Perttu; et al. (PLoS One, 2015)
We tested for interactions between body mass index (BMI) and common genetic variants affecting serum urate levels, genome-wide, in up to 42569 participants. Both stratified genome-wide association (GWAS) analyses, in lean, overweight and obese individuals, and regression-type analyses in a non BMI-stratified overall sample were performed. The former did not uncover any novel locus with a major main effect, but supported modulation of effects for some known and potentially new urate loci. The latter highlighted a SNP at RBFOX3 reaching genome-wide significant level (effect size 0.014, 95% CI 0.008-0.02, Pinter= 2.6 x 10-8). Two top loci in interaction term analyses, RBFOX3 and ERO1LB-EDARADD, also displayed suggestive differences in main effect size between the lean and obese strata. All top ranking loci for urate effect differences between BMI categories were novel and most had small magnitude but opposite direction effects between strata. They include the locus RBMS1-TANK (men, Pdifflean-overweight= 4.7 x 10-8), a region that has been associated with several obesity related traits, and TSPYL5 (men, Pdifflean-overweight= 9.1 x 10-8), regulating adipocytes-produced estradiol. The top-ranking known urate loci was ABCG2, the strongest known gout risk locus, with an effect halved in obese compared to lean men (Pdifflean-obese= 2 x 10-4). Finally, pathway analysis suggested a role for N-glycan biosynthesis as a prominent urate-associated pathway in the lean stratum. These results illustrate a potentially powerful way to monitor changes occurring in obesogenic environment.

More than (Double) Bubble. - Ferrara, Giovanna; Stampalija, Tamara; Codrich, Daniela; Simionato, Cristina; Taddio, Andrea; Travan, Laura (J Pediatr, 2015)
Keywords: Amniotic Fluid; Duodenum; Female; Humans; Infant; Infant, Newborn; Polyhydramnios; Pregnancy; Pregnancy Trimester, Third; Prenatal Diagnosis; Ultrasonography, Prenatal

Multicohort analysis of the maternal age effect on recombination. - Martin, Hilary C; Christ, Ryan; Hussin, Julie G; O'Connell, Jared; Gordon, Scott; Mbarek, Hamdi; Hottenga, Jouke-Jan; McAloney, Kerrie; Willemsen, Gonnecke; Gasparini, Paolo; Pirastu, Nicola; Montgomery, Grant W; et al. (Nat Commun, 2015)
Several studies have reported that the number of crossovers increases with maternal age in humans, but others have found the opposite. Resolving the true effect has implications for understanding the maternal age effect on aneuploidies. Here, we revisit this question in the largest sample to date using single nucleotide polymorphism (SNP)-chip data, comprising over 6,000 meioses from nine cohorts. We develop and fit a hierarchical model to allow for differences between cohorts and between mothers. We estimate that over 10 years, the expected number of maternal crossovers increases by 2.1% (95% credible interval (0.98%, 3.3%)). Our results are not consistent with the larger positive and negative effects previously reported in smaller cohorts. We see heterogeneity between cohorts that is likely due to chance effects in smaller samples, or possibly to confounders, emphasizing that care should be taken when interpreting results from any specific cohort about the effect of maternal age on recombination.

Music Training Increases Phonological Awareness and Reading Skills in Developmental Dyslexia: A Randomized Control Trial. - Flaugnacco, Elena; Lopez, Luisa; Terribili, Chiara; Montico, Marcella; Zoia, Stefania; Schön, Daniele (PLoS One, 2015)
There is some evidence for a role of music training in boosting phonological awareness, word segmentation, working memory, as well as reading abilities in children with typical development. Poor performance in tasks requiring temporal processing, rhythm perception and sensorimotor synchronization seems to be a crucial factor underlying dyslexia in children. Interestingly, children with dyslexia show deficits in temporal processing, both in language and in music. Within this framework, we test the hypothesis that music training, by improving temporal processing and rhythm abilities, improves phonological awareness and reading skills in children with dyslexia. The study is a prospective, multicenter, open randomized controlled trial, consisting of test, rehabilitation and re-test (ID NCT02316873). After rehabilitation, the music group (N = 24) performed better than the control group (N = 22) in tasks assessing rhythmic abilities, phonological awareness and reading skills. This is the first randomized control trial testing the effect of music training in enhancing phonological and reading abilities in children with dyslexia. The findings show that music training can modify reading and phonological abilities even when these skills are severely impaired. Through the enhancement of temporal processing and rhythmic skills, music might become an important tool in both remediation and early intervention programs.Trial Registration: ClinicalTrials.gov NCT02316873

Nasal irrigation with saline solution significantly improves oxygen saturation in infants with bronchiolitis. - Schreiber, Silvana; Ronfani, Luca; Ghirardo, Sergio; Minen, Federico; Taddio, Andrea; Jaber, Mohamad; Rizzello, Elisa; Barbi, Egidio (Acta Paediatr, 2015)
AIM: Published guidelines do not recommend nasal irrigation in bronchiolitis, but it is common practice in Italy, despite a lack of data on its benefits or adverse effects. This single-blind, multicentre, randomised controlled trial compared nasal irrigation using either isotonic 0.9% sodium chloride or hypertonic 3% sodium chloride with simple supportive care in infants with bronchiolitis. METHOD: We randomly assigned 133 Infants up one year of age, who were admitted to the emergency department with bronchiolitis and an oxygen saturation (SpO2) of between 88-94%, to the isotonic (n=47), hypertonic (n=44) or standard care (n=42) groups. Variations in SpO2 and the wheeze, air exchange, respiratory rate, muscle use (WARM) respiratory distress score were recorded at zero, five, 15, 20 and 50 minutes. RESULTS: Five minutes after the intervention, the median SpO2 value (95%) in the isotonic group was higher than both the hypertonic (94%) and the standard care (93%) groups. The differences between the isotonic and standard treatment groups were statistically significant at each time point, while the hypertonic group only reached significantly higher values after 50 minutes. However, the WARM score did not improve. CONCLUSION: A single nasal irrigation with saline solution significantly improved oxygen saturation in infants with bronchiolitis. This article is protected by copyright. All rights reserved.

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

Next-generation sequencing and its initial applications for molecular diagnosis of systemic auto-inflammatory diseases. - Rusmini, Marta; Federici, Silvia; Caroli, Francesco; Grossi, Alice; Baldi, Maurizia; Obici, Laura; Insalaco, Antonella; Tommasini, Alberto; Caorsi, Roberta; Gallo, Eleonora; Olivieri, Alma Nunzia; Marzano, AngeloValerio; et al. (Ann Rheum Dis, 2015)
OBJECTIVES: Systemic auto-inflammatory disorders (SAIDs) are a heterogeneous group of monogenic diseases sharing a primary dysfunction of the innate immune system. More than 50% of patients with SAID does not show any mutation at gene(s) tested because of lack of precise clinical classification criteria and/or incomplete gene screening. To improve the molecular diagnosis and genotype interpretation of SAIDs, we undertook the development of a next-generation sequencing (NGS)-based protocol designed to simultaneous screening of 10 genes. METHODS: Fifty patients with SAID, already genotyped for the respective causative gene(s), were massively sequenced for the coding portions of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12, NOD2, PSTPIP1, IL1RN, LPIN2 and PSMB8. Three different bioinformatic pipelines (Ion Reporter, CLC Bio Genomics Workbench, GATK-based in-house workflow) were compared. RESULTS: Once resulting variants were compared with the expected mutation list, no workflow turned out to be able to detect all the 79 variants known in the 50 DNAs. Additional variants were also detected, validated by Sanger sequencing and compared to assess true and false positive detection rates of the three workflows. Finally, the overall clinical picture of 34 patients was re-evaluated in the light of the new mutations found. CONCLUSIONS: The present gene panel has resulted suitable for molecular diagnosis of SAIDs. Moreover, genotype-phenotype correlation has confirmed that the interpretation of NGS data in patients with an undefined inflammatory phenotype is remarkably difficult, thus supporting the need of evidence-based and validated clinical criteria to be used concurrently with the genetic analysis for the final diagnosis and classification of patients with SAIDs.

NLRP1 and NLRP3 polymorphisms in mesothelioma patients and asbestos exposed individuals a population-based autopsy study from North East Italy. - Borelli, Violetta; Moura, Ronal R; Trevisan, Elisa; Crovella, Sergio (Infect Agent Cancer, 2015)
NRLP1 (rs12150220, rs9889625, rs9900356, rs6502867, rs2670660) and NLRP3 (rs35829419, rs10754558) polymorphisms have been analyzed in 69 subjects with documented asbestos exposure and death for malignant pleural mesothelioma and 59 patients with documented asbestos exposure but death for other causes, all from a North East Italy. No association was found between NLRP1 and NLRP3 polymorphisms and susceptibility to develop mesothelioma using the general, dominant or recessive models. Also haplotype analysis did not reveal any significant association with mesothelioma. Our findings, being controversial with respect to another study on Italian patients, do suggest the need of further studies to unravel the contribution of NLRP1 and NLRP3 in susceptibility to mesothelioma.

Normal saline flushes performed once daily maintain peripheral intravenous catheter patency: a randomised controlled trial. - Schreiber, Silvana; Zanchi, Chiara; Ronfani, Luca; Delise, Anna; Corbelli, Alessandra; Bortoluzzi, Rosamaria; Taddio, Andrea; Barbi, Egidio (Arch Dis Child, 2015)
OBJECTIVE: Recent evidence supports the use of normal saline flushes in place of heparin to maintain the patency of peripheral intravenous locks (IVLs); however, there are no data regarding the recommended flush frequency. STUDY DESIGN: This was an open, non-inferiority, randomised controlled trial. Children with IVLs, aged 1-17 years, were randomly assigned to receive saline flushing every 12 h (group A) or every 24 h (group B). The main outcome was the maintenance of catheter patency. RESULTS: Four hundred patients were randomised; 198 subjects were analysed in the 12 h group and 199 in the 24 h group (three patients were lost at follow-up). Occlusion occurred in 15 children (7.6%) in group A versus 9 (4.5%) in group B (p=0.21). The difference in catheter patency was +3.1% in favour of the 24 h group (95% CI -1.6% to 7.7%), showing the non-inferiority of the 24 h procedure (the non-inferiority margin was set at -4%). Catheter-related complications were not different between the two groups (12.1% in group A vs 9.5% in group B; p=0.42). CONCLUSIONS: A flushing procedure with one flush per day allows maintenance of catheter patency without an increase in catheter-related complications. We propose a simplification of the flushing procedure with only one flush per day, thereby reducing costs (materials use and nursing time), labour and unnecessary manipulation of the catheters which can cause distress in younger children and their parents. TRIAL REGISTRATION NUMBER: The study is registered in the international database ClinicalTrial.gov under registration number NCT02221024.
Keywords: Adolescent; Catheterization, Peripheral; Catheters, Indwelling; Child; Child, Preschool; Equipment Failure; Female; Humans; Infant; Male; Outcome Assessment (Health Care); Risk Assessment; Sodium Chloride; Therapeutic Irrigation

The novel dual PI3K/mTOR inhibitor NVP-BGT226 displays cytotoxic activity in both normoxic and hypoxic hepatocarcinoma cells. - Simioni, Carolina; Cani, Alice; Martelli, Alberto M; Zauli, Giorgio; Alameen, Ayman A M; Ultimo, Simona; Tabellini, Giovanna; McCubrey, James A; Capitani, Silvano; Neri, Luca M (Oncotarget, 2015)
Hepatocellular carcinoma (HCC) is one of the most common lethal human malignancies worldwide and its advanced status is frequently resistant to conventional chemotherapeutic agents and radiation. We evaluated the cytotoxic effect of the orally bioavailable dual PI3K/mTOR inhibitor, NVP-BGT226, on a panel of HCC cell lines, since hyperactivated PI3K/Akt/mTOR signaling pathway could represent a biomolecular target for Small Inhibitor Molecules in this neoplasia. We analyzed the drug activity in both normoxia and hypoxia conditions, the latter playing often a relevant role in the induction of chemoresistance and angiogenesis.In normoxia NVP-BGT226 caused cell cycle arrest in the G0/G1 phase of the cell cycle, induced apoptosis and autophagy at low concentrations. Interestingly the drug inactivated p-Akt and p-S6 at < 10 nM concentration.In hypoxia NVP-BGT226 maintained its cytotoxic efficacy at the same concentration as documented by MTT assays and Western blot analysis. Moreover, the drug showed in hypoxia inhibitory properties against angiogenesis by lowering the expression of the transcription factor HIF-1α and of VEGF.Our results indicate that NVP-BGT226 has a potent cytotoxic effect on HCC cell lines also in hypoxia condition, thus emerging as a potential candidate for cancer treatment in HCC targeted therapy.

Is "option B+" also being adopted in pregnant women in high-income countries? Temporal trends from a national study in Italy. - Floridia, Marco; Guaraldi, Giovanni; Ravizza, Marina; Tibaldi, Cecilia; Pinnetti, Carmela; Maccabruni, Anna; Molinari, Atim; Liuzzi, Giuseppina; Alberico, Salvatore; Meloni, Alessandra; Rizzi, Laura; Dalzero, Serena; et al. (Clin Infect Dis, 2015)
Keywords: Anti-Retroviral Agents; Antiretroviral Therapy, Highly Active; Developed Countries; Female; HIV Infections; Humans; Infant, Newborn; Italy; Patient Acceptance of Health Care; Pregnancy; Pregnancy Complications, Infectious

Orofacial granulomatosis in children: think about Crohn's disease. - Lazzerini, Marzia; Martelossi, Stefano; Cont, Gabriele; Bersanini, Chiara; Ventura, Giovanna; Fontana, Massimo; Zuin, Giovanna; Ventura, Alessandro; Taddio, Andrea (Dig Liver Dis, 2015)
BACKGROUND: The term orofacial granulomatosis is conventionally used to describe patients with granulomatous lesions affecting the orofacial tissues, in absence of intestinal lesions. Lip swelling and facial swelling are the most common clinical signs. Despite the fact that histologically it is not distinguishable from Crohn's disease, and that both diseases have a chronic/recurrent course, the relationship between orofacial granulomatosis and Crohn's disease is still debated. METHODS: Herein we present five cases of orofacial granulomatosis. RESULTS: All patients presented concomitant Crohn's disease, supporting the hypothesis that orofacial granulomatosis and Crohn's disease may be one single disease. Thalidomide was effective in inducing remission of oral and intestinal symptoms in all five cases and could be considered a valid treatment opportunity for these patients. CONCLUSIONS: Orofacial granulomatosis and Crohn's disease may be part of the same disease; both may respond to thalidomide.
Keywords: Adolescent; Biopsy; Child; Colonoscopy; Crohn Disease; Diagnosis, Differential; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Thalidomide

Pain activates a defined area of the somatosensory and motor cortex in newborn infants. - Bembich, Stefano; Brovedani, Pierpaolo; Cont, Gabriele; Travan, Laura; Grassi, Veronica; Demarini, Sergio (Acta Paediatr, 2015)

Patients' Induced Pluripotent Stem Cells to Model Drug Induced Adverse Events: A Role in Predicting Thiopurine Induced Pancreatitis? - Stocco, Gabriele; Lanzi, Gaetana; Yue, Fengming; Giliani, Silvia; Sasaki, Katsunori; Tommasini, Alberto; Pelin, Marco; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana (Curr Drug Metab, 2015)
Induced pluripotent stem cells (iPSC) can be produced from adult cells by transfecting them with a definite set of pluripotency-associated genes. Under adequate growth conditions and stimulation iPSC can differentiate to almost every somatic lineage in the body. Patients' derived iPSC are an innovative model to study mechanisms of adverse drug reactions in individual patients and in cell types that cannot be easily obtained from human subjects. Proof-of concept studies with known toxicants have been performed for liver, cardiovascular and central nervous system cells: neurons obtained from iPSC have been used to elucidate the mechanism of chemotherapy-induced peripheral neuropathy by evaluating the effects of neurotoxic drugs such as vincristine. However, no study has been performed yet on pancreatic tissue and drug induced pancreatitis. Thiopurines (azathioprine and mercaptopurine) are immunosuppressive antimetabolite drugs, commonly used to treat Crohn's disease. About 5% of Crohn's disease patients treated with thiopurines develop pancreatitis, a severe idiosyncratic adverse event; these patients have to stop thiopurine administration and may require medical treatment, with significant personal and social costs. Molecular mechanism of thiopurine induced pancreatitis (TIP) is currently unknown and no fully validated biomarker is available to assist clinicians in preventing this adverse event. Hence, in this review we have reflected upon the probable research applications of exocrine pancreatic cells generated from patient specific iPS cells. Such pancreatic cells can provide excellent insights into the molecular mechanism of TIP. In particular three hypotheses on the mechanism of TIP could be explored: drug biotransformation, innate immunity and adaptative immunity.

Polyclonal gammopathy after BKV infection in HSCT recipient: a novel trigger for plasma cells replication? - Maximova, Natalia; Pizzol, Antonio; Sonzogni, Aurelio; Gregori, Massimo; Granzotto, Marilena; Tamaro, Paolo (Virol J, 2015)
BACKGROUND: BK polyomavirus infects most of the general population. However, its clinical manifestations are almost exclusively seen in immunocompromised patients, particularly in kidney and hematopoietic stem cell transplantation recipients. CASE PRESENTATION: A 15-y-old female suffering from common B-cell acute lymphoblastic leukaemia underwent hematopoietic stem cell transplantation. The patient had reactivation of BKPyV infection and developed an haemorrhagic cystitis. Three months after transplant, BKPyV viremia and viruria increased and she developed a severe nephropathy associated to a polyclonal gammopathy with high levels of isolated IgM. CONCLUSION: This case report describes a rare and unexpected polyclonal gammopathy developed during a polyomavirus-associated nephropathy confirmed by immunohistochemical and laboratory analyses.

PRE- AND POSTNATAL MODIFICATIONS IN PARENTAL MENTAL REPRESENTATIONS IN THREE CASES OF FETAL GASTROSCHISIS DIAGNOSED DURING PREGNANCY. - Tripani, Antonella; Pellizzoni, Sandra; Giuliani, Rosella; Bembich, Stefano; Clarici, Andrea; Lonciari, Isabella; Ammaniti, Massimo (Infant Ment Health J, 2015)
The aim of this study was to identify possible effects of gastroschisis on parents' intrapsychic dynamics by applying an observational clinical approach. More specifically, we intend to (a) evaluate the representational style of parents informed about the diagnosis of fetal gastroschisis during pregnancy using the Interview of Maternal Representations During Pregnancy and the Interview of Paternal Representations During Pregnancy (M. Ammaniti, C. Candelori, M. Pola, & R. Tambelli, ) and (b) observe whether the baby's birth influences the parents' representational styles through the application of the same tools (the Interview of Maternal Representations After the Birth, M. Ammaniti & R. Tambelli, , and the Interview of Paternal Representations After the Birth, M. Ammaniti & R. Tambelli, ), adapted to the postnatal period. During the prenatal period, all parents showed a restricted/disinvested style. Three parents-one mother and two fathers-changed their styles from restricted/disinvested to integrated between pregnancy and Month 6 after the birth of their child. Clinical data from the interviews and observations are discussed in an attempt at better defining intrapsychic dynamics of parents after a diagnosis of gastroschisis.

R705H mutation of MYH9 is associated with MYH9-related disease and not only with non-syndromic deafness DFNA17. - Verver, E; Pecci, A; De Rocco, D; Ryhänen, S; Barozzi, S; Kunst, H; Topsakal, V; Savoia, A (Clin Genet, 2015)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant disease caused by mutation of MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (NMMHC-IIA). MYH9-RD patients have macrothrombocytopenia and granulocyte inclusions (pathognomonic sign of the disease) containing wild-type and mutant NMMHC-IIA. During life they might develop sensorineural hearing loss, cataract, glomerulonephritis, and elevation of liver enzymes. One of the MYH9 mutations, p.R705H, was previously reported to be associated with DFNA17, an autosomal dominant non-syndromic sensorineural hearing loss without any other features associated. We identified the same mutation in two unrelated families, whose four affected individuals had not only hearing impairment but also thrombocytopenia, giant platelets, leukocyte inclusions, as well as mild to moderate elevation of some liver enzymes. Our data suggest that DFNA17 should not be a separate genetic entity but part of the wide phenotypic spectrum of MYH9-RD characterized by congenital hematological manifestations and variable penetrance and expressivity of the extra-hematological features.

Rare coding variants and X-linked loci associated with age at menarche. - Lunetta, Kathryn L; Day, Felix R; Sulem, Patrick; Ruth, Katherine S; Tung, Joyce Y; Hinds, David A; Esko, Tõnu; Elks, Cathy E; Altmaier, Elisabeth; He, Chunyan; Huffman, Jennifer E; Mihailov, Evelin; et al. (Nat Commun, 2015)
More than 100 loci have been identified for age at menarche by genome-wide association studies; however, collectively these explain only ∼3% of the trait variance. Here we test two overlooked sources of variation in 192,974 European ancestry women: low-frequency protein-coding variants and X-chromosome variants. Five missense/nonsense variants (in ALMS1/LAMB2/TNRC6A/TACR3/PRKAG1) are associated with age at menarche (minor allele frequencies 0.08-4.6%; effect sizes 0.08-1.25 years per allele; P<5 × 10(-8)). In addition, we identify common X-chromosome loci at IGSF1 (rs762080, P=9.4 × 10(-13)) and FAAH2 (rs5914101, P=4.9 × 10(-10)). Highlighted genes implicate cellular energy homeostasis, post-transcriptional gene silencing and fatty-acid amide signalling. A frequently reported mutation in TACR3 for idiopathic hypogonatrophic hypogonadism (p.W275X) is associated with 1.25-year-later menarche (P=2.8 × 10(-11)), illustrating the utility of population studies to estimate the penetrance of reportedly pathogenic mutations. Collectively, these novel variants explain ∼0.5% variance, indicating that these overlooked sources of variation do not substantially explain the 'missing heritability' of this complex trait.

Relapse and metastasis of atypical teratoid/rhabdoid tumor in a boy with neurofibromatosis type 1 treated with recombinant human growth hormone. - Tornese, Gianluca; Faleschini, Elena; Matarazzo, Lorenza; Bibalo, Cristina; Zanazzo, Giulio Andrea; Rabusin, Marco; Tonini, Giorgio; Zennaro, Floriana; Ventura, Alessandro (Neuropediatrics, 2015)
Even though no increased recurrence rate seems to be reported in patients with brain tumors receiving recombinant human growth hormone (rhGH) replacement, in some patients multiple risk factors could put at higher risk for recurrence. In such cases, the decision to start rhGH therapy should be very cautious. A boy with neurofibromatosis type 1 developed an atypical teratoid/rhabdoid tumor (AT/RT) of right cerebellum, treated with surgery, radiotherapy, and chemotherapy. After 3 years of remission, he started rhGH for growth hormone deficiency, having a negative magnetic resonance imaging (MRI) scan. Ten weeks after starting therapy, the boy became symptomatic and MRI showed relapse of AT/RT in the right cerebellum and a new lesion in the brainstem. The boy died of progressive disease. In this case, the connection between AT/RT recurrence and the beginning of rhGH therapy, with a negative pretreatment MRI, cannot be excluded. Additional caution should be used for rhGH in patients with multiple risk factors.
Keywords: Brain Stem Neoplasms; Cerebellar Neoplasms; Child; Human Growth Hormone; Humans; Magnetic Resonance Imaging; Male; Neurofibromatosis 1; Recombinant Proteins; Recurrence; Rhabdoid Tumor; Risk Factors; Teratoma

RelB activation in anti-inflammatory decidual endothelial cells: a master plan to avoid pregnancy failure? - Masat, Elisa; Gasparini, Chiara; Agostinis, Chiara; Bossi, Fleur; Radillo, Oriano; De Seta, Francesco; Tamassia, Nicola; Cassatella, Marco A; Bulla, Roberta (Sci Rep, 2015)
It is known that excessive inflammation at fetal-maternal interface is a key contributor in a compromised pregnancy. Female genital tract is constantly in contact with microorganisms and several strategies must be adopted to avoid pregnancy failure. Decidual endothelial cells (DECs) lining decidual microvascular vessels are the first cells that interact with pro-inflammatory stimuli released into the environment by microorganisms derived from gestational tissues or systemic circulation. Here, we show that DECs are hypo-responsive to LPS stimulation in terms of IL-6, CXCL8 and CCL2 production. Our results demonstrate that DECs express low levels of TLR4 and are characterized by a strong constitutive activation of the non-canonical NF-κB pathway and a low responsiveness of the canonical pathway to LPS. In conclusion, DECs show a unique hypo-responsive phenotype to the pro-inflammatory stimulus LPS in order to control the inflammatory response at feto-maternal interface.

Relevance of random biopsy at the transformation zone when colposcopy is negative. - Wiesenfeld, Uri; Mangino, Francesco Paolo; Toffoletti, Franco Giovanni; Ricci, Giuseppe (Obstet Gynecol, 2015)
Keywords: Cervical Intraepithelial Neoplasia; Colposcopy; Early Detection of Cancer; Female; Humans; Papillomavirus Infections; Precancerous Conditions; Uterine Cervical Neoplasms

Risk-adjusted operative delivery rates and maternal-neonatal outcomes as measures of quality assessment in obstetric care: a multicenter prospective study. - Maso, Gianpaolo; Monasta, Lorenzo; Piccoli, Monica; Ronfani, Luca; Montico, Marcella; De Seta, Francesco; Parolin, Sara; Businelli, Caterina; Travan, Laura; Alberico, Salvatore (BMC Pregnancy Childbirth, 2015)
BACKGROUND: Although the evaluation of caesarean delivery rates has been suggested as one of the most important indicators of quality in obstetrics, it has been criticized because of its controversial ability to capture maternal and neonatal outcomes. In an "ideal" process of labor and delivery auditing, both caesarean (CD) and assisted vaginal delivery (AVD) rates should be considered because both of them may be associated with an increased risk of complications. The aim of our study was to evaluate maternal and neonatal outcomes according to the outlier status for case-mix adjusted CD and AVD rates in the same obstetric population. METHODS: Standardized data on 15,189 deliveries from 11 centers were prospectively collected. Multiple logistic regression was used to estimate the risk-adjusted probability of a woman in each center having an AVD or a CD. Centers were classified as "above", "below", or "within" the expected rates by considering the observed-to-expected rates and the 95% confidence interval around the ratio. Adjusted maternal and neonatal outcomes were compared among the three groupings. RESULTS: Centers classified as "above" or "below" the expected CD rates had, in both cases, higher adjusted incidence of composite maternal (2.97%, 4.69%, 3.90% for "within", "above" and "below", respectively; p = 0.000) and neonatal complications (3.85%, 9.66%, 6.29% for "within", "above" and "below", respectively; p = 0.000) than centers "within" CD expected rates. Centers with AVD rates above and below the expected showed poorer and better composite maternal (3.96%, 4.61%, 2.97% for "within", "above" and "below", respectively; p = 0.000) and neonatal (6.52%, 9.77%, 3.52% for "within", "above" and "below", respectively; p = 0.000) outcomes respectively than centers with "within" AVD rates. CONCLUSIONS: Both risk-adjusted CD and AVD delivery rates should be considered to assess the level of obstetric care. In this context, both higher and lower-than-expected rates of CD and "above" AVD rates are significantly associated with increased risk of complications, whereas the "below" status for AVD showed a "protective" effect on maternal and neonatal outcomes.

Role of oxidative stress mediated by glutathione-s-transferase in thiopurines' toxic effects. - Pelin, Marco; De Iudicibus, Sara; Fusco, Laura; Taboga, Eleonora; Pellizzari, Giulia; Lagatolla, Cristina; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Chem Res Toxicol, 2015)
Azathioprine (AZA), 6-mercaptopurine (6-MP), and 6-thioguanine (6-TG) are antimetabolite drugs, widely used as immunosuppressants and anticancer agents. Despite their proven efficacy, a high incidence of toxic effects in patients during standard-dose therapy is recorded. The aim of this study is to explain, from a mechanistic point of view, the clinical evidence showing a significant role of glutathione-S-transferase (GST)-M1 genotype on AZA toxicity in inflammatory bowel disease patients. To this aim, the human nontumor IHH and HCEC cell lines were chosen as predictive models of the hepatic and intestinal tissues, respectively. AZA, but not 6-MP and 6-TG, induced a concentration-dependent superoxide anion production that seemed dependent on GSH depletion. N-Acetylcysteine reduced the AZA antiproliferative effect in both cell lines, and GST-M1 overexpression increased both superoxide anion production and cytotoxicity, especially in transfected HCEC cells. In this study, an in vitro model to study thiopurines' metabolism has been set up and helped us to demonstrate, for the first time, a clear role of GST-M1 in modulating AZA cytotoxicity, with a close dependency on superoxide anion production. These results provide the molecular basis to shed light on the clinical evidence suggesting a role of GST-M1 genotype in influencing the toxic effects of AZA treatment.

Sensorineural hearing loss in very low birth weight infants with histological chorioamnionitis. - Vedovato, Stefania; Lo Iacono, Angela; Morando, Carla; Suppiej, Agnese; Orzan, Eva; Trevisanuto, Daniele; Visentin, Silvia; Cavallin, Francesco; Chiarelli, Silvia; Zanardo, Vincenzo (J Matern Fetal Neonatal Med, 2015)
OBJECTIVE: Histological chorioamnionitis (HCAM) has been associated with inflammatory diseases of preterm infants. Recently we have observed that it increased the risk of speech delay and hearing loss. So the aim of this study was to evaluate the relationship between sensorineural hearing loss (SNHL) of VLBW infants and HCAM. METHODS: We performed an observational study on VLBW infants admitted to the NICU of Padua. Each patient with HCAM was matched with one control without HCAM. All infants underwent hearing screening before discharge by means of automated transient-evoked otoacustic emissions and automated auditory brainstem responses, which were repeated at 3 and 6 months of age with tympanometry measurement. Incidence of SNHL at 6 months of age was compared in the 2 groups and risk factors for hearing loss were studied. RESULTS: Two of 77 (2.6%) newborns with HCAM e 6/73 (8.2%) without it presented SNHL at 6 months of corrected age (p = 0.16). Multivariable logistic regression analysis identified surgical ligation of patent ductus arteriosus (PDA) as independent predictors of SNHL (OR: 5.75, 95% CI 1.34-24.84, p = 0.02), whereas the effect of HCAM on SNHL was only near to statistical significance level. CONCLUSIONS: Surgical ligation of PDA is associated with an increased risk of SNHL in VLBW infants, regardless of HCAM.

Serum TRAIL levels increase shortly after insulin therapy and metabolic stabilization in children with type 1 diabetes mellitus. - Tornese, Gianluca; Tisato, Veronica; Monasta, Lorenzo; Vecchi Brumatti, Liza; Zauli, Giorgio; Secchiero, Paola (Acta Diabetol, 2015)

Short Communication FYB polymorphisms in Brazilian patients with type I diabetes mellitus and autoimmune polyglandular syndrome type III. - Addobbati, C J C; de Azevêdo Silva, J; Tavares, N A C; Araujo, J; Guimarães, R L; Brandão, L; Crovella, S; Sandrin-Garcia, P (Genet Mol Res, 2015)
The aim of this study was to perform an association study between seven Fyn-binding protein gene (FYB)-tag single nucleotide polymorphisms (SNPs) and type I diabetes mellitus (T1DM), as well as with disease age of onset. We also assessed the role of FYB SNPs in the insurgence of autoimmune polyglandular syndrome type III (APSIII), characterized by the simultaneous presence of autoimmune thyroid disease and celiac disease, in patients with T1DM from a Northeastern Brazilian population. One hundred and seventy-seven patients with T1DM and 190 healthy individuals were genotyped for seven tag SNPs, covering most of the FYB locus, using real-time polymerase chain reaction amplification. There was no significant difference in the distribution of allele and genotype frequencies among patients and healthy individuals. Moreover, none of the tag SNPs were associated either to T1DM age of onset or to the insurgence of APSIII. However, since the FYB protein is a key component in T cell response, its gene variants might play a role in protein function, which might be testable in a population with different genetic backgrounds or by using functional assays.

Sirolimus Therapy in Congenital Hyperinsulinism: A Successful Experience Beyond Infancy. - Minute, Marta; Patti, Giuseppa; Tornese, Gianluca; Faleschini, Elena; Zuiani, Chiara; Ventura, Alessandro (Pediatrics, 2015)
Congenital hyperinsulinism (CHI) due to diffuse involvement of the pancreas is a challenging and severe illness in children. Its treatment is based on chronic therapy with diazoxide and/or octreotide, followed by partial pancreatectomy, which is often not resolutive. Sirolimus, a mammalian target of rapamycin inhibitor, was reported to be effective in treating CHI in infants. We report here the case of an 8-year-old boy affected by a severe form of CHI due to a biallelic heterozygous ABCC8 mutation who responded to sirolimus with a dramatic improvement in his glucose blood level regulation and quality of life, with no serious adverse events after 6 months of follow-up. To the best of our knowledge, this is the first report of a successful intervention in an older child. It provides a promising basis for further studies comparing sirolimus with other treatments, particularly in older children.

Targeted tumor imaging of anti-CD20-polymeric nanoparticles developed for the diagnosis of B-cell malignancies. - Capolla, Sara; Garrovo, Chiara; Zorzet, Sonia; Lorenzon, Andrea; Rampazzo, Enrico; Spretz, Ruben; Pozzato, Gabriele; Núñez, Luis; Tripodo, Claudio; Macor, Paolo; Biffi, Stefania (Int J Nanomedicine, 2015)
The expectations of nanoparticle (NP)-based targeted drug delivery systems in cancer, when compared with convectional therapeutic methods, are greater efficacy and reduced drug side effects due to specific cellular-level interactions. However, there are conflicting literature reports on enhanced tumor accumulation of targeted NPs, which is essential for translating their applications as improved drug-delivery systems and contrast agents in cancer imaging. In this study, we characterized biodegradable NPs conjugated with an anti-CD20 antibody for in vivo imaging and drug delivery onto tumor cells. NPs' binding specificity mediated by anti-CD20 antibody was evaluated on MEC1 cells and chronic lymphocytic leukemia patients' cells. The whole-body distribution of untargeted NPs and anti-CD20 NPs were compared by time-domain optical imaging in a localized human/mouse model of B-cell malignancy. These studies provided evidence that NPs' functionalization by an anti-CD20 antibody improves tumor pharmacokinetic profiles in vivo after systemic administration and increases in vivo imaging of tumor mass compared to non-targeted NPs. Together, drug delivery and imaging probe represents a promising theranostics tool for targeting B-cell malignancies.

Three cases of Bartonella quintana infection in children. - Magnolato, Andrea; Pederiva, Federica; Spagnut, Giulia; Maschio, Massimo; Ventura, Alessandro; Taddio, Andrea (Pediatr Infect Dis J, 2015)
We present 3 children affected by B. quintana infection treated at the IRCCS Burlo Garofolo of Trieste between March and April 2013. B. quintana infection is rare but it should be suspected in patients with fever and lymphadenopathy who do not respond to conventional antibiotic treatment. All patients had a complete recovery without sequelae or relapses.

To Extinguish the Fire from Outside the Cell or to Shutdown the Gas Valve Inside? Novel Trends in Anti-Inflammatory Therapies. - Marcuzzi, Annalisa; Piscianz, Elisa; Valencic, Erica; Monasta, Lorenzo; Vecchi Brumatti, Liza; Tommasini, Alberto (Int J Mol Sci, 2015)
Cytokines are the most important soluble mediators of inflammation. Rare pediatric diseases provided exemplar conditions to study the anti-inflammatory efficacy of new generation therapies (biologics/biopharmaceuticals) selectively targeting single cytokines. Monoclonal antibodies and recombinant proteins have revolutionized anti-inflammatory therapies in the last two decades, allowing the specific targeting of single cytokines. They are very effective in extinguishing inflammation from outside the cell, even with the risk of an excessive and prolonged immunosuppression. Small molecules can enter the cell and shutdown the valve of inflammation by directly targeting signal proteins involved in cytokine release or in response to cytokines. They are orally-administrable drugs whose dosage can be easily adjusted to obtain the desired anti-inflammatory effect. This could make these drugs more suitable for a wide range of diseases as stroke, gout, or neurological impairment, where inflammatory activation plays a pivotal role as trigger. Autoinflammatory diseases, which have previously put anti-cytokine proteins in the limelight, can again provide a valuable model to measure the real potential of small inhibitors as anti-inflammatory agents.

Trace samples of human blood in mosquitoes as a forensic investigation tool. - Rabelo, K C N; Albuquerque, C M R; Tavares, V B; Santos, S M; Souza, C A; Oliveira, T C; Oliveira, N C L; Crovella, S (Genet Mol Res, 2015)
Investigations of any type of crime invariably starts at the crime scene by collecting evidence. Thus, the purpose of this research was to collect and analyze an entomological trace from an environment that is similar to those of indoor crime scenes. Hematophagous mosquitoes were collected from two residential units; saliva of volunteers that were residents in the units was also collected for genetic analysis as reference samples. We examined the allele frequencies of 15 short tandem repeat loci (D8S1179, D21S11, D7S820, CSF1PO, D3S1358, TH01, D13S317, D16S539, D2S1338, D19S433, vWA, TPOX, D18S51, D5S818, and FGA) and amelogenin. A total of 26 female hematophagous mosquitoes were identified as Aedes aegypti, Aedes albopictus, and Culex quinquefasciatus; we were able to obtain 11 forensically valid genetic profiles, with a minimum of 0.028203 ng/μL of human DNA. Thus, the results of this study showed that it was possible to correlate human genetic information from mosquitoes with the volunteer reference samples, which validates the use of this information as forensic evidence. Furthermore, we observed mixed genetic profiles from one mosquito. Therefore, it is clearly important to collect these insects indoors where crimes were committed, because it may be possible to find intact genetic profiles of suspects in the blood found in the digestive tract of hematophagous mosquitoes for later comparison to identify an offender and/or exclude suspects.

Triple Akt inhibition as a new therapeutic strategy in T-cell acute lymphoblastic leukemia. - Cani, Alice; Simioni, Carolina; Martelli, Alberto M; Zauli, Giorgio; Tabellini, Giovanna; Ultimo, Simona; McCubrey, James A; Capitani, Silvano; Neri, Luca M (Oncotarget, 2015)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive neoplastic disorder in which chemotherapy resistance and refractory relapses occur, with a poorer prognostic outcome.Constitutively active PI3K/Akt/mTOR pathway is a common feature of T-ALL upregulating cell proliferation, survival and drug resistance. This pathway is currently under clinical trials with small molecules inhibitors (SMI).To verify whether a multi-inhibition treatment against Akt protein could enhance the efficacy of individual drug administration and overcome drug resistance as well as to obtain a decrease in single drug concentration, we tested on T-ALL cell lines the effects of combined treatments with three Akt inhibitors with different mode of action, GSK690693, MK-2206 and Perifosine.In cells with hyperactivated Akt, combined administration of the drugs displayed a significant synergistic and cytotoxic effect and affected PI3K/Akt/mTOR pathway at much lower concentration than single drug use. Highest synergistic effect for full inhibition of Akt was also related to the timing of every drug administration. Furthermore the triple treatment had greater efficacy in inducing cell cycle arrest in G0/G1 phase and both apoptosis and autophagy.Targeting Akt as a key protein of PI3K/Akt/mTOR pathway with multiple drugs might represent a new and promising pharmacological strategy for treatment of T-ALL patients.

Tumor necrosis factor (TNF) alpha and interleukin (IL) 18 genes polymorphisms are correlated with susceptibility to HPV infection in patients with and without cervical intraepithelial lesion. - Tavares, Mayara C Mansur; de Lima Júnior, Sérgio F; Coelho, Antonio V C; Marques, Trícia Ruschelle N M; de Araújo, Diêgo Henrique T; Heráclio, Sandra de A; Amorim, Melânia M Ramos; de Souza, Paulo Roberto E; Crovella, Sergio (Ann Hum Biol, 2015)
BACKGROUND: The Human Papillomavirus (HPV) predisposes 500 000 women to cervical cancer. Host genetic background may facilitate virus persistence in the uterine cervix. Polymorphisms in regulatory and coding regions of cytokine genes have been associated with susceptibility to some human diseases. AIM: This study aims at investigating whether TNFA -308 G/A and IL18 -137 G/C and -607 C/A polymorphisms are associated with susceptibility to HPV infection/progression to high-grade squamous intraepithelial lesion (HSIL). SUBJECTS AND METHODS: One hundred and twenty-two HPV infected and 132 HPV negative women (the latter used as healthy controls) were analysed. TNFA -308 G/A and IL18 (-137G/C and -607 C/A) polymorphisms were analysed using specific sequence polymorphism PCR (SSP-PCR). Univariate statistical analysis and a logistic regression were performed. RESULTS: The TNFA -308A allele was associated with susceptibility to HPV infection (p = 0.0008), while the IL18 -607A allele conferred protection against HPV infection (p = 0.0043). TNFA -308 G/A and IL18 (-137G/C and -607 C/A) polymorphisms were not associated with development of cervical lesions (p > 0.05). An association was also observed between smoking and susceptibility to the development of HSIL. CONCLUSION: The findings suggest an association between two TNFA SNPs and susceptibility to HPV infection in women from Northeast Brazil. The results need to be functionally validated and replicated in other populations with different ethnic backgrounds.

Two‑gene mutation in a single patient: Biochemical and functional analysis for a correct interpretation of exome results. - Bianco, Anna Monica; Faletra, Flavio; Vozzi, Diego; Girardelli, Martina; Knowles, Alessandra; Tommasini, Alberto; Zauli, Giorgio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Next-generation sequencing (NGS) has generated a large amount of sequence data with the requirement of frequent critical revisions of reported mutations. This innovative tool has proved to be effective in detecting pathogenic mutations; however, it requires a certain degree of experience to identify incidental findings. In the present study, whole exome sequencing analysis was performed for the molecular diagnosis and correct genotype/phenotype correlation between parents and a patient presenting with an atypical phenotype. In addition, mevalonic acid quantification and frequency analysis of detected variants in public databases and X‑chromosome inactivation (XCI) studies on the patient's mother were performed. V377I as well as the S135L mutations were identified on the mevalonate kinase deficiency gene and the levels of mevalonic acid in the patient were 5,496 µg/ml. A D59G variation, reported in ESP6500 in two healthy individuals, was found on the Martin Probst syndrome gene (RAB40AL). Based on XCI studies on the patient's mother, it is likely that RAB40AL escapes XCI, while still remaining balanced. In conclusion, the results of the present study indicated that the Martin Probst syndrome is an X‑linked condition, which is probably not caused by RAB40AL mutations. Although NGS is a powerful tool to identify pathogenic mutations, the analysis of genetic data requires expert critical revision of all detected variants.

Ultrastructural Morphology of Sperm from Human Globozoospermia. - Ricci, Giuseppe; Andolfi, Laura; Zabucchi, Giuliano; Luppi, Stefania; Boscolo, Rita; Martinelli, Monica; Zweyer, Marina; Trevisan, Elisa (Biomed Res Int, 2015)
Globozoospermia is a rare disorder characterized by the presence of sperm with round head, lacking acrosome. Coiling tail around the nucleus has been reported since early human studies, but no specific significance has conferred it. By contrast, studies on animal models suggest that coiling tail around the nucleus could represent a crucial step of defective spermatogenesis, resulting in round-headed sperm. No observations, so far, support the transfer of this hypothesis to human globozoospermia. The purpose of this work was to compare ultrastructural morphology of human and mouse model globozoospermic sperm. Sperm have been investigated by using scanning and transmission electron microscopy. The images that we obtained show significant similarities to those described in GOPC knockout mice, an animal model of globozoospermia. By using this model as reference, we were able to identify the probable steps of the tail coiling process in human globozoospermia. Although we have no evidence that there is the same pathophysiology in man and knocked-out mouse, the similarities between these ultrastructural observations in human and those in the experimental model are very suggestive. This is the first demonstration of the existence of relevant morphological homologies between the tail coiling in animal model and human globozoospermia.

Wharton's jelly derived mesenchymal stromal cells: Biological properties, induction of neuronal phenotype and current applications in neurodegeneration research. - Frausin, Stefano; Viventi, Serena; Verga Falzacappa, Lucia; Quattromani, Miriana Jlenia; Leanza, Giampiero; Tommasini, Alberto; Valencic, Erica (Acta Histochem, 2015)
Multipotent mesenchymal stromal cells, also known as mesenchymal stem cells (MSC), can be isolated from bone marrow or other tissues, including fat, muscle and umbilical cord. It has been shown that MSC behave in vitro as stem cells: they self-renew and are able to differentiate into mature cells typical of several mesenchymal tissues. Moreover, the differentiation toward non-mesenchymal cell lineages (e.g. neurons) has been reported as well. The clinical relevance of these cells is mainly related to their ability to spontaneously migrate to the site of inflammation/damage, to their safety profile thanks to their low immunogenicity and to their immunomodulation capacities. To date, MSCs isolated from the post-natal bone marrow have represented the most extensively studied population of adult MSCs, in view of their possible use in various therapeutical applications. However, the bone marrow-derived MSCs exhibit a series of limitations, mainly related to their problematic isolation, culturing and use. In recent years, umbilical cord (UC) matrix (i.e. Wharton's jelly, WJ) stromal cells have therefore emerged as a more suitable alternative source of MSCs, thanks to their primitive nature and the easy isolation without relevant ethical concerns. This review seeks to provide an overview of the main biological properties of WJ-derived MSCs. Moreover, the potential application of these cells for the treatment of some known dysfunctions in the central and peripheral nervous system will also be discussed.

When Feeding Difficulties Are due to Genetics: The Case of Familial Partial 9q Duplication. - Travan, Laura; Rocca, Maria Santa; Buonomo, Francesca; Cleva, Lisa; Pecile, Vanna; De Cunto, Angela (J Investig Med High Impact Case Rep, 2015)
Chromosomal abnormalities may cause growth failure before or since birth. 9q duplication is reported as a cause of intrauterine growth restriction, mild dysmporphism, and intellectual disabilities. We report a case of a maternally inherited 9q21.31q21.33 duplication causing prenatal and postnatal growth restriction with feeding refusal and mild facial dysmorphisms, prenatally diagnosed by single-nucleotide polymorphism array analysis. Hypothesis of the possible pathogenic mechanisms are discussed.

Analysis of 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. - Noris, Patrizia; Schlegel, Nicole; Klersy, Catherine; Heller, Paula G; Civaschi, Elisa; Pujol-Moix, Núria; Fabris, Fabrizio; Favier, Rémi; Gresele, Paolo; Latger-Cannard, Véronique; Cuker, Adam; Nurden, Paquita; et al. (Haematologica, 2014)
Pregnancy in women with inherited thrombocytopenias is a major matter of concern as both the mothers and the newborns are potentially at risk of bleeding. However, medical management of this condition cannot be based on evidence because of the lack of consistent information in the literature. To advance knowledge on this matter, we performed a multicentric, retrospective study evaluating 339 pregnancies in 181 women with 13 different forms of inherited thrombocytopenia. Neither the degree of thrombocytopenia nor the severity of bleeding tendency worsened during pregnancy and the course of pregnancy did not differ from that of healthy subjects in terms of miscarriages, fetal bleeding and pre-term births. The degree of thrombocytopenia in the babies was similar to that in the mother. Only 7 of 156 affected newborns had delivery-related bleeding, but 2 of them died of cerebral hemorrhage. The frequency of delivery-related maternal bleeding ranged from 6.8% to 14.2% depending on the definition of abnormal blood loss, suggesting that the risk of abnormal blood loss was increased with respect to the general population. However, no mother died or had to undergo hysterectomy to arrest bleeding. The search for parameters predicting delivery-related bleeding in the mother suggested that hemorrhages requiring blood transfusion were more frequent in women with history of severe bleedings before pregnancy and with platelet count at delivery below 50 × 10(9)/L.
Keywords: Adult; Female; Humans; Infant, Newborn; Pregnancy; Pregnancy Complications, Hematologic; Retrospective Studies; Thrombocytopenia; Young Adult

Association analysis of bitter receptor genes in five isolated populations identifies a significant correlation between TAS2R43 variants and coffee liking. - Pirastu, Nicola; Kooyman, Maarten; Traglia, Michela; Robino, Antonietta; Willems, Sara M; Pistis, Giorgio; d'Adamo, Pio; Amin, Najaf; D'Eustacchio, Angela; Navarini, Luciano; Sala, Cinzia; Karssen, Lennart C; et al. (PLoS One, 2014)
Coffee, one of the most popular beverages in the world, contains many different physiologically active compounds with a potential impact on people's health. Despite the recent attention given to the genetic basis of its consumption, very little has been done in understanding genes influencing coffee preference among different individuals. Given its markedly bitter taste, we decided to verify if bitter receptor genes (TAS2Rs) variants affect coffee liking. In this light, 4066 people from different parts of Europe and Central Asia filled in a field questionnaire on coffee liking. They have been consequently recruited and included in the study. Eighty-eight SNPs covering the 25 TAS2R genes were selected from the available imputed ones and used to run association analysis for coffee liking. A significant association was detected with three SNP: one synonymous and two functional variants (W35S and H212R) on the TAS2R43 gene. Both variants have been shown to greatly reduce in vitro protein activity. Surprisingly the wild type allele, which corresponds to the functional form of the protein, is associated to higher liking of coffee. Since the hTAS2R43 receptor is sensible to caffeine, we verified if the detected variants produced differences in caffeine bitter perception on a subsample of people coming from the FVG cohort. We found a significant association between differences in caffeine perception and the H212R variant but not with the W35S, which suggests that the effect of the TAS2R43 gene on coffee liking is mediated by caffeine and in particular by the H212R variant. No other significant association was found with other TAS2R genes. In conclusion, the present study opens new perspectives in the understanding of coffee liking. Further studies are needed to clarify the role of the TAS2R43 gene in coffee hedonics and to identify which other genes and pathways are involved in its genetics.
Keywords: Coffee; Genetic Association Studies; Humans; Polymorphism, Single Nucleotide; Receptors, G-Protein-Coupled; Taste

Block of the mevalonate pathway triggers oxidative and inflammatory molecular mechanisms modulated by exogenous isoprenoid compounds. - Tricarico, Paola Maura; Kleiner, Giulio; Valencic, Erica; Campisciano, Giuseppina; Girardelli, Martina; Crovella, Sergio; Knowles, Alessandra; Marcuzzi, Annalisa (Int J Mol Sci, 2014)
Deregulation of the mevalonate pathway is known to be involved in a number of diseases that exhibit a systemic inflammatory phenotype and often neurological involvements, as seen in patients suffering from a rare disease called mevalonate kinase deficiency (MKD). One of the molecular mechanisms underlying this pathology could depend on the shortage of isoprenoid compounds and the subsequent mitochondrial damage, leading to oxidative stress and pro-inflammatory cytokines' release. Moreover, it has been demonstrated that cellular death results from the balance between apoptosis and pyroptosis, both driven by mitochondrial damage and the molecular platform inflammasome. In order to rescue the deregulated pathway and decrease inflammatory markers, exogenous isoprenoid compounds were administered to a biochemical model of MKD obtained treating a murine monocytic cell line with a compound able to block the mevalonate pathway, plus an inflammatory stimulus. Our results show that isoprenoids acted in different ways, mainly increasing the expression of the evaluated markers [apoptosis, mitochondrial dysfunction, nucleotide-binding oligomerization-domain protein-like receptors 3 (NALP3), cytokines and nitric oxide (NO)]. Our findings confirm the hypothesis that inflammation is triggered, at least partially, by the shortage of isoprenoids. Moreover, although further studies are necessary, the achieved results suggest a possible role for exogenous isoprenoids in the treatment of MKD.
Keywords: Animals; Apoptosis; Carotenoids; Carrier Proteins; Cell Line; Cytokines; Diterpenes; Humans; Mevalonate Kinase Deficiency; Mevalonic Acid; Mice; Mitochondria; Nitric Oxide; Phytol; Terpenes

C1q as a unique player in angiogenesis with therapeutic implication in wound healing. - Bossi, Fleur; Tripodo, Claudio; Rizzi, Lucia; Bulla, Roberta; Agostinis, Chiara; Guarnotta, Carla; Munaut, Carine; Baldassarre, Gustavo; Papa, Giovanni; Zorzet, Sonia; Ghebrehiwet, Berhane; Ling, Guang Sheng; et al. (Proc Natl Acad Sci U S A, 2014)
We have previously shown that C1q is expressed on endothelial cells (ECs) of newly formed decidual tissue. Here we demonstrate that C1q is deposited in wound-healing skin in the absence of C4 and C3 and that C1q mRNA is locally expressed as revealed by real-time PCR and in situ hybridization. C1q was found to induce permeability of the EC monolayer, to stimulate EC proliferation and migration, and to promote tube formation and sprouting of new vessels in a rat aortic ring assay. Using a murine model of wound healing we observed that vessel formation was defective in C1qa(-/-) mice and was restored to normal after local application of C1q. The mean vessel density of wound-healing tissue and the healed wound area were significantly increased in C1q-treated rats. On the basis of these results we suggest that C1q may represent a valuable therapeutic agent that can be used to treat chronic ulcers or other pathological conditions in which angiogenesis is impaired, such as myocardial ischemia.
Keywords: Animals; Cell Proliferation; Complement C1q; DNA Primers; Endothelial Cells; Enzyme-Linked Immunosorbent Assay; Human Umbilical Vein Endothelial Cells; Humans; Immunoblotting; Immunohistochemistry; In Situ Hybridization; Mice; Mice, Inbred C57BL; Mice, Knockout; Neovascularization, Physiologic; Rats; Rats, Wistar; Real-Time Polymerase Chain Reaction; Wound Healing

Can body mass index accurately predict adiposity in newborns? - De Cunto, Angela; Paviotti, Giulia; Ronfani, Luca; Travan, Laura; Bua, Jenny; Cont, Gabriele; Demarini, Sergio (Arch Dis Child Fetal Neonatal Ed, 2014)
Body mass index (BMI) is correlated with body fatness and risk of related diseases in children and adults. Proportionality indexes such as BMI and ponderal index (PI) have been suggested as complementary measures in neonatal growth assessment. Yet, they are still not used in neonates and their correlation with fatness is unknown. The aim of the study was to test the hypothesis that BMI z-score would predict neonatal adiposity. Body composition measurements (ie, fat mass, fat-free mass) by air displacement plethysmography (PEA POD, LMI, Concord-USA), weight and length were obtained in 200 infants ≥36 weeks' gestational age (GA) at birth. Linear regression analysis showed a direct association between BMI z-score and %fat mass (r(2)=0.43, p<0.0001). This association was confirmed independently from sex, GA and maternal prepregnancy BMI. BMI z-score predicted adiposity better than PI. However, both BMI z-score and PI were poor predictors of adiposity at birth.
Keywords: Adiposity; Adult; Anthropometry; Body Composition; Body Mass Index; Cross-Sectional Studies; Female; Gestational Age; Humans; Infant, Newborn; Male; Mothers; Plethysmography; Predictive Value of Tests; Regression Analysis; Reproducibility of Results; Sex Factors

Childhood high-risk acute lymphoblastic leukemia in first remission: results after chemotherapy or transplant from the AIEOP ALL 2000 study. - Conter, Valentino; Valsecchi, Maria Grazia; Parasole, Rosanna; Putti, Maria Caterina; Locatelli, Franco; Barisone, Elena; Lo Nigro, Luca; Santoro, Nicola; Aricò, Maurizio; Ziino, Ottavio; Pession, Andrea; Testi, Anna Maria; et al. (Blood, 2014)
The outcome of high-risk (HR) acute lymphoblastic leukemia patients enrolled in the AIEOP-BFM ALL 2000 study in Italy is described. HR criteria were minimal residual disease (MRD) levels ≥10(-3) at day 78 (MRD-HR), no complete remission (CR) at day 33, t(4;11) translocation, and prednisone poor response (PPR). Treatment (2 years) included protocol I, 3 polychemotherapy blocks, delayed intensification (protocol IIx2 or IIIx3), cranial radiotherapy, and maintenance. A total of 312 HR patients had a 5-year event-free survival (EFS) of 58.9% (standard error [SE] = 2.8) and an overall survival of 68.9% (SE = 2.6). In hierarchical order, EFS was 45.9% (4.4) in 132 MRD-HR patients, 41.2% (11.9) in 17 patients with no CR at day 33, 36.4% (14.5) in 11 patients with t(4;11), and 74.0% (3.6) in 152 HR patients only for PPR. No statistically significant difference was found for disease-free survival in patients with very HR features [MRD-HR, no CR at day 33, t(4;11) translocation], given hematopoietic stem cell transplantation (HSCT) (n = 66) or chemotherapy only (n = 88), after adjusting for waiting time to HSCT (5.7 months). Patients at HR only for PPR have a favorable outcome. MRD-HR is associated with poor outcome despite intensive treatment and/or HSCT and may qualify for innovative therapies. The study was registered at www.clinicaltrials.gov as #NCT00613457.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Combined Modality Therapy; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Neoplasm, Residual; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Radiotherapy; Remission Induction; Treatment Outcome

Class IV laser therapy as treatment for chemotherapy-induced oral mucositis in onco-haematological paediatric patients: a prospective study. - Chermetz, Maddalena; Gobbo, Margherita; Ronfani, Luca; Ottaviani, Giulia; Zanazzo, Giulio A; Verzegnassi, Federico; Treister, Nathaniel S; Di Lenarda, Roberto; Biasotto, Matteo; Zacchigna, Serena (Int J Paediatr Dent, 2014)
BACKGROUND: Oral mucositis is a debilitating side effect of chemotherapy. Laser therapy has recently demonstrated efficacy in the management of oral mucositis (OM). AIM: This prospective study was conducted to evaluate the efficacy of class IV laser therapy in patients affected by OM. DESIGN: Eighteen onco-haematological paediatric patients receiving chemotherapy and/or haematopoietic stem cell transplantation, prior to total body irradiation, affected by OM, were enrolled in this study. Patients were treated with class IV laser therapy for four consecutive days; the assessment of OM was performed through WHO Oral Mucositis Grading Objective Scale, and pain was evaluated through visual analogue scale. Patients completed a validated questionnaire, and photographs of lesions were taken during each session. Patients were re-evaluated 11 days after the first day of laser therapy. RESULTS: All patients demonstrated improvement in pain sensation, and all mucositis was fully resolved at the 11-day follow-up visit, with no apparent side effects. Laser therapy was well tolerated with remarkable reduction in pain associated with oral mucositis after 1-2 days of laser therapy. CONCLUSIONS: Given class IV laser therapy appears to be safe, non-invasive, and potentially effective, prospective, randomized, controlled trials are necessary to further assess efficacy and to determine optimal treatment parameters.

Clinical features and follow-up in patients with 22q11.2 deletion syndrome. - Cancrini, Caterina; Puliafito, Pamela; Digilio, Maria Cristina; Soresina, Annarosa; Martino, Silvana; Rondelli, Roberto; Consolini, Rita; Ruga, Ezia Maria; Cardinale, Fabio; Finocchi, Andrea; Romiti, Maria Luisa; Martire, Baldassarre; et al. (J Pediatr, 2014)
OBJECTIVE: To investigate the clinical manifestations at diagnosis and during follow-up in patients with 22q11.2 deletion syndrome to better define the natural history of the disease. STUDY DESIGN: A retrospective and prospective multicenter study was conducted with 228 patients in the context of the Italian Network for Primary Immunodeficiencies. Clinical diagnosis was confirmed by cytogenetic or molecular analysis. RESULTS: The cohort consisted of 112 males and 116 females; median age at diagnosis was 4 months (range 0 to 36 years 10 months). The diagnosis was made before 2 years of age in 71% of patients, predominantly related to the presence of heart anomalies and neonatal hypocalcemia. In patients diagnosed after 2 years of age, clinical features such as speech and language impairment, developmental delay, minor cardiac defects, recurrent infections, and facial features were the main elements leading to diagnosis. During follow-up (available for 172 patients), the frequency of autoimmune manifestations (P = .015) and speech disorders (P = .002) increased. After a median follow-up of 43 months, the survival probability was 0.92 at 15 years from diagnosis. CONCLUSIONS: Our data show a delay in the diagnosis of 22q11.2 deletion syndrome with noncardiac symptoms. This study provides guidelines for pediatricians and specialists for early identification of cases that can be confirmed by genetic testing, which would permit the provision of appropriate clinical management.
Keywords: Abnormalities, Multiple; Adolescent; Adult; Age Factors; Child; Child, Preschool; Chromosomes, Human, Pair 22; Delayed Diagnosis; Developmental Disabilities; DiGeorge Syndrome; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; Genetic Testing; Humans; Infant; Infant, Newborn; Male; Monitoring, Physiologic; Prospective Studies; Retrospective Studies; Risk Assessment; Severity of Illness Index; Sex Factors; Time Factors; Young Adult

Clinical significance of hyper-IgA in a paediatric laboratory series. - Copetti, Valentina; Pastore, Serena; De Pieri, Carlo; Radillo, Oriano; Taddio, Andrea; Ventura, Alessandro; Tommasini, Alberto (Arch Dis Child, 2014)
The causes of extremely elevated IgA, whether isolated or associated with an increase in other classes of immunoglobulin, are poorly defined in paediatrics. We reviewed the diagnostic significance of very high IgA levels (greater than 3 SD above the mean for age) in a cohort of patients referred to a tertiary care children's hospital. Hyper-IgA was found in 91 of 6364 subjects (1.4%) and in 68 cases was not associated with an increased IgG and/or IgM level. Most subjects with hyper-IgA (73.5%) had a severe immune defect, a chronic rheumatic disease or inflammatory bowel disease, while these conditions were very rare in a control group with normal IgA values (8%). Although our results may in part reflect the experience of a tertiary care centre, we suggest that hyper-IgA in children should always arouse suspicion of a serious disease.
Keywords: Adolescent; Child; Child, Preschool; Female; Hospitals, Pediatric; Humans; Hypergammaglobulinemia; Immunoglobulin A; Infant; Italy; Male; Tertiary Care Centers

Common variants in UMOD associate with urinary uromodulin levels: a meta-analysis. - Olden, Matthias; Corre, Tanguy; Hayward, Caroline; Toniolo, Daniela; Ulivi, Sheila; Gasparini, Paolo; Pistis, Giorgio; Hwang, Shih-Jen; Bergmann, Sven; Campbell, Harry; Cocca, Massimiliano; Gandin, Ilaria; et al. (J Am Soc Nephrol, 2014)
Uromodulin is expressed exclusively in the thick ascending limb and is the most abundant protein excreted in normal urine. Variants in UMOD, which encodes uromodulin, are associated with renal function, and urinary uromodulin levels may be a biomarker for kidney disease. However, the genetic factors regulating uromodulin excretion are unknown. We conducted a meta-analysis of urinary uromodulin levels to identify associated common genetic variants in the general population. We included 10,884 individuals of European descent from three genetic isolates and three urban cohorts. Each study measured uromodulin indexed to creatinine and conducted linear regression analysis of approximately 2.5 million single nucleotide polymorphisms using an additive model. We also tested whether variants in genes expressed in the thick ascending limb associate with uromodulin levels. rs12917707, located near UMOD and previously associated with renal function and CKD, had the strongest association with urinary uromodulin levels (P<0.001). In all cohorts, carriers of a G allele of this variant had higher uromodulin levels than noncarriers did (geometric means 10.24, 14.05, and 17.67 μg/g creatinine for zero, one, or two copies of the G allele). rs12446492 in the adjacent gene PDILT (protein disulfide isomerase-like, testis expressed) also reached genome-wide significance (P<0.001). Regarding genes expressed in the thick ascending limb, variants in KCNJ1, SORL1, and CAB39 associated with urinary uromodulin levels. These data indicate that common variants in the UMOD promoter region may influence urinary uromodulin levels. They also provide insights into uromodulin biology and the association of UMOD variants with renal function.
Keywords: Creatinine; European Continental Ancestry Group; Genetic Variation; Humans; Polymorphism, Single Nucleotide; Uromodulin

A comparison of three scales for measuring pain in children with cognitive impairment. - Massaro, Marta; Ronfani, Luca; Ferrara, Giovanna; Badina, Laura; Giorgi, Rita; D'Osualdo, Flavio; Taddio, Andrea; Barbi, Egidio (Acta Paediatr, 2014)
AIM: Pain is a neglected problem in children with cognitive impairments, and few studies compare the clinical use of specific pain scales. We compared the Non-Communicating Children's Pain Checklist Postoperative Version (NCCPC-PV), the Echelle Douleur Enfant San Salvador (DESS) and the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS). The first two were developed for children with cognitive impairment, and the third is a more general pain scale. METHODS: Two external observers and the child's caregiver assessed 40 children with cognitive impairment for pain levels. We assessed inter-rater agreement, correlation, dependence on knowledge of the child's behaviour, simplicity and adequacy in pain rating according to the caregiver for all three scales. RESULTS: The correlation between the NCCPC-PV and the DESS was strong (Spearman correlation coefficient = 0.76) and better than between each scale and the CHEOPS. Although the DESS showed better inter-rater agreement, it was more dependent on familiarity with the child and was judged more difficult to use by all observers. The NCCPC-PV was the easiest use and the most appropriate for rating the child's pain. CONCLUSION: The NCCPC-PV was the easiest to use for pain assessment in cognitively impaired children and should be adopted in clinical settings.

Curcumin and inflammatory bowel disease: potential and limits of innovative treatments. - Vecchi Brumatti, Liza; Marcuzzi, Annalisa; Tricarico, Paola Maura; Zanin, Valentina; Girardelli, Martina; Bianco, Anna Monica (Molecules, 2014)
Curcumin belongs to the family of natural compounds collectively called curcuminoids and it possesses remarkable beneficial anti-oxidant, anti-inflammatory, anti-cancer, and neuroprotective properties. Moreover it is commonly assumed that curcumin has also been suggested as a remedy for digestive diseases such as inflammatory bowel diseases (IBD), a chronic immune disorder affecting the gastrointestinal tract and that can be divided in two major subgroups: Crohn's disease (CD) and Ulcerative Colitis (UC), depending mainly on the intestine tract affected by the inflammatory events. The chronic and intermittent nature of IBD imposes, where applicable, long-term treatments conducted in most of the cases combining different types of drugs. In more severe cases and where there has been no good response to the drugs, a surgery therapy is carried out. Currently, IBD-pharmacological treatments are generally not curative and often present serious side effects; for this reason, being known the relationship between nutrition and IBD, it is worthy of interesting the study and the development of new dietary strategy. The curcumin principal mechanism is the suppression of IBD inflammatory compounds (NF-κB) modulating immune response. This review summarizes literature data of curcumin as anti-inflammatory and anti-oxidant in IBD, trying to understand the different effects in CD e UC.
Keywords: Animals; Anti-Inflammatory Agents, Non-Steroidal; Chemistry, Pharmaceutical; Clinical Trials as Topic; Curcumin; Humans; Inflammatory Bowel Diseases; Molecular Targeted Therapy; Nanotechnology; Treatment Outcome

DC-SIGN polymorphisms are associated to type 1 diabetes mellitus. - da Silva, Ronaldo Celerino; Cunha Tavares, Nathália de Alencar; Moura, Ronald; Coelho, Antônio; Guimarães, Rafael Lima; Araújo, Jacqueline; Crovella, Sergio; Brandão, Lucas André Cavalcanti; Silva, Jaqueline de Azevêdo (Immunobiology, 2014)
Type I diabetes mellitus (T1DM) is an autoimmune disorder featured by raised glucoses levels. It has been hypothesised that raised glucose levels in T1DM might be recognised as PAMPs, leading to immune response by overloading the cell receptors for pathogens recognition. DC-SIGN is a transmembrane protein, present in dendritic cells (DC) and macrophages: it has an important role in inflammatory response and T cells activation. Notably, DC-SIGN activation and triggering of the immune response depend on the type of ligand, which may lead to a pro or anti-inflammatory pathway. In our association study, we analysed the SNPs rs4804803 (-336 A>G) and rs735239 (-871 A>G), both at DC-SIGN promoter region, in 210 T1DM patients and 157 healthy controls, also looking for a correlation with the age of onset of the disease. We found that the allele G and genotypes G/G and A/G of SNP-871 (rs735239), as well as the alleles G-G (rs735239-rs4804803) and genotypes combined AA-GG (rs735239-rs4804803) were associated with protection of T1DM development. We did not find association between these variations with the age of onset of the disease and the presence of other autoimmune disorders. Our results suggest that SNPs in DC-SIGN promoter region can be associated to protection for T1DM in the Northeast Brazilian population.
Keywords: Adolescent; Alleles; Case-Control Studies; Cell Adhesion Molecules; Child; Child, Preschool; Diabetes Mellitus, Type 1; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Infant; Infant, Newborn; Lectins, C-Type; Male; Odds Ratio; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface

DNA mismatch repair gene MSH6 implicated in determining age at natural menopause. - Perry, John R B; Hsu, Yi-Hsiang; Chasman, Daniel I; Johnson, Andrew D; Elks, Cathy; Albrecht, Eva; Andrulis, Irene L; Beesley, Jonathan; Berenson, Gerald S; Bergmann, Sven; Bojesen, Stig E; Bolla, Manjeet K; et al. (Hum Mol Genet, 2014)
The length of female reproductive lifespan is associated with multiple adverse outcomes, including breast cancer, cardiovascular disease and infertility. The biological processes that govern the timing of the beginning and end of reproductive life are not well understood. Genetic variants are known to contribute to ∼50% of the variation in both age at menarche and menopause, but to date the known genes explain <15% of the genetic component. We have used genome-wide association in a bivariate meta-analysis of both traits to identify genes involved in determining reproductive lifespan. We observed significant genetic correlation between the two traits using genome-wide complex trait analysis. However, we found no robust statistical evidence for individual variants with an effect on both traits. A novel association with age at menopause was detected for a variant rs1800932 in the mismatch repair gene MSH6 (P = 1.9 × 10(-9)), which was also associated with altered expression levels of MSH6 mRNA in multiple tissues. This study contributes to the growing evidence that DNA repair processes play a key role in ovarian ageing and could be an important therapeutic target for infertility.
Keywords: Age Factors; DNA-Binding Proteins; Female; Genome-Wide Association Study; Humans; Menopause; Polymorphism, Single Nucleotide

Effects of estroprogestins containing natural estrogen on vaginal flora. - De Seta, Francesco; Restaino, Stefano; Banco, Rubina; Conversano, Ester; De Leo, Rossella; Tonon, Maddalena; Maso, Gianpaolo; Barbati, Giulia; Lello, Stefano (Gynecol Endocrinol, 2014)
Estroprogestins with "natural oestrogen" has represented a new option in terms of combined hormonal contraception. So, the aim of this study is to investigate how estroprogestins with natural estrogen may modify the vaginal niche. In literature, very few studies focused on the interaction between hormonal contraception and vaginal milieu. This is a prospective comparative study. We enrolled 60 women from January 2013 to September 2013, 30 of them were administered estradiol valerate dienogest (E2V+DNG - Klaira®) in a quadriphasic regimen, while the other 30 women were administered 17-β estradiol with nomestrol acetate (EV+NOMAC - Zoely®) in a monophasic regimen. After a baseline study of vaginal milieu at recruitment of patients (Gram stain with Nugent score, vaginal pH, vaginal wet mount for the quantification of leukocytes, Lactobacilli and/or presence of Candida), we performed the same follow-up after six months of estroprogestin therapy. Our results showed that the women treated with E2V+DNG had a trend of an improvement of vaginal health in terms of increase of lactobacillar flora and reduction of vaginal pH in place of women treated with EV+NOMAC that showed a reduction of cervical mucus. Finally, our data about the effects on vaginal flora exerted by two estroprogestin pills (EPs) containing a natural estrogen suggest slight, but interesting differences in terms of vaginal ecology. These differences could be related to the type of estrogen, type of progestin, regimen of administration and, after all, to the net balance between estrogenic and progestin component of the EPs.
Keywords: Adolescent; Adult; Drug Combinations; Estradiol; Female; Humans; Megestrol; Middle Aged; Nandrolone; Norpregnadienes; Prospective Studies; Vagina; Young Adult

Experience from a single paediatric transplant centre with identification of some protective and risk factors concerning the development of hepatic veno-occlusive disease in children after allogeneic hematopoietic stem cell transplant. - Maximova, N; Ferrara, G; Minute, M; Pizzol, A; Kiren, V; Montico, M; Gregori, M; Tamaro, P (Int J Hematol, 2014)
Hepatic veno-occlusive disease (VOD) is a frequent and severe complication of hematopoietic stem cell transplantation (HSCT) affecting 9.6-17.3 % of cases. 200 HSCT, performed between January 1995 and March 2013 in our Paediatric HSCT Centre in Trieste, were retrospectively analysed to evaluate the frequency of VOD and to identify the associated risk factors. The frequency of VOD according to the Seattle criteria was 17 %, within the range reported in literature. The mortality rate was 37.5 % (75 out of 200 transplantations) in the general population and 73.5 % (25 out of 34) in VOD patients (p < 0.05). Veno-occlusive disease significantly decreased from 38 % (1995-2000) to 8 % (2007-2013) p < 0.05. Univariate and multivariate analyses identified sepsis and pre-transplant ferritin levels above 1000 ng/ml as two significant risk factors for VOD, while the use of tacrolimus appeared to be associated with a lower VOD risk. Veno-occlusive disease still remains an important cause of transplant-related mortality even if it appears to have decreased over the last few years.
Keywords: Adolescent; Child; Child, Preschool; Female; Hematopoietic Stem Cell Transplantation; Hepatic Veno-Occlusive Disease; Humans; Infant; Infant, Newborn; Male; Mortality; Retrospective Studies; Risk Factors; Transplantation, Homologous; Young Adult

F402L variant in NLRP12 in subjects with undiagnosed periodic fevers and in healthy controls. - De Pieri, Carlo; Vuch, Josef; Athanasakis, Emmanouil; Severini, Giovanni Maria; Crovella, Sergio; Bianco, Anna Monica; Tommasini, Alberto (Clin Exp Rheumatol, 2014)
Keywords: Cryopyrin-Associated Periodic Syndromes; Female; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation

Fate of lymphocytes after withdrawal of tofacitinib treatment. - Piscianz, Elisa; Valencic, Erica; Cuzzoni, Eva; De Iudicibus, Sara; De Lorenzo, Elisa; Decorti, Giuliana; Tommasini, Alberto (PLoS One, 2014)
Tofacitinib (Tofa) is an inhibitor of Janus Kinase 3, developed for the treatment of autoimmune diseases and for the prevention of transplant rejection. Due to its selective action on proliferating cells, Tofa can offer a way to block T cell activation, without toxic effects on resting cells. However, few studies have investigated the effects of Tofa on lymphocyte activation in vitro. Our aim was to study the action of Tofa on different lymphocyte subsets after in vitro stimulation and to track the behaviour of treated cells after interruption of the treatment. Peripheral blood lymphocytes were stimulated in vitro with mitogen and treated with two concentrations of Tofa. After a first period in culture, cells were washed and further incubated for an additional time. Lymphocyte subsets, activation phenotype and proliferation were assessed at the different time frames. As expected, Tofa was able to reduce the activation and proliferation of lymphocytes in the first four days of treatment. In addition the drug led to a relative decrease of Natural Killer, B cells and CD8 T cells compared to CD4 T cells. However, treated cells were still viable after the first period in culture and begun to proliferate, strikingly, in a dose dependent manner when the drug was removed from the environment by replacing the culture medium. This novel data does not necessarily predict a similar behaviour in vivo, but can warn about the clinical use of this drug when a discontinuation of treatment with Tofa is considered for any reason.
Keywords: Antigens, CD; B-Lymphocytes; CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Drug Administration Schedule; Humans; Janus Kinase 3; Killer Cells, Natural; Lymphocyte Activation; Lymphocyte Count; Phytohemagglutinins; Piperidines; Primary Cell Culture; Protein Kinase Inhibitors; Pyrimidines; Pyrroles

A general approach for haplotype phasing across the full spectrum of relatedness. - O'Connell, Jared; Gurdasani, Deepti; Delaneau, Olivier; Pirastu, Nicola; Ulivi, Sheila; Cocca, Massimiliano; Traglia, Michela; Huang, Jie; Huffman, Jennifer E; Rudan, Igor; McQuillan, Ruth; Fraser, Ross M; et al. (PLoS Genet, 2014)
Many existing cohorts contain a range of relatedness between genotyped individuals, either by design or by chance. Haplotype estimation in such cohorts is a central step in many downstream analyses. Using genotypes from six cohorts from isolated populations and two cohorts from non-isolated populations, we have investigated the performance of different phasing methods designed for nominally 'unrelated' individuals. We find that SHAPEIT2 produces much lower switch error rates in all cohorts compared to other methods, including those designed specifically for isolated populations. In particular, when large amounts of IBD sharing is present, SHAPEIT2 infers close to perfect haplotypes. Based on these results we have developed a general strategy for phasing cohorts with any level of implicit or explicit relatedness between individuals. First SHAPEIT2 is run ignoring all explicit family information. We then apply a novel HMM method (duoHMM) to combine the SHAPEIT2 haplotypes with any family information to infer the inheritance pattern of each meiosis at all sites across each chromosome. This allows the correction of switch errors, detection of recombination events and genotyping errors. We show that the method detects numbers of recombination events that align very well with expectations based on genetic maps, and that it infers far fewer spurious recombination events than Merlin. The method can also detect genotyping errors and infer recombination events in otherwise uninformative families, such as trios and duos. The detected recombination events can be used in association scans for recombination phenotypes. The method provides a simple and unified approach to haplotype estimation, that will be of interest to researchers in the fields of human, animal and plant genetics.
Keywords: Chromosome Mapping; Cohort Effect; Family; Genotype; Haplotypes; Humans; Models, Genetic; Pedigree; Phenotype; Recombination, Genetic

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty. - Cousminer, Diana L; Stergiakouli, Evangelia; Berry, Diane J; Ang, Wei; Groen-Blokhuis, Maria M; Körner, Antje; Siitonen, Niina; Ntalla, Ioanna; Marinelli, Marcella; Perry, John R B; Kettunen, Johannes; Jansen, Rick; et al. (Hum Mol Genet, 2014)
Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first genome-wide significant locus for male sexual development upstream of myocardin-like 2 (MKL2) (P = 8.9 × 10(-9)), a menarche locus tagging a developmental pathway linking earlier puberty with reduced pubertal growth (P = 4.6 × 10(-5)) and short adult stature (p = 7.5 × 10(-6)) in both males and females. Furthermore, our results indicate that a proportion of menarche loci are important for pubertal initiation in both sexes. Consistent with epidemiological correlations between increased prepubertal body mass and earlier pubertal timing in girls, body mass index (BMI)-increasing alleles correlated with earlier breast development. In boys, some BMI-increasing alleles associated with earlier, and others with delayed, sexual development; these genetic results mimic the controversy in epidemiological studies, some of which show opposing correlations between prepubertal BMI and male puberty. Our results contribute to our understanding of the pubertal initiation program in both sexes and indicate that although mechanisms regulating pubertal onset in males and females may largely be shared, the relationship between body mass and pubertal timing in boys may be complex and requires further genetic studies.

Global, regional, and national incidence and mortality for HIV, tuberculosis, and malaria during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Murray, Christopher J L; Ortblad, Katrina F; Guinovart, Caterina; Lim, Stephen S; Wolock, Timothy M; Roberts, D Allen; Dansereau, Emily A; Graetz, Nicholas; Barber, Ryan M; Brown, Jonathan C; Wang, Haidong; Duber, Herbert C; et al. (Lancet, 2014)
BACKGROUND: The Millennium Declaration in 2000 brought special global attention to HIV, tuberculosis, and malaria through the formulation of Millennium Development Goal (MDG) 6. The Global Burden of Disease 2013 study provides a consistent and comprehensive approach to disease estimation for between 1990 and 2013, and an opportunity to assess whether accelerated progress has occured since the Millennium Declaration. METHODS: To estimate incidence and mortality for HIV, we used the UNAIDS Spectrum model appropriately modified based on a systematic review of available studies of mortality with and without antiretroviral therapy (ART). For concentrated epidemics, we calibrated Spectrum models to fit vital registration data corrected for misclassification of HIV deaths. In generalised epidemics, we minimised a loss function to select epidemic curves most consistent with prevalence data and demographic data for all-cause mortality. We analysed counterfactual scenarios for HIV to assess years of life saved through prevention of mother-to-child transmission (PMTCT) and ART. For tuberculosis, we analysed vital registration and verbal autopsy data to estimate mortality using cause of death ensemble modelling. We analysed data for corrected case-notifications, expert opinions on the case-detection rate, prevalence surveys, and estimated cause-specific mortality using Bayesian meta-regression to generate consistent trends in all parameters. We analysed malaria mortality and incidence using an updated cause of death database, a systematic analysis of verbal autopsy validation studies for malaria, and recent studies (2010-13) of incidence, drug resistance, and coverage of insecticide-treated bednets. FINDINGS: Globally in 2013, there were 1·8 million new HIV infections (95% uncertainty interval 1·7 million to 2·1 million), 29·2 million prevalent HIV cases (28·1 to 31·7), and 1·3 million HIV deaths (1·3 to 1·5). At the peak of the epidemic in 2005, HIV caused 1·7 million deaths (1·6 million to 1·9 million). Concentrated epidemics in Latin America and eastern Europe are substantially smaller than previously estimated. Through interventions including PMTCT and ART, 19·1 million life-years (16·6 million to 21·5 million) have been saved, 70·3% (65·4 to 76·1) in developing countries. From 2000 to 2011, the ratio of development assistance for health for HIV to years of life saved through intervention was US$4498 in developing countries. Including in HIV-positive individuals, all-form tuberculosis incidence was 7·5 million (7·4 million to 7·7 million), prevalence was 11·9 million (11·6 million to 12·2 million), and number of deaths was 1·4 million (1·3 million to 1·5 million) in 2013. In the same year and in only individuals who were HIV-negative, all-form tuberculosis incidence was 7·1 million (6·9 million to 7·3 million), prevalence was 11·2 million (10·8 million to 11·6 million), and number of deaths was 1·3 million (1·2 million to 1·4 million). Annualised rates of change (ARC) for incidence, prevalence, and death became negative after 2000. Tuberculosis in HIV-negative individuals disproportionately occurs in men and boys (versus women and girls); 64·0% of cases (63·6 to 64·3) and 64·7% of deaths (60·8 to 70·3). Globally, malaria cases and deaths grew rapidly from 1990 reaching a peak of 232 million cases (143 million to 387 million) in 2003 and 1·2 million deaths (1·1 million to 1·4 million) in 2004. Since 2004, child deaths from malaria in sub-Saharan Africa have decreased by 31·5% (15·7 to 44·1). Outside of Africa, malaria mortality has been steadily decreasing since 1990. INTERPRETATION: Our estimates of the number of people living with HIV are 18·7% smaller than UNAIDS's estimates in 2012. The number of people living with malaria is larger than estimated by WHO. The number of people living with HIV, tuberculosis, or malaria have all decreased since 2000. At the global level, upward trends for malaria and HIV deaths have been reversed and declines in tuberculosis deaths have accelerated. 101 countries (74 of which are developing) still have increasing HIV incidence. Substantial progress since the Millennium Declaration is an encouraging sign of the effect of global action. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Epidemics; Female; Global Health; HIV Infections; Humans; Incidence; Malaria; Male; Mortality; Organizational Objectives; Sex Distribution; Tuberculosis

Global, regional, and national levels and causes of maternal mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Kassebaum, Nicholas J; Bertozzi-Villa, Amelia; Coggeshall, Megan S; Shackelford, Katya A; Steiner, Caitlyn; Heuton, Kyle R; Gonzalez-Medina, Diego; Barber, Ryan; Huynh, Chantal; Dicker, Daniel; Templin, Tara; Wolock, Timothy M; et al. (Lancet, 2014)
BACKGROUND: The fifth Millennium Development Goal (MDG 5) established the goal of a 75% reduction in the maternal mortality ratio (MMR; number of maternal deaths per 100,000 livebirths) between 1990 and 2015. We aimed to measure levels and track trends in maternal mortality, the key causes contributing to maternal death, and timing of maternal death with respect to delivery. METHODS: We used robust statistical methods including the Cause of Death Ensemble model (CODEm) to analyse a database of data for 7065 site-years and estimate the number of maternal deaths from all causes in 188 countries between 1990 and 2013. We estimated the number of pregnancy-related deaths caused by HIV on the basis of a systematic review of the relative risk of dying during pregnancy for HIV-positive women compared with HIV-negative women. We also estimated the fraction of these deaths aggravated by pregnancy on the basis of a systematic review. To estimate the numbers of maternal deaths due to nine different causes, we identified 61 sources from a systematic review and 943 site-years of vital registration data. We also did a systematic review of reports about the timing of maternal death, identifying 142 sources to use in our analysis. We developed estimates for each country for 1990-2013 using Bayesian meta-regression. We estimated 95% uncertainty intervals (UIs) for all values. FINDINGS: 292,982 (95% UI 261,017-327,792) maternal deaths occurred in 2013, compared with 376,034 (343,483-407,574) in 1990. The global annual rate of change in the MMR was -0·3% (-1·1 to 0·6) from 1990 to 2003, and -2·7% (-3·9 to -1·5) from 2003 to 2013, with evidence of continued acceleration. MMRs reduced consistently in south, east, and southeast Asia between 1990 and 2013, but maternal deaths increased in much of sub-Saharan Africa during the 1990s. 2070 (1290-2866) maternal deaths were related to HIV in 2013, 0·4% (0·2-0·6) of the global total. MMR was highest in the oldest age groups in both 1990 and 2013. In 2013, most deaths occurred intrapartum or postpartum. Causes varied by region and between 1990 and 2013. We recorded substantial variation in the MMR by country in 2013, from 956·8 (685·1-1262·8) in South Sudan to 2·4 (1·6-3·6) in Iceland. INTERPRETATION: Global rates of change suggest that only 16 countries will achieve the MDG 5 target by 2015. Accelerated reductions since the Millennium Declaration in 2000 coincide with increased development assistance for maternal, newborn, and child health. Setting of targets and associated interventions for after 2015 will need careful consideration of regions that are making slow progress, such as west and central Africa. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Cause of Death; Female; Global Health; HIV Infections; Humans; Maternal Mortality; Models, Statistical; Organizational Objectives; Pregnancy; Pregnancy Complications, Infectious; Risk Factors; Socioeconomic Factors; Time Factors

Global, regional, and national levels of neonatal, infant, and under-5 mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Wang, Haidong; Liddell, Chelsea A; Coates, Matthew M; Mooney, Meghan D; Levitz, Carly E; Schumacher, Austin E; Apfel, Henry; Iannarone, Marissa; Phillips, Bryan; Lofgren, Katherine T; Sandar, Logan; Dorrington, Rob E; et al. (Lancet, 2014)
BACKGROUND: Remarkable financial and political efforts have been focused on the reduction of child mortality during the past few decades. Timely measurements of levels and trends in under-5 mortality are important to assess progress towards the Millennium Development Goal 4 (MDG 4) target of reduction of child mortality by two thirds from 1990 to 2015, and to identify models of success. METHODS: We generated updated estimates of child mortality in early neonatal (age 0-6 days), late neonatal (7-28 days), postneonatal (29-364 days), childhood (1-4 years), and under-5 (0-4 years) age groups for 188 countries from 1970 to 2013, with more than 29,000 survey, census, vital registration, and sample registration datapoints. We used Gaussian process regression with adjustments for bias and non-sampling error to synthesise the data for under-5 mortality for each country, and a separate model to estimate mortality for more detailed age groups. We used explanatory mixed effects regression models to assess the association between under-5 mortality and income per person, maternal education, HIV child death rates, secular shifts, and other factors. To quantify the contribution of these different factors and birth numbers to the change in numbers of deaths in under-5 age groups from 1990 to 2013, we used Shapley decomposition. We used estimated rates of change between 2000 and 2013 to construct under-5 mortality rate scenarios out to 2030. FINDINGS: We estimated that 6·3 million (95% UI 6·0-6·6) children under-5 died in 2013, a 64% reduction from 17·6 million (17·1-18·1) in 1970. In 2013, child mortality rates ranged from 152·5 per 1000 livebirths (130·6-177·4) in Guinea-Bissau to 2·3 (1·8-2·9) per 1000 in Singapore. The annualised rates of change from 1990 to 2013 ranged from -6·8% to 0·1%. 99 of 188 countries, including 43 of 48 countries in sub-Saharan Africa, had faster decreases in child mortality during 2000-13 than during 1990-2000. In 2013, neonatal deaths accounted for 41·6% of under-5 deaths compared with 37·4% in 1990. Compared with 1990, in 2013, rising numbers of births, especially in sub-Saharan Africa, led to 1·4 million more child deaths, and rising income per person and maternal education led to 0·9 million and 2·2 million fewer deaths, respectively. Changes in secular trends led to 4·2 million fewer deaths. Unexplained factors accounted for only -1% of the change in child deaths. In 30 developing countries, decreases since 2000 have been faster than predicted attributable to income, education, and secular shift alone. INTERPRETATION: Only 27 developing countries are expected to achieve MDG 4. Decreases since 2000 in under-5 mortality rates are accelerating in many developing countries, especially in sub-Saharan Africa. The Millennium Declaration and increased development assistance for health might have been a factor in faster decreases in some developing countries. Without further accelerated progress, many countries in west and central Africa will still have high levels of under-5 mortality in 2030. FUNDING: Bill & Melinda Gates Foundation, US Agency for International Development.
Keywords: Child Mortality; Child, Preschool; Global Health; Humans; Infant; Infant Mortality; Infant, Newborn; Organizational Objectives; Risk Factors; Socioeconomic Factors

Hematopoietic stem cell transplantation effects on spinal cord compression in Hurler. - Ferrara, Giovanna; Maximova, Natalia; Zennaro, Floriana; Gregori, Massimo; Tamaro, Paolo (Pediatr Transplant, 2014)
Hurler syndrome type 1 (MPS-1) is an autosomal recessive lysosomal disorder due to the deficiency of the enzyme alpha-L-iduronidase which is necessary for the degradation of dermatan and heparan sulfate. It is characterized by deposit of glycosaminoglycans in tissues, progressive multisystem dysfunction, and early death. HSCT for children with MPS-I is effective, resulting in increased life expectancy and improvement of clinical parameters. The spinal MRI performed on a female 10 yr old undergoing HSCT at the age of 18 months and receiving ERT revealed a considerable decrease in soft tissue around the tip of odontoid causing a significant reduction in spinal cord compression. In light of this result, we suppose that combined ERT and HSCT are successful in Hurler I disease.
Keywords: Bone Marrow Transplantation; Child; Enzyme Replacement Therapy; Female; Glycosaminoglycans; Hematopoietic Stem Cell Transplantation; Humans; Iduronidase; Magnetic Resonance Imaging; Mucopolysaccharidosis I; Odontoid Process; Spinal Cord Compression; Treatment Outcome

Hemophagocytic lymphohistiocytosis in total parenteral nutrition dependent children: description of 5 cases and practical tips for management. - Pastore, Serena; Barbieri, Francesca; Di Leo, Grazia; Valencic, Erica; Tommasini, Alberto; Ventura, Alessandro (J Pediatr Hematol Oncol, 2014)
Although total parenteral nutrition (TPN) is mandatory in children with intestinal failure, this treatment is not risk free. The main complications of TPN include catheter-related sepsis, thrombosis, hepatic cholestasis and cirrhosis, metabolic bone disease, and, rarely, reactive hemophagocytic lymphohistiocytosis (HLH). The pathogenesis of HLH in patients with TPN is not known, although some authors hypothesized that it can result from the activation of macrophages because of "fat overload." We reported 5 cases of HLH that occurred in patients with 4 different underlying disorders, all requiring TPN for a long term. In our series, an underlying immunological defect or a serious infection (sepsis) can have triggered HLH. Therefore, it could be reasonable to hypothesize that besides TPN in itself, minor immune defects and infections may act together by overcoming a threshold of immune stimulation, which ultimately leads to HLH.
Keywords: Child, Preschool; Fatty Acids; Female; Humans; Infant; Intestinal Diseases; Lymphohistiocytosis, Hemophagocytic; Male; Parenteral Nutrition, Total; Steroids; Treatment Outcome

Heterogeneity of mesenchymal stromal cells in lymphoproliferative disorders. - Campioni, Diana; Voltan, Rebecca; Tisato, Veronica; Zauli, Giorgio (Front Biosci (Landmark Ed), 2014)
Accumulating evidence indicates that bone marrow microenvironment plays an important role in the pathogenesis of some myeloid and lymphoid hematological malignancies (HM). Among different environmental associated parameters, those related to functional, cytogenetic and immunological integrity of mesenchymal stromal cells (MSC) are particularly relevant. Functional alterations and immunophenotypic abnormalities have been described in MSC obtained from HM patients. These data seem to confirm the defective biological pattern of MSC especially in myeloid diseases, while MSC cytogenetic profile in HM is still an open question, because it is not clear whether BM stromal cells are "culprit or bystander" displaying or not an abnormal karyotype. Contradictory findings were reported in different HM but the functional implications of altered MSC karyotype need to be further addressed also in light of a clinical use of MSC. A "pathological" in vivo supportive function of endogenous MSC, which provide important survival and drug resistance signals to leukemic cells especially in lymphoproliferative disorders, is suggested. Thus, the mechanisms underlying these protective versus cytotoxic effects exerted by MSC on leukemic cells need further investigations.
Keywords: Humans; Immunophenotyping; Karyotyping; Lymphoproliferative Disorders; Mesenchymal Stromal Cells

High-frequency percussive ventilation as rescue treatment in severe hypoxemic respiratory failure in term neonates. - Paviotti, Giulia; Bua, Jenny; De Cunto, Angela; Travan, Laura; Demarini, Sergio (J Crit Care, 2014)
Keywords: Female; High-Frequency Ventilation; Humans; Male; Oxygen; Pulmonary Gas Exchange; Respiratory Insufficiency

HLA-G 14 bp deletion/insertion polymorphism and mother-to-child transmission of HIV. - Segat, L; Zupin, L; Kim, H-Y; Catamo, E; Thea, D M; Kankasa, C; Aldrovandi, G M; Kuhn, L; Crovella, S (Tissue Antigens, 2014)
The human leukocyte antigen HLA-G, highly expressed at the maternal-fetal interface, has a pivotal role in mediating immune tolerance. In this study we investigated the influence of HLA-G 14 bp insertion polymorphism in human immunodeficiency virus (HIV)-1 mother-to-child HIV-1 transmission. The 14 bp insertion polymorphism was analyzed among 99 HIV-1 positive mothers and 329 infants born to HIV-positive mothers in Zambia, among whom vertical transmission status and timing had been determined. HLA-G 14 bp insertion polymorphism was detected using a custom TaqMan single nucleotide polymorphisms (SNPs) genotyping assay. Logistic regression was conducted to examine the associations between HLA-G alleles and the risk of HIV transmission. The 14 bp insertion allele was more frequent in HIV exposed-uninfected (EU) infants than in infected infants, and was associated with reduced risk of both in utero (IU) and intrapartum (IP) HIV transmission, after adjusting for maternal cluster of differentiation 4 (CD4) cell count and plasma viral load. Maternal HLA-G 14 bp insertion genotype and HLA-G concordance between mother and child were not associated with the risk of perinatal HIV transmission. The presence of the 14 bp insertion associates with protection toward IU and IP HIV infection in children from Zambia, suggesting that HLA-G could be involved in the vertical transmission of HIV.
Keywords: Adult; Alleles; Base Pairing; Child; Genotype; HIV Infections; HLA-G Antigens; Humans; INDEL Mutation; Infant; Infectious Disease Transmission, Vertical; Mothers; Polymorphism, Genetic; Young Adult

HPV and Chlamydia trachomatis co-detection in young asymptomatic women from high incidence area for cervical cancer. - Bellaminutti, Serena; Seraceni, Silva; De Seta, Francesco; Gheit, Tarik; Tommasino, Massimo; Comar, Manola (J Med Virol, 2014)
Chlamydia trachomatis causing chronic inflammatory diseases has investigated as possible human papillomavirus (HPV) cofactor in cervical cancer. The aim of this study is to evaluate the prevalence of Chlamydia trachomatis and HPV co-infection in different cohorts of asymptomatic women from a Northern Italy area at high incidence for cervical cancer. Cervical samples from 441 females were collected from Cervical Cancer Screening Program, Sexually Transmitted Infectious and Assisted Reproductive Technology centres. HPV and Chlamydia trachomatis were detected simultaneously and genotyped using a highly sensitive bead based assay. The overall prevalence of Chlamydia trachomatis was estimated 9.7%, in contrast with the reported national data of 2.3%, and co-infection with HPV was diagnosed in the 17% of the samples. In females ≤ 25 years of age, the infection reached a peak of 22% and co-infection with HPV of 45.8% (P < 0.001). Of note, in young females diagnosed with low grade cervical lesions, no significant difference between Chlamydia trachomatis and HPV distribution was observed, while differently, HPV co-infection was found significantly associated to the presence of intraepithelial lesions when compared to older females (20% vs. 1%; P < 0.001). In this study, the use of a high sensitive molecular technique exhibited higher analytical sensitivity than the referred assays for the diagnosis of Chlamydia trachomatis and HPV co-infection in asymptomatic females, leading to reduction of the potential to identify incorrectly the infection status. An active screening for timely treatment of Chlamydia trachomatis infection is suggested in young females to evaluate a possible decrease in incidence of pre-cancer intraepithelial lesions.
Keywords: Adolescent; Adult; Age Factors; Cervix Uteri; Chlamydia Infections; Chlamydia trachomatis; Coinfection; Female; Genotype; Humans; Incidence; Italy; Middle Aged; Papillomaviridae; Papillomavirus Infections; Prevalence; Young Adult

In vitro endothelial cell proliferation assay reveals distinct levels of proangiogenic cytokines characterizing sera of healthy subjects and of patients with heart failure. - Voltan, Rebecca; Zauli, Giorgio; Rizzo, Paola; Fucili, Alessandro; Pannella, Micaela; Marci, Roberto; Tisato, Veronica; Ferrari, Roberto; Secchiero, Paola (Mediators Inflamm, 2014)
Although myocardial angiogenesis is thought to play an important role in heart failure (HF), the involvement of circulating proinflammatory and proangiogenic cytokines in the pathogenesis and/or prognosis of HF has not been deeply investigated. By using a highly standardized proliferation assay with human endothelial cells, we first demonstrated that sera from older (mean age 52 ± 7.6 years; n = 46) healthy donors promoted endothelial cell proliferation to a significantly higher extent compared to sera obtained from younger healthy donors (mean age 29 ± 8.6 years; n = 20). The promotion of endothelial cell proliferation was accompanied by high serum levels of several proangiogenic cytokines. When we assessed endothelial cell proliferation in response to HF patients' sera, we observed that a subset of sera (n = 11) promoted cell proliferation to a significantly lesser extent compared to the majority of sera (n = 18). Also, in this case, the difference between the patient groups in the ability to induce endothelial cell proliferation correlated to significant (P < 0.05) differences in serum proangiogenic cytokine levels. Unexpectedly, HF patients associated to the highest endothelial proliferation index showed the worst prognosis as evaluated in terms of subsequent cardiovascular events in the follow-up, suggesting that high levels of circulating proangiogenic cytokines might be related to a worse prognosis.
Keywords: Adult; Cell Proliferation; Cells, Cultured; Chemokines; Cytokines; Heart Failure; Human Umbilical Vein Endothelial Cells; Humans; Middle Aged; Neovascularization, Pathologic; Prognosis

In vivo detection of polyomaviruses JCV and SV40 in mesenchymal stem cells from human umbilical cords. - Comar, Manola; Delbue, Serena; Zanotta, Nunzia; Valencic, Erica; Piscianz, Elisa; Del Savio, Rossella; Tesser, Alessandra; Tommasini, Alberto; Ferrante, Pasquale (Pediatr Blood Cancer, 2014)
BACKGROUND: Multipotent stromal cells are present in the Wharton's jelly matrix (WJSC) of the umbilical cord and can be used as an allogeneic source of cells to treat immunological disorders. Recently it was demonstrated that adult bone marrow (BM)-derived mesenchimal stromal cells (MSC) are susceptible to infection with viruses showing potential oncogenic properties, such as the polyomavirus JC (JCV). The aim of this study was to investigate the presence of human polyomaviruses (JCV, BK Virus-BKV, SV40, and Merkel cell polyomavirus-MCPyV) in WJSC, and explore the risk of infection. PROCEDURE: MSC samples from 35 umbilical cords were investigated by quantitative Real Time PCRs for the presence of DNA sequences of JCV, BKV, SV40, and MCPyV. RESULTS: JCV DNA was detected in 1/35 (2.8%) of MSC samples, while SV40 DNA was found in 3/35 (8.6%) of the examined samples. None of the samples showed sequences of BKV and MCPyV. CONCLUSIONS: The present study demonstrates the in vivo ability of polyomaviruses to infect WJSC. Since the therapeutic approach with the WJSC has high potentiality and a more intensive use can be easily hypothesized, the need to develop consensus guidelines to detect rare viral infections in MSC is pressing.
Keywords: DNA, Viral; Female; Fetal Blood; Humans; JC Virus; Male; Mesenchymal Stromal Cells; Polyomavirus Infections; Simian virus 40; Tumor Virus Infections

Increased levels of C-C chemokine RANTES in asbestos exposed workers and in malignant mesothelioma patients from an hyperendemic area. - Comar, Manola; Zanotta, Nunzia; Bonotti, Alessandra; Tognon, Mauro; Negro, Corrado; Cristaudo, Alfonso; Bovenzi, Massimo (PLoS One, 2014)
BACKGROUND: Asbestos-induced mesothelial inflammatory processes are thought to be the basic mechanisms underlying Malignant Mesothelioma (MM) development. Detection of MM often occurs at late stage due to the long and unpredictable latent period and the low incidence in asbestos exposed individuals. The aim of this study was to investigate early immunological biomarkers to characterize the prognostic profile of a possible asbestos-induced disease, in subjects from a MM hyperendemic area. METHODS: The Luminex Multiplex Panel Technology was used for the simultaneous measurement of serum levels of a large panel of 47 analytes, including cytokines and growth factors, from workers previously exposed to asbestos (Asb-workers), asbestos-induced MM patients and healthy subjects. In addition, to explore the influence on serum cytokines profile exerted by SV40 infection, a cofactor in MM development, a quantitative real time PCR was performed for sequences detection in the N-terminal and intronic regions of the SV40 Tag gene. Statistical analysis was done by means of the Mann-Whitney test and the Kruskall-Wallis test for variance analysis. RESULTS: A variety of 25 cytokines linked to pulmonary inflammation and tumor development were found significantly associated with Asb-workers and MM patients compared with healthy controls. A specific pattern of cytokines were found highly expressed in Asb-workers: IFN-alpha (p<0.05), EOTAXIN (p<0.01), RANTES (p<0.001), and in MM patients: IL-12(p40), IL-3, IL-1 alpha, MCP-3, beta-NGF, TNF-beta, RANTES (p<0.001). Notably, the chemokine RANTES measured the highest serum level showing an increased gradient of concentration from healthy subjects to Asb-workers and MM patients (p<0.001), independently of SV40 infection. CONCLUSION: This study shows that, in subjects from an hyperendemic area for MM, the C-C chemokine RANTES is associated with the exposure to asbestos fibres. If validated in larger samples, this factor could have the potential to be a critical biomarker for MM prognosis as recently reported for breast tumor.
Keywords: Aged; Aged, 80 and over; Asbestos; Biomarkers, Tumor; Case-Control Studies; Chemokine CCL5; Cytokines; Endemic Diseases; Gene Expression; Gene Expression Profiling; Humans; Lung Neoplasms; Mesothelioma; Middle Aged; Occupational Exposure; Simian virus 40; Viral Proteins

Informed consent, and an ethico-legal framework for paediatric observational research and biobanking: the experience of an Italian birth cohort study. - Toccaceli, Virgilia; Serino, Laura; Stazi, Maria Antonietta (Cell Tissue Bank, 2014)
Birth cohort studies are important tools for life-course epidemiology, given the spectrum of the environmental, behavioural, and genetic factors that should be considered when making judgements on human health. Biobanks are valuable components of studies designed to investigate the genetic variability of diseases and improve phenotypic characterisation. In studies involving vulnerable populations and biobanks, it is essential to provide ethical reasoning and analyse the legal requirements. We describe the processes and the tools used in the iterative design of an appropriate informed consent model and the ethico-legal framework of the Piccolipiù study. The Piccolipiù study is a prospective population-based study funded by the Italian Ministry of Health that intends to enrol 3,000 newborns and their mothers in five Italian cities, and to store biological samples for future use. To realise these objectives, we performed a thorough evaluation of the literature, of national and international guidelines, and of the impact of the Italian legal requirements for research biobanking. Discussions among stakeholders facilitated the design of the informed consent and the ethico-legal framework. Several topics are addressed, including the suitability of a broad informed consent for paediatric biobanks, infant vulnerability, access to and sharing of data, and the disclosure of individual's genetic results. Discussion of the ethical and legal procedures adopted in epidemiological biobanking might be a fruitful ground for comparison both at the national level, where standardization and homogeneity are lacking, and at the international level, where different regulatory issues are often in the background and might hamper research biobanks networking.
Keywords: Cohort Studies; Confidentiality; Databases, Genetic; Genetic Privacy; Genetic Research; Genotype; Humans; Infant, Newborn; Information Dissemination; Informed Consent; Internationality; Italy; Parents; Phenotype

Inhibition of mesenchymal stromal cells by pre-activated lymphocytes and their culture media. - Valencic, Erica; Loganes, Claudia; Cesana, Stefania; Piscianz, Elisa; Gaipa, Giuseppe; Biagi, Ettore; Tommasini, Alberto (Stem Cell Res Ther, 2014)
INTRODUCTION: Despite having a proven immunosuppressive potential in vitro, human mesenchymal stromal cells (MSCs) are reported to display variable efficacy in vivo and, in fact, their proven benefit in the clinical practice is still limited and controversial. METHODS: The interplay between clinical grade MSCs and pre-activated donor lymphocytes or selected lymphocyte subsets was studied in vitro. The kinetics of MSC growth and viability was evaluated by adhesion-dependent changes of culture plate impedance and biochemically by a colorimetric assay. Activation of natural killer (NK) cells was assessed as well, using a flow cytometry assay. RESULTS: A strong inhibition of MSC growth was rapidly induced by the addition of pre-activated lymphocytes but not of resting lymphocytes. Inhibition seems not to be attributable to a single cell population, as similar results can be obtained by depleting NK cells or by using either selected CD4+ or CD8+ lymphocytes. In addition, conditioned medium (CM) from activated lymphocytes was able to inhibit MSC growth in a dose-dependent manner. Furthermore, licensing with IFN-γ partially protected MSCs from pre-activated lymphocytes but not from their CM. These results suggest an inhibitory role of lymphocyte-activation-derived substances. However, the identification of a single molecule responsible for MSC inhibition remained elusive, even if preliminary experiments showed that ATP and, to a lesser extent, TNF-α might play a role. CONCLUSIONS: These results suggest that survival of MSCs can be affected by soluble mediators released by activated lymphocytes. Thus it can be hypothesized that MSC immunosuppressive action in vivo could be impaired by ongoing immune activation through the release of inflammatory mediators.
Keywords: CD4-Positive T-Lymphocytes; CD8-Positive T-Lymphocytes; Cell Proliferation; Cell Survival; Cells, Cultured; Coculture Techniques; Culture Media, Conditioned; Cytokines; Humans; Killer Cells, Natural; Lymphocyte Activation; Mesenchymal Stromal Cells

Intestinal-mucosa anti-transglutaminase antibody assays to test for genetic gluten intolerance. - Quaglia, Sara; De Leo, Luigina; Ziberna, Fabiana; Vatta, Serena; Villanacci, Vincenzo; Granzotto, Marilena; Petix, Vincenzo; Martelossi, Stefano; Di Leo, Grazia; Torelli, Lucio; Not, Tarcisio (Cell Mol Immunol, 2014)
Keywords: Celiac Disease; Cell Surface Display Techniques; Child; Diet, Gluten-Free; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; HLA-DQ Antigens; Humans; Immunoassay; Immunoglobulin A; Intestinal Mucosa; Male; Prospective Studies; Transglutaminases

Inverse correlation between circulating levels of TNF-related apoptosis-inducing ligand and 17β-estradiol. - Zauli, Giorgio; Tisato, Veronica; Melloni, Elisabetta; Volpato, Stefano; Cervellati, Carlo; Bonaccorsi, Gloria; Radillo, Oriano; Marci, Roberto; Secchiero, Paola (J Clin Endocrinol Metab, 2014)
CONTEXT: The regulation of the circulating levels of TNF-related apoptosis-inducing ligand (TRAIL), a cytokine of the TNF family, playing a key role in the immune surveillance against cancer, is incompletely understood. OBJECTIVE: The objective of the study was to investigate the potential link between TRAIL and 17β-estradiol. DESIGN, SETTING, AND PARTICIPANTS: Circulating TRAIL levels were measured by an ELISA in plasma samples (n = 246) of healthy, age-matched (range 30-70 y) men and women and in the sera (n = 180) of females belonging to different physiopathological conditions (childhood, pregnancy, under gonadotropin treatment, menopause) characterized by different levels of circulating 17β-estradiol. RESULTS: TRAIL plasma levels in women with aged younger than 50 years were significantly lower compared with age-matched men, whereas in woman 50 years old or older, TRAIL levels were significantly higher compared with the age-matched men and with the younger women. Moreover, an analysis of women with different conditions revealed a significant inverse correlation between the serum levels of TRAIL and 17β-estradiol, with the lowest levels of TRAIL being observed during pregnancy and the highest in childhood and in postmenopausal women. Moreover, gonadotropin treatment in women undergoing assisted reproduction was accompanied by an acute decrease of serum TRAIL levels. Finally, in vitro treatment with 17β-estradiol decreased the TRAIL expression levels in peripheral blood mononuclear cells. CONCLUSIONS: Our data suggest that 17β-estradiol plays a role in regulating TRAIL circulating levels. The demonstration that postmenopausal women exhibit the highest TRAIL levels is of particular interest in light of a previous large study population showing that TRAIL is positively correlated to the overall survival.
Keywords: Adult; Aged; Case-Control Studies; Child; Child, Preschool; Estradiol; Female; Humans; Infant; Male; Middle Aged; Pregnancy; Sex Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

Lactobacillus plantarum P17630 for preventing Candida vaginitis recurrence: a retrospective comparative study. - De Seta, F; Parazzini, F; De Leo, R; Banco, R; Maso, G P; De Santo, D; Sartore, A; Stabile, G; Inglese, S; Tonon, M; Restaino, S (Eur J Obstet Gynecol Reprod Biol, 2014)
BACKGROUND: Recurrence is a frequent complaint of patients with vulvovaginal candidiasis (VVC). Although the pathogenesis of VVC remains a controversial issue, disruption of the balance between the vaginal microbiota may facilitate overgrowth by Candida. Some probiotic bacterial strains can suppress Candida albicans; Lactobacillus plantarum P17630 is able to attach to vaginal epithelial cells and significantly reduce the adhesion of C. albicans. OBJECTIVE: To evaluate the effect of the application of Lactobacillus plantarum P17630 in restoring the vaginal microbiota and prevention of relapses among women with acute VVC undergoing conventional (azole) local and main therapy. METHODS: Retrospective comparative study. We recruited 89 women with a diagnosis of VVC, who were placed into two groups on the basis of reported treatment. The control group was treated with a daily dose of 2% clotrimazole vaginal cream at bedtime for 3 days, followed by vaginal application of a capsule containing lubricant once a day for 6 days and then once a week for another 4 weeks. The probiotic group was treated with the same azole-based protocol but followed by vaginal application of a capsule containing Lactobacillus plantarum P17630 (>10₈ CFU) once a day for 6 days and then once a week for another 4 weeks beginning the day following clotrimazole discontinuation. Clinical and diagnostic patterns were monitored for three months of follow-up. RESULTS: At the end of study the probiotic-treated women showed a statistically significant increase in Lactobacillus values "+++" (80% versus 40%, p<0.001) and a better subjective resolution of symptoms such as vaginal discomfort described as burning or itching (90% versus 67.5%, p<0.03). Among controls there was a non-significant increase at 3 months of recurrence of infection, but a significant increase of women with value of pH=5 or >5. CONCLUSION: Although the results of different studies are controversial, most have suggested use of probiotics in the prevention or treatment of VVC, and no adverse effects have been reported. Our data with L. plantarum P17630 (Gyno-Canesflor - Bayer) confirm the role of this specific strain as a potential empirical preventive agent for reducing vaginal discomfort after conventional treatment of acute VVC and shifting the vaginal milieu toward a predominance of lactobacilli with an improvement of the vaginal pH value.
Keywords: Administration, Intravaginal; Adolescent; Adult; Antifungal Agents; Candidiasis, Vulvovaginal; Clotrimazole; Female; Humans; Lactobacillus plantarum; Microbiota; Middle Aged; Probiotics; Recurrence; Retrospective Studies; Secondary Prevention; Vagina; Vaginal Creams, Foams, and Jellies; Young Adult

Long-term follow-up in children with benign convulsions associated with gastroenteritis. - Verrotti, Alberto; Moavero, Romina; Vigevano, Federico; Cantonetti, Laura; Guerra, Azzurra; Spezia, Elisabetta; Tricarico, Antonella; Nanni, Giuliana; Agostinelli, Sergio; Chiarelli, Francesco; Parisi, Pasquale; Capovilla, Giuseppe; et al. (Eur J Paediatr Neurol, 2014)
BACKGROUND: The outcome of benign convulsions associated with gastroenteritis (CwG) has generally been reported as being excellent. However, these data need to be confirmed in studies with longer follow-up evaluations. AIM: To assess the long-term neurological outcome of a large sample of children presenting with CwG. METHODS: We reviewed clinical features of 81 subjects presenting with CwG (1994-2010) from three different Italian centers with a follow-up period of at least 3 years. RESULTS: Follow-up period ranged from 39 months to 15 years (mean 9.8 years). Neurological examination and cognitive level at the last evaluation were normal in all the patients. A mild attention deficit was detected in three cases (3.7%). Fourteen children (17.3%) received chronic anti-epileptic therapy. Interictal EEG abnormalities detected at onset in 20 patients (24.7%) reverted to normal. Transient EEG epileptiform abnormalities were detected in other three cases (3.7%), and a transient photosensitivity in one (1.2%). No recurrence of CwG was observed. Three patients (3.7%) presented with a febrile seizure and two (2.5%) with an unprovoked seizure, but none developed epilepsy. CONCLUSIONS: The long-term evaluation of children with CwG confirms the excellent prognosis of this condition, with normal psychomotor development and low risk of relapse and of subsequent epilepsy.
Keywords: Adolescent; Anticonvulsants; Attention Deficit Disorder with Hyperactivity; Child; Child, Preschool; Electroencephalography; Epilepsy; Female; Gastroenteritis; Humans; Longitudinal Studies; Male; Neurologic Examination; Retrospective Studies

Midline 1 directs lytic granule exocytosis and cytotoxicity of mouse killer T cells. - Boding, Lasse; Hansen, Ann K; Meroni, Germana; Johansen, Bo B; Braunstein, Thomas H; Bonefeld, Charlotte M; Kongsbak, Martin; Jensen, Benjamin A H; Woetmann, Anders; Thomsen, Allan R; Odum, Niels; von Essen, Marina R; et al. (Eur J Immunol, 2014)
Midline 1 (MID1) is a microtubule-associated ubiquitin ligase that regulates protein phosphatase 2A activity. Loss-of-function mutations in MID1 lead to the X-linked Opitz G/BBB syndrome characterized by defective midline development during embryogenesis. Here, we show that MID1 is strongly upregulated in murine cytotoxic lymphocytes (CTLs), and that it controls TCR signaling, centrosome trafficking, and exocytosis of lytic granules. In accordance, we find that the killing capacity of MID1(-/-) CTLs is impaired. Transfection of MID1 into MID1(-/-) CTLs completely rescued lytic granule exocytosis, and vice versa, knockdown of MID1 inhibited exocytosis of lytic granules in WT CTLs, cementing a central role for MID1 in the regulation of granule exocytosis. Thus, MID1 orchestrates multiple events in CTL responses, adding a novel level of regulation to CTL activation and cytotoxicity.
Keywords: Animals; Blotting, Western; Cytotoxicity, Immunologic; Exocytosis; Flow Cytometry; Mice; Mice, Knockout; Mice, Transgenic; Proteins; Reverse Transcriptase Polymerase Chain Reaction; Secretory Vesicles; T-Lymphocytes, Cytotoxic

Modulation of circulating cytokine-chemokine profile in patients affected by chronic venous insufficiency undergoing surgical hemodynamic correction. - Tisato, Veronica; Zauli, Giorgio; Gianesini, Sergio; Menegatti, Erica; Brunelli, Laura; Manfredini, Roberto; Zamboni, Paolo; Secchiero, Paola (J Immunol Res, 2014)
The expression of proinflammatory cytokines/chemokines has been reported in in vitro/ex vivo settings of chronic venous insufficiency (CVI), but the identification of circulating mediators that might be associated with altered hemodynamic forces or might represent innovative biomarkers is still missing. In this study, the circulating levels of 31 cytokines/chemokines involved in inflammatory/angiogenic processes were analysed in (i) CVI patients at baseline before surgical hemody namic correction, (ii) healthy subjects, and (iii) CVI patients after surgery. In a subgroup of CVI patients, in whom the baseline levels of cytokines/chemokines were analyzed in paired blood samples obtained from varicose vein and forearm vein, EGF, PDGF, and RANTES were increased at the varicose vein site as compared to the general circulation. Moreover, while at baseline, CVI patients showed increased levels of 14 cytokines/chemokines as compared to healthy subjects, 6 months after surgery, 11 cytokines/chemokines levels were significantly reduced in the treated CVI patients as compared to the CVI patients before surgery. Of note, a patient who exhibited recurrence of the disease 6 months after surgery, showed higher levels of EGF, PDGF, and RANTES compared to nonrecurrent patients, highlighting the potential role of the EGF/PDGF/RANTES triad as sensitive biomarkers in the context of CVI.
Keywords: Adult; Aged; Chemokines; Chronic Disease; Cytokines; Female; Hemodynamics; Humans; Male; Middle Aged; Saphenous Vein; Varicose Veins; Venous Insufficiency

Molecular analysis of Fanconi anemia: the experience of the Bone Marrow Failure Study Group of the Italian Association of Pediatric Onco-Hematology. - De Rocco, Daniela; Bottega, Roberta; Cappelli, Enrico; Cavani, Simona; Criscuolo, Maria; Nicchia, Elena; Corsolini, Fabio; Greco, Chiara; Borriello, Adriana; Svahn, Johanna; Pillon, Marta; Mecucci, Cristina; et al. (Haematologica, 2014)
Fanconi anemia is an inherited disease characterized by congenital malformations, pancytopenia, cancer predisposition, and sensitivity to cross-linking agents. The molecular diagnosis of Fanconi anemia is relatively complex for several aspects including genetic heterogeneity with mutations in at least 16 different genes. In this paper, we report the mutations identified in 100 unrelated probands enrolled into the National Network of the Italian Association of Pediatric Hematoly and Oncology. In approximately half of these cases, mutational screening was carried out after retroviral complementation analyses or protein analysis. In the other half, the analysis was performed on the most frequently mutated genes or using a next generation sequencing approach. We identified 108 distinct variants of the FANCA, FANCG, FANCC, FANCD2, and FANCB genes in 85, 9, 3, 2, and 1 families, respectively. Despite the relatively high number of private mutations, 45 of which are novel Fanconi anemia alleles, 26% of the FANCA alleles are due to 5 distinct mutations. Most of the mutations are large genomic deletions and nonsense or frameshift mutations, although we identified a series of missense mutations, whose pathogenetic role was not always certain. The molecular diagnosis of Fanconi anemia is still a tiered procedure that requires identifying candidate genes to avoid useless sequencing. Introduction of next generation sequencing strategies will greatly improve the diagnostic process, allowing a rapid analysis of all the genes.
Keywords: Amino Acid Substitution; Cell Line; Cohort Studies; Computational Biology; Databases, Nucleic Acid; Fanconi Anemia; Fanconi Anemia Complementation Group Proteins; Founder Effect; Genotype; Humans; Italy; Mosaicism; Mutation; Polymorphism, Single Nucleotide

Neutralizing and IgG antibodies against simian virus 40 in healthy pregnant women in Italy. - Comar, Manola; Wong, Connie; Tognon, Mauro; Butel, Janet S (PLoS One, 2014)
OBJECTIVE: Polyomavirus simian virus 40 (SV40) sequences have been detected in various human specimens and SV40 antibodies have been found in human sera from both healthy individuals and cancer patients. This study analyzed serum samples from healthy pregnant women as well as cord blood samples to determine the prevalence of SV40 antibodies in pregnancy. METHODS: Serum samples were collected at the time of delivery from two groups of pregnant women as well as cord bloods from one group. The women were born between 1967 and 1993. Samples were assayed by two different serological methods, one group by neutralization of viral infectivity and the other by indirect ELISA employing specific SV40 mimotopes as antigens. Viral DNA assays by real-time polymerase chain reaction were carried out on blood samples. RESULTS: Neutralization and ELISA tests indicated that the pregnant women were SV40 antibody-positive with overall prevalences of 10.6% (13/123) and 12.7% (14/110), respectively. SV40 neutralizing antibodies were detected in a low number of cord blood samples. Antibody titers were generally low. No viral DNA was detected in either maternal or cord bloods. CONCLUSIONS: SV40-specific serum antibodies were detected in pregnant women at the time of delivery and in cord bloods. There was no evidence of transplacental transmission of SV40. These data indicate that SV40 is circulating at a low prevalence in the northern Italian population long after the use of contaminated vaccines.

A non-complement-fixing antibody to β2 glycoprotein I as a novel therapy for antiphospholipid syndrome. - Agostinis, Chiara; Durigutto, Paolo; Sblattero, Daniele; Borghi, Maria O; Grossi, Claudia; Guida, Filomena; Bulla, Roberta; Macor, Paolo; Pregnolato, Francesca; Meroni, Pier Luigi; Tedesco, Francesco (Blood, 2014)
A single-chain fragment variable (scFv) recognizing β2-glycoprotein 1 (β2GPI) from humans and other species was isolated from a human phage display library and engineered to contain an IgG1 hinge-CH2-CH3 domain. The scFv-Fc directed against β2GPI domain I-induced thrombosis and fetal loss, thus mimicking the effect of antibodies from patients with antiphospholipid syndrome (APS). Complement is involved in the biological effect of anti-β2GPI scFv-Fc, as demonstrated by its ability to promote in vitro and in vivo complement deposition and the failure to induce vascular thrombosis in C6-deficient rats and fetal loss in C5-depleted mice. A critical role for complement was also supported by the inability of the CH2-deleted scFv-Fc to cause vessel occlusion and pregnancy failure. This antibody prevented the pathological effects of anti-β2GPI antibodies from APS patients and displaced β2GPI-bound patient antibodies. The CH2-deleted antibody represents an innovative approach potentially useful to treat APS patients refractory to standard therapy.
Keywords: Abortion, Spontaneous; Animals; Antibodies, Monoclonal; Antiphospholipid Syndrome; Autoantigens; beta 2-Glycoprotein I; Complement Activation; Complement System Proteins; Human Umbilical Vein Endothelial Cells; Humans; Immunoglobulin G; Male; Mice; Protein Binding; Rats; Recombinant Proteins; Single-Chain Antibodies; Thrombosis; Trophoblasts

Novel missense mutation in the NOD2 gene in a patient with early onset ulcerative colitis: causal or chance association? - Girardelli, Martina; Vuch, Josef; Tommasini, Alberto; Crovella, Sergio; Bianco, Anna Monica (Int J Mol Sci, 2014)
Deregulated immune response to gut microflora in genetically predisposed individuals is typical for inflammatory bowel diseases. It is reasonable to assume that genetic association with the disease will be more pronounced in subjects with early onset than adult onset. The nucleotide-binding oligomerization domain containing-2 gene, commonly involved in multifactorial risk of Crohn's disease, and interleukin 10 receptor genes, associated with rare forms of early onset inflammatory bowel diseases, were sequenced in an early onset patient. We identified a novel variant in the NOD2 gene (c.2857A > G p.K953E) and two already described missense variants in the IL10RA gene (S159G and G351R). The new NOD2 missense variant was examined in silico with two online bioinformatics tools to predict the potentially deleterious effects of the mutation. Although cumulative effect of these variations in the early onset of the disease can be only hypothesized, we demonstrated that family information and in silico studies can be used to predict association with the disease.
Keywords: Age of Onset; Amino Acid Sequence; Base Sequence; Child; Colitis, Ulcerative; Crohn Disease; DNA Mutational Analysis; Genetic Predisposition to Disease; Genotype; Humans; Interleukin-10 Receptor alpha Subunit; Interleukin-10 Receptor beta Subunit; Molecular Sequence Data; Mutation, Missense; Nod2 Signaling Adaptor Protein; Polymorphism, Single Nucleotide; Risk Factors; Sequence Homology, Amino Acid

Osteoprotegerin increases in metabolic syndrome and promotes adipose tissue proinflammatory changes. - Bernardi, Stella; Fabris, Bruno; Thomas, Merlin; Toffoli, Barbara; Tikellis, Christos; Candido, Riccardo; Catena, Cristiana; Mulatero, Paolo; Barbone, Fabio; Radillo, Oriano; Zauli, Giorgio; Secchiero, Paola (Mol Cell Endocrinol, 2014)
BACKGROUND: Inflammation is believed to link obesity to insulin resistance, as in the setting of metabolic syndrome (MetS). Osteoprotegerin (OPG) is a soluble protein that seems to exert proatherogenic and prodiabetogenic effects. This study aims at determining OPG levels in MetS and whether OPG might contribute to MetS development and progression. METHODOLOGY/PRINCIPAL FINDINGS: Circulating OPG was measured in 46 patients with MetS and 63 controls, and was found significantly elevated in those with MetS. In addition, circulating and tissue OPG was significantly increased in high-fat diet (HFD) fed C57BL6 mice, which is one of the animal models for the study of MetS. To evaluate the consequences of OPG elevation, we delivered this protein to C57BL6 mice, finding that it promoted systemic and adipose tissue proinflammatory changes in association with metabolic abnormalities. CONCLUSIONS/SIGNIFICANCE: These data suggest that OPG may trigger adipose tissue proinflammatory changes in MetS/HFD-induced obesity.
Keywords: Adipose Tissue; Adult; Animals; Blood Glucose; Body Mass Index; C-Reactive Protein; Case-Control Studies; Cholesterol, HDL; Cholesterol, LDL; Diet, High-Fat; Female; Humans; Inflammation; Insulin; Insulin Resistance; Male; Metabolic Syndrome X; Mice; Mice, Inbred C57BL; Middle Aged; Obesity; Osteoprotegerin; Triglycerides

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche. - Perry, John R B; Day, Felix; Elks, Cathy E; Sulem, Patrick; Thompson, Deborah J; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I; Esko, Tõnu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and γ-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
Keywords: Adolescent; Age Factors; Alleles; Body Mass Index; Breast Neoplasms; Cardiovascular Diseases; Child; Diabetes Mellitus, Type 2; Europe; Female; Genetic Loci; Genome-Wide Association Study; Genomic Imprinting; Humans; Hypothalamo-Hypophyseal System; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Obesity; Ovary; Parents; Polymorphism, Single Nucleotide; Potassium Channels, Tandem Pore Domain; Proteins; Quantitative Trait Loci; Receptors, GABA-B; Receptors, Retinoic Acid; Ribonucleoproteins

Piccolipiù, a multicenter birth cohort in Italy: protocol of the study. - Farchi, Sara; Forastiere, Francesco; Vecchi Brumatti, Liza; Alviti, Sabrina; Arnofi, Antonio; Bernardini, Tommaso; Bin, Maura; Brescianini, Sonia; Colelli, Valentina; Cotichini, Rodolfo; Culasso, Martina; De Bartolo, Paolo; et al. (BMC Pediatr, 2014)
BACKGROUND: The fetal and infant life are periods of rapid development, characterized by high susceptibility to exposures. Birth cohorts provide unique opportunities to study early-life exposures in association with child development and health, as well as, with longer follow-up, the early life origin of adult diseases. Piccolipiù is an Italian birth cohort recently set up to investigate the effects of environmental exposures, parental conditions and social factors acting during pre-natal and early post-natal life on infant and child health and development. We describe here its main characteristics. METHODS/DESIGN: Piccolipiù is a prospective cohort of expected 3000 newborns, who will be recruiting in six maternity units of five Italian cities (Florence, Rome, Trieste, Turin and Viareggio) since October 2011. Mothers are contacted during pregnancy or at delivery and are offered to participate in the study. Upon acceptance, their newborns are recruited at birth and followed up until at least 18 years of age. At recruitment, the mothers donate a blood sample and complete a baseline questionnaire. Umbilical cord blood, pieces of umbilical cord and heel blood spots are also collected. Postnatal follow-up currently occurs at 6, 12, and 24 months of age using on-line or postal self administered questionnaire; further questionnaires and medical examinations are envisaged. Questionnaires collect information on several factors, including mother's and/or child's environmental exposures, anthropometric measures, reproductive factors, diet, supplements, medical history, cognitive development, mental health and socioeconomic factors. Health promotion materials are also offered to parents. DISCUSSION: Piccolipiù will broaden our understanding of the contribution of early-life factors to infant and child health and development. Several hypotheses on the developmental origins of health can be tested or piloted using the data collected from the Piccolipiù cohort. By pooling these data with those collected by other existing birth cohorts it will be possible to validate previous findings and to study rare exposures and outcomes.
Keywords: Adolescent; Child; Child Development; Child Welfare; Child, Preschool; Cohort Studies; Environmental Exposure; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Socioeconomic Factors

A population-based approach to study the impact of PROP perception on food liking in populations along the Silk Road. - Robino, Antonietta; Mezzavilla, Massimo; Pirastu, Nicola; Dognini, Maddalena; Tepper, Beverly J; Gasparini, Paolo (PLoS One, 2014)
Taste is one of the main factors determining food choices. Differences in PROP bitter taste perception have been implicated in individual differences in food preferences and selection. The present study examined associations between, PROP phenotypes, self-reported food liking and TAS2R38 polymorphisms, the major gene implicated in PROP bitterness, in six different populations of the Caucasus and Central Asia, located along the ancient Silk Road. Differences in the distribution of PROP phenotypes across populations were detected, with a higher frequency of super tasters in Tajikistan (31.3%) and Armenia (39.0%) and a higher frequency of non tasters in Georgia (50.9%). While no relationships were observed between PROP phenotypes and food liking using standard statistical tests, we used an approach based on comparison of distance matrices derived from these data. The first matrix compared the food liking ratings of each population to all others pairwise using the Kruskal-Wallis test (at p<0.00063), and the second one compared the distribution of PROP phenotypes across all populations in a similar manner calculating the chi-square statistic as a distance measure. A strong correlation between the two matrices was found (Mantel test: r = 0.67, p-value = 0.03), suggesting that the pattern of food liking across populations was closely related to the distribution of PROP phenotypes. This same relationship was not observed when TAS2R38 genotypes were substituted for PROP phenotypes in this analysis. Our data suggest that a population-based approach utilizing distance matrices is a useful technique for detecting PROP-related differences in food liking and can be applied to other taste phenotypes.
Keywords: Armenia; Azerbaijan; Food; Genetic Association Studies; Genotype; Haplotypes; Humans; Polymorphism, Single Nucleotide; Propylthiouracil; Receptors, G-Protein-Coupled; Tajikistan; Taste; Taste Perception; Uzbekistan

Pregnancy and postpartum following a prenatal diagnosis of fetal thoracoabdominal malformation: the parental perspective. - Giuliani, Rosella; Tripani, Antonella; Pellizzoni, Sandra; Clarici, Andrea; Lonciari, Isabella; D'Ottavio, Giuseppina; Schleef, Jurgen (J Pediatr Surg, 2014)
PURPOSE: The study's aim was to evaluate how information related to a prenatal diagnosis of fetal malformation could modify parenthood experience descriptions during pregnancy and after the child's birth. METHODS: A longitudinal case-control clinical study was conducted. Data on parenthood experience descriptions collected using a validated semantic differential technique during pregnancy and after the child's birth were compared between seven couples of parents receiving a prenatal diagnosis of fetal malformation and seven couples without any fetal diagnosis. RESULTS: Our results show that during pregnancy parents in the clinical group describe themselves as more fragile, passive, and timid [p=0.007] than those in the control group. On the other hand, after the child's birth, there are no significant differences between groups. CONCLUSIONS: Data are discussed with reference to better knowledge of the psychological dynamics involved in becoming a parent and to rational planning of support for parents receiving a diagnosis of fetal malformation.
Keywords: Adult; Case-Control Studies; Counseling; Cystic Adenomatoid Malformation of Lung, Congenital; Female; Hernia, Diaphragmatic; Hernias, Diaphragmatic, Congenital; Humans; Hydronephrosis; Kidney Diseases; Longitudinal Studies; Male; Musculoskeletal Abnormalities; Parents; Pregnancy; Psychological Tests; Stress, Psychological; Ultrasonography, Prenatal; Urogenital Abnormalities

Procedural sedation for intra-articular corticosteroid injections in juvenile idiopathic arthritis (JIA) should be a standard of care. - Pastore, Serena; Gortani, Giulia; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2014)
Keywords: Arthritis, Juvenile; Conscious Sedation; Female; Glucocorticoids; Humans; Male; Pain; Patient Preference

Promoting effective child development practices in the first year of life: does timing make a difference? - Roia, Anna; Paviotti, Elena; Ferluga, Valentina; Montico, Marcella; Monasta, Lorenzo; Ronfani, Luca; Tamburlini, Giorgio (BMC Pediatr, 2014)
BACKGROUND: There is an increasing need for parenting programs aimed at promoting parent-child interaction. A variety of interventions have been proposed. The use of audiovisual materials for parents has been shown to be effective but limited information is available on the optimal timing for its use, particularly for new parents during the first year of life of their children. The aim of this study is to compare the effectiveness of a video administered at two different times to first-time parents in modifying parental knowledge, attitudes and intentions with regards to effective care practices. METHODS: Open randomized controlled trial carried out in a referral mother and child hospital. Eligible parents were randomly assigned to receive a video at one month (early intervention) or at seven months (late intervention) of age of their child. The video addressed four specific activities related to early child development: reading aloud to the baby, early exposure to music, promotion of early socialization for parents and for children. The primary outcome was the proportion of parents who declared that their knowledge, attitudes and intentions changed after having seen the video at one or seven months of age of the child. RESULTS: One hundred and five families were randomly allocated either to the early (53) or to the late (52) intervention group. For 99 families (52 in the early and 47 in the late group) a complete outcome evaluation was available. Parents included in the early administration group more frequently reported modifications in their knowledge of the suggested practices while parents in the late group more frequently reported a change in their attitudes. This finding was consistent across all four practices. The video was found to influence parental intentions in the great majority of interviewed parents with no significant difference between groups (82.7% and 87.2% in the early and late intervention group, respectively). CONCLUSIONS: Audiovisual materials can be an effective complementary tool in programs aimed at supporting parents, particularly those dealing with their first baby. The results provide some useful insights into the differential benefits of using audiovisual aids at different times during the first year of life of the baby. TRIAL REGISTRATION: ClinicalTrials.gov NCT02120430.

A randomized trial of hyperimmune globulin to prevent congenital cytomegalovirus. - Revello, Maria Grazia; Lazzarotto, Tiziana; Guerra, Brunella; Spinillo, Arsenio; Ferrazzi, Enrico; Kustermann, Alessandra; Guaschino, Secondo; Vergani, Patrizia; Todros, Tullia; Frusca, Tiziana; Arossa, Alessia; Furione, Milena; et al. (N Engl J Med, 2014)
BACKGROUND: Congenital infection with human cytomegalovirus (CMV) is a major cause of morbidity and mortality. In an uncontrolled study published in 2005, administration of CMV-specific hyperimmune globulin to pregnant women with primary CMV infection significantly reduced the rate of intrauterine transmission, from 40% to 16%. METHODS: We evaluated the efficacy of hyperimmune globulin in a phase 2, randomized, placebo-controlled, double-blind study. A total of 124 pregnant women with primary CMV infection at 5 to 26 weeks of gestation were randomly assigned within 6 weeks after the presumed onset of infection to receive hyperimmune globulin or placebo every 4 weeks until 36 weeks of gestation or until detection of CMV in amniotic fluid. The primary end point was congenital infection diagnosed at birth or by means of amniocentesis. RESULTS: A total of 123 women could be evaluated in the efficacy analysis (1 woman in the placebo group withdrew). The rate of congenital infection was 30% (18 fetuses or infants of 61 women) in the hyperimmune globulin group and 44% (27 fetuses or infants of 62 women) in the placebo group (a difference of 14 percentage points; 95% confidence interval, -3 to 31; P=0.13). There was no significant difference between the two groups or, within each group, between the women who transmitted the virus and those who did not, with respect to levels of virus-specific antibodies, T-cell-mediated immune response, or viral DNA in the blood. The clinical outcome of congenital infection at birth was similar in the two groups. The number of obstetrical adverse events was higher in the hyperimmune globulin group than in the placebo group (13% vs. 2%). CONCLUSIONS: In this study involving 123 women who could be evaluated, treatment with hyperimmune globulin did not significantly modify the course of primary CMV infection during pregnancy. (Funded by Agenzia Italiana del Farmaco; CHIP ClinicalTrials.gov number, NCT00881517; EudraCT no. 2008-006560-11.).
Keywords: Adult; Amniocentesis; Cytomegalovirus; Cytomegalovirus Infections; Female; Fetal Diseases; Humans; Immunoglobulins; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious

Recommendations for self-monitoring in pediatric diabetes: a consensus statement by the ISPED. - Scaramuzza, Andrea; Cherubini, Valentino; Tumini, Stefano; Bonfanti, Riccardo; Buono, Pietro; Cardella, Francesca; d'Annunzio, Giuseppe; Frongia, Anna Paola; Lombardo, Fortunato; Monciotti, Anna Carla Maria; Rabbone, Ivana; Schiaffini, Riccardo; et al. (Acta Diabetol, 2014)
A panel of experts of the Italian Society of Pediatric Endocrinology and Diabetology comprehensively discussed and approved the Italian recommendations regarding self-monitoring of blood glucose, continuous glucose monitoring and other measures of glycemic control in children and adolescents with type 1 diabetes. After an extensive review of the literature, we took these issues into account: self-monitoring blood glucose, continuous glucose monitoring, glycemic variability, glycosuria, ketonuria, ketonemia, glycated hemoglobin, fructosamine and glycated albumin, logbook, data downloading, lancing devices, carbohydrate counting, and glycemic measurements at school. We concluded that clinical guidelines on self-management should be developed in every country with faithful adaptation to local languages and taking into account specific contexts and local peculiarities, without any substantial modifications to the international recommendations. We believe that the National Health Service should provide all necessary resources to ensure self-monitoring of blood glucose and possibly continuous glucose monitoring of all children and adolescents with type 1 diabetes, according to the standards of care provided by these recommendations and internationally.

Rhythm perception and production predict reading abilities in developmental dyslexia. - Flaugnacco, Elena; Lopez, Luisa; Terribili, Chiara; Zoia, Stefania; Buda, Sonia; Tilli, Sara; Monasta, Lorenzo; Montico, Marcella; Sila, Alessandra; Ronfani, Luca; Schön, Daniele (Front Hum Neurosci, 2014)
Rhythm organizes events in time and plays a major role in music, but also in the phonology and prosody of a language. Interestingly, children with developmental dyslexia-a learning disability that affects reading acquisition despite normal intelligence and adequate education-have a poor rhythmic perception. It has been suggested that an accurate perception of rhythmical/metrical structure, that requires accurate perception of rise time, may be critical for phonological development and subsequent literacy. This hypothesis is mostly based on results showing a high degree of correlation between phonological awareness and metrical skills, using a very specific metrical task. We present new findings from the analysis of a sample of 48 children with a diagnosis of dyslexia, without comorbidities. These children were assessed with neuropsychological tests, as well as specifically-devised psychoacoustic and musical tasks mostly testing temporal abilities. Associations were tested by multivariate analyses including data mining strategies, correlations and most importantly logistic regressions to understand to what extent the different auditory and musical skills can be a robust predictor of reading and phonological skills. Results show a strong link between several temporal skills and phonological and reading abilities. These findings are discussed in the framework of the neuroscience literature comparing music and language processing, with a particular interest in the links between rhythm processing in music and language.

The second generation of HIV-1 vertically exposed infants: a case series from the Italian Register for paediatric HIV infection. - Calitri, Carmelina; Gabiano, Clara; Galli, Luisa; Chiappini, Elena; Giaquinto, Carlo; Buffolano, Wilma; Genovese, Orazio; Esposito, Susanna; Bernardi, Stefania; de Martino, Maurizio; Tovo, Pier-Angelo (BMC Infect Dis, 2014)
BACKGROUND: In the Highly Active Antiretroviral Therapy (HAART) era, the prognosis of children perinatally infected with HIV-1 has significantly improved, so the number of perinatally-infected females entering child-bearing age and experiencing motherhood is increasing. METHODS: A description of the medical history and pregnancy outcomes of women with perinatal acquired HIV-1 infection enrolled in the Italian Register for HIV infection in Children. RESULTS: Twenty-three women had 29 pregnancies. They had started an antiretroviral therapy at a median of 7.7 years (interquartile range, IQR 2.3 - 11.4), and had experienced a median of 4 therapeutic regimens (IQR 2-6). Twenty women (87%) had taken zidovudine (AZT) before pregnancy, in 14 cases as a starting monotherapy. In 21 pregnancies a protease inhibitor-based regimen was used. At delivery, the median of CD4+ T lymphocytes was 450/μL (IQR 275-522), and no viral load was detectable in 15 cases (reported in 21 pregnancies). Twenty-eight children were delivered through caesarean section (median gestational age: 38 weeks, IQR 36-38, median birth weight: 2550 grams, IQR 2270 - 3000). Intravenous AZT was administered during delivery in 26 cases. All children received oral AZT (median: 42 days, IQR 31 - 42), with no adverse events reported. No child acquired HIV-1 infection. CONCLUSIONS: Despite a long history of maternal infection, multiple antiretroviral regimens and, perhaps, the development of drug-resistant viruses, the risk of mother-to-child transmission does not seem to have increased among the second-generation of HIV-1 exposed infants.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Birth Weight; Cesarean Section; Child; Female; HIV Infections; HIV-1; Humans; Infant; Infectious Disease Transmission, Vertical; Italy; Male; Pediatrics; Pregnancy; Pregnancy Complications, Infectious; Pregnancy Outcome; Prospective Studies; Viral Load; Young Adult; Zidovudine

Serum amyloid protein A concentration in cryopyrin-associated periodic syndromes patients treated with interleukin-1 beta antagonist. - Pastore, Serena; Paloni, Giulia; Caorsi, Roberta; Ronfani, Luca; Taddio, Andrea; Lepore, Loredana (Clin Exp Rheumatol, 2014)
OBJECTIVES: Cryopyrin-associated periodic syndromes (CAPS) are a group of chronic, relapsing autoinflammatory disorders which may be complicated by systemic AA amyloidosis. The aim of our study was to evaluate serum amyloid protein A (SAA) level in CAPS patients treated with Interleukin-1beta (IL-1β) antagonist and to correlate its level with treatment response. METHODS: All patients of CAPS Italian Register treated with IL-1β inhibitor were enrolled. SAA levels before starting therapy, and at last visit were evaluated. Patients were then divided in complete responders and partial responders. RESULTS: Twenty-five patients were enrolled. SAA level before starting therapy was increased (median 118.5 mg/L, IQR 96.4-252.8; normal value <6.4 mg/L), while at last visit SAA was significantly reduced (median 4.3 mg/L, IQR 2.3-12.7) (p<0.001). However 12 patients still presented SAA levels beyond normal range, 10/25 patients (40%) showed a complete response to treatment. Conversely, 15 patients presented only a partial response, of which 12 for increased SAA value and 3 for increased CRP value. Patients with partial response had SAA values significantly higher than patients with complete response (median 12.6 mg/L; IQR 8.3-20.0 vs. 2.7 mg/L; IQR 1.6-4.1, p<0.001). CONCLUSIONS: Our results confirm the long term efficacy of anti IL-1β treatment in CAPS and the decrease of SAA levels; however 48% of patients still presented SAA elevation despite treatment. The real risk of these patients in developing amyloidosis is not clear but the persistent increase of SAA needs a close follow-up.
Keywords: Adolescent; Adult; Amyloidosis; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Drug Monitoring; Female; Humans; Immunosuppressive Agents; Interleukin-1beta; Male; Middle Aged; Serum Amyloid A Protein; Treatment Outcome; Young Adult

Severe inflammatory bowel disease associated with congenital alteration of transforming growth factor beta signaling. - Naviglio, Samuele; Arrigo, Serena; Martelossi, Stefano; Villanacci, Vincenzo; Tommasini, Alberto; Loganes, Claudia; Fabretto, Antonella; Vignola, Silvia; Lonardi, Silvia; Ventura, Alessandro (J Crohns Colitis, 2014)
Transforming growth factor beta is a pleiotropic cytokine which plays a central role in the homeostasis of the immune system. A complex dysregulation of its signaling occurs in Loeys-Dietz syndrome, a monogenic disorder caused by mutations of transforming growth factor beta receptors type 1 or type 2, characterized by skeletal involvement, craniofacial abnormalities, and arterial tortuosity with a strong predisposition for aneurysm and dissection. In addition, several immunologic abnormalities have been described in these patients, including an increased risk of allergic disorders as well as eosinophilic gastrointestinal disorders. The occurrence of inflammatory bowel disorders has been also reported, but it is poorly documented. We describe two unrelated children with Loeys-Dietz syndrome affected by severe chronic inflammatory colitis appearing at an early age. The intestinal disease presented similar features in both patients, including a histopathological picture of non-eosinophilic chronic ulcerative colitis, striking elevation of inflammatory markers, and a distinctly severe clinical course leading to failure to thrive, with resistance to multiple immunosuppressive treatments. One of the patients also presented autoimmune thyroiditis. Our report confirms that chronic ulcerative colitis may be associated with Loeys-Dietz syndrome. This finding suggests that an alteration of transforming growth factor beta signaling may by itself predispose to inflammatory colitis in humans, and represent an invaluable model to understand inflammatory bowel diseases.
Keywords: Child, Preschool; Colon; Colonoscopy; Female; Humans; Infant; Inflammatory Bowel Diseases; Loeys-Dietz Syndrome; Male; Signal Transduction; Transforming Growth Factor beta

Severe neonatal hyperbilirubinemia and UGT1A1 promoter polymorphism. - Travan, Laura; Lega, Sara; Crovella, Sergio; Montico, Marcella; Panontin, Elisa; Demarini, Sergio (J Pediatr, 2014)
OBJECTIVE: To assess whether UGT1A1 promoter polymorphisms associated with Gilbert Syndrome (GS) occur with a greater frequency in neonates with severe hyperbilirubinemia. STUDY DESIGN: In a case-control study performed at a single hospital center in Italy, 70 case subjects with severe hyperbilirubinemia (defined as bilirubin level ≥20 mg/dL or 340 μmol/L) and 70 controls (bilirubin level <12 mg/dL or 210 μmol/L) were enrolled. Both case and control subjects were full term newborns. Polymerase chain reaction analysis on blood spot was performed to determine the frequency of UGTA1A1 promoter polymorphisms in cases and controls. RESULTS: No statistical difference in the prevalence of UGTA1A1 gene variants was found between cases and controls (P = 1). Thirteen infants homozygous for (TA)7 polymorphism associated with GS were in the case group (18.6%) and 14 in the control group (20.0%). A heterozygous group was also equally distributed between cases (44.3%) and controls (42.9%). No (TA)8 repeat was found in the 2 groups. CONCLUSIONS: In our study population, GS polymorphism alone does not appear to play a major role in severe neonatal hyperbilirubinemia in neonates without signs of hemolysis.
Keywords: Case-Control Studies; Female; Genotype; Gilbert Disease; Glucuronosyltransferase; Humans; Hyperbilirubinemia, Neonatal; Infant, Newborn; Male; Polymerase Chain Reaction; Polymorphism, Genetic; Prevalence; Promoter Regions, Genetic

Single-day trimethoprim/sulfamethoxazole prophylaxis for Pneumocystis pneumonia in children with cancer. - Caselli, Désirée; Petris, Maria Grazia; Rondelli, Roberto; Carraro, Francesca; Colombini, Antonella; Muggeo, Paola; Ziino, Ottavio; Melchionda, Fraia; Russo, Giovanna; Pierani, Paolo; Soncini, Elena; DeSantis, Raffaella; et al. (J Pediatr, 2014)
OBJECTIVE: To determine whether a simplified, 1-day/week regimen of trimethoprim/sulfamethoxazole is sufficient to prevent Pneumocystis (jirovecii [carinii]) pneumonia (PCP). Current recommended regimens for prophylaxis against PCP range from daily administration to 3 consecutive days per week dosing. STUDY DESIGN: A prospective survey of the regimens adopted for the PCP prophylaxis in all patients treated for childhood cancer at pediatric hematology-oncology centers of the Associazione Italiana Ematologia Oncologia Pediatrica. RESULTS: The 20 centers participating in the study reported a total of 2466 patients, including 1093 with solid tumor and 1373 with leukemia/lymphoma (or primary immunodeficiency; n = 2). Of these patients, 1371 (55.6%) received the 3-day/week prophylaxis regimen, 406 (16.5%) received the 2-day/week regimen, and 689 (27.9%), including 439 with leukemia/lymphoma, received the 1-day/week regimen. Overall, only 2 cases of PCP (0.08%) were reported, both in the 2-day/week group. By intention to treat, the cumulative incidence of PCP at 3 years was 0.09% overall (95% CI, 0.00-0.40%) and 0.51% for the 2-day/week group (95% CI, 0.10%-2.00%). Remarkably, both patients who failed had withdrawn from prophylaxis. CONCLUSION: A single-day course of prophylaxis with trimethoprim/sulfamethoxazole may be sufficient to prevent PCP in children with cancer undergoing intensive chemotherapy regimens. This simplified strategy might have implications for the emerging need for PCP prophylaxis in other patients subjected to the increased use of biological and nonbiological agents that induce higher levels of immune suppression, such as those with rheumatic diseases.
Keywords: Anti-Infective Agents; Child; Dose-Response Relationship, Drug; Drug Administration Schedule; Follow-Up Studies; Hematologic Neoplasms; Humans; Incidence; Italy; Pneumocystis carinii; Pneumonia, Pneumocystis; Prospective Studies; Treatment Outcome; Trimethoprim, Sulfamethoxazole Drug Combination

Spectrum of the mutations in Bernard-Soulier syndrome. - Savoia, Anna; Kunishima, Shinji; De Rocco, Daniela; Zieger, Barbara; Rand, Margaret L; Pujol-Moix, Núria; Caliskan, Umran; Tokgoz, Huseyin; Pecci, Alessandro; Noris, Patrizia; Srivastava, Alok; Ward, Christopher; et al. (Hum Mutat, 2014)
Bernard-Soulier syndrome (BSS) is a rare autosomal recessive bleeding disorder characterized by defects of the GPIb-IX-V complex, a platelet receptor for von Willebrand factor (VWF). Most of the mutations identified in the genes encoding for the GP1BA (GPIbα), GP1BB (GPIbβ), and GP9 (GPIX) subunits prevent expression of the complex at the platelet membrane or more rarely its interaction with VWF. As a consequence, platelets are unable to adhere to the vascular subendothelium and agglutinate in response to ristocetin. In order to collect information on BSS patients, we established an International Consortium for the study of BSS, allowing us to enrol and genotype 132 families (56 previously unreported). With 79 additional families for which molecular data were gleaned from the literature, the 211 families characterized so far have mutations in the GP1BA (28%), GP1BB (28%), or GP9 (44%) genes. There is a wide spectrum of mutations with 112 different variants, including 22 novel alterations. Consistent with the rarity of the disease, 85% of the probands carry homozygous mutations with evidence of founder effects in some geographical areas. This overview provides the first global picture of the molecular basis of BSS and will lead to improve patient diagnosis and management.
Keywords: Alleles; Bernard-Soulier Syndrome; Databases, Nucleic Acid; Founder Effect; Genetic Variation; Humans; Mutation; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Single Nucleotide; von Willebrand Diseases; Web Browser

TNF-α SNP rs1800629 and risk of relapse in childhood acute lymphoblastic leukemia: relation to immunophenotype. - Franca, Raffaella; Rebora, Paola; Athanasakis, Emmanouil; Favretto, Diego; Verzegnassi, Federico; Basso, Giuseppe; Tommasini, Alberto; Valsecchi, Maria Grazia; Decorti, Giuliana; Rabusin, Marco (Pharmacogenomics, 2014)
AIM: In the AIEOP-BFM ALL (Associazione Italiana Ematologia Oncologia Pediatrica-Berlin Frankfurt Münster acute lymphoblastic leukemia) 2000 protocol, 70% of relapsed patients had favorable prognostic features and fell within less intensive polychemotherapeutic regimens, suggesting the need for better assessing lower risk stratification. MATERIALS & METHODS: A novel two-phase study design selected 614 children to be genotyped for TNF-α SNP rs1800629 (-308G>A). A weighted Cox model was applied to evaluate the SNP effect on hazard of relapse, adjusting for immunophenotype, risk group, age and gender and including interaction terms. RESULTS: Significant interaction was found with immunophenotypes (p = 0.0007, with minor allele genotypes being adverse genetic markers in B-cell acute lymphoblastic leukemia and protective ones in T-cell acute lymphoblastic leukemia), and also with risk protocols (p = 0.0041, with minor allele genotypes as prognostic factor of relapse for standard risk patients [only one T-cell acute lymphoblastic leukemia in the subgroup analyzed]). CONCLUSION: The presence of at least one A allele in TNF-α SNP rs1800629 should suggest a closer monitoring in B-cell acute lymphoblastic leukemia standard risk patients.
Keywords: Adolescent; Antineoplastic Agents; Child; Child, Preschool; Drug Resistance, Neoplasm; Female; Genotype; Humans; Infant; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Phenotype; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Precursor T-Cell Lymphoblastic Leukemia-Lymphoma; Recurrence; Risk Assessment; Steroids; Tumor Necrosis Factor-alpha

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Validation of point-of-care testing for coeliac disease in children in a tertiary hospital in north India. - Singh, Prashant; Wadhwa, Nitya; Chaturvedi, Mona K; Bhatia, Vidyut; Saini, Savita; Tandon, Nikhil; Makharia, Govind K; Maki, Markku; Not, Tarcisio; Phillips, Alan; Bhatnagar, Shinjini (Arch Dis Child, 2014)
OBJECTIVE: Some of the conventional serological tests for coeliac disease (CD) are expensive, time-consuming and not readily available in developing countries, leading to a delay in diagnosis. Recently, point-of-care tests (POCT) have been manufactured and tested in Europe but have not been validated in our setting. We therefore aimed to study the diagnostic accuracy of the POCT 'Biocard' test in diagnosing CD in Indian children. DESIGN: Cross-sectional study. SETTING: Tertiary care centre in north India. PATIENTS: Children, aged 2-18 years, with chronic diarrhoea, short stature or refractory anaemia underwent serological testing for CD with antiendomysial antibodies (AEA), antitissue transglutaminase (tTG) antibodies and Biocard test followed by duodenal biopsy irrespective of serological results. CD was diagnosed with positive AEA and duodenal biopsy showing >grade 2 changes using modified Marsh criteria. Those who were both AEA negative and had normal histology were considered CD negative. RESULTS: Of 319 children who underwent the serological testing, 170 agreed for biopsy. Of these, 110 were diagnosed with CD and 30 were found to be CD negative. Remaining 30 had discordant AEA and histology results and were not included in analysis. Biocard test agreed with 92/110 positive and 27/30 negative diagnoses based on reference tests (83.6% sensitivity and 90% specificity). tTG was found to be 93.8% sensitive and 96.4% specific. CONCLUSIONS: We successfully validated the POCT for CD in our setting. It could be used to increase case detection rates in developing countries with a large undiagnosed CD burden.
Keywords: Adolescent; Celiac Disease; Child; Child, Preschool; Cross-Sectional Studies; Female; Humans; India; Male; Point-of-Care Systems; Sensitivity and Specificity; Serologic Tests; Tertiary Care Centers

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Patients affected by metabolic syndrome show decreased levels of circulating platelet derived growth factor (PDGF)-BB. - Tisato, Veronica; Toffoli, Barbara; Monasta, Lorenzo; Bernardi, Stella; Candido, Riccardo; Zauli, Giorgio; Secchiero, Paola (Clin Nutr, 2013)
BACKGROUND & AIMS: The development and/or progression of metabolic syndrome (MetS) in overweight and obese individuals have been associated to low-grade inflammation, but few studies have simultaneously analyzed the circulating levels of several cytokines. METHODS: In this pilot study, a group of 27 cytokines and growth factors was analyzed in the serum of obese patients (n=40) diagnosed for MetS in comparison with sex- and age-matched control subjects without MetS (n=53) by using a multiplex immunoassay. Release of cytokines was measured in culture supernatants of human primary endothelial cells, THP-1 macrophagic cells and HuH-7 hepatoma cells upon exposure to a high fat mixture. RESULTS: While the majority of cytokines did not show significant differences between the investigated groups, the circulating levels of CXCL10/IP-10 and IL-6 were higher in the MetS group versus overweight control group. In contrast, PDGF-BB serum levels were significantly decreased in MetS patients. The in vitro addition of a high fat mixture increased the release of IL-6 and/or CXCL10/IP-10 in the culture supernatant of human primary endothelial cells and THP-1 macrophagic cells, while the same mixture significantly decreased the release of PDGF-BB by human THP-1 macrophagic and HuH-7 hepatoma cells. CONCLUSIONS: The current demonstration that MetS is associated with decrease of the pro-fibrotic PDGF cytokine is a completely novel finding, which adds complexity to the interplay between inflammation and fibrosis in patients affected by MetS.
Keywords: Adolescent; Adult; Aged; Case-Control Studies; Cell Line, Tumor; Chemokine CXCL10; Endothelial Cells; Female; Humans; Interleukin-6; Linear Models; Male; Metabolic Syndrome X; Middle Aged; Obesity; Pilot Projects; Proto-Oncogene Proteins c-sis; RNA, Messenger; Young Adult

Type 1 diabetes mellitus and celiac disease: usefulness of gluten-free diet. - Pascolo, Paola; Faleschini, Elena; Tonini, Giorgio; Ventura, Alessandro (Acta Diabetol, 2013)

Acute febrile cholestatic jaundice in children: keep in mind Kawasaki disease. - Taddio, Andrea; Pellegrin, Maria Chiara; Centenari, Chiara; Filippeschi, Irene Pellegrini; Ventura, Alessandro; Maggiore, Giuseppe (J Pediatr Gastroenterol Nutr, 2012)
Kawasaki disease (KD) is characterized by persistent fever in addition to 4 of 5 signs of mucocutaneous inflammation. Although gastrointestinal involvement does not belong to the classic diagnostic criteria, it has been often associated with KD onset. We reviewed patients who were admitted for febrile cholestatic jaundice between 2003 and 2010 in 2 tertiary pediatric care centers. KD was the second most frequent cause (21%) after viral infections. Considering the relative high frequency of this condition, a high index of suspicion of KD should be maintained in patients presenting with febrile cholestatic jaundice.
Keywords: Child; Child, Preschool; Diagnosis, Differential; Female; Fever; Humans; Infant; Jaundice, Obstructive; Male; Mucocutaneous Lymph Node Syndrome; Virus Diseases

Association between the JC polyomavirus infection and male infertility. - Comar, Manola; Zanotta, Nunzia; Croci, Eleonora; Murru, Immacolata; Marci, Roberto; Pancaldi, Cecilia; Dolcet, Ornella; Luppi, Stefania; Martinelli, Monica; Giolo, Elena; Ricci, Giuseppe; Tognon, Mauro (PLoS One, 2012)
In recent years the incidence of male infertility has increased. Many risk factors have been taken into consideration, including viral infections. Investigations into viral agents and male infertility have mainly been focused on human papillomaviruses, while no reports have been published on polyomaviruses and male infertility. The aim of this study was to verify whether JC virus and BK virus are associated with male infertility. Matched semen and urine samples from 106 infertile males and 100 fertile males, as controls, were analyzed. Specific PCR analyses were carried out to detect and quantify large T (Tag) coding sequences of JCV and BKV. DNA sequencing, carried out in Tag JCV-positive samples, was addressed to viral protein 1 (VP1) coding sequences. The prevalence of JCV Tag sequences in semen and urine samples from infertile males was 34% (72/212), whereas the BKV prevalence was 0.94% (2/212). Specifically, JCV Tag sequences were detected in 24.5% (26/106) of semen and 43.4% (46/106) of urine samples from infertile men. In semen and urine samples from controls the prevalence was 11% and 28%, respectively. A statistically significant difference (p<0.05) in JCV prevalence was disclosed in semen and urine samples of cases vs. controls. A higher JC viral DNA load was detected in samples from infertile males than in controls. In samples from infertile males the JC virus type 2 strain, subtype 2b, was more prevalent than ubiquitous type 1. JCV type 2 strain infection has been found to be associated with male infertility. These data suggest that the JC virus should be taken into consideration as an infectious agent which is responsible for male infertility.
Keywords: Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; BK Virus; Capsid Proteins; DNA, Viral; Humans; Infertility, Male; JC Virus; Male; Molecular Sequence Data; Polyomavirus Infections; Semen; Sequence Analysis, DNA; Tumor Virus Infections

Autoimmune-polyendocrinopathy-candidiasis-ectodermal-dystrophy in Calabria: clinical, immunological and genetic patterns. - Betterle, C; Ghizzoni, L; Cassio, A; Baronio, F; Cervato, S; Garelli, S; Barbi, E; Tonini, G (J Endocrinol Invest, 2012)
UNLABELLED: Autoimmune polyendocrinopathy-candidiasis-ectodermal- dystrophy (APECED), also known as autoimmune polyendocrine syndrome type 1 (APS-1), is a very rare disease. Diagnosis requires the presence of at least two of three major clinical features: chronic mucocutaneous candidiasis, chronic hypoparathyroidism, and Addison's disease. DESIGN: In this study, we analyzed Autoimmune Regulator (AIRE) gene mutations and genotype-phenotype correlation in APECED patients originating from Calabria, a region in the south of Italy. PATIENTS AND METHODS: Four patients and their first-degree relatives were evaluated for clinical manifestations, autoantibody presence and AIRE gene mutations. RESULTS: Three patients carried a homozygous W78R mutation on exon 2, typical of patients with APECED from Apulia; the fourth patient had a homozygous R203X mutation on exon 5, typical of APECED patients from Sicily. Clinical disease expression showed wide variability. Analysis of relatives allowed the identification of 6 heterozygotes, none of whom showed major findings of APECED. CONCLUSIONS: No AIRE gene mutations specific to Calabria were found in patients with APS-1, but mutations similar to those in patients from Apulia and Sicily. Heterozygosity for AIRE gene mutation is not associated with major findings of APECED.
Keywords: Adolescent; Adult; Autoantibodies; Child; Female; Genetic Association Studies; Heterozygote; Homozygote; Humans; Italy; Male; Mutation; Polyendocrinopathies, Autoimmune; Prognosis; Sicily; Transcription Factors; Young Adult

Burden of disease caused by otitis media: systematic review and global estimates. - Monasta, Lorenzo; Ronfani, Luca; Marchetti, Federico; Montico, Marcella; Vecchi Brumatti, Liza; Bavcar, Alessandro; Grasso, Domenico; Barbiero, Chiara; Tamburlini, Giorgio (PLoS One, 2012)
BACKGROUND: Otitis media (OM) is a leading cause of health care visits and drugs prescription. Its complications and sequelae are important causes of preventable hearing loss, particularly in developing countries. Within the Global Burden of Diseases, Injuries, and Risk Factors Study, for the year 2005 we estimated the incidence of acute OM, chronic suppurative OM, and related hearing loss and mortality for all ages and the 21 WHO regional areas. METHODS: We identified risk factors, complications and sequelae of OM. We carried out an extensive literature review (Medline, Embase, Lilacs and Wholis) which lead to the selection of 114 papers comprising relevant data. Data were available from 15 of the 21 WHO regions. To estimate incidence and prevalence for all countries we adopted a two stage approach based on risk factors formulas and regression modelling. RESULTS: Acute OM incidence rate is 10.85% i.e. 709 million cases each year with 51% of these occurring in under-fives. Chronic suppurative OM incidence rate is 4.76 ‰ i.e. 31 million cases, with 22.6% of cases occurring annually in under-fives. OM-related hearing impairment has a prevalence of 30.82 per ten-thousand. Each year 21 thousand people die due to complications of OM. CONCLUSIONS: Our study is the first attempt to systematically review the available information and provide global estimates for OM and related conditions. The overall burden deriving from AOM, CSOM and their sequelae is considerable, particularly in the first five years of life and in the poorest countries. The findings call for incorporating OM-focused action within preventive and case management strategies, with emphasis on the more affected.
Keywords: Cost of Illness; Hearing Loss; Humans; Internationality; Otitis Media

A case of familial hemiplegic migraine associated with a novel ATP1A2 gene mutation. - De Cunto, Angela; Bensa, Marco; Tonelli, Alessandra (Pediatr Neurol, 2012)
Hemiplegic migraine constitutes an unusual form, characterized by periodic attacks of migraine with a motor component (hemiplegia). Familial forms are dominantly inherited, and are attributable to mutations in genes encoding proteins involved in ion transportation, including ATP1A2, which codes for the α-2 isoform of the sodium-potassium adenosine triphosphatase, a P-type cation transport adenosine triphosphatase, and responsible for the so-called familial hemiplegic migraine type 2. We describe a 9-year-old boy affected by familial hemiplegic migraine, with a novel ATP1A2 gene mutation (c.1799T>C p.V600A) in exon 13. Long-term treatment with flunarizine resulted in a good clinical response and the prevention of further attacks.
Keywords: Amino Acid Sequence; Child, Preschool; Humans; Male; Migraine with Aura; Molecular Sequence Data; Mutation; Pedigree; Sodium-Potassium-Exchanging ATPase

Chemerin regulates NK cell accumulation and endothelial cell morphogenesis in the decidua during early pregnancy. - Carlino, Claudia; Trotta, Eleonora; Stabile, Helena; Morrone, Stefania; Bulla, Roberta; Soriani, Alessandra; Iannitto, Maria Luisa; Agostinis, Chiara; Mocci, Carlo; Minozzi, Massimo; Aragona, Cesare; Perniola, Giorgia; et al. (J Clin Endocrinol Metab, 2012)
CONTEXT: Although decidual natural killer (NK) cell accumulation and vascular remodeling are critical steps to ensure successful pregnancy, the molecular mechanisms controlling these events are poorly defined. OBJECTIVE: Herein we analyzed whether chemerin, a recently identified chemoattractant involved in many pathophysiological processes, could be expressed in the uterine compartment and could regulate events relevant for the good outcome of pregnancy. DESIGN: Chemerin expression in human primary culture of stromal (ST) cells, extravillous trophoblast cells, and decidual endothelial cells (DEC) was analyzed by RT-PCR, ELISA, and Western blot. Migration through ST or DEC of peripheral blood and decidual (d) NK cells from pregnant women was performed using a transwell assay. A DEC capillary-like tube formation assay was used to evaluate endothelial morphogenesis. RESULTS: Chemerin is differentially expressed by decidual cells during early pregnancy being present at high levels in ST and extravillous trophoblast cells but not in DEC. Notably, ST cells from pregnant women exhibit and release higher levels of chemerin as compared with ST cells from menopausal or fertile nonpregnant women. Chemerin can support peripheral blood NK cell migration through both DEC and ST cells. Although dNK cells exhibit lower chemerin receptor (CMKLR1) expression than their blood counterpart, CMKLR1 engagement on dNK cells resulted in both ERK activation and migration through decidual ST cells. Interestingly, DEC also express CMKLR1 and undergo ERK activation and capillary-like tube structure formation upon exposure to chemerin. CONCLUSIONS: Our data indicate that chemerin is up-regulated during decidualization and might contribute to NK cell accumulation and vascular remodeling during early pregnancy.
Keywords: Capillaries; Cell Movement; Chemokines; Decidua; Endothelial Cells; Female; Humans; Killer Cells, Natural; MAP Kinase Signaling System; Neovascularization, Physiologic; Pregnancy; Pregnancy Trimester, First; Receptors, Chemokine; RNA, Messenger; Stromal Cells; Trophoblasts

Coeliac disease diagnosis: ESPGHAN 1990 criteria or need for a change? Results of a questionnaire. - Ribes-Koninckx, C; Mearin, M L; Korponay-Szabó, I R; Shamir, R; Husby, S; Ventura, A; Branski, D; Catassi, C; Koletzko, S; Mäki, M; Troncone, R; Zimmer, K P (J Pediatr Gastroenterol Nutr, 2012)
BACKGROUND AND OBJECTIVES: A revision of criteria for diagnosing coeliac disease (CD) is being conducted by The European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN). In parallel, we have performed a survey aimed to evaluate present practices for CD among paediatric gastroenterologists and to learn their views on the need for modification of present criteria for CD diagnosis. PATIENTS AND METHODS: Questionnaires were distributed to experienced paediatric gastroenterologists (ESPGHAN members) via the Internet. RESULTS: Overall, 95 valid questionnaires were available for analysis, pertaining to 28 different countries, with the majority of responders treating patients with CD for >15 years. Only about 12% of the responders comply with present criteria, noncompliance being related mainly to the challenge policy. Approximately 90% request a revision and modification of the present criteria. Forty-four percent want to omit the small bowel biopsy in symptomatic children with positive anti-tissue transglutaminase immunoglobulin (Ig) A or endomysial IgA antibodies, especially if they are DQ2/DQ8 positive. For silent cases detected by screening with convincingly positive anti-tissue transglutaminase IgA or EMA IgA, about 30% consider that no small bowel biopsy should be required in selected cases. Adding human leukocyte antigen typing in the diagnostic workup was asked for by 42% of the responders. As for gluten challenge, a new policy is advocated restricting its obligation to cases whenever the diagnosis is doubtful or unclear. CONCLUSIONS: Based on these opinions, revision of the ESPGHAN criteria for diagnosing CD is urgently needed.
Keywords: Adolescent; Adult; Biopsy; Celiac Disease; Child; Child, Preschool; Glutens; Guideline Adherence; Guidelines as Topic; Health Care Surveys; Humans; Immunoglobulin A; Intestine, Small; Physician's Practice Patterns; Questionnaires; Societies, Medical; Transglutaminases; Young Adult

A common genetic background could explain early-onset Crohn's disease. - Bianco, Anna Monica; Zanin, Valentina; Girardelli, Martina; Magnolato, Andrea; Martelossi, Stefano; Martellossi, Stefano; Tommasini, Alberto; Marcuzzi, Annalisa; Crovella, Sergio (Med Hypotheses, 2012)
Crohn's disease (CD) is a multifactorial disease, in which environmental, microbial and genetic factors play important roles. CD is characterized by a chronic granulomatous inflammation by necrotic scarring with aspects of full-thickness wall. In spite of affecting mainly young adults, sometimes, CD can be present in the first year of life (early onset Crohn disease, EOCD) showing an unpredictable course and being often more severe than at older ages. In this paper we propose the hypothesis that EOCD patients should be analyzed using a Mendelian approach with family studies aimed to identify new loci directly involved in the early onset Crohn's disease. So we will leave the classic association study approach used until now for the identification of genes responsible for susceptibility to CD and propose linkage family analysis as alternative and powerful tool for the identification of new genetic variants associated with familiar cases of EOCD.
Keywords: Crohn Disease; Genetic Linkage; Genetic Predisposition to Disease; Humans; Models, Biological

Comparison of hybrid capture II, linear array, and a bead-based multiplex genotyping assay for detection of human papillomavirus in women with negative pap test results and atypical squamous cells of undetermined significance. - Comar, Manola; Iannacone, Michelle R; Casalicchio, Giorgia; McKay-Chopin, Sandrine; Tommasino, Massimo; Gheit, Tarik (J Clin Microbiol, 2012)
Many methods with different levels of analytical sensitivity and clinical specificity have been developed to detect the presence of high-risk (HR) types of the human papillomavirus (HPV) in cervical samples. The Hybrid Capture II (HC-II) assay is broadly used for primary screening. In addition, several HPV genotyping assays, based on PCR methods, display higher sensitivity than the HC-II and are also used in screening programs. We evaluated the performance of three HPV DNA tests, namely, the HC-II, the Linear Array (LA) HPV genotyping assay, and an HPV type-specific E7 PCR bead-based multiplex genotyping assay (TS-MPG) that is a laboratory-developed method for the detection of HPV, in 94 women with atypical squamous cells of undetermined significance (ASC-US) and in cytological samples from 86 women with a negative Pap test. The HPV prevalence with the TS-MPG assay was increased compared to the prevalence with the LA and HC-II assays. The HPV DNA prevalence in women with ASC-US was greater with the TS-MPG assay (46.2%) than with the LA (36.3%) and HC-II (29.7%) assays. The HPV DNA prevalence in the control group was greater with the TS-MPG assay (32.1%) than with the LA assay (10.7%). Two women with ASC-US who were HPV DNA negative by the HC-II and positive by the TS-MPG or/and LA assays had lesions that progressed to low-grade squamous intraepithelial and high-grade squamous intraepithelial lesions. This study shows that the TS-MPG assay exhibited higher analytical sensitivity than the LA and HC-II assays for the detection of HPV DNA, which reduces the potential to incorrectly identify a woman's HPV infection status.
Keywords: Adult; DNA, Viral; Female; Humans; Molecular Diagnostic Techniques; Papillomavirus Infections; Sensitivity and Specificity; Uterine Cervical Neoplasms; Virology

Congenital hemangiopericytoma. - Travan, Laura; Demarini, Sergio; Del Frate, Giovanni; Zacchi, Alberto (J Pediatr, 2012)
Keywords: Biopsy, Needle; Female; Gestational Age; Hemangiopericytoma; Humans; Immunohistochemistry; Infant, Newborn; Magnetic Resonance Imaging; Pregnancy; Prognosis; Risk Assessment; Soft Tissue Neoplasms; Treatment Outcome; Ultrasonography, Prenatal

Dealing with abdominal pain in children affected by systemic lupus erythematosus. - Taddio, Andrea; Rosé, Carlos; Lepore, Loredana; Ventura, Alessandro (Semin Arthritis Rheum, 2012)
Keywords: Abdominal Pain; Female; Humans; Lupus Erythematosus, Systemic; Male

DEFB1 gene 5' untranslated region (UTR) polymorphisms in inflammatory bowel diseases. - Zanin, Valentina; Segat, Ludovica; Bianco, Anna Monica; Padovan, Lara; Tavares, Nathalia de Alencar Cunha; Crovella, Sergio (Clinics (Sao Paulo), 2012)
Keywords: 5' Untranslated Regions; Adult; Antimicrobial Cationic Peptides; beta-Defensins; Case-Control Studies; Colitis, Ulcerative; Crohn Disease; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Inflammatory Bowel Diseases; Male; Polymorphism, Genetic; Polymorphism, Single Nucleotide

Defective and excessive immunities in pediatric diseases. - Notarangelo, Luigi Daniele; Tommasini, Alberto (Curr Pharm Des, 2012)
Inflammatory and autoimmune diseases are classically considered as disorders arising from hyper-activation of immunity and hence are treated with drugs that suppress the lymphocyte activation and inflammation. Although this strategy has proven useful to cure symptoms, it rarely can heal the disease and long-term treatments are usually needed. Inflammatory and autoimmune diseases frequently occur also in patients with primary immune deficiency disease, proving that immune hyper-activation may paradoxically arise from defective function of immune genes. In these cases, the phenotype of hyper-activation is believed to reflect the attempts of the immune system to compensate for immune defects. Recent data suggest that similar mechanisms could be involved also in the pathogenesis of some multifactorial disorders, such as Crohn's disease and systemic lupus erythematosus. Based on these considerations, novel therapies could be developed to cure severe autoimmune and inflammatory disorders, not only by aiming to hyper-activation but as well by focusing on the possible underlying immune defects.
Keywords: Autoimmune Diseases; Child; Drug Design; Humans; Immunologic Deficiency Syndromes; Inflammation; Lymphocyte Activation; Severity of Illness Index

Does the LATCH score assessed in the first 24 hours after delivery predict non-exclusive breastfeeding at hospital discharge? - Tornese, Gianluca; Ronfani, Luca; Pavan, Carla; Demarini, Sergio; Monasta, Lorenzo; Davanzo, Riccardo (Breastfeed Med, 2012)
AIM: The aims of this study were to analyze the relationship between the LATCH score assessed in the first 24 hours after delivery and non-exclusive breastfeeding at discharge and to identify a cutoff for the LATCH score in order to identify women with higher risk of non-exclusive breastfeeding who may need additional breastfeeding support. SUBJECTS AND METHODS: We conducted a prospective observational study in the Maternity Ward of the Institute for Maternal and Child Health "Burlo Garofolo" (Trieste, Italy) and collected data from 299 mother-infant dyads. RESULTS: The rate of nonexclusive breastfeeding was inversely related to the LATCH score (p<0.001) with non-exclusive breastfeeding infants scoring less (6.9) than infants exclusively breastfed at discharge (7.6) (p=0.001). In multivariate analysis, non-exclusive breastfeeding was also associated with cesarean section, primiparity, and infant phototherapy. In order to support maternity staff in providing targeted interventions, we identified four LATCH score cutoffs associated with as many risk groups for non-exclusive breastfeeding at discharge. CONCLUSIONS: The LATCH score is a useful tool to identify mother-infant pairs who might benefit from additional skilled support in specific subgroups at risk of non-exclusive breastfeeding at discharge. Future research is needed to explore if the LATCH score assessed in the first days of life can also predict the duration of breastfeeding.
Keywords: Adult; Breast Feeding; Female; Health Promotion; Humans; Infant, Newborn; Italy; Logistic Models; Multivariate Analysis; Patient Care Planning; Patient Discharge; Prospective Studies; Risk Assessment; ROC Curve; Sensitivity and Specificity; Social Support

Effects of prone and supine position on cerebral blood flow in preterm infants. - Bembich, Stefano; Oretti, Chiara; Travan, Laura; Clarici, Andrea; Massaccesi, Stefano; Demarini, Sergio (J Pediatr, 2012)
We evaluated the effect of prone and supine position on cerebral blood flow (CBF) in stable preterm infants. CBF, PO(2), and PCO(2) were measured in the two positions. Peripheral oxygenation increased and CBF decreased in prone position. We speculate that CBF autoregulation may compensate for increased peripheral oxygenation, by decreasing CBF.
Keywords: Cerebrovascular Circulation; Female; Humans; Infant, Newborn; Infant, Premature; Male; Prone Position; Regional Blood Flow; Supine Position

Efficacy of rifaximin vaginal tablets in treatment of bacterial vaginosis: a molecular characterization of the vaginal microbiota. - Cruciani, Federica; Brigidi, Patrizia; Calanni, Fiorella; Lauro, Vittoria; Tacchi, Raffaella; Donders, Gilbert; Peters, Klaus; Guaschino, Secondo; Vitali, Beatrice (Antimicrob Agents Chemother, 2012)
Bacterial vaginosis (BV) is a common vaginal disorder characterized by an alteration of the vaginal bacterial morphotypes, associated with sexually transmitted infections and adverse pregnancy outcomes. The purpose of the present study was to evaluate the impact of different doses of rifaximin vaginal tablets (100 mg/day for 5 days, 25 mg/day for 5 days, and 100 mg/day for 2 days) on the vaginal microbiota of 102 European patients with BV enrolled in a multicenter, double-blind, randomized, placebo-controlled study. An integrated molecular approach based on quantitative PCR (qPCR) and PCR-denaturing gradient gel electrophoresis (PCR-DGGE) was used to investigate the effects of vaginal tablets containing the antibiotic. An increase in members of the genus Lactobacillus and a decrease in the BV-related bacterial groups after the antibiotic treatment were demonstrated by qPCR. PCR-DGGE profiles confirmed the capability of rifaximin to modulate the composition of the vaginal microbial communities and to reduce their complexity. This molecular analysis supported the clinical observation that rifaximin at 25 mg/day for 5 days represents an effective treatment to be used in future pivotal studies for the treatment of BV.
Keywords: Adolescent; Adult; Anti-Bacterial Agents; Double-Blind Method; Female; Humans; Lactobacillus; Metagenome; Middle Aged; Rifamycins; RNA, Ribosomal, 16S; Vagina; Vaginal Creams, Foams, and Jellies; Vaginosis, Bacterial; Young Adult

Endothelial cells obtained from patients affected by chronic venous disease exhibit a pro-inflammatory phenotype. - Tisato, Veronica; Zauli, Giorgio; Voltan, Rebecca; Gianesini, Sergio; di Iasio, Maria Grazia; Volpi, Ilaria; Fiorentini, Guido; Zamboni, Paolo; Secchiero, Paola (PLoS One, 2012)
BACKGROUND: The inflammatory properties of vein endothelium in relation to chronic venous disease (CVD) have been poorly investigated. Therefore, new insights on the characteristics of large vein endothelium would increase our knowledge of large vessel physiopathology. METHODOLOGY/PRINCIPAL FINDINGS: Surgical specimens of veins were obtained from the tertiary venous network (R3) and/or saphenous vein (SF) of patients affected by CVD and from control individuals. Highly purified venous endothelial cell (VEC) cultures obtained from CVD patients were characterized for morphological, phenotypic and functional properties compared to control VEC. An increase of CD31/PECAM-1, CD146 and ICAM-1 surface levels was documented at flow cytometry in pathological VEC with respect to normal controls. Of note, the strongest expression of these pro-inflammatory markers was observed in VEC obtained from patients with more advanced disease. Similarly, spontaneous cell proliferation and resistance to starvation was higher in pathological than in normal VEC, while the migratory response of VEC showed an opposite trend, being significantly lower in VEC obtained from pathological specimens. In addition, in keeping with a higher baseline transcriptional activity of NF-kB, the release of the pro-inflammatory cytokines osteoprotegerin (OPG) and vascular endothelial growth factor (VEGF) was higher in pathological VEC cultures with respect to control VEC. Interestingly, there was a systemic correlation to these in vitro data, as demonstrated by higher serum OPG and VEGF levels in CVD patients with respect to normal healthy controls. CONCLUSION/SIGNIFICANCE: Taken together, these data indicate that large vein endothelial cells obtained from CVD patients exhibit a pro-inflammatory phenotype, which might significantly contribute to systemic inflammation in CVD patients.
Keywords: Adult; Antigens, CD146; Antigens, CD31; Body Mass Index; Cell Culture Techniques; Endothelial Cells; Female; Flow Cytometry; Humans; Inflammation; Intercellular Adhesion Molecule-1; Kinetics; Male; Microscopy, Electron, Scanning; Middle Aged; Phenotype; Saphenous Vein; Vascular Diseases

The energy balance positively regulates the levels of circulating TNF-related apoptosis inducing ligand in humans. - Biolo, Gianni; Secchiero, Paola; De Giorgi, Sara; Tisato, Veronica; Zauli, Giorgio (Clin Nutr, 2012)
BACKGROUND & AIMS: Although decreased levels of circulating TRAIL have been associated to cardiovascular risk and overall mortality, the mechanisms controlling TRAIL levels in physiopathological conditions are currently unknown. The aim of the present study was to investigate whether changes in the energy intake and insulin sensitivity may influence circulating TRAIL, and to analyze potential relationships between circulating TRAIL and changes in fat mass in healthy subjects receiving hypocaloric or hypercaloric diets. METHODS: Three distinct groups of participants were studied, at the end of a 14-day (n = 9), 35-day (n = 30) or 60-day (n = 16) period of experimental bed rest to induce insulin resistance and during controlled ambulation, after receiving eucaloric, hypocaloric or hypercaloric diets. RESULTS: After bed rest conditions, energy restriction significantly decreased circulating TRAIL, while overfeeding significantly increased TRAIL levels with respect to eucaloric control subjects. Moreover, a positive correlation was found between levels of circulating TRAIL and energy intake as well as between circulating TRAIL and energy balance, as determined by changes in fat mass in these subjects. CONCLUSIONS: Circulating levels of TRAIL exhibit a clear-cut positive correlation with the energy intake and balance in healthy subjects during experimental physical inactivity.
Keywords: Adult; Apoptosis; Bed Rest; Cross-Over Studies; Diet; Energy Intake; Energy Metabolism; Female; Humans; Insulin Resistance; Male; Motor Activity; Risk Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

European Society for Pediatric Gastroenterology, Hepatology, and Nutrition guidelines for the diagnosis of coeliac disease. - Husby, S; Koletzko, S; Korponay-Szabó, I R; Mearin, M L; Phillips, A; Shamir, R; Troncone, R; Giersiepen, K; Branski, D; Catassi, C; Lelgeman, M; Mäki, M; et al. (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: Diagnostic criteria for coeliac disease (CD) from the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) were published in 1990. Since then, the autoantigen in CD, tissue transglutaminase, has been identified; the perception of CD has changed from that of a rather uncommon enteropathy to a common multiorgan disease strongly dependent on the haplotypes human leukocyte antigen (HLA)-DQ2 and HLA-DQ8; and CD-specific antibody tests have improved. METHODS: A panel of 17 experts defined CD and developed new diagnostic criteria based on the Delphi process. Two groups of patients were defined with different diagnostic approaches to diagnose CD: children with symptoms suggestive of CD (group 1) and asymptomatic children at increased risk for CD (group 2). The 2004 National Institutes of Health/Agency for Healthcare Research and Quality report and a systematic literature search on antibody tests for CD in paediatric patients covering the years 2004 to 2009 was the basis for the evidence-based recommendations on CD-specific antibody testing. RESULTS: In group 1, the diagnosis of CD is based on symptoms, positive serology, and histology that is consistent with CD. If immunoglobulin A anti-tissue transglutaminase type 2 antibody titers are high (>10 times the upper limit of normal), then the option is to diagnose CD without duodenal biopsies by applying a strict protocol with further laboratory tests. In group 2, the diagnosis of CD is based on positive serology and histology. HLA-DQ2 and HLA-DQ8 testing is valuable because CD is unlikely if both haplotypes are negative. CONCLUSIONS: The aim of the new guidelines was to achieve a high diagnostic accuracy and to reduce the burden for patients and their families. The performance of these guidelines in clinical practice should be evaluated prospectively.
Keywords: Adolescent; Celiac Disease; Child; Duodenum; HLA-DQ Antigens; Humans; Immunoglobulin A; Transglutaminases

Evidence of inbreeding depression on human height. - McQuillan, Ruth; Eklund, Niina; Pirastu, Nicola; Kuningas, Maris; McEvoy, Brian P; Esko, Tõnu; Corre, Tanguy; Davies, Gail; Kaakinen, Marika; Lyytikäinen, Leo-Pekka; Kristiansson, Kati; Havulinna, Aki S; et al. (PLoS Genet, 2012)
Stature is a classical and highly heritable complex trait, with 80%-90% of variation explained by genetic factors. In recent years, genome-wide association studies (GWAS) have successfully identified many common additive variants influencing human height; however, little attention has been given to the potential role of recessive genetic effects. Here, we investigated genome-wide recessive effects by an analysis of inbreeding depression on adult height in over 35,000 people from 21 different population samples. We found a highly significant inverse association between height and genome-wide homozygosity, equivalent to a height reduction of up to 3 cm in the offspring of first cousins compared with the offspring of unrelated individuals, an effect which remained after controlling for the effects of socio-economic status, an important confounder (χ(2) = 83.89, df = 1; p = 5.2 × 10(-20)). There was, however, a high degree of heterogeneity among populations: whereas the direction of the effect was consistent across most population samples, the effect size differed significantly among populations. It is likely that this reflects true biological heterogeneity: whether or not an effect can be observed will depend on both the variance in homozygosity in the population and the chance inheritance of individual recessive genotypes. These results predict that multiple, rare, recessive variants influence human height. Although this exploratory work focuses on height alone, the methodology developed is generally applicable to heritable quantitative traits (QT), paving the way for an investigation into inbreeding effects, and therefore genetic architecture, on a range of QT of biomedical importance.
Keywords: Adult; Aged; Body Height; Consanguinity; Databases, Genetic; Family; Female; Genes, Recessive; Genetic Heterogeneity; Genome-Wide Association Study; Homozygote; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Febrile urinary tract infections in young children: recommendations for the diagnosis, treatment and follow-up. - Ammenti, Anita; Cataldi, Luigi; Chimenz, Roberto; Fanos, Vassilios; La Manna, Angela; Marra, Giuseppina; Materassi, Marco; Pecile, Paolo; Pennesi, Marco; Pisanello, Lorena; Sica, Felice; Toffolo, Antonella; et al. (Acta Paediatr, 2012)
UNLABELLED: We report the recommendations for the diagnosis, treatment, imaging evaluation and use of antibiotic prophylaxis in children with the first febrile urinary tract infection, aged 2 months to 3 years. They were prepared by a working group of the Italian Society of Pediatric Nephrology after careful review of the available literature and a consensus decision, when clear evidence was not available. CONCLUSION: These recommendations are endorsed by the Italian Society of Pediatric Nephrology. They can also be a tool of comparison with other existing guidelines in issues in which much controversy still exists.
Keywords: Anti-Bacterial Agents; Child, Preschool; Female; Fever; Follow-Up Studies; Humans; Infant; Male; Urinary Tract Infections

From bone marrow transplantation to cellular therapies: possible therapeutic strategies in managing autoimmune disorders. - Taddio, Andrea; Biondi, Andrea; Piscianz, Elisa; Valencic, Erica; Biagi, Ettore; Badolato, Raffaele (Curr Pharm Des, 2012)
Chronic inflammatory disorders occurring in childhood represent a serious therapeutic challenge. However, available therapies seem not to be targeted on the pathogenic mechanism of the disease and are often not actively affecting the natural history of the disease. Emerging treatments might be of some benefit to many patients who did not respond to conventional therapeutic options. Biological therapies with monoclonal antibodies and other recombinant proteins have been introduced in clinical practice. At the same time, mesenchymal stromal cells (MSC) have gained attention as a savage treatment in patients subjected to hematopoietic stem cell transplantation who develop severe graft versus host disease (GvHD); in addition, recent reports from clinical trials on larger cohorts of patients support their use as second-line treatment after failure of corticosteroid treatment. For analogy, they have been proposed for the treatment of intractable autoimmune disorders. Hematopoietic stem cell transplantation (HSCT) has been shown to be effective for treatment of rheumatic disorder cases that were resistant to traditional therapies especially if combined with cell manipulation techniques, such as selection of regulatory T cell and depletion of harmful lymphocytes. We herein present the rationale of different strategies, the preliminary data obtained in clinical trials, unsolved problems and possible next developments of novel treatment protocols of autoimmune disorders.
Keywords: Autoimmune Diseases; Bone Marrow Transplantation; Child; Chronic Disease; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Inflammation; Lymphocytes; Mesenchymal Stem Cell Transplantation; T-Lymphocytes, Regulatory; Treatment Outcome

Genetics of food preferences: a first view from silk road populations. - Pirastu, Nicola; Robino, Antonietta; Lanzara, Carmela; Athanasakis, Emmanouil; Esposito, Laura; Tepper, Beverly J; Gasparini, Paolo (J Food Sci, 2012)
Food preferences are the main factor driving food intake and choice. There are good reasons to suspect some genetic influence on food acceptance, not least because genetic factors are implicated in a number of factors that are likely to be related to food choice. In addition, some food dislikes show themselves early in life, before there is any evidence for aversive experiences. Although taste has been widely studied in regards of pure tastes such as bitter or sweet perception, the relationship between taste-related genes and food preferences has seldom been explored. In this work we investigated relationship of 37 taste-related genes with food preferences. The study was carried out during a scientific expedition through Caucasus and Central Asia (Silk Road) analyzing more than 400 samples from 5 different countries. A food preference questionnaire was administered to each participant and a DNA sample was obtained. Other information, such as age, sex, life style and anthropometrical measures, were also collected. We found significant associations with variants of: (1) TAS1R2 [Correction added after initial online publication on 27 Aug 2012. TAS1R3 was changed to TAS1R2.] gene and liking of Vodka (P= 1.6 × 10(-3)), white wine (P= 4.0 × 10(-4)) and lamb meat (P= 1.6 × 10(-3)); (2) PCLB2 gene and preference for Hot Tea (P= 8.0 × 10(-4)); (3) TPRV1 gene and beet liking (P= 3.8 × 10(-5)); and (4) ITPR3 gene and liking of both lamb meat (5.8 × 10(-4)) and sheep cheese (8.9×10(-4)). These findings give a new insight on a better understanding, of genetic factors influencing food preferences which is critical to the development of effective dietary interventions, especially for people that may be genetically not predisposed for liking specific nutrients.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Azerbaijan; Child; Choice Behavior; Cohort Studies; Female; Food Habits; Food Preferences; Gene Frequency; Genotype; Georgia; Humans; Kazakhstan; Linear Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Questionnaires; Tajikistan; Taste; Uzbekistan; Young Adult

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Genomic profiling by whole-genome single nucleotide polymorphism arrays in Wilms tumor and association with relapse. - Perotti, Daniela; Spreafico, Filippo; Torri, Federica; Gamba, Beatrice; d'Adamo, Pio; Pizzamiglio, Sara; Terenziani, Monica; Catania, Serena; Collini, Paola; Nantron, Marilina; Pession, Andrea; Bianchi, Maurizio; et al. (Genes Chromosomes Cancer, 2012)
Despite the excellent survival rate of Wilms tumor (WT) patients, only approximately one-half of children who suffer tumor recurrence reach second durable remission. This underlines the need for novel markers to optimize initial treatment. We investigated 77 tumors using Illumina 370CNV-QUAD genotyping BeadChip arrays and compared their genomic profiles to detect copy number (CN) abnormalities and allelic ratio anomalies associated with the following clinicopathological variables: relapse (yes vs. no), age at diagnosis (≤ 24 months vs. >24 months), and disease stage (low stage, I and II, vs. high stage, III and IV). We found that CN gains at chromosome region 1q21.1-q31.3 were significantly associated with relapse. Additional genetic events, including allelic imbalances at chromosome arms 1p, 1q, 3p, 3q, and 14q were also found to occur at higher frequency in relapsing tumors. Interestingly, allelic imbalances at 1p and 14q also showed a borderline association with higher tumor stages. No genetic events were found to be associated with age at diagnosis. This is the first genome wide analysis with single nucleotide polymorphism (SNP) arrays specifically investigating the role of genetic anomalies in predicting WT relapse on cases prospectively enrolled in the same clinical trial. Our study, besides confirming the role of 1q gains, identified a number of additional candidate genetic markers, warranting further molecular investigations.
Keywords: Adolescent; Allelic Imbalance; Child; Child, Preschool; Chromosome Aberrations; DNA Copy Number Variations; Female; Genetic Markers; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Infant; Kaplan-Meier Estimate; Male; Polymorphism, Single Nucleotide; Prospective Studies; Recurrence; Wilms Tumor

High prevalence of serum antibodies reacting with simian virus 40 capsid protein mimotopes in patients affected by malignant pleural mesothelioma. - Mazzoni, Elisa; Corallini, Alfredo; Cristaudo, Alfonso; Taronna, Angelo; Tassi, Gianfranco; Manfrini, Marco; Comar, Manola; Bovenzi, Massimo; Guaschino, Roberto; Vaniglia, Francesca; Magnani, Corrado; Casali, Ferruccio; et al. (Proc Natl Acad Sci U S A, 2012)
Human malignant pleural mesothelioma (MPM) is considered a rare tumor, but recent estimations indicate that one-quarter million people will die of this neoplasm in Europe in the next three decades. The mineral asbestos is considered the main causative agent of this neoplasm. MPM is largely unresponsive to conventional chemotherapy/radiotherapy. In addition to asbestos exposure, genetic predisposition to asbestos carcinogenesis and to simian virus (SV)40 infection has also been suggested. SV40 is a DNA tumor virus found in some studies to be associated at high prevalence with MPM. SV40 sequences have also been detected, although at a lower prevalence than in MPM, in blood specimens from healthy donors. However, some studies have failed to reveal SV40 footprints in MPM and its association with this neoplasm. These conflicting results indicate the need for further investigations with new approaches. We report on the presence of antibodies in serum samples from patients affected by MPM that specifically react with two different SV40 mimotopes. The two SV40 peptides used in indirect ELISAs correspond to viral capsid proteins. ELISA with the two SV40 mimotopes gave overlapping results. Our data indicate that in serum samples from MPM-affected patients (n = 97), the prevalence of antibodies against SV40 viral capsid protein antigens is significantly higher (26%, P = 0.043) than in the control group (15%) represented by healthy subjects (n = 168) with the same median age (66 y) and sex. Our results suggest that SV40 is associated with a subset of MPM and circulates in humans.
Keywords: Amino Acid Sequence; Antibodies, Viral; Capsid Proteins; Enzyme-Linked Immunosorbent Assay; Female; Humans; Male; Mesothelioma; Molecular Sequence Data; Pleural Neoplasms; Pregnancy; Simian virus 40

How the newly introduced compression, airway, and breathing sequence affects the training in pediatric cardiopulmonary resuscitation. - Lubrano, Riccardo; Messi, Gianni; Elli, Marco (Am J Emerg Med, 2012)
Keywords: Cardiopulmonary Resuscitation; Clinical Competence; Feedback; Female; Heart Massage; Humans; Inservice Training; Male

Immunomodulatory drugs in autoimmune lymphoproliferative syndrome (ALPS). - Tommasini, Alberto; Valencic, Erica; Piscianz, Elisa; Rabusin, Marco (Pediatr Blood Cancer, 2012)
Keywords: Antineoplastic Agents; Autoimmune Lymphoproliferative Syndrome; Diseases in Twins; Humans; Male; Pentostatin

Inflammation profile of four early onset Crohn patients. - Marcuzzi, Annalisa; Girardelli, Martina; Bianco, Anna Monica; Martelossi, Stefano; Magnolato, Andrea; Tommasini, Alberto; Crovella, Sergio (Gene, 2012)
Crohn disease (CD) is a multifactorial disorder affecting mainly young adults. Sometimes, however, it can present in the first year of life (Early onset Crohn disease (EOCD)) showing an unpredictable course and can often be more severe than at older ages. Some cases have been associated to an underlying primary immunodeficiency such as IL10R deficiency. We studied the functional response to IL-10 and the genotype of IL-10 receptor in four patients with early onset crohn-like colitis. We found an IL10R variant, which may be associated with a decreased response to the cytokine in one patient. Further studies to determine its pathogenic effect should be performed. In addition IL-10 mediated inhibition of LPS-induced TNFα expression was measured in patient's monocytes.
Keywords: Crohn Disease; Cytokines; Humans; Inflammation; Monocytes; Nod2 Signaling Adaptor Protein; Polymorphism, Genetic; Receptors, Interleukin-10; Tumor Necrosis Factor-alpha

Influence of age, sex and ethnicity on platelet count in five Italian geographic isolates: mild thrombocytopenia may be physiological. - Biino, Ginevra; Gasparini, Paolo; d'Adamo, Pio; Ciullo, Marina; Nutile, Teresa; Toniolo, Daniela; Sala, Cinzia; Minelli, Cosetta; Gögele, Martin; Balduini, Carlo L (Br J Haematol, 2012)
Keywords: Adolescent; Adult; Age Distribution; Aged; Aged, 80 and over; Child; Child, Preschool; Female; Humans; Infant; Italy; Male; Middle Aged; Platelet Count; Reference Values; Sex Distribution; Thrombocytopenia; Young Adult

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide

JCV+ Patients with Inflammatory bowel disease show elevated plasma levels of MIG and SCF. - Comar, Manola; Secchiero, Paola; De Lorenzo, Elisa; Martelossi, Stefano; Tommasini, Alberto; Zauli, Giorgio (Inflamm Bowel Dis, 2012)
Keywords: Adolescent; Adult; Chemokine CXCL9; Child; DNA, Viral; Female; Humans; Inflammatory Bowel Diseases; JC Virus; Leukoencephalopathy, Progressive Multifocal; Male; Stem Cell Factor; Young Adult

Lovastatin-induced apoptosis is modulated by geranylgeraniol in a neuroblastoma cell line. - Marcuzzi, Annalisa; Zanin, Valentina; Piscianz, Elisa; Tricarico, Paola Maura; Vuch, Josef; Girardelli, Martina; Monasta, Lorenzo; Bianco, Anna Monica; Crovella, Sergio (Int J Dev Neurosci, 2012)
Mevalonic aciduria (MA), the most severe form of mevalonate kinase deficiency (MKD), is still an orphan drug disease and the pathogenetic mechanisms underlying neuronal dysfunction is still poorly understood. In our study we have investigated the apoptotic mechanism mediated by the exposure of the cultured neuroblastoma cell line, SH-SY5Y, to lovastatin in absence or in presence of the isoprenoid, geranylgeraniol, with the aim of unraveling the pathogenesis of MA. Lovastatin, blocks the mevalonate pathway inhibiting the 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CR), an enzyme of the mevalonate pathway upstream the mevalonate kinase enzyme, reproducing biochemical features similar to those found in MKD. We demonstrate that apoptosis in neuronal lovastatin treated-cells is induced by the mitochondrial pathway, with caspase-9 as the initiator and caspase-3 as the effector caspase. The presence of geranylgeraniol modulates both the caspase-9 and caspase-3 activity in a dose-dependent way, confirming that this isoprenoid enters the mevalonate pathway, is metabolized and finally is able to by-pass the statin biochemical block reconstituting the mevalonate pathway. According to our findings, it should not be the time course adopted that modulates the apoptotic response but rather the isoprenoid itself. Being aware that our results have been obtained using a biochemical model of MKD, and not cells from patients with the disease, we believe our findings increase the knowledge of MA pathogenesis, and may possibly contribute to the development of novel therapeutic strategies.
Keywords: Analysis of Variance; Apoptosis; Caspases; Cell Line, Tumor; Diterpenes; Dose-Response Relationship, Drug; Drug Interactions; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Lovastatin; Neuroblastoma; Time Factors

Management of cryptorchidism: a survey of clinical practice in Italy. - Marchetti, Federico; Bua, Jenny; Tornese, Gianluca; Piras, Gianni; Toffol, Giacomo; Ronfani, Luca (BMC Pediatr, 2012)
BACKGROUND: An evidence-based Consensus on the treatment of undescended testis (UT) was recently published, recommending to perform orchidopexy between 6 and 12 months of age, or upon diagnosis and to avoid the use of hormones. In Italy, current practices on UT management are little known. Our aim was to describe the current management of UT in a cohort of Italian children in comparison with the Consensus guidelines. As management of retractile testis (RT) differs, RT cases were described separately. METHODS: Ours is a retrospective, multicenter descriptive study. An online questionnaire was filled in by 140 Italian Family Paediatricians (FP) from Associazione Culturale Pediatri (ACP), a national professional association of FP. The questionnaire requested information on all children with cryptorchidism born between 1/01/2004 and 1/01/2006. Data on 169 children were obtained. Analyses were descriptive. RESULTS: Overall 24% of children were diagnosed with RT, 76% with UT. Among the latter, cryptorchidism resolved spontaneously in 10% of cases at a mean age of 21.6 months. Overall 70% of UT cases underwent orchidopexy at a mean age of 22.8 months (SD 10.8, range 1.2-56.4), 13% of whom before 1 year. The intervention was performed by a paediatric surgeon in 90% of cases, with a success rate of 91%. Orchidopexy was the first line treatment in 82% of cases, while preceded by hormonal treatment in the remaining 18%. Hormonal treatment was used as first line therapy in 23% of UT cases with a reported success rate of 25%. Overall, 13 children did not undergo any intervention (mean age at last follow up 39.6 months). We analyzed the data from the 5 Italian Regions with the largest number of children enrolled and found a statistically significant regional difference in the use of hormonal therapy, and in the use of and age at orchidopexy. CONCLUSIONS: Our study showed an important delay in orchidopexy. A quarter of children with cryptorchidism was treated with hormonal therapy. In line with the Consensus guidelines, surgery was carried out by a paediatric surgeon in the majority of cases, with a high success rate.
Keywords: Child, Preschool; Chorionic Gonadotropin; Cryptorchidism; Gonadotropin-Releasing Hormone; Guideline Adherence; Humans; Infant; Italy; Male; Middle Aged; Orchiopexy; Pediatrics; Physician's Practice Patterns; Practice Guidelines as Topic; Questionnaires; Retrospective Studies; Treatment Outcome

Managing children under 36 months of age with febrile urinary tract infection: a new approach. - Pennesi, Marco; L'erario, Ines; Travan, Laura; Ventura, Alessandro (Pediatr Nephrol, 2012)
BACKGROUND: Recent guidelines on urinary tract infection (UTI) agree on reducing the number of invasive procedures. None of these has been validated by a long-term study. We describe our 11-years experience in the application of a diagnostic protocol that uses a reduced number of invasive procedures. METHODS: We reviewed retrospectively the records of 406 children aged between 1 and 36 months at their first UTI. All patients underwent renal ultrasound (RUS). Children with abnormal RUS and those with UTI recurrences underwent voiding cystourethrography (VCUG) and dimercaptosuccinic acid (DMSA) renal scans. RESULTS: RUS after the first UTI was pathological in 7.4% children; 4.4 % had a second UTI. We performed 48 VCUG: 14 patients (29%) had vesicoureteral reflux (VUR), 12 of which showed an abnormal RUS while 2 had recurrent UTI. After DMSA renal scan renal damage appeared in only 6 of them (12.5%); all these children showed grade IV VUR. CONCLUSIONS: The application of our guidelines leads to a decrease in invasive examinations without missing any useful diagnoses or compromising the child's health.
Keywords: Anti-Bacterial Agents; Child, Preschool; Female; Humans; Infant; Male; Pediatrics; Recurrence; Retrospective Studies; Urinary Tract Infections

MBL interferes with endovascular trophoblast invasion in pre-eclampsia. - Agostinis, Chiara; Bossi, Fleur; Masat, Elisa; Radillo, Oriano; Tonon, Maddalena; De Seta, Francesco; Tedesco, Francesco; Bulla, Roberta (Clin Dev Immunol, 2012)
The spiral arteries undergo physiologic changes during pregnancy, and the failure of this process may lead to a spectrum of pregnancy disorders, including pre-eclampsia. Our recent data indicate that decidual endothelial cells (DECs), covering the inner side of the spiral arteries, acquire the ability to synthesize C1q, which acts as a link between endovascular trophoblast and DECs favouring the process of vascular remodelling. In this study, we have shown that sera obtained from pre-eclamptic patients strongly inhibit the interaction between extravillous trophoblast (EVT) and DECs, preventing endovascular invasion of trophoblast cells. We further demonstrated that mannose-binding lectin (MBL), one of the factor increased in pre-eclamptic patient sera, strongly inhibits the interaction of EVT with C1q interfering with the process of EVT adhesion to and migration through DECs. These data suggest that the increased level of MBL in pre-eclampsia may contribute to the failure of the endovascular invasion of trophoblast cells.
Keywords: Cell Communication; Decidua; Endothelial Cells; Female; Humans; Mannose-Binding Lectin; Pre-Eclampsia; Pregnancy; Transendothelial and Transepithelial Migration; Trophoblasts

The MDM2 inhibitor Nutlin-3 modulates dendritic cell-induced T cell proliferation. - Gasparini, Chiara; Tommasini, Alberto; Zauli, Giorgio (Hum Immunol, 2012)
Nutlin-3, a small molecule inhibitor of the MDM2/p53 interaction, has been recently taken into consideration as a promising therapeutic tool for tumor treatment based on its ability to stabilize and activate the p53 transcription factor pathway. Since Nutlin-3 displays non cell-autonomous tumor-suppressor activities, we wanted to investigate its effect on dendritic cell functions, given the central role of these cells in the modulation of the immune response. We found that Nutlin-3 alone slightly affected the levels of major histocompatibility complex and costimulatory molecules and significantly promoted the ability of dendritic cells to stimulate T cells in the mixed lymphocyte reaction. Taken together, our findings suggest that the ability of Nutlin-3 to modulate dendritic cell functions and therefore lymphocyte proliferation might represent an additional important mechanism by which Nutlin-3 exerts its non cell-autonomous tumor-suppression function.
Keywords: Dendritic Cells; Humans; Imidazoles; Immunologic Factors; Immunophenotyping; Lymphocyte Activation; Piperazines; Proto-Oncogene Proteins c-mdm2; T-Lymphocytes

Mesenchymal stem cells display hepato-protective activity in lymphoma bearing xenografts. - Secchiero, Paola; Corallini, Federica; Zavan, Barbara; Tripodo, Claudio; Vindigni, Vincenzo; Zauli, Giorgio (Invest New Drugs, 2012)
A disseminated model of non-Hodgkin's lymphoma with prevalent liver metastasis was generated by intraperitoneal (i.p.) injection of EBV(+) B lymphoblastoid SKW6.4 in nude-SCID mice. The survival of SKW6.4 xenografts (median survival = 27 days) was significantly improved when hyaluronan scaffolds embedded with mesenchimal stem cells (MSC) were implanted in the abdominal area 4 days after SKW6.4 injection (median survival = 39.5 days). Mice implanted with MSC showed a significant improvement of hepatic functionality in lymphoma xenografts, as demonstrated by measurement of serum ALT/AST levels. Co-culture of MSC with lymphoma cells enhanced the release of hepatocyte growth factor (HGF) by MSC. These data suggest that hyaluronan-embedded MSC exert anti-lymphoma activity by ameliorating hepatic functionality.
Keywords: Alanine Transaminase; Animals; Aspartate Aminotransferases; Biological Markers; Cell Communication; Cell Line, Tumor; Cell Survival; Coculture Techniques; Hepatocyte Growth Factor; Humans; Hyaluronic Acid; Liver; Liver Neoplasms; Lymphoma, Non-Hodgkin; Mesenchymal Stem Cell Transplantation; Mesenchymal Stromal Cells; Mice; Mice, Nude; Mice, SCID; Time Factors; Tissue Scaffolds; Xenograft Model Antitumor Assays

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies multiple loci associated with kidney function-related traits in east Asian populations. - Okada, Yukinori; Sim, Xueling; Go, Min Jin; Wu, Jer-Yuarn; Gu, Dongfeng; Takeuchi, Fumihiko; Takahashi, Atsushi; Maeda, Shiro; Tsunoda, Tatsuhiko; Chen, Peng; Lim, Su-Chi; Wong, Tien-Yin; et al. (Nat Genet, 2012)
Chronic kidney disease (CKD), impairment of kidney function, is a serious public health problem, and the assessment of genetic factors influencing kidney function has substantial clinical relevance. Here, we report a meta-analysis of genome-wide association studies for kidney function-related traits, including 71,149 east Asian individuals from 18 studies in 11 population-, hospital- or family-based cohorts, conducted as part of the Asian Genetic Epidemiology Network (AGEN). Our meta-analysis identified 17 loci newly associated with kidney function-related traits, including the concentrations of blood urea nitrogen, uric acid and serum creatinine and estimated glomerular filtration rate based on serum creatinine levels (eGFRcrea) (P < 5.0 × 10(-8)). We further examined these loci with in silico replication in individuals of European ancestry from the KidneyGen, CKDGen and GUGC consortia, including a combined total of ∼110,347 individuals. We identify pleiotropic associations among these loci with kidney function-related traits and risk of CKD. These findings provide new insights into the genetics of kidney function.
Keywords: Asian Continental Ancestry Group; Blood Urea Nitrogen; Cohort Studies; Creatinine; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Uric Acid

More on professionals' attitudes on blood-tinged milk: a survey from Italy. - Bua, J; Travan, L; Davanzo, R; Demarini, S (J Perinatol, 2012)
Keywords: Attitude of Health Personnel; Breast Feeding; Clinical Protocols; Female; Humans; Intensive Care Units, Neonatal; Intensive Care, Neonatal; Male; Milk, Human; Professional Practice

MYH9-related disorders: report on a patient of Greek origin presenting with macroscopic hematuria and presenile cataract, caused by an R1165C mutation. - Economou, Marina; Batzios, Spyros P; Pecci, Alessandro; Printza, Nikoletta; Savoia, Anna; Barozzi, Serena; Theodoridou, Stamatia; Teli, Aikaterini; Psillas, Georgios; Zafeiriou, Dimitrios I (J Pediatr Hematol Oncol, 2012)
Myosin heavy chain-9 (MYH9)-related disorders represent a heterogenous group of hereditary diseases caused by mutations in the gene encoding the heavy chain of nonmuscle myosin IIA. May-Hegglin anomaly and Fechtner, Sebastian, and Epstein syndromes are the four phenotypes of the disease, characterized by congenital macrothrombocytopenia and distinguished by different combinations of clinical signs that may include glomerulonephritis, sensorineural hearing loss, and presenile cataract. The spectrum of mutations responsible for the disease is wide and the existence of genotype-phenotype correlation remains a critical issue. We report the first case of an MYH9-RD in a patient of Greek origin presenting with macroscopic hematuria and presenile cataract caused by a p.R1165C mutation. The same mutation was present in the patient's father, who exhibited no extrahematological features of the disease. The p.R1165C mutation is one of the MYH9 alterations whose prognostic significance is still poorly defined. Thus, the patients described add to the limited existing data on the MYH9 mutations and their resultant phenotypes.
Keywords: Adolescent; Cataract; Diagnosis, Differential; DNA Mutational Analysis; Greece; Hematuria; Humans; Male; Molecular Motor Proteins; Myosin Heavy Chains; Point Mutation

NLRP1 polymorphisms in patients with asbestos-associated mesothelioma. - Girardelli, Martina; Maestri, Iva; Rinaldi, Rosa R; Tognon, Mauro; Boldorini, Renzo; Bovenzi, Massimo; Crovella, Sergio; Comar, Manola (Infect Agent Cancer, 2012)
UNLABELLED: BACKGROUND: An increasing incidence of malignant mesothelioma (MM) cases in patients with low levels of asbestos exposure suggests the interference of alternative cofactors. SV40 infection was detected, as co-morbidity factor, only in 22% of asbestos-MM patients from a North-Eastern Italy area. An additional mechanism of injury related to asbestos exposure in MM development has been recently associated to inflammatory responses, principally driven by interleukin (IL)-1 beta (ß) activated within the inflammasome complex.NLRP3 inflammosome has been described as the intracellular sensor for asbestos able to induce inflammasome activation and IL-1ß secretion while NLRP1 is expressed in lung epithelial cells and alveolar macrophages and contributes to the immune response and to survival/apoptosis balance. This study proposes to evaluate the impact of known NLRP3 and NLRP1 polymorphisms in the individual susceptibility to asbestos-induced mesothelioma in subjects from a hyperendemic area for MM. METHODS: 134 Italian patients with diagnosis of mesothelioma due (MMAE, n=69) or not (MMAF, n=65) to asbestos, 256 healthy Italian blood donors and 101 Italian healthy subjects exposed to asbestos (HCAE) were genotyped for NLRP1 (rs2670660 and rs12150220) and NLRP3 (rs35829419 and rs10754558) polymorphisms. RESULTS: While NLRP3 SNPs were not associated to mesothelioma, the NLRP1 rs12150220 allele T was significantly more frequent in MMAE (0.55) than in HCAE (0.41) (p=0.011; OR=1.79) suggesting a predisponent effect of this allele on the development of mesothelioma. This effect was amplified when the NLRP1 rs2670660 allele was combined with the NLRP1 rs12150220 allele (p=0.004; OR=0.52). CONCLUSION: Although NLRP3 SNPs was not involved in mesothelioma predisposition, these data proposed NLRP1 as a novel factor possibly involved in the development of mesothelioma.

Pelvic inflammatory disease (PID) from Chlamydia trachomatis versus PID from Neisseria gonorrhea: from clinical suspicion to therapy. - De Seta, F; Banco, R; Turrisi, A; Airoud, M; De Leo, R; Stabile, G; Ceccarello, M; Restaino, S; De Santo, D (G Ital Dermatol Venereol, 2012)
Pelvic inflammatory disease (PID) is the most significant complication of sexually transmitted infections in childbearing-age women and it represents an important public health problem because of its long-term sequelae (chronic pelvic pain, tubal infertility, ectopic pregnancy). Prior to the mid 1970s PID was considered a monoetiologic infection, due primarily to Neisseria gonorrhea. Now it is well documented as a polymicrobial process, with a great number of microrganisms involved. In addition to Neisseria gonorrhea and Chlamydia trachomatis, other vaginal microrganisms (anaerobes, Gardnerella vaginalis, Haemophilus influenzae, enteric Gram negative rods, Streptococco agalactie, Mycoplasma genitalium) also have been associated with PID. There is a wide variation in PID clinical features; the type and severity of symptoms vary by microbiologic etiology. Women who have chlamydial PID seem more likely than women who have gonococcal PID to be asymptomatic. Since clinical diagnosis is imprecise, the suspicion of PID should be confirmed by genital assessment for signs of inflammation or infection, blood test and imaging evaluation. Laparoscopic approach is considered the gold standard. According to the polymicrobial etiology of PID, antibiotic treatment must provide broad spectrum coverage of likely pathogens. Early administration of antibiotics is necessary to reduce the risk of long-term sequelae.
Keywords: Chlamydia Infections; Chlamydia trachomatis; Female; Gonorrhea; Humans; Neisseria gonorrhoeae; Pelvic Inflammatory Disease

Peroxidase-like activity of ferruginous bodies isolated by exploiting their magnetic property. - Borelli, Violetta; Trevisan, Elisa; Vita, Francesca; Bottin, Cristina; Melato, Mauro; Rizzardi, Clara; Zabucchi, Giuliano (J Toxicol Environ Health A, 2012)
Ferruginous bodies (FB) are polymorphic structures whose formation is macrophage dependent, and are composed of a core, which may consist of an asbestos fiber coated with proteins, among which ferritin is the main component. Within ferritin, the ferric and ferrous ions are coordinated as ferrihydrite, which is the main iron (Fe) storage compound. However, when ferritin accumulates in some tissues following Fe overload it also contains magnetite along with ferrihydrite, which endows it with magnetic properties. Recently studies showed that magnetite exerts peroxidase-like activity, and since ferruginous bodies display magnetic properties, it was postulated that these particular structures may also contain magnetite within the ferritin coating, and thus may also exert peroxidase-like activity. Histochemical analysis for peroxidase of isolated FB smears demonstrated positive staining. Samples isolated from 4 different autopsy lung fragments were also able to oxidize 3,3',5,5'-tetramethyl-benzidine to a blue colored compound that absorbs at 655 nm. This activity was (1) azide and heat insensitive with optimal pH from 5 to 6, and (2) highly variable, changing more than 25-fold from one sample to another. These findings, together with evidence that the peroxidase-like activity of ferruginous bodies has a hydrogen peroxide and substrate requirement different from that of human myeloperoxidase, can exclude that this enzyme gives a significant contribution to the formation of FB. Standard Fe-rich asbestos fibers also express a peroxidase-like activity, but this appears negligible compared to that of ferruginous bodies. Strong acidification of standard Fe-containing asbestos fibers or magnetically isolated ferruginous bodies liberates a high amount of peroxidase-like activity, which is probably accounted for by the release of Fe ions. Further, FB also damage mesothelial cells in vitro. Data suggest that FB exert peroxidase-like activity and cytotoxic activity against mesothelial cells, and hence may be an important factor in pathogenesis of asbestos-related diseases.
Keywords: Air Pollutants, Occupational; Asbestos; Asbestosis; Benzidines; Catalysis; Cell Line; Chromogenic Compounds; Cytotoxins; Ferric Compounds; Ferritins; Ferrosoferric Oxide; Humans; Hydrogen-Ion Concentration; Lung; Magnetic Phenomena; Mesothelioma; Mineral Fibers; Oxidation-Reduction; Peroxidases; Respiratory Mucosa

Phylloid pattern of hypomelanosis closely related to chromosomal abnormalities in the 13q detected by SNP array analysis. - Faletra, F; Berti, I; Tommasini, A; Pecile, V; Cleva, L; Alberini, E; Bruno, I; Gasparini, P (Dermatology, 2012)
Phylloid hypomelanosis is a distinct type of pigmentary mosaicism characterized by congenital hypochromic macules resembling a floral ornament with various elements such as round or oval patches, asymmetrical macules similar to begonia leaves, or oblong lesions. It has been found to be predominantly associated with abnormalities in chromosome 13 and sometimes as-sociated with different extracutaneous abnormalities. Here, we report 2 new cases of phylloid hypomelanosis due to mosaicism involving chromosome 13. The first one is a mosaicism for a supernumerary marker belonging to chromosome 13 and the second one is the first report of phylloid hypomelanosis associated with a mosaic deletion of 13q. Because of the extremely low level of mosaicism in these 2 cases, SNP array analysis on skin fibroblasts was carried out, showing a 13q21.33-q34 duplication (71,024,411-115,103,529) and a 13q13.3-q34 (38,368,012-115,103,529) deletion. Both cases underline on the one hand the strict connection between phylloid hypomelanosis and anomalies of chromosome 13, and on the other hand the relevance of the SNP array analysis on skin fibroblasts in the detection of low-level mosaicism.
Keywords: Chromosomes, Human, Pair 13; Humans; Hypopigmentation; Male; Mosaicism; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide

Potential role of TRAIL in the management of autoimmune diabetes mellitus. - Bernardi, Stella; Norcio, Alessia; Toffoli, Barbara; Zauli, Giorgio; Secchiero, Paola (Curr Pharm Des, 2012)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease, due to the immune-mediated destruction of pancreatic β-cells, whose incidence has been steadily increasing during the last decades. Insulin replacement therapy can treat T1DM, which, however, is still associated with substantial morbidity and mortality. For this reason, great effort is being put into developing strategies that could eventually prevent and/or cure this disease. These strategies are mainly focused on blocking the immune system from attacking β-cells together with functional islet restoration either by regeneration or transplantation. Recent experimental evidences suggest that TNFrelated apoptosis-inducing ligand (TRAIL), which is an immune system modulator protein, could represent an interesting candidate for the cure for T1DM and/or its complications. Here we review the evidences on the potential role of TRAIL in the management of T1DM.
Keywords: Animals; Autoimmunity; Diabetes Mellitus, Type 1; Humans; Hypoglycemic Agents; Insulin; Insulin-Secreting Cells; Islets of Langerhans; TNF-Related Apoptosis-Inducing Ligand

A red baby should not be taken too lightly. - Faletra, Flavio; Bruno, Irene; Berti, Irene; Pastore, Serena; Pirrone, Angela; Tommasini, Alberto (Acta Paediatr, 2012)
AIM: To identify clinical and laboratory features that can drive the differential diagnosis of a primary immunodeficiency diseases in patients with ectodermal defects. METHODS: Analysis of selected teaching cases. RESULTS: We identified four exemplary cases that allowed to point out specific clues. CONCLUSIONS: A careful evaluation of immune and ectodermal signs is the key to the diagnosis. Therefore, a multidisciplinary approach can lead to diagnosis and to an appropriate treatment in most of the cases.
Keywords: Child, Preschool; Dermatitis; Ectodermal Dysplasia; Female; Humans; Immunologic Deficiency Syndromes; Infant; Male; Netherton Syndrome; Severe Combined Immunodeficiency; Skin

Relation between maternal thrombophilia and stillbirth according to causes/associated conditions of death. - Monari, F; Alberico, S; Avagliano, L; Cetin, I; Cozzolino, S; Gargano, G; Marozio, L; Mecacci, F; Neri, I; Tranquilli, A L; Venturini, P; Facchinetti, F (Early Hum Dev, 2012)
OBJECTIVE: To investigate maternal thrombophilia in cases of Stillbirth (SB), also an uncertain topic because most case series were not characterised for cause/associated conditions of death. STUDY DESIGN: In a consecutive, prospective, multicentre design, maternal DNA was obtained in 171 cases of antenatal SB and 326 controls (uneventful pregnancy at term, 1:2 ratio). Diagnostic work-up of SB included obstetric history, neonatologist inspection, placenta histology, autopsy, microbiology/chromosome evaluations. Results audited in each centre were classified by two of us by using CoDAC. Cases were subdivided into explained SB where a cause of death was identified and although no defined cause was detected in the remnants, 64 cases found conditions associated with placenta-vascular disorders (including preeclampsia, growth restriction and placenta abruption - PVD). In the remnant 79 cases, no cause of death or associated condition was found. Antithrombin activity, Factor V Leiden, G20210A Prothrombin mutation (FII mutation) and acquired thrombophilia were analysed. RESULTS: Overall, the presence of a thrombophilic defect was significantly more prevalent in mothers with SBs compared to controls. In particular, SB mothers showed an increased risk of carrying Factor II mutation (OR=3.2, 95% CI: 1.3-8.3, p=0.01), namely in unexplained cases. Such mutation was significantly associated also with previous SB (OR=8.9, 95%CI 1.2-70.5). At multiple logistic regression, Factor II mutation was the only significantly associated variable with SB (adj OR=3.8, 95% CI: 1.3-13.5). CONCLUSION: These data suggest that Factor II mutation is the only condition specifically associated with unexplained SB and could represents a risk of recurrence. PVD-associated condition is unrelated to thrombophilia.
Keywords: Adult; Case-Control Studies; Cause of Death; Female; Fetal Diseases; Fetal Mortality; Humans; Infant, Newborn; Male; Placenta Diseases; Pre-Eclampsia; Pregnancy; Pregnancy Complications, Hematologic; Socioeconomic Factors; Stillbirth; Thrombophilia; Young Adult

Serum amyloid A and cholesterol: a pivotal role on inflammation. - Tricarico, Paola Maura; Marcuzzi, Annalisa; Zanin, Valentina; Kleiner, Giulio; Bianco, Anna Monica; Crovella, Sergio (Amyloid, 2012)
Keywords: Animals; Humans; Serum Amyloid A Protein

Simian virus 40 efficiently infects human T lymphocytes and extends their lifespan. - Mazzoni, Elisa; Rigolin, Gian Matteo; Alaribe, Franca Nneka; Pancaldi, Cecilia; Maniero, Stefania; Comar, Manola; Martini, Fernanda; Tognon, Mauro (Exp Hematol, 2012)
The relevance of viral infections to the onset and progression of human hematologic malignancies and other blood diseases is still a matter of active investigation. Purified human T lymphocytes isolated from the peripheral blood mononuclear cells of healthy blood donors were experimentally infected with simian virus 40 (SV40), a small DNA tumor virus. SV40-positive T lymphocytes extended their lifespan up to day 80 postinfection (PI). Expression of viral antigens, such as the large T antigen and the viral capsid protein VP1 from the early and late regions, respectively, was detected up to day 40 PI. SV40 viral progeny were continuously produced from day 10 to 40 PI. SV40 DNA sequences were detected in infected T cells for up to 80 days. Our data indicate that human T lymphocytes can be efficiently infected with SV40. Although T cells infected by SV40 were not immortalized, 30% of these lymphocytes appeared to be morphologically transformed with an enlarged T-cell shape. Our investigation provides a simple model for studying the interactions of human T lymphocytes with this small DNA tumor virus and it might represent an experimental tool for investigating new biomarkers and targets for innovative therapeutic approaches.
Keywords: Antigens, Polyomavirus Transforming; Cell Line, Transformed; Cell Survival; Humans; Microscopy, Electron, Transmission; Simian virus 40; T-Lymphocytes

Simultaneous determination of multiple cytokines reveals a pro-inflammatory and pro-angiogenic signature after major cardiothoracic surgery: potential role of C-reactive protein. - Tisato, Veronica; Monasta, Lorenzo; Biolo, Gianni; Donatelli, Francesco; Secchiero, Paola; Zauli, Giorgio (Cytokine, 2012)
Keywords: C-Reactive Protein; Coronary Artery Bypass; Cytokines; Humans; Inflammation; Macrophages; Neovascularization, Physiologic; Risk Factors

Slow growth: do not forget the thyroid. - Tornese, Gianluca; Tonini, Giorgio; Ventura, Alessandro (J Pediatr Gastroenterol Nutr, 2012)
Keywords: Constipation; Female; Humans; Hypothyroidism; Male; Thyroid Function Tests

Soluble TRAIL is elevated in recurrent miscarriage and inhibits the in vitro adhesion and migration of HTR8 trophoblastic cells. - Agostinis, Chiara; Bulla, Roberta; Tisato, Veronica; De Seta, Francesco; Alberico, Salvatore; Secchiero, Paola; Zauli, Giorgio (Hum Reprod, 2012)
STUDY QUESTION: What is the potential physiopathological role of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) in recurrent miscarriage (RM), characterized by at least three consecutive pregnancy losses. SUMMARY ANSWER: The levels of serum TRAIL immediately after miscarriage in RM patients are significantly elevated with respect to that in first-trimester normal pregnant women, and recombinant TRAIL inhibits the adhesion and migration of HTR8 trophoblastic cells in vitro. WHAT IS KNOWN ALREADY: Both TRAIL and its trans-membrane receptors (TRAIL-R1, TRAIL-R2, TRAIL-R3 and TRAIL-R4) have been documented in the placenta, but their physiopathological role is incompletely understood. STUDY DESIGN, SIZE, DURATION: The study populations consisted of RM patients (n = 80) and first-trimester normal pregnant women (n = 80). Blood samples were obtained within 24 h after abortion (RM) or at gestational 12-week (normal pregnant women). As additional controls, third-trimester normal pregnant women (n = 28) were examined before (within 72 h) and after (within 24 h) partum. PARTICIPANTS/MATERIALS, SETTING, METHODS: The concentrations of TRAIL were analysed in serum samples by ELISA. In parallel, the effect of soluble recombinant TRAIL (0.1-1000 ng/ml) was analysed on the survival of primary extravillus trophoblasts (EVTs) and on the survival, proliferation, adhesion and migration of trophoblastic HTR8 cells. MAIN RESULTS AND THE ROLE OF CHANCE: The circulating levels of TRAIL in RM women (median: 52.5 pg/ml; mean and SD: 55.5 ± 24.4 pg/ml) were significantly higher with respect to first-trimester normal pregnant women (median: 44.9 pg/ml; mean and SD: 47 ± 15.1 pg/ml) and third-trimester normal pregnant women, as assessed before (median: 45.1 pg/ml; mean and SD: 46 ± 12.4 pg/ml) and after partum (median: 35.4 pg/ml; mean and SD: 38 + 17.5 pg/ml). Both primary EVT and HTR8 cells expressed detectable levels of TRAIL death receptors, but exposure to soluble recombinant TRAIL did not induce cell death of trophoblastic cells. On the other hand, TRAIL dose-dependently inhibited the adhesion of HTR8 cells to decidual endothelial cells (DEC) as well as the migration of HTR8 in transwell assays using either fibronectin or DEC. LIMITATIONS, REASONS FOR CAUTION: Although this study suggests that TRAIL might have a pathogenic role in RM by inhibiting both the adhesion and migration capabilities of first trimester trophoblastic cells, there is a possibility that the elevated serum levels of TRAIL in RM are not cause but rather the result of RM. WIDER IMPLICATIONS OF THE FINDINGS: Our current findings together with data of other authors suggest that circulating TRAIL should be further analysed as a potential important biomarker in different physiopathological settings. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by FIRB projects (RBAP11Z4Z9_002 to Giorgio Zauli and RBAP10447J_002 to Paola Secchiero). The authors have no competing interests to declare.
Keywords: Abortion, Habitual; Apoptosis; Cell Adhesion; Cell Line; Cell Movement; Cells, Cultured; Enzyme-Linked Immunosorbent Assay; Female; Humans; Pregnancy; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand; Trophoblasts

The sorafenib plus nutlin-3 combination promotes synergistic cytotoxicity in acute myeloid leukemic cells irrespectively of FLT3 and p53 status. - Zauli, Giorgio; Celeghini, Claudio; Melloni, Elisabetta; Voltan, Rebecca; Ongari, Manuele; Tiribelli, Mario; di Iasio, Maria Grazia; Lanza, Francesco; Secchiero, Paola (Haematologica, 2012)
BACKGROUND: Both the multi-kinase inhibitor sorafenib and the small molecule inhibitor of the MDM2/p53 interaction, nutlin-3, used alone, have shown promising anti-leukemic activity in acute myeloid leukemia cells. Thus, in this study we investigated the effect of the combination of sorafenib plus nutlin-3 in acute myeloid leukemia. DESIGN AND METHODS: Primary acute myeloid leukemia blasts (n=13) and FLT3(wild-type)/p53(wild-type) (OCI-AML3), FLT3(mutated)/p53(wild-type) (MOLM), FLT3(mutated)/p53(mutated) (MV4-11), FLT3(wild-type)/p53(deleted) (HL60) or FLT3(wild-type)/p53(mutated) (NB4) acute myeloid cell lines were exposed to sorafenib, used alone or in association with nutlin-3 at a 1:1 ratio, in a range of clinically achievable concentrations (1-10 μM). Induction of apoptosis and autophagy was evaluated by transmission electron microscopy and by specific flow cytometry analyses. The levels of Mcl-1, p53 and Bak proteins were analyzed by western blotting. Knock-down of Bax and Bak gene expression was performed in transfection experiments with specific short interfering RNA. RESULTS: The sorafenib+nutlin-3 drug combination exhibits synergistic cytotoxicity in primary acute myeloid leukemia blasts and in acute myeloid leukemia cell lines with maximal cytotoxicity in FLT3(mutated) MV4-11 and MOLM, followed by the FLT3(wild-type) OCI-AML3, HL60 and NB4 cell lines. The cytotoxic activity of sorafenib+nutlin-3 was characterized by an increase of both apoptosis and autophagy. Moreover, Bax and Bak showed prominent roles in mediating the decrease of cell viability in response to the drug combination in p53(wild-type) OCI-AML3 and p53(deleted) HL-60 cells, respectively, as demonstrated in transfection experiments performed with specific short interfering RNA. CONCLUSIONS: Our data demonstrate that acute myeloid leukemia cells show a variable but overall good susceptibility to the innovative therapeutic combination of sorafenib+nutlin-3, which differentially involves the pro-apoptotic Bcl-2 family members Bax and Bak in p53(wild-type) and p53(deleted) cells.
Keywords: Antineoplastic Agents; Drug Synergism; Female; fms-Like Tyrosine Kinase 3; HL-60 Cells; Humans; Imidazoles; Leukemia, Myeloid, Acute; Male; Niacinamide; Phenylurea Compounds; Piperazines; Tumor Suppressor Protein p53

Specific protein profile in cerebrospinal fluid from HIV-1-positive cART-treated patients affected by neurological disorders. - Zanin, Valentina; Delbue, Serena; Marcuzzi, Annalisa; Tavazzi, Eleonora; Del Savio, Rossella; Crovella, Sergio; Marchioni, Enrico; Ferrante, Pasquale; Comar, Manola (J Neurovirol, 2012)
Cytokines/chemokines are involved in the immune response of infections, including HIV-1. We defined the profile of 48 cytokines/chemokines in cerebrospinal fluid from 18 cART patients with chronic HIV-1 infection by Luminex technology. Nine patients were affected with leukoencephalopathies: five with John Cunningham virus (JCV) + progressive multifocal leukoencephalopathy (PML) and four with JCV-not determined leukoencephalopathy (NDLE). In addition, nine HIV-1-positive patients with no neurological signs (NND) and five HIV-1-negative patients affected with acute disseminated encephalomyelitis (ADEM) were enrolled. Ten cytokines (IL-15, IL-3, IL-16, IL-18, CTACK, GRO1, SCF, MCP-1, MIF, SDF) were highly expressed in HIV-1-positive patients while IL-1Ra and IL-17 were present at a lower level. In addition, the levels of IL-17, IL-9, FGF-basic, MIP-1β, and MCP-1 were significantly higher (p < 0.05) in patients with neurological diseases (PML, NDLE, ADEM) with respect to NND. Focusing the attention to the cytokine profile in JCV + PML patients with respect to JCV-NDLE patients, only TNF-β was significantly downregulated (p < 0.05) in JCV + PML patients. This pilot study emphasized the role of immunoregulation in HIV-1-related neurological disorders during cART treatment.
Keywords: Adult; Aged; Anti-HIV Agents; Cytokines; Encephalomyelitis, Acute Disseminated; Female; HIV Infections; HIV-1; Humans; Leukoencephalopathy, Progressive Multifocal; Male; Middle Aged; Pilot Projects

State of the art of the therapeutic perspective of sorafenib against hematological malignancies. - Zauli, G; Voltan, R; Tisato, V; Secchiero, P (Curr Med Chem, 2012)
The bi-aryl urea multi-kinase inhibitor Sorafenib (BAY 43-9006, Nexavar) was initially approved for the treatment of unresectable hepatocellular carcinoma and advanced renal cell carcinoma. Eleven years after its first description in PubMed, the therapeutic potential of Sorafenib has been evaluated in an increasing number of studies, mainly focused on solid tumors. More recently, the potential usefullness of Sorafenib has started to emerge also against hematological malignancies. At the molecular level, besides the RAF kinase pathway, which represents the first therapeutic target of Sorafenib, additional kinases, in particular the vascular endothelial growth factor receptor, have been identified as important targets of Sorafenib. A great interest for the potential use of Sorafenib against acute myeloid leukemia (AML) arose when it was demonstrated that a specific mutation of a kinase gene, called FMS-like tyrosin-kinase-3- internal tandem duplication (FLT-3-ITD) and occurring in more than 30% of AML, represents a molecular target of Sorafenib. However, recent phase I and II clinical studies showed that, in spite of its ability to suppress the activity of this mutated kinase, resistence to Sorafenib rapidly occurs in AML, suggesting that Sorafenib will be more effective in combined therapy than used as single drug. Another critical molecular target of Sorafenib is the anti-apoptotic protein Mcl-1. The ability of Sorafenib to rapidly shut-off Mcl-1 in virtually all the hematological malignancies investigated, including the B-chronic lymphocytic leukemia, represents a key element for its antileukemic activity as well as for therapeutic combinations based on Sorafenib. In this respect, it is of particular interest that many chemotherapeutic drugs or innovative anti-neoplastic compounds, such as recombinant TRAIL or inibitors of MDM2 protein, are either unable to down-regulate Mcl-1 or in some instances promote a paradoxical induction of Mcl-1. In this review, the growing evidences for the role of Mcl-1 in mediating the anti-leukemic activity of Sorafenib will be discussed in relationship with promising therapeutic perspectives.
Keywords: Apoptosis; Clinical Trials as Topic; fms-Like Tyrosine Kinase 3; Hematologic Neoplasms; Humans; Leukemia, Myeloid, Acute; Myeloid Cell Leukemia Sequence 1 Protein; Niacinamide; Phenylurea Compounds; Proto-Oncogene Proteins c-bcl-2; Proto-Oncogene Proteins c-mdm2; Receptors, Vascular Endothelial Growth Factor; TNF-Related Apoptosis-Inducing Ligand

The submerged dyslexia iceberg: how many school children are not diagnosed? Results from an Italian study. - Barbiero, Chiara; Lonciari, Isabella; Montico, Marcella; Monasta, Lorenzo; Penge, Roberta; Vio, Claudio; Tressoldi, Patrizio Emanuele; Ferluga, Valentina; Bigoni, Anna; Tullio, Alessia; Carrozzi, Marco; Ronfani, Luca (PLoS One, 2012)
BACKGROUND: Although dyslexia is one of the most common neurobehavioral disorders affecting children, prevalence is uncertain and available data are scanty and dated. The objective of this study is to evaluate the prevalence of dyslexia in an unselected school population using clearly defined and rigorous diagnostic criteria and methods. METHODS: Cross sectional study. We selected a random cluster sample of 94 fourth grade elementary school classes of Friuli Venezia Giulia, a Region of North Eastern Italy. We carried out three consecutive levels of screening: the first two at school and the last at the Neuropsychiatry Unit of a third level Mother and Child Hospital. The main outcome measure was the prevalence of dyslexia, defined as the number of children positive to the third level of screening divided by the total number of children enrolled. RESULTS: We recruited 1774 children aged 8-10 years, of which 1528 received parents' consent to participate. After applying exclusion criteria, 1357 pupils constituted the final working sample. The prevalence of dyslexia in the enrolled population ranged from 3.1% (95% CI 2.2-4.1%) to 3.2% (95% CI 2.4-4.3%) depending on different criteria adopted. In two out of three children with dyslexia the disorder had not been previously diagnosed. CONCLUSIONS: This study shows that dyslexia is largely underestimated in Italy and underlines the need for reliable information on prevalence, in order to better allocate resources both to Health Services and Schools.
Keywords: Area Under Curve; Child; Cross-Sectional Studies; Delayed Diagnosis; Dyslexia; Female; Humans; Italy; Male; Neuropsychological Tests; Prevalence; Questionnaires; ROC Curve

TNF-related apoptosis-inducing ligand significantly attenuates metabolic abnormalities in high-fat-fed mice reducing adiposity and systemic inflammation. - Bernardi, Stella; Zauli, Giorgio; Tikellis, Christos; Candido, Riccardo; Fabris, Bruno; Secchiero, Paola; Cooper, Mark E; Thomas, Merlin C (Clin Sci (Lond), 2012)
TRAIL [TNF (tumour necrosis factor)-related apoptosis-inducing ligand] has recently been shown to ameliorate the natural history of DM (diabetes mellitus). It has not been determined yet whether systemic TRAIL delivery would prevent the metabolic abnormalities due to an HFD [HF (high-fat) diet]. For this purpose, 27 male C57bl6 mice aged 8 weeks were randomly fed on a standard diet, HFD or HFD+TRAIL for 12 weeks. TRAIL was delivered weekly by intraperitoneal injection. Body composition was evaluated; indirect calorimetry studies, GTT (glucose tolerance test) and ITT (insulin tolerance test) were performed. Pro-inflammatory cytokines, together with adipose tissue gene expression and apoptosis, were measured. TRAIL treatment reduced significantly the increased adiposity associated with an HFD. Moreover, it reduced significantly hyperglycaemia and hyperinsulinaemia during a GTT and it improved significantly the peripheral response to insulin. TRAIL reversed the changes in substrate utilization induced by the HFD and ameliorated skeletal muscle non-esterified fatty acids oxidation rate. This was associated with a significant reduction of pro-inflammatory cytokines together with a modulation of adipose tissue gene expression and apoptosis. These findings shed light on the possible anti-adipogenic and anti-inflammatory effects of TRAIL and open new therapeutic possibilities against obesity, systemic inflammation and T2DM (Type 2 DM).
Keywords: Adiposity; Animals; Apoptosis; Calorimetry; Cytokines; Dietary Fats; Energy Intake; Glucose Tolerance Test; Hyperglycemia; Hyperinsulinism; Inflammation; Inflammation Mediators; Male; Mice; Mice, Inbred C57BL; Oxidation-Reduction; Palmitic Acid; Real-Time Polymerase Chain Reaction; TNF-Related Apoptosis-Inducing Ligand

TRAIL shows potential cardioprotective activity. - Toffoli, Barbara; Bernardi, Stella; Candido, Riccardo; Zacchigna, Serena; Fabris, Bruno; Secchiero, Paola (Invest New Drugs, 2012)
Recent clinical trials carried out in patients with advanced cancer have shown that recombinant TRAIL administration is usually safe and well tolerated when used either alone or in association with chemotherapeutic drugs. Notably, anticancer chemotherapy can be associated to cardiomiopathy. We have here demonstrated that TRAIL (administrated as either recombinant soluble TRAIL or as AAV-TRAIL expression viral vector) reduced the development of cardiomyopathy in the ApoE(-/-) diabetic mouse model. These data suggest, for the first time, that therapeutically administration of TRAIL might have a cardioprotective effect.
Keywords: Animals; Apolipoproteins E; Apoptosis; Cardiotonic Agents; Diabetes Mellitus, Experimental; Diabetes Mellitus, Type 1; Diabetic Cardiomyopathies; Fibrosis; Male; Mice; Mice, Knockout; Recombinant Proteins; TNF-Related Apoptosis-Inducing Ligand

Use of specific antiretroviral regimens among HIV-infected women in Italy at time of conception: 2001-2011. - Floridia, Marco; Ravizza, Marina; Guaraldi, Giovanni; Pinnetti, Carmela; Martinelli, Pasquale; Tamburrini, Enrica (AIDS Patient Care STDS, 2012)
Keywords: Anti-HIV Agents; Drug Administration Schedule; Female; Fertilization; HIV Protease Inhibitors; HIV Seropositivity; Humans; Infectious Disease Transmission, Vertical; Italy; Pregnancy; Reverse Transcriptase Inhibitors; Sentinel Surveillance

Β-hexosaminidase over-expression affects lysosomal glycohydrolases expression and glycosphingolipid metabolism in mammalian cells. - Tancini, Brunella; Magini, Alessandro; Bortot, Barbara; Polchi, Alice; Urbanelli, Lorena; Sonnino, Sandro; Severini, Giovanni Maria; Emiliani, Carla (Mol Cell Biochem, 2012)
Lysosomes are not only degrading organelles but also involved in other critical cellular processes. In addition, active lysosomal glycohydrolases have been detected in an extra-lysosomal compartment: the presence of glycohydrolases on the plasma membrane (PM) has been widely demonstrated, and a possible role on the modification of the cell surface glycosphingolipids (GSL) participating in the modulation of cell functions such as cell-to-cell interactions and signal transduction pathways has been proposed. On this basis, the coordinated expression of lysosomal glycohydrolases and their translocation to the PM appear to be crucial for many cellular events. In this paper, we report evidence for the existence of a coordinated mechanism regulating the expression/activity of both lysosomal and PM-associated glycohydrolases. We show that the over-expression of the acidic glycohydrolase β-hexosaminidase α-subunit in mouse NIH/3T3 fibroblasts induces the increased expression of the Hex β-subunit necessary to form the active isoenzyme dimers as well as of other glycohydrolases participating in the GSL catabolism, such as β-galactosidase and β-glucocerebrosidase. More interestingly, this regulatory effect was also extended to the PM-associated hydrolases. In addition, transfected cells displayed a rearrangement of the GSL expression pattern that cannot be simply explained by the increased activity of a single enzyme. These observations clearly indicate that the expression level of metabolically related glycohydrolases is regulated in a coordinated manner and this regulation mechanism also involves the PM-associated isoforms.
Keywords: Animals; beta-Hexosaminidase alpha Chain; Cell Membrane; Exocytosis; Fibroblasts; Glycoside Hydrolases; Glycosphingolipids; Humans; Lysosomes; Mice; NIH 3T3 Cells; Transfection

The active Zot domain (aa 288-293) increases ZO-1 and myosin 1C serine/threonine phosphorylation, alters interaction between ZO-1 and its binding partners, and induces tight junction disassembly through proteinase activated receptor 2 activation. - Goldblum, Simeon E; Rai, Usha; Tripathi, Amit; Thakar, Manjusha; De Leo, Luigina; Di Toro, Nicola; Not, Tarcisio; Ramachandran, Rithwik; Puche, Adam C; Hollenberg, Morley D; Fasano, Alessio (FASEB J, 2011)
Vibrio cholerae-derived zonula occludins toxin (Zot) is a multifunctional protein that reversibly disassembles intestinal tight junctions (tjs). Zot structure-function analysis has mapped this activity to aa 288-293, named AT1002. AT1002 reduced transepithelial electrical resistance across rat small intestine, ex vivo, as did Zot and its processed mature form, ΔG. AT1002 increased in vivo permeability to sugar tracers, whereas scrambled control peptides did not. Binding and barrier assays in proteinase activated receptor (PAR)(2)-expressing and PAR(2)-null cells established AT1002 activity to be PAR(2) dependent. Coincident with the increased intestinal permeability, confocal microscopy of AT1002-exposed rat intestinal IEC6 cells revealed displacement of ZO-1 and occludin from intercellular boundaries. In coimmunoprecipitation assays, AT1002 decreased ZO-1-occludin and ZO-1-claudin 1 interactions coincident with PKCα-dependent ZO-1 serine/threonine phosphorylation. Further, AT1002 increased serine phosphorylation of myosin 1C and, at the same time, transiently diminished its association with ZO-1. The COOH-terminal domain of ZO-1 was required for its association with myosin 1C. These data indicate that the NH(2)-terminal portion of active Zot contains a PAR(2)-activating motif, FCIGRL, that increases PKCα-dependent ZO-1 and myosin 1C serine/threonine phosphorylation. These modifications provoke selective disengagement of ZO-1 from its binding partners, occludin, claudin 1, and myosin 1C, coincident with opening of tjs.
Keywords: Amino Acid Sequence; Animals; Caco-2 Cells; Cell Line; Cells, Cultured; Cholera Toxin; Epithelial Cells; Humans; Immunoblotting; Male; Membrane Proteins; Mice; Mice, Inbred BALB C; Molecular Sequence Data; Myosins; Oligopeptides; Phosphoproteins; Phosphorylation; Protein Binding; Protein Kinase C-alpha; Rats; Rats, Wistar; Receptor, PAR-2; RNA Interference; Serine; Threonine; Tight Junctions; Zonula Occludens-1 Protein

Acute cardiac valvular involvement in Kawasaki Disease. - Pellegrin, Maria Chiara; Taddio, Andrea; Lepore, Loredana (Clin Exp Rheumatol, 2011)
Keywords: Adrenal Cortex Hormones; Child, Preschool; Female; Heart Valve Diseases; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant; Male; Mucocutaneous Lymph Node Syndrome; Treatment Outcome

Ages of celiac disease: from changing environment to improved diagnostics. - Tommasini, Alberto; Not, Tarcisio; Ventura, Alessandro (World J Gastroenterol, 2011)
From the time of Gee's landmark writings, the recent history of celiac disease (CD) can be divided into many ages, each driven by a diagnostic advance and a deeper knowledge of disease pathogenesis. At the same time, these advances were paralleled by the identification of new clinical patterns associated with CD and by a continuous redefinition of the prevalence of the disease in population. In the beginning, CD was considered a chronic indigestion, even if the causative food was not known; later, the disease was proven to depend on an intolerance to wheat gliadin, leading to typical mucosal changes in the gut and to a malabsorption syndrome. This knowledge led to curing the disease with a gluten-free diet. After the identification of antibodies to gluten (AGA) in the serum of patients and the identification of gluten-specific lymphocytes in the mucosa, CD was described as an immune disorder, resembling a chronic "gluten infection". The use of serological testing for AGA allowed identification of the higher prevalence of this disorder, revealing atypical patterns of presentation. More recently, the characterization of autoantibodies to endomysium and to transglutaminase shifted the attention to a complex autoimmune pathogenesis and to the increased risk of developing autoimmune disorders in untreated CD. New diagnostic assays, based on molecular technologies, will introduce new changes, with the promise of better defining the spectrum of gluten reactivity and the real burden of gluten related-disorders in the population. Herein, we describe the different periods of CD experience, and further developments for the next celiac age will be proposed.
Keywords: Autoantibodies; Celiac Disease; Diet, Gluten-Free; Gliadin; Glutens; History, 19th Century; History, 20th Century; History, 21st Century; History, Ancient; History, Medieval; Humans; Transglutaminases

Antibiotics in severely malnourished children: systematic review of efficacy, safety and pharmacokinetics. - Lazzerini, Marzia; Tickell, David (Bull World Health Organ, 2011)
OBJECTIVE: To systemically review the evidence in support of World Health Organization guidelines recommending broad-spectrum antibiotics for children with severe acute malnutrition (SAM). METHODS: CENTRAL, MEDLINE, EMBASE, LILACS, POPLINE, CAB Abstracts and ongoing trials registers were searched. Experts were contacted. Conference proceedings and reference lists were manually searched. All study types, except single case reports, were included. FINDINGS: Two randomized controlled trials (RCTs), one before-and-after study and two retrospective reports on clinical efficacy and safety were retrieved, together with 18 pharmacokinetic studies. Trial quality was generally poor and results could not be pooled due to heterogeneity. Oral amoxicillin for 5 days was as effective as intramuscular ceftriaxone for 2 days (1 RCT). For uncomplicated SAM, amoxicillin showed no benefit over placebo (1 retrospective study). The introduction of a standardized regimen using ampicillin and gentamicin significantly reduced mortality in hospitalized children (odds ratio, OR: 4.0; 95% confidence interval, CI: 1.7-9.8; 1 before-and-after study). Oral chloramphenicol was as effective as trimethoprim-sulfamethoxazole in children with pneumonia (1 RCT). Pharmacokinetic data suggest that normal doses of penicillins, cotrimoxazole and gentamicin are safe in malnourished children, while the dose or frequency of chloramphenicol requires adjustment. Existing evidence is not strong enough to further clarify recommendations for antibiotic treatment in children with SAM. CONCLUSION: Large RCTs are needed to define optimal antibiotic treatment in children with SAM with and without complications. Further research into gentamicin and chloramphenicol toxicity and into the pharmacokinetics of ceftriaxone and ciprofloxacin is also required.
Keywords: Anti-Bacterial Agents; Child; Child Nutrition Disorders; Child, Preschool; Humans; Severity of Illness Index; Treatment Outcome

Association of a variant in the CHRNA5-A3-B4 gene cluster region to heavy smoking in the Italian population. - Sorice, Rossella; Bione, Silvia; Sansanelli, Serena; Ulivi, Sheila; Athanasakis, Emmanouil; Lanzara, Carmela; Nutile, Teresa; Sala, Cinzia; Camaschella, Clara; d'Adamo, Pio; Gasparini, Paolo; Ciullo, Marina; et al. (Eur J Hum Genet, 2011)
Large-scale population studies have established that genetic factors contribute to individual differences in smoking behavior. Linkage and genome-wide association studies have shown many chromosomal regions and genes associated with different smoking behaviors. One study was the association of single-nucleotide polymorphisms (SNPs) in the CHRNA5-A3-B4 gene cluster to nicotine addiction. Here, we report a replication of this association in the Italian population represented by three genetically isolated populations. One, the Val Borbera, is a genetic isolate from North-Western Italy; the Cilento population, is located in South-Western Italy; and the Carlantino village is located in South-Eastern Italy. Owing to their position and their isolation, the three populations have a different environment, different history and genetic structure. The variant A of the rs1051730 SNP was significantly associated with smoking quantity in two populations, Val Borbera and Cilento, no association was found in Carlantino population probably because difference in LD pattern in the variant region.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Italy; Multigene Family; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Nicotinic; Smoking; Tobacco Use Disorder

Atlanto-axial joint involvement as exclusive manifestation of juvenile idiopathic arthritis (JIA). - Taddio, A; Pellegrin, M C; Gregori, M; Wientroub, S; Padeh, S; Lepore, L (Clin Exp Rheumatol, 2011)
Keywords: Antirheumatic Agents; Arthritis, Juvenile; Atlanto-Axial Joint; Child; Dislocations; Female; Glucocorticoids; Humans; Magnetic Resonance Imaging; Pulse Therapy, Drug; Torticollis; Treatment Outcome; Uveitis

Celiac disease and immigration in Northeastern Italy: the "drawn double nostalgia" of "cozonac" and "panettone" slices. - Parco, Sergio; Città, Angelo; Vascotto, Fulvia; Tamaro, Giorgio (Clin Exp Gastroenterol, 2011)
Many investigators consider children's drawings to be an important test in the evaluation of stress and anxiety, but few studies have examined the reliability and validity of indicators of emotional distress in children's projective drawings. In this report, we describe screening tests in children coming to the Friuli Venezia Giulia region in Northeastern Italy from non-European Union regions and suspected to have celiac disease, the problems involved in diagnosis of the disease, and the "drawn double nostalgia" of Romanian children for both Italian food and traditional Romanian foods. Of 3150 Western European cases, we found 712 with positive antibodies for IgA/IgG antitransglutaminase, 174 with a positive antiendomysium antibody confirmation test, and 20 with an IgA deficit. Of the children examined, 93% were children native to Western Europe, 4% were immigrants from Eastern Europe, and 1.6% originated from Africa. Among these, four Romanian children with celiac disease brought in their drawings, as requested in a hospital questionnaire. The prevalence of celiac disease is destined to increase among immigrants. Economic problems are common, and the twin nostalgia of immigrant children for foods and tastes that are "cozonac" (from the native country) and "panettone" (Italian cake flavor) represents a problem that will be difficult to resolve. Only some children's hospitals in Italy, ie, Burlo Garofolo and Gaslini, public and private foundations, or volunteer associations would be able to deal with this problem.

Childhood chronic anterior uveitis associated with vernal keratoconjunctivitis (VKC): successful treatment with topical tacrolimus. Case series. - Taddio, Andrea; Cimaz, Rolando; Caputo, Roberto; de Libero, Cinzia; Di Grande, Laura; Simonini, Gabriele; Mori, Francesca; Novembre, Elio; Pucci, Neri (Pediatr Rheumatol Online J, 2011)
Uveitis treatment involves topical corticosteroids along with cycloplegic-mydriatics. Particularly severe cases may require systemic corticosteroids and immunosuppressive drugs. Vernal keratoconjunctivitis (VKC) treatment consists of a brief period of topical corticosteroids and/or cyclosporine. In patients refractory to traditional treatment, the use of 0.1% topical ophtalmic FK- 506 (tacrolimus) ointment has been occasionally reported.This is the first report of the coexistence of uveitis and VKC. The documented response to topical tacrolimus eyedrop of uveitis and VKC is also of interest, in particular since to our knowledge there are no published reports on its clinical use in uveitis.

Clinical heterogeneity and diagnostic delay of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy syndrome. - Mazza, Cinzia; Buzi, Fabio; Ortolani, Federica; Vitali, Alberto; Notarangelo, Lucia D; Weber, Giovanna; Bacchetta, Rosa; Soresina, Annarosa; Lougaris, Vassilios; Greggio, Nella A; Taddio, Andrea; Pasic, Srdjan; et al. (Clin Immunol, 2011)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive organ-specific autoimmune disorder that is characterized by a variable combination of (i) chronic mucocutaneous candidiasis, (ii) polyendocrinopathy and/or hepatitis and (iii) dystrophy of the dental enamel and nails. We analyzed the AIRE (autoimmune regulator) gene in subjects who presented any symptom that has been associated with APECED, including candidiasis and autoimmune endocrinopathy. We observed that 83.3% of patients presented at least two of the three typical manifestations of APECED, while the remaining 16.7% of patients showed other signs of the disease. Analysis of the genetic diagnosis of these subjects revealed that a considerable delay occurs in the majority of patients between the appearance of symptoms and the diagnosis. Overall, the mean diagnostic delay in our patients was 10.2 years. These results suggest that molecular analysis of AIRE should be performed in patients with relapsing mucocutaneous candidiasis for early identification of APECED.
Keywords: Adolescent; Adult; Child; Child, Preschool; Heterozygote; Homozygote; Humans; Middle Aged; Mutation; Polyendocrinopathies, Autoimmune; Time Factors; Young Adult

Differential action of 3-hydroxyanthranilic acid on viability and activation of stimulated lymphocytes. - Piscianz, Elisa; Cuzzoni, Eva; De Iudicibus, Sara; Valencic, Erica; Decorti, Giuliana; Tommasini, Alberto (Int Immunopharmacol, 2011)
Lymphocytes proliferation after antigen-driven activation leads to an increase in cell count, which could last some week, until apoptosis mechanisms allow the homeostatic control of the system. During the first days of this stimulation, activated lymphocytes display high resistance to apoptosis and to most immunosuppressive drugs. According to the literature, few compounds have been described to kill recently activated cells, by inhibiting metabolic processes fundamental to proliferation. The aim of our work was to evaluate comparatively these different compounds, in order to identify the best strategy to kill cells that have undergone proliferation, while sparing the repertoire of resting cells. After preliminary experiments, 3-HAA and bortezomib were selected as the most suitable compounds for our purposes. The possible synergic effect of 3-HAA with bortezomib or with manganese ions was also assessed. 3-HAA was confirmed to be the most reliable pharmacologic approach to inhibit proliferation with acceptable toxicity on resting cells. While in the case of PHA stimulation 3-HAA led to death of most lymphocytes, only a minor percentage of cells were killed after allo-stimulation, suggesting that the effect is proportional to the percentage of stimulated lymphocytes. Manganese ions further enhanced this effect, while results with bortezomib seemed to be less consistent. These results deserve further investigations to develop new procedures for targeting activated cells with pharmacological approaches.
Keywords: 3-Hydroxyanthranilic Acid; Boronic Acids; Cell Survival; Cells, Cultured; Humans; Lymphocyte Activation; Lymphocytes; Manganese; Pyrazines

The farnesyltransferase inhibitors tipifarnib and lonafarnib inhibit cytokines secretion in a cellular model of mevalonate kinase deficiency. - Marcuzzi, Annalisa; De Leo, Luigina; Decorti, Giuliana; Crovella, Sergio; Tommasini, Alberto; Pontillo, Alessandra (Pediatr Res, 2011)
The shortage of geranylgeranyl-pyrophosphate (GGPP) was associated to an increased IL-1β release in the autoinflammatory syndrome mevalonate kinase deficiency (MKD), a rare inherited disease that has no specific therapy. Farnesyltransferase inhibitors (FTIs) act at the end of mevalonate pathway. Two FTIs, tipifarnib (Tip) and lonafarnib (Lon), were therefore evaluated as possible therapeutical choices for the treatment of MKD. FTIs could lead to a redirection of the limited available number of mevalonate intermediates preferentially to GGPP synthesis, eventually preventing the uncontrolled inflammatory response. The effect of Tip and Lon on intracellular cholesterol level (ICL) and on proinflammatory cytokines secretion was evaluated in a cellular model of MKD, chemically obtained treating RAW 264.7 cells with lovastatin (Lova) and alendronate (Ald). The combination of FTIs with the isoprenoid geraniol (GOH) was also tested both in this model and in monocytes isolated from MKD patients. Tip and Lon proved to revert the ICL lowering and to significantly reduce the lipopolysaccharide-induced cytokines secretion in Ald-Lova -RAW 264.7 cells. This anti-inflammatory effect was amplified combining the use of GOH with FTIs. The effect of GOH and Tip was successfully replicated in MKD patients' monocytes. Tip and Lon showed a dramatic anti-inflammatory effect in monocytes where mevalonate pathway was chemically or genetically impaired.
Keywords: Alendronate; Animals; Anti-Inflammatory Agents; Cell Line; Child; Child, Preschool; Cholesterol; Cytokines; Dose-Response Relationship, Drug; Enzyme Inhibitors; Farnesyltranstransferase; Humans; Inflammation Mediators; Lovastatin; Male; Mevalonate Kinase Deficiency; Mice; Monocytes; Phosphotransferases (Alcohol Group Acceptor); Piperidines; Polyenes; Polyisoprenyl Phosphates; Polyunsaturated Alkamides; Pyridines; Quinolones; Terpenes

Foreign children with cancer in Italy. - Rondelli, Roberto; Dini, Giorgio; De Rosa, Marisa; Quarello, Paola; Bisogno, Gianni; Aricò, Maurizio; Vasconcelos, Carivaldo; Tamaro, Paolo; Casazza, Gabriella; Zecca, Marco; De Laurentis, Clementina; Porta, Fulvio; et al. (Ital J Pediatr, 2011)
BACKGROUND: There has been a noticeable annual increase in the number of children coming to Italy for medical treatment, just like it has happened in the rest of the European Union. In Italy, the assistance to children suffering from cancer is assured by the current network of 54 centres members of the Italian Association of Paediatric Haematology and Oncology (AIEOP), which has kept records of all demographic and clinical data in the database of Mod.1.01 Registry since 1989. METHODS: We used the information stored in the already mentioned database to assess the impact of immigration of foreign children with cancer on centres' activity, with the scope of drawing a map of the assistance to these cases. RESULTS: Out of 14,738 cases recorded by all centres in the period from 1999 to 2008, 92.2% were born and resident in Italy, 4.1% (608) were born abroad and living abroad and 3.7% (538) were born abroad and living in Italy. Foreign children cases have increased over the years from 2.5% in 1999 to. 8.1% in 2008.Most immigrant children came from Europe (65.7%), whereas patients who came from America, Asia and Oceania amounted to 13.2%, 10.1%, 0.2%, respectively. The immigrant survival rate was lower compared to that of children who were born in Italy. This is especially true for acute lymphoblastic leukaemia patients entered an AIEOP protocol, who showed a 10-years survival rate of 71.0% vs. 80.7% (p < 0.001) for immigrants and patients born in Italy, respectively. CONCLUSIONS: Children and adolescents are an increasingly important part of the immigration phenomenon, which occurs in many parts of the world. In Italy the vast majority of children affected by malignancies are treated in AIEOP centres. Since immigrant children are predominantly treated in northern Italy, these centres have developed a special expertise in treating immigrant patients, which is certainly very useful for the entire AIEOP network.
Keywords: Adolescent; Africa; Asia; Child; Child, Preschool; Databases, Factual; Emigrants and Immigrants; Ethnic Groups; Europe, Eastern; European Union; Female; Humans; Incidence; Infant; Infant, Newborn; Italy; Male; Neoplasms; North America; Oceania; Prevalence; Retrospective Studies; South America; Survival Rate

Forkhead box protein 3 (FOXP3) mutations lead to increased TH17 cell numbers and regulatory T-cell instability. - Passerini, Laura; Olek, Sven; Di Nunzio, Sara; Barzaghi, Federica; Hambleton, Sophie; Abinun, Mario; Tommasini, Alberto; Vignola, Silvia; Cipolli, Marco; Amendola, Mario; Naldini, Luigi; Guidi, Luisa; et al. (J Allergy Clin Immunol, 2011)
Keywords: Forkhead Transcription Factors; Gene Expression Regulation; Genetic Diseases, X-Linked; Humans; Immunologic Deficiency Syndromes; Intestinal Diseases; Male; Mutation; Polyendocrinopathies, Autoimmune

Functional type 1 regulatory T cells develop regardless of FOXP3 mutations in patients with IPEX syndrome. - Passerini, Laura; Di Nunzio, Sara; Gregori, Silvia; Gambineri, Eleonora; Cecconi, Massimiliano; Seidel, Markus G; Cazzola, Giantonio; Perroni, Lucia; Tommasini, Alberto; Vignola, Silvia; Guidi, Luisa; Roncarolo, Maria G; et al. (Eur J Immunol, 2011)
Mutations of forkhead box p3 (FOXP3), the master gene for naturally occurring regulatory T cells (nTregs), are responsible for the impaired function of nTregs, resulting in an autoimmune disease known as the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. The relevance of other peripheral tolerance mechanisms, such as the presence and function of type 1 regulatory T (Tr1) cells, the major adaptive IL-10-producing Treg subset, in patients with IPEX syndrome remains to be clarified. FOXP3(mutated) Tr1-polarized cells, differentiated in vitro from CD4(+) T cells of four IPEX patients, were enriched in IL-10(+) IL-4(-) IFN-γ(+) T cells, a cytokine production profile specific for Tr1 cells, and expressed low levels of FOXP3 and high levels of Granzyme-B. IPEX Tr1 cells were hypoproliferative and suppressive, thus indicating that FOXP3 mutations did not impair their function. Furthermore, we isolated Tr1 cell clones from the peripheral blood of one FOXP3(null) patient, demonstrating that Tr1 cells are present in vivo and they can be expanded in vitro in the absence of WT FOXP3. Overall, our results (i) show that functional Tr1 cells differentiate independently of FOXP3, (ii) confirm that human Tr1 and nTregs are distinct T-cell lineages, and (iii) suggest that under favorable conditions Tr1 cells could exert regulatory functions in IPEX patients.
Keywords: Cell Differentiation; Cell Lineage; Cells, Cultured; Enteritis; Forkhead Transcription Factors; Genetic Diseases, X-Linked; Humans; Immunity, Innate; Interleukin-2 Receptor alpha Subunit; Mutation; Polyendocrinopathies, Autoimmune; Syndrome; T-Lymphocytes, Regulatory

Gastroesophageal reflux disease at any cost: a dangerous paediatric attitude. - Taddio, Andrea; Bersanini, Chiara; Basile, Lucio; Fontana, Massimo; Ventura, Alessandro (Acta Paediatr, 2011)
Keywords: Diagnostic Errors; Gastroesophageal Reflux; Humans; Inappropriate Prescribing; Infant; Infant, Newborn; Male; Proton Pump Inhibitors; Spasms, Infantile

Gastrointestinal Foxp3 expression in normal, inflammatory and neoplastic conditions. - Villanacci, Vincenzo; Not, Tarcisio; Nascimbeni, Riccardo; Ferrara, Fortunato; Tommasini, Alberto; Manenti, Stefania; Antonelli, Elisabetta; Bassotti, Gabrio (Pathology, 2011)
BACKGROUND: Foxp3(+) regulatory T lymphocytes (T-regs) represent an important regulatory cell subset in inflammatory, preneoplastic and neoplastic conditions of the gastrointestinal tract. METHODS: Inflammatory, preneoplastic and neoplastic conditions of the gastrointestinal tract (189 cases) were studied with the evaluation of Foxp3 regulatory T cells based on immunohistochemistry. RESULTS: Few Foxp3(+) cells were found in controls and inflammatory conditions (oesophagitis, gastritis, coeliac disease, inflammatory bowel disease); in preneoplastic and neoplastic conditions the number of Foxp3(+) cells was significatively increased. CONCLUSIONS: In normal conditions the number of mucosal lymphocytes is very low throughout the gastro-intestinal tract; in active coeliac disease patients or on a gluten-free diet, only a slight increase in Foxp3(+) cells may be found. Gastrointestinal cancers are associated with higher Foxp3(+) cell proportion, compared with microscopically normal tissue and with precancerous conditions. However, it is uncertain whether the increase in these regulatory cells is a cause or a consequence of tumour progression.
Keywords: Adult; Aged; Celiac Disease; Cell Count; Disease Progression; Esophagitis; Female; Forkhead Transcription Factors; Gastric Mucosa; Gastritis; Humans; Inflammatory Bowel Diseases; Lymphocytes; Male; Middle Aged; Precancerous Conditions; Stomach Diseases; Stomach Neoplasms; Young Adult

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

High incidence of NLRP3 somatic mosaicism in patients with chronic infantile neurologic, cutaneous, articular syndrome: results of an International Multicenter Collaborative Study. - Tanaka, Naoko; Izawa, Kazushi; Saito, Megumu K; Sakuma, Mio; Oshima, Koichi; Ohara, Osamu; Nishikomori, Ryuta; Morimoto, Takeshi; Kambe, Naotomo; Goldbach-Mansky, Raphaela; Aksentijevich, Ivona; de Saint Basile, Geneviève; et al. (Arthritis Rheum, 2011)
OBJECTIVE: Chronic infantile neurologic, cutaneous, articular (CINCA) syndrome, also known as neonatal-onset multisystem inflammatory disease (NOMID), is a dominantly inherited systemic autoinflammatory disease. Although heterozygous germline gain-of-function NLRP3 mutations are a known cause of this disease, conventional genetic analyses fail to detect disease-causing mutations in ∼40% of patients. Since somatic NLRP3 mosaicism has been detected in several mutation-negative NOMID/CINCA syndrome patients, we undertook this study to determine the precise contribution of somatic NLRP3 mosaicism to the etiology of NOMID/CINCA syndrome. METHODS: An international case-control study was performed to detect somatic NLRP3 mosaicism in NOMID/CINCA syndrome patients who had shown no mutation during conventional sequencing. Subcloning and sequencing of NLRP3 was performed in these mutation-negative NOMID/CINCA syndrome patients and their healthy relatives. Clinical features were analyzed to identify potential genotype-phenotype associations. RESULTS: Somatic NLRP3 mosaicism was identified in 18 of the 26 patients (69.2%). Estimates of the level of mosaicism ranged from 4.2% to 35.8% (mean ± SD 12.1 ± 7.9%). Mosaicism was not detected in any of the 19 healthy relatives (18 of 26 patients versus 0 of 19 relatives; P < 0.0001). In vitro functional assays indicated that the detected somatic NLRP3 mutations had disease-causing functional effects. No differences in NLRP3 mosaicism were detected between different cell lineages. Among nondescript clinical features, a lower incidence of mental retardation was noted in patients with somatic mosaicism. Genotype-matched comparison confirmed that patients with somatic NLRP3 mosaicism presented with milder neurologic symptoms. CONCLUSION: Somatic NLRP3 mutations were identified in 69.2% of patients with mutation-negative NOMID/CINCA syndrome. This indicates that somatic NLRP3 mosaicism is a major cause of NOMID/CINCA syndrome.
Keywords: Adolescent; Adult; Carrier Proteins; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Genetic Association Studies; Humans; Infant; Male; Mosaicism

High prevalence of BK polyomavirus sequences in human papillomavirus-16-positive precancerous cervical lesions. - Comar, Manola; Bonifacio, Daniela; Zanconati, Fabrizio; Di Napoli, Michela; Isidoro, Erica; Martini, Fernanda; Torelli, Lucio; Tognon, Mauro (J Med Virol, 2011)
High- and low-grade cervical lesions were analyzed for the presence of polyomavirus (PYV) and human papillomavirus (HPV) sequences. In precancerous cervical lesions, the overall prevalence of PYV sequences was 44% (41/93). Specifically, among the PYV-positive samples, 83% (34/41) tested positive for BK polyomavirus (BKV) sequences, whereas 17% (7/41) were positive for JC-virus. None of the samples were positive for simian virus 40. The presence of BKV DNA in high-grade squamous intraepithelial lesions was confirmed by in situ PCR. BKV sequences were detected more frequently in high-grade squamous intraepithelial lesions, together with the genotype HPV-16. The association of BKV with precancerous cervical lesions suggests that this polyomavirus participates with HPV-16 in the cell transformation process. Alternatively, BKV might multiply better in HPV-16-positive cells from precancerous cervical lesions than in HPV-16-negative cells.
Keywords: Adult; BK Virus; Cervical Intraepithelial Neoplasia; Cervix Uteri; DNA, Viral; Female; Human papillomavirus 16; Human papillomavirus 18; Human papillomavirus 31; Humans; JC Virus; Middle Aged; Oncogene Proteins, Viral; Papillomavirus Infections; Precancerous Conditions; Simian virus 40; Uterine Cervical Diseases

In vivo distribution of β2 glycoprotein I under various pathophysiologic conditions. - Agostinis, Chiara; Biffi, Stefania; Garrovo, Chiara; Durigutto, Paolo; Lorenzon, Andrea; Bek, Alpan; Bulla, Roberta; Grossi, Claudia; Borghi, Maria O; Meroni, Pierluigi; Tedesco, Francesco (Blood, 2011)
In vitro studies have documented β2 glycoprotein I (β2GPI) binding to endothelial cells (ECs) and trophoblast using antiphospholipid antibodies. The in vivo binding of β2GPI to these cells and the conditions that favor their interaction have not been investigated. We analyzed the in vivo distribution of cyanine 5.5-labeled β2GPI in mice and evaluated the effect of pregnancy and circulating antibodies on its tissue localization. The signal was detected in the liver by whole body scan and ex vivo analysis. The β2GPI failed to bind to the vascular endothelium and reacted only with the ECs of uterine vessels. In pregnant mice the protein was localized on ECs and trophoblast at the embryo implantation sites. Immunized mice showed a similar β2GPI biodistribution to naive mice but the immunized pregnant animals exhibited a significant increase in fetal loss associated with C3 and C9 deposition at the implantation sites. Treatment of mice with LPS after β2GPI-Cy5.5 injection promoted protein localization on gut and brain ECs associated with IgG, C1q, and C9 deposition in immunized mice. These findings indicate that β2GPI binding to EC requires priming with pro-inflammatory factors which is not needed for uterine and placental localization probably dependent on hormonal changes.
Keywords: Animals; beta 2-Glycoprotein I; Complement C1q; Complement C3; Complement C9; Endothelial Cells; Endothelium, Vascular; Female; Fetal Death; Humans; Mice; Mice, Inbred BALB C; Pregnancy; Trophoblasts; Uterus

Long-term clinical profile of children with the low-penetrance R92Q mutation of the TNFRSF1A gene. - Pelagatti, M A; Meini, A; Caorsi, R; Cattalini, M; Federici, S; Zulian, F; Calcagno, G; Tommasini, A; Bossi, G; Sormani, M P; Caroli, F; Plebani, A; et al. (Arthritis Rheum, 2011)
OBJECTIVE: To analyze the long-term impact of the R92Q mutation of TNFRSF1A in children with periodic fever, in comparison with children with tumor necrosis factor receptor-associated periodic syndrome (TRAPS) with TNFRSF1A structural mutations and children with periodic fever of unknown origin fulfilling the criteria for periodic fever, aphthosis, pharyngitis, and adenitis syndrome (PFAPA). METHODS: The extracellular region of TNFRSF1A was analyzed in 720 consecutive children with periodic fever, using denaturing high-performance liquid chromatography and DNA sequencing. Followup data on 11 pediatric patients with TNFRSF1A structural mutations (cysteine or T50M), 23 pediatric patients with an R92Q substitution, and 64 pediatric patients with PFAPA were collected during routine clinic visits. The 50-item Child Health Questionnaire was used to assess health-related quality of life (HRQOL). RESULTS: The frequency of typical TRAPS-related clinical manifestations was significantly lower and the impact of the disease on HRQOL was significantly reduced in patients with the R92Q mutation compared with TRAPS patients carrying structural mutations of TNFRSF1A. Followup data on 11 TRAPS patients with TNFRSF1A structural mutations (mean followup 7.9 years), 16 patients with theR92Q substitution (mean followup 7.3 years), and 64 patients with PFAPA (mean followup 5.2 years) were available. Patients with R92Q mutations and patients with PFAPA displayed a higher rate of self-resolution or amelioration of the fever episodes than did TRAPS patients with structural mutations. CONCLUSION: Although some cases may progress to a more chronic disease course, the majority of children with an R92Q mutation of the TNFRSFA1 gene show a milder disease course than that in children with TNFRSFA1 structural mutations and have a high rate of spontaneous resolution and amelioration of the recurrent fever episodes.
Keywords: Adolescent; Antirheumatic Agents; Biological Therapy; Child; Child, Preschool; Familial Mediterranean Fever; Female; Fever; Follow-Up Studies; Genotype; Health Surveys; Humans; Infant; Interleukin 1 Receptor Antagonist Protein; Longitudinal Studies; Lymphadenitis; Male; Mutation; Pharyngitis; Quality of Life; Receptors, Tumor Necrosis Factor; Receptors, Tumor Necrosis Factor, Type I; Recurrence; Retrospective Studies; Steroids; Syndrome

Management of immigration and pregnancy screening in northeastern Italy. - Tamaro, Giorgio; Parco, Sergio (Risk Manag Healthc Policy, 2011)
This study assesses the impact of immigration in Friuli Venezia Giulia, a region of northeastern Italy, on the epidemiological features of hemoglobin patterns and on prothrombotic and trisomy risk in pregnancy for patients of non-Italian origin. This study follows a series of studies on the incidence of thalassemia and other hemoglobinopathies with reduced globin chain synthesis, that were performed during the postwar (1939-45) period in Friuli Venezia Giulia following immigration into the region from Istria and Sardinia (regions of northern and central Italy). Current data show that today's constantly growing immigration into the region differs from previous decades, in terms of origin and quantity of migrants, who mainly come from third world countries. This has a significant impact on health care issues, and more specifically on prospective health screening for foreigners. The authors conclude that scholastic education and hospital services, either public or private, and voluntary associations, may contribute to solving the problem, but only in terms of training and organization, for non-European Union citizens arriving in northern Italy and neighboring areas, especially those from Africa, Asia, Latin America, and eastern Europe.

Marriage and parenthood among childhood cancer survivors: a report from the Italian AIEOP Off-Therapy Registry. - Pivetta, Emanuele; Maule, Milena M; Pisani, Paola; Zugna, Daniela; Haupt, Riccardo; Jankovic, Momcilo; Aricò, Maurizio; Casale, Fiorina; Clerico, Anna; Cordero di Montezemolo, Luca; Kiren, Valentina; Locatelli, Franco; et al. (Haematologica, 2011)
BACKGROUND: The aim of this study was to describe the patterns of marriage and parenthood in a cohort of childhood cancer survivors included in the Off-Therapy Registry maintained by the Italian Association of Pediatric Hematology and Oncology. DESIGN AND METHODS: We analyzed a cohort of 6,044 patients diagnosed with cancer between 1960 and 1998, while aged 0 to 14 years and who were 18 years old or older by December 2003. They were followed up through the regional vital statistics registers until death or the end of follow up (October 30, 2006), whichever occurred first, and their marital status and date of birth of their children were recorded. The cumulative probabilities of being married and having a first child were computed by gender and compared by tumor type within the cohort. Marriage and fertility rates (the latter defined as the number of live births per woman-year) were compared with those of the Italian population of the same age, gender, area of residence and calendar period by means of the observed to expected (O/E) ratios. RESULTS: During the follow-up period, 4,633 (77%) subjects had not married. The marriage O/E ratios were 0.56 (95% CI: 0.51-0.61) and 0.70 (95% CI: 0.65-0.76) among men and women, respectively. Overall, 263 men had 367 liveborn children, and 473 women had 697 liveborn children. The female fertility O/E ratio was 0.57 (95% CI: 0.53-0.62) overall, and 1.08 (95% CI: 0.99-1.17) when analyses were restricted to married/cohabiting women CONCLUSIONS: Childhood cancer survivors are less likely to marry and to have children than the general population, confirming the life-long impact of their previous disease on their social behavior and choices. The inclusion of counseling in the strategies of management and long-term surveillance of childhood cancer patients could be beneficial to survivors as they approach adulthood.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Female; Follow-Up Studies; Hematologic Neoplasms; Humans; Infant; Infant, Newborn; Italy; Male; Marriage; Middle Aged; Parents; Registries; Survivors

Mast cells are critically involved in serum-mediated vascular leakage in chronic urticaria beyond high-affinity IgE receptor stimulation. - Bossi, F; Frossi, B; Radillo, O; Cugno, M; Tedeschi, A; Riboldi, P; Asero, R; Tedesco, F; Pucillo, C (Allergy, 2011)
BACKGROUND: Chronic urticaria (CU) is one of the most common skin disorders whose pathogenic mechanisms are not fully clarified. Autoimmune aetiology can be ascribed to 45% of patients with CU, and basophil histamine release is positive in 40% of cases. Our aim was to use a novel approach to evaluate the serum permeabilizing effect to identify the mediators of endothelial cell (EC) leakage and to define the role of mast cells (MCs) in the process. METHODS: Permeabilizing activity of sera from 19 patients with CU and 11 healthy blood donors was evaluated by measuring serum-induced degranulation of two MC lines, expressing (LAD2) or lacking (HMC-1) the IgE receptor. Mast cell supernatant (SN) was then incubated with an EC monolayer, and endothelial permeability was evaluated by Fluorescein isothiocyanate-bovine serum albumin leakage in a transwell system. RESULTS: All 19 patient sera failed to induce direct EC leakage, but 15/19 and 17/19 promoted degranulation of HMC-1 and LAD2, respectively. Interestingly, 85% of autologous serum skin test-negative sera were able to cause MC degranulation. Also, 17/19 SNs from HMC-1 and all SNs from LAD2 incubated with CU sera increased endothelial permeability. Endothelial cell leakage remained unchanged after Ig depletion and was prevented by antihistamine, platelet-activating factor or leukotriene antagonist. CONCLUSIONS: Our study shows that CU sera are able to degranulate MCs through an IgE- and IgG-independent mechanism. The nature of histamine-releasing factors involved is still unclear, but our finding opens new ways to the understanding of the pathogenesis of CU, particularly in patients not showing circulating autoantibodies to FcεRI or IgE.
Keywords: Adult; Aged; Capillary Permeability; Chronic Disease; Endothelial Cells; Female; Histamine Release; Humans; Male; Mast Cells; Middle Aged; Receptors, IgE; Serum; Urticaria; Young Adult

Merkel cell polyomavirus DNA sequences in the buffy coats of healthy blood donors. - Pancaldi, Cecilia; Corazzari, Valentina; Maniero, Stefania; Mazzoni, Elisa; Comar, Manola; Martini, Fernanda; Tognon, Mauro (Blood, 2011)
Merkel cell polyomavirus (MCPyV), a DNA tumor virus, has been found to be associated with Merkel cell carcinoma and chronic lymphocytic leukemia. MCPyV sequences have also been detected in various normal tissues in tumor-affected patients. Immunologic studies have detected MCPyV antibodies in as many as 80% of healthy blood donors. This high seroprevalence suggests that MCPyV infection is widespread in humans. In our study, buffy coats, which were examined for MCPyV DNA Tag sequences, showed a prevalence of 22%. Viral DNA load was revealed in blood samples from 10 to 100 molecules/100 000 cells. DNA sequencing confirmed that polymerase chain reaction amplicons belong to the MCPyV strain, MKL-1. To interpret the putative role of MCPyV in chronic lymphocytic leukemia, we may infer that, during a long period of viral persistence in blood cells, this DNA tumor virus may generate mutants, which are able to participate as cofactors in the multistep process of cell transformation.
Keywords: Adult; Aged; Base Sequence; Blood Buffy Coat; Carcinoma, Merkel Cell; Databases, Nucleic Acid; DNA, Viral; Expressed Sequence Tags; Humans; Italy; Middle Aged; Molecular Sequence Data; Polymerase Chain Reaction; Polyomavirus; Polyomavirus Infections; Prevalence; Reverse Transcriptase Polymerase Chain Reaction; Sequence Alignment; Sequence Analysis, DNA; Tumor Virus Infections; Viral Load; Young Adult

A multicenter, case-control study on risk factors for antepartum stillbirth. - Facchinetti, Fabio; Alberico, Salvatore; Benedetto, Chiara; Cetin, Irene; Cozzolino, Sabrina; Di Renzo, Gian Carlo; Del Giovane, Cinzia; Ferrari, Francesca; Mecacci, Federico; Menato, Guido; Tranquilli, Andrea L; Baronciani, Dante (J Matern Fetal Neonatal Med, 2011)
OBJECTIVE: As the influence of socio-demographic variables, lifestyle and medical conditions on the epidemiology of stillbirth (SB) is modified by population features, we aimed at investigating the role played by these factors on the incidence of SB in a developed country. STUDY DESIGN: Multivariate logistic regression analysis (OR with 95% CI) was utilized in a prospective multicentre nested case-control study to compare in a 1:2 ratio stillborn of >22 weeks gestation with matched for gestational age live-born (LB) infants. Intrapartum SB were excluded. RESULTS: Two hundred fifty-four consecutive SBs and 497 LBs were enrolled. Socio-demographic variables were equally distributed. Fetal malformations (7.96, 2.69-23.55), severe intrauterine growth restriction (IUGR) (birthweight ≤ 5(th) %ile) (4.32, 2.27?8.24), BMI > 25 (2.87, 1.90-4.33), and preeclampsia (PE, 0.40, 0.21-0.77) were recognized as independent predictors for SB. At term, only BMI > 25 was associated with SB (7.70, 2.9-20.5). CONCLUSION: Fetal malformations, severe IUGR and maternal BMI > 25 were associated with a significant increase in the risk of SB; PE presented instead a protective role. Maternal BMI > 25 was the only risk factor for SB identified in term pregnancies.
Keywords: Adult; Case-Control Studies; Cause of Death; Congenital Abnormalities; Female; Fetal Death; Fetal Growth Retardation; Humans; Infant, Newborn; Male; Obstetric Labor Complications; Pre-Eclampsia; Pregnancy; Risk Factors; Stillbirth; Young Adult

Multiple loci are associated with white blood cell phenotypes. - Nalls, Michael A; Couper, David J; Tanaka, Toshiko; van Rooij, Frank J A; Chen, Ming-Huei; Smith, Albert V; Toniolo, Daniela; Zakai, Neil A; Yang, Qiong; Greinacher, Andreas; Wood, Andrew R; Garcia, Melissa; et al. (PLoS Genet, 2011)
White blood cell (WBC) count is a common clinical measure from complete blood count assays, and it varies widely among healthy individuals. Total WBC count and its constituent subtypes have been shown to be moderately heritable, with the heritability estimates varying across cell types. We studied 19,509 subjects from seven cohorts in a discovery analysis, and 11,823 subjects from ten cohorts for replication analyses, to determine genetic factors influencing variability within the normal hematological range for total WBC count and five WBC subtype measures. Cohort specific data was supplied by the CHARGE, HeamGen, and INGI consortia, as well as independent collaborative studies. We identified and replicated ten associations with total WBC count and five WBC subtypes at seven different genomic loci (total WBC count-6p21 in the HLA region, 17q21 near ORMDL3, and CSF3; neutrophil count-17q21; basophil count- 3p21 near RPN1 and C3orf27; lymphocyte count-6p21, 19p13 at EPS15L1; monocyte count-2q31 at ITGA4, 3q21, 8q24 an intergenic region, 9q31 near EDG2), including three previously reported associations and seven novel associations. To investigate functional relationships among variants contributing to variability in the six WBC traits, we utilized gene expression- and pathways-based analyses. We implemented gene-clustering algorithms to evaluate functional connectivity among implicated loci and showed functional relationships across cell types. Gene expression data from whole blood was utilized to show that significant biological consequences can be extracted from our genome-wide analyses, with effect estimates for significant loci from the meta-analyses being highly corellated with the proximal gene expression. In addition, collaborative efforts between the groups contributing to this study and related studies conducted by the COGENT and RIKEN groups allowed for the examination of effect homogeneity for genome-wide significant associations across populations of diverse ancestral backgrounds.
Keywords: Genetic Loci; Genome-Wide Association Study; Humans; Leukocyte Count; Leukocytes; Molecular Epidemiology; Multigene Family; Phenotype; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Neonatal necrotizing tracheobronchitis. - Bua, Jenny; Trappan, Antonella; Demarini, Sergio; Grasso, Domenico; Schleef, Jurgen; Zennaro, Floriana (J Pediatr, 2011)
Keywords: Bronchitis; Bronchoscopy; High-Frequency Ventilation; Humans; Infant, Newborn; Male; Necrosis; Respiratory Insufficiency; Respiratory Mucosa; Tracheitis

Osteoprotegerin induces morphological and functional alterations in mouse pancreatic islets. - Toffoli, Barbara; Bernardi, Stella; Candido, Riccardo; Sabato, Nicoletta; Carretta, Renzo; Corallini, Federica; Secchiero, Paola; Zauli, Giorgio; Fabris, Bruno (Mol Cell Endocrinol, 2011)
Although serum osteoprotegerin (OPG) is significantly increased in diabetic subjects, its potential role in beta cell dysfunction has not been investigated. This study aimed to assess the effect of full-length OPG administered in vivo in mice on pancreatic islet structure and function and its interaction with the renin-angiotensin system (RAS). OPG-treated mice showed increased islet monocyte/macrophage infiltration, fibrosis and apoptosis with reduction of islet function. The remodeling of islet architecture was associated with increased pancreatic expression of components of the RAS, growth factor genes (transforming growth factor β and connective tissue growth factor) and inflammatory molecules (monocyte chemotactic protein-1 and vascular adhesion molecule type 1). Prevention of these changes with improvement of insulin secretion was observed in ramipril treated animals. Our data suggest that OPG might play an important role in promoting beta cell dysfunction and that the upregulation of the local RAS represents one possible mechanism responsible for the OPG-induced beta cell dysfunction.
Keywords: Animals; Apoptosis; Blood Glucose; Blood Pressure; Body Weight; Cell Lineage; Cell Movement; Chemokine CCL2; Connective Tissue Growth Factor; Fibrosis; Gene Expression Regulation; Humans; Insulin; Islets of Langerhans; Macrophages; Mice; Monocytes; Organ Size; Osteoprotegerin; Peptidyl-Dipeptidase A; Receptor, Angiotensin, Type 1; Systole; Transforming Growth Factor beta; Vascular Cell Adhesion Molecule-1

Osteoprotegerin promotes vascular fibrosis via a TGF-β1 autocrine loop. - Toffoli, Barbara; Pickering, Raelene J; Tsorotes, Despina; Wang, Bo; Bernardi, Stella; Kantharidis, Phillip; Fabris, Bruno; Zauli, Giorgio; Secchiero, Paola; Thomas, Merlin C (Atherosclerosis, 2011)
BACKGROUND: This study was designed to evaluate the potential role of osteoprotegerin (OPG) in arterial fibrosis. METHODS: Aortic samples were analyzed after in vivo treatment of ApoE(-/-) mice with recombinant human OPG. Mouse vascular smooth muscle cells (VSMC) were exposed in vitro to recombinant OPG and analyzed for markers of inflammation and fibrosis, such as fibronectin, collagen I, III, IV and transforming growth factor-β1 (TGF-β1). Conversely, the potential modulation of endogenous OPG expression and release by VSMC was analyzed in response to different pro-atherosclerotic cytokines, TGF-β1, platelet derived growth factor (PDGF) and angiogensin II (Ang II). RESULTS: In vivo treatment with human OPG induced signs of fibrosis and up-regulated the arterial expression of TGF-β1. Consistently, in vitro treatment of VSMC with human OPG induced the expression of fibronectin, collagen type I, III, IV, metalloprotein-2 (MMP-2) and MMP-9, as well as of TGF-β1. On the other hand, exposure to recombinant TGF-β1 promoted the expression/release of endogenous OPG and mediated the increase of OPG release induced by PDGF and Ang II in VSMC. CONCLUSIONS: Taken together, these data support a pathogenic role for OPG in the development and progression of atherosclerotic lesions and suggest the existence of a vicious circle between TGF-β1 and OPG.
Keywords: Animals; Apolipoproteins E; Cell Proliferation; Collagen; Fibronectins; Fibrosis; Gene Expression Regulation; Humans; Mice; Mice, Inbred C57BL; Mice, Transgenic; Muscle, Smooth, Vascular; Myocytes, Smooth Muscle; Osteoprotegerin; Platelet-Derived Growth Factor; Transforming Growth Factor beta1

A Phase II study on the safety and efficacy of a single dose of pegfilgrastim for mobilization and transplantation of autologous hematopoietic stem cells in pediatric oncohematology patients. - Cesaro, Simone; Zanazzo, Andrea Giulio; Frenos, Stefano; Luksch, Roberto; Pegoraro, Anna; Tridello, Gloria; Dallorso, Sandro (Transfusion, 2011)
BACKGROUND: Limited data are available on the use of pegfilgrastim in pediatric patients as a mobilizing agent in association with chemotherapy. STUDY DESIGN AND METHODS: This was a prospective, multicenter, Phase II study to evaluate the safety and efficacy of a single dose of 100 µg/kg pegfilgrastim in mobilizing peripheral blood stem cells (PBSCs) in pediatric patients. The primary endpoint of the study was the percentage of good mobilizers with pegfilgrastim (blood peak of CD34+ cells ≥ 20 × 10(6) /L). The results were compared with a historical control group. RESULTS: Thirty of 36 recruited patients were classified as good mobilizers (83%). The median value of circulating CD34+ at leukapheresis was 143 × 10(6) /L (range, 20 × 10(6) -1988 × 10(6) /L). No significant adverse effects were associated with the use of pegfilgrastim and no patient was withdrawn from using the drug. A blood peak of 20 × 10(6) /L or more CD34+ was observed in 33 of 36 control patients (92%) and the median CD34+ count at leukapheresis was 158 × 10(6) /kg (range, 28 × 10(6) -4529 × 10(6) /kg; p = 0.7). No significant differences were found between the two groups in terms of toxicity or other variables of mobilization. As at October 2008, 23 patients of the pegfilgrastim group and 32 patients of the filgrastim group underwent autologous transplant. No significant differences were found in terms of early toxicity, myeloid recovery, and Day 100 survival. CONCLUSION: A single dose of 100 µg/kg pegfilgrastim was safe and effective for PBSC collection in pediatric patients. We suggest that these results support the use of pegfilgrastim for pediatric patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Female; Granulocyte Colony-Stimulating Factor; Hematopoietic Stem Cell Mobilization; Humans; Infant; Male; Neoplasms; Peripheral Blood Stem Cell Transplantation; Prospective Studies; Recombinant Proteins; Transplantation, Autologous

Phospholipase C-β3 is a key modulator of IL-8 expression in cystic fibrosis bronchial epithelial cells. - Bezzerri, Valentino; d'Adamo, Pio; Rimessi, Alessandro; Lanzara, Carmen; Crovella, Sergio; Nicolis, Elena; Tamanini, Anna; Athanasakis, Emmanouil; Tebon, Maela; Bisoffi, Giulia; Drumm, Mitchell L; Knowles, Michael R; et al. (J Immunol, 2011)
Respiratory insufficiency is the major cause of morbidity and mortality in patients affected by cystic fibrosis (CF). An excessive neutrophilic inflammation, mainly orchestrated by the release of IL-8 from bronchial epithelial cells and amplified by chronic bacterial infection with Pseudomonas aeruginosa, leads to progressive tissue destruction. The anti-inflammatory drugs presently used in CF patients have several limitations, indicating the need for identifying novel molecular targets. To address this issue, we preliminarily studied the association of 721 single nucleotide polymorphisms from 135 genes potentially involved in signal transduction implicated in neutrophil recruitment in a cohort of F508del homozygous CF patients with either severe or mild progression of lung disease. The top ranking association was found for a nonsynonymous polymorphism of the phospholipase C-β3 (PLCB3) gene. Studies in bronchial epithelial cells exposed to P. aeruginosa revealed that PLCB3 is implicated in extracellular nucleotide-dependent intracellular calcium signaling, leading to activation of the protein kinase Cα and Cβ and of the nuclear transcription factor NF-κB p65. The proinflammatory pathway regulated by PLCB3 acts by potentiating the Toll-like Receptors' signaling cascade and represents an interesting molecular target to attenuate the excessive recruitment of neutrophils without completely abolishing the inflammatory response.
Keywords: Adenosine Triphosphate; Calcium; Cell Line, Transformed; Cystic Fibrosis; Enzyme Activation; Epithelial Cells; Gene Expression; Gene Frequency; Genotype; Green Fluorescent Proteins; Host-Pathogen Interactions; Humans; Interleukin-8; Isoenzymes; Lung Diseases; Microscopy, Fluorescence; Phospholipase C beta; Polymorphism, Single Nucleotide; Protein Kinase C; Protein Kinase C beta; Pseudomonas aeruginosa; RNA Interference; Toll-Like Receptors; Transcription Factor RelA

A polymorphism in the 5' UTR of the DEFB1 gene is associated with the lung phenotype in F508del homozygous Italian cystic fibrosis patients. - Crovella, Sergio; Segat, Ludovica; Amato, Annalisa; Athanasakis, Emmanouil; Bezzerri, Valentino; Braggion, Cesare; Casciaro, Rosaria; Castaldo, Giuseppe; Colombo, Carla; Covone, Angela Elvira; De Rose, Virginia; Gagliardini, Rolando; et al. (Clin Chem Lab Med, 2011)
BACKGROUND: The identification of cystic fibrosis (CF) patients who are at greater risk of lung damage could be clinically valuable. Thus, we attempted to replicate previous findings and verify the possible association between three single nucleotide polymorphisms (SNPs c.-52G>A, c.-44C>G and c.-20G>A) in the 5' untranslated region (5' UTR) of the β defensin 1 (DEFB1) gene and the CF pulmonary phenotype. METHODS: Genomic DNA from 92 Italian CF patients enrolled in different regional CF centres was extracted from peripheral blood and genotyped for DEFB1 SNPs using TaqMan(®) allele specific probes. In order to avoid genetic confounding causes that can account for CF phenotype variability, all patients were homozygous for the F508del CFTR mutation, and were then classified on the basis of clinical and functional data as mild lung phenotype (Mp, n=50) or severe lung phenotype patients (Sp, n=42). RESULTS: For the c.-20G>A SNP, the frequency of the A allele, as well as the AA genotype, were significantly more frequent in Mp than in Sp patients, and thus this was associated with a protective effect against severe pulmonary disease (OR=0.48 and 0.28, respectively). The effect of the c.-20G>A A allele is consistent with a recessive model, and the protective effect against Sp is exerted only when it is present in homozygosis. For the other two SNPs, no differences were observed as allelic and genotypic frequency in the two subgroups of CF patients. CONCLUSIONS: Our results, although necessary to be confirmed in larger and multiethnic populations, reinforce DEFB1 as a candidate modifier gene of the CF pulmonary phenotype.
Keywords: 5' Untranslated Regions; Adult; beta-Defensins; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Genotype; Homozygote; Humans; Italy; Male; Mutation; Phenotype; Polymorphism, Genetic; Young Adult

[Proteomic applications in gynecology-obstetrics]. - De Seta, F; Banco, R; Guaschino, S; De Santo, D; Turrisi, A; Piva, C (Minerva Ginecol, 2011)
Proteomics has recently emerged as a powerful approach both for discovering biomarkers as well as for understanding the physiopathology of unclear gynecological-obstetrical disorders. Currently, several biological fluids and fetal tissues were successfully tested, including maternal plasma, amniotic fluid, cervical-vaginal fluid, urine, saliva, placental trophoblast, amnio-chorionic membranes and cord blood. The potential of proteomics on the polycystic ovary syndrome (PCOS) involves biomarkers discovery for a more accurate diagnosis of the syndrome and identification, within the patients with PCOS, those who respond more easily to treatment and those who will be at increased risk for future metabolic complications. The proteomic approach applied to patients with endometriosis would allow not only a non-invasive early diagnosis, but also a staging of the disease and a prediction of infertility risk. Proteomics also involves oncological field, in order to discover biomarkers that allow early diagnosis and prognosis of female genital malignancies. In addition to this, proteomics could be used to understand and predict obstetrical complications such as recurrent spontaneous abortion, preterm birth and preeclampsia. However, further studies are needed on a larger cohort of patients to introduce these biomarkers in clinical practice.
Keywords: Endometriosis; Female; Genital Diseases, Female; Genital Neoplasms, Female; Humans; Polycystic Ovary Syndrome; Pregnancy; Pregnancy Complications; Proteomics

Quality of maternal and neonatal care in Albania, Turkmenistan and Kazakhstan: a systematic, standard-based, participatory assessment. - Tamburlini, Giorgio; Siupsinskas, Gelmius; Bacci, Alberta (PLoS One, 2011)
BACKGROUND: Progress in maternal and neonatal mortality has been slow in many countries despite increasing access to institutional births, suggesting deficiencies in the quality of care. We carried out a systematic assessment of the quality of maternal and newborn care in three CEE/CIS countries, using an innovative approach to identify priority issues and promote action. METHODS: A standard-based tool, covering over 400 items grouped in 13 main areas ranging from support services to case management, was used to assess a sample of ten maternity hospitals in Albania, Kazakhstan and Turkmenistan. Sources of information were visit to services, medical records, observation of cases, and interviews with staff and mothers. A score (range 0 to 3) was attributed to each item and area of care. The assessment was carried out by a multidisciplinary team of international and national professionals. Local managers and staff provided the necessary information and were involved in discussing the findings and the priority actions. RESULTS: Quality of care was found to be substandard in all 13 areas. The lowest scores (between one and two) were obtained by: management of normal labour, delivery, obstetric complications and sick babies; infection prevention; use of guidelines and audits; monitoring and follow-up. Neonatal care as a whole scored better than obstetric care. Interviewed mothers identified lack of information, insufficient support during labour and lack of companionship as main issues. Actions to improve quality of care were identified at facility as well as at central level and framed according to main health system functions. CONCLUSIONS: Quality of care is a key issue to improve maternal and neonatal outcomes, particularly in countries such as CEE/CIS where access to institutional births is nearly universal. Approaches that involve health professionals and managers in comprehensive, action-oriented assessments of quality of care are promising and should be further supported.
Keywords: Albania; Child Health Services; Female; Humans; Infant, Newborn; Kazakhstan; Maternal Health Services; Pregnancy; Quality of Health Care; Turkmenistan

The resurgence of rheumatic fever in a developed country area: the role of echocardiography. - Pastore, Serena; De Cunto, Angela; Benettoni, Alessandra; Berton, Emanuela; Taddio, Andrea; Lepore, Loredana (Rheumatology (Oxford), 2011)
OBJECTIVES: The annual incidence of ARF ranges from 5 to 51/100, 000 population worldwide in the 5- to 15-year age group. In the past, there was a decline in the incidence of ARF; however, focal outbreaks have been reported. This study evaluated the incidence of ARF in 2007-08 in a region of a developed country compared with the previous decade. METHODS: A retrospective review of all admission records for ARF in Trieste between January 2007 and December 2008 was undertaken. The diagnosis of ARF was established by the Jones criteria according to the 1992 revision. RESULTS: Between January 2007 and December 2008: 13 cases of ARF were recorded, 11 females and 2 males. The estimated incidence was 23 and 27/100, 000 population new cases each year, respectively, in the 5- to 15-year age group. Migratory polyarthritis occurred in 6/13, chorea in 7/13 and clinical carditis in 5/13 cases. Five out of 13 patients had only echocardiographic abnormalities, with no clinical cardiac manifestations. Another two patients did not fulfil diagnostic criteria for ARF, presenting with only three minor criteria, but they revealed silent carditis at echocardiography evaluation. During the follow-up, in one case the carditis receded and in the other it significantly improved. CONCLUSIONS: Our experience underlines that ARF has not yet disappeared in industrialized countries. We observed a high incidence of chorea, always associated with mild carditis. Echocardiographic assessment should be routinely performed in all patients with suspected ARF in order to identify those subclinical cases of valvulitis that would otherwise pass undiagnosed without receiving proper prophylaxis.
Keywords: Adolescent; Child; Child, Preschool; Chorea; Developed Countries; Diagnosis, Differential; Echocardiography; Female; Humans; Italy; Male; Myocarditis; Retrospective Studies; Rheumatic Fever

Rubella susceptibility profile in pregnant women with HIV. - Floridia, Marco; Pinnetti, Carmela; Ravizza, Marina; Tibaldi, Cecilia; Sansone, Matilde; Fiscon, Marta; Guaraldi, Giovanni; Guerra, Brunella; Alberico, Salvatore; Spinillo, Arsenio; Castelli, Paula; Dalzero, Serena; et al. (Clin Infect Dis, 2011)
Keywords: Female; HIV Infections; Humans; Pregnancy; Pregnancy Complications, Infectious; Rubella

Setting research priorities to reduce global mortality from childhood pneumonia by 2015. - Rudan, Igor; El Arifeen, Shams; Bhutta, Zulfiqar A; Black, Robert E; Brooks, Abdullah; Chan, Kit Yee; Chopra, Mickey; Duke, Trevor; Marsh, David; Pio, Antonio; Simoes, Eric A F; Tamburlini, Giorgio; et al. (PLoS Med, 2011)
Keywords: Biomedical Research; Child, Preschool; Humans; Infant; Infant, Newborn; Pneumonia

The significance of mannose-binding lectin gene polymorphisms on the risk of BK virus coinfection in women with human papillomavirus-positive cervical lesions. - Comar, Manola; Segat, Ludovica; Crovella, Sergio; Bovenzi, Massimo; Cortini, Enzo; Tognon, Mauro (Hum Immunol, 2011)
The simultaneous detection of oncogenic human papillomavirus (HPV) and BK virus (BKV) has been recently reported in cervical cancers, suggesting that these viruses may act together in the process of cell transformation; host genetic polymorphisms may also influence virus persistence/reactivation. To disclose a possible role of the gene encoding for the mannose-binding lectin, MBL2, in susceptibility to BKV infection, we analyzed functional polymorphisms in the first exon of MBL2 in women stratified for the presence/absence of BKV and affected by different grades of HPV-induced cervical precancerous lesions. All BKV-positive samples were also HPV positive (HPV 16), and all presented with high-grade squamous intraepithelial lesions. The MBL2 A allele was significantly more frequent in BKV-negative patients than in BKV-positive patients. These data indicate a possible role for the A allele in conferring protection to BKV infection in high-risk HPV-positive women (odds ratio 0.40, 95% confidence interval 0.20-0.85, p = 0.01).
Keywords: Adult; Aged; Alleles; BK Virus; Cervical Intraepithelial Neoplasia; Cervix Uteri; DNA Fingerprinting; DNA, Viral; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Human papillomavirus 16; Humans; Italy; Mannose-Binding Lectin; Odds Ratio; Papillomavirus Infections; Polymorphism, Genetic; Polyomavirus Infections; Risk; Viral Load

Somatic mosaic IDH1 and IDH2 mutations are associated with enchondroma and spindle cell hemangioma in Ollier disease and Maffucci syndrome. - Pansuriya, Twinkal C; van Eijk, Ronald; d'Adamo, Pio; van Ruler, Maayke A J H; Kuijjer, Marieke L; Oosting, Jan; Cleton-Jansen, Anne-Marie; van Oosterwijk, Jolieke G; Verbeke, Sofie L J; Meijer, Daniëlle; van Wezel, Tom; Nord, Karolin H; et al. (Nat Genet, 2011)
Ollier disease and Maffucci syndrome are non-hereditary skeletal disorders characterized by multiple enchondromas (Ollier disease) combined with spindle cell hemangiomas (Maffucci syndrome). We report somatic heterozygous mutations in IDH1 (c.394C>T encoding an R132C substitution and c.395G>A encoding an R132H substitution) or IDH2 (c.516G>C encoding R172S) in 87% of enchondromas (benign cartilage tumors) and in 70% of spindle cell hemangiomas (benign vascular lesions). In total, 35 of 43 (81%) subjects with Ollier disease and 10 of 13 (77%) with Maffucci syndrome carried IDH1 (98%) or IDH2 (2%) mutations in their tumors. Fourteen of 16 subjects had identical mutations in separate lesions. Immunohistochemistry to detect mutant IDH1 R132H protein suggested intraneoplastic and somatic mosaicism. IDH1 mutations in cartilage tumors were associated with hypermethylation and downregulated expression of several genes. Mutations were also found in 40% of solitary central cartilaginous tumors and in four chondrosarcoma cell lines, which will enable functional studies to assess the role of IDH1 and IDH2 mutations in tumor formation.
Keywords: Adult; Case-Control Studies; Cell Line, Tumor; DNA Methylation; Enchondromatosis; Female; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Humans; Isocitrate Dehydrogenase; Male; Middle Aged; Mosaicism; Mutation, Missense; Sequence Analysis, DNA; Transcription, Genetic; Young Adult

TRAIL promotes a pro-survival signal in erythropoietin-deprived human erythroblasts through the activation of an NF-kB/IkBalpha pathway. - Sancilio, S; Di Giacomo, V; Quaglietta, A M; Iacone, A; Angelucci, D; Tatasciore, U; Rana, R A; Cataldi, A; Zauli, G; Di Pietro, R (J Biol Regul Homeost Agents, 2011)
The biological activity of TNF-related apoptosis inducing ligand (TRAIL) was analyzed in primary human erythroblasts derived from mononuclear cells of blood donors, kept in culture in the presence of 20 percent foetal calf serum, growth factors (EPO, SCF, IL-3) and glucocorticoids (10-6 M dexamethasone, 10-6 M oestradiol) or under growth factor and serum starvation. In the presence of growth factors and serum, primary erythroblasts showed a differential expression of TRAIL-Receptors (Rs) at various degrees of maturation and responded to TRAIL treatment with a mild cytotoxicity. On the other hand, in the absence of serum and growth factors, TRAIL treatment unexpectedly up-regulated TRAIL-R4 decoy receptor and promoted erythroblast survival. The concomitant activation of NF-kB/IkB survival pathway was detected with Western blotting and immunofluorescence procedures and confirmed by experiments performed with SN50, a pharmacological inhibitor of the NF-kB/IkB pathway. Our study indicates that TRAIL has a twofold activity on erythroid lineages: it induces a mild erythroid cell cytotoxicity in the presence of serum and growth factors, while it promotes erythroid cell survival through the activation of the NF-kB/IkB pathway under starvation conditions.
Keywords: Cell Survival; Erythroblasts; Erythropoietin; Gene Expression Regulation; Humans; I-kappa B Kinase; Jurkat Cells; NF-kappa B; Peptides; TNF-Related Apoptosis-Inducing Ligand; Tumor Necrosis Factor Decoy Receptors

Use of zidovudine-sparing HAART in pregnant HIV-infected women in Europe: 2000-2009. - Tariq, Shema; Townsend, Claire L; Cortina-Borja, Mario; Duong, Trinh; Elford, Jonathan; Thorne, Claire; Tookey, Pat A (J Acquir Immune Defic Syndr, 2011)
BACKGROUND: Increasing numbers of women in resource-rich settings are prescribed zidovudine (ZDV)-sparing highly active antiretroviral therapy (HAART) in pregnancy. We compare ZDV-sparing with ZDV-containing HAART in relation to maternal viral load at delivery, mother-to-child transmission (MTCT) of HIV, and congenital abnormality. METHODS: This is an analysis of data from the National Study of HIV in Pregnancy and Childhood and the European Collaborative Study. Data on 7573 singleton births to diagnosed HIV-infected women between January 2000 and June 2009 were analyzed. Logistic regression models were fitted to estimate adjusted odds ratios (AORs). RESULTS: Overall, 15.8% (1199 of 7573) of women received ZDV-sparing HAART, with increasing use between 2000 and 2009 (P < 0.001). Nearly a fifth (18.4%) of women receiving ZDV-sparing HAART in pregnancy had a detectable viral load at delivery compared with 28.6% of women on ZDV-containing HAART [AOR 0.90; 95% confidence interval (CI): 0.72 to 1.14, P = 0.4]. MTCT rates were 0.8% and 0.9% in the ZDV-sparing and ZDV-containing groups, respectively (AOR 1.81; 95% CI: 0.77 to 4.26, P = 0.2). The congenital abnormality rate was the same in both groups (2.7%, AOR 0.98; 95% CI: 0.66 to 1.45, P = 0.9), with no significant difference between the groups in a subanalysis of pregnancies with first trimester HAART exposure (AOR 0.79; 95% CI: 0.48 to 1.30, P = 0.4). CONCLUSIONS: We found no difference in risk of detectable viral load at delivery, MTCT, or congenital abnormality when comparing ZDV-sparing with ZDV-containing HAART. With increasing use of ZDV-sparing HAART, continued monitoring of pregnancy outcomes and long-term consequences of in utero exposure to these drugs is required.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; CD4 Lymphocyte Count; Europe; Female; HIV Infections; Humans; Infant; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious; Retrospective Studies; Time Factors; Viral Load; Zidovudine

Usefulness of wireless capsule endoscopy for detecting inflammatory bowel disease in children presenting with arthropathy. - Taddio, Andrea; Simonini, Gabriele; Lionetti, Paolo; Lepore, Loredana; Martelossi, Stefano; Ventura, Alessandro; Cimaz, Rolando (Eur J Pediatr, 2011)
Inflammatory bowel disease (IBD) is a cause of chronic intestinal inflammation in children. In a subset of patients affected by IBD, arthropathy may be the leading presenting sign. In the past years, remarkable advances in gastrointestinal endoscopy techniques have been achieved; recently, the development of capsule endoscopy (CE) provided a non-invasive method for the complete endoscopic evaluation, including small bowel assessment. We report three children suffering from IBD but presenting with articular complaints in whom CE was a useful tool for detecting gut inflammation. Patients were investigated with the wireless CE: PillCam SB2 (Given Imaging, Yoqneam, Israel) capsule, the second-generation capsule, was used in our paediatric patients. Three patients were initially evaluated for arthropathy. Enteropathic arthritis was suspected for gastrointestinal symptoms and/or persistence of inflammatory markers elevation. In one of these children, conventional endoscopy was refused by parents, while in the other two children, CE was proposed as first-line diagnostic tool. In all patients, CE revealed to be safe and provided information that led to diagnosis. Paediatric rheumatologists should consider CE as a valid, non-invasive tool, eventually first level diagnostic approach in order to evaluate the presence of IBD in children presenting with chronic articular complaints.
Keywords: Adolescent; Arthritis, Juvenile; Capsule Endoscopy; Child; Colitis, Ulcerative; Colon; Crohn Disease; Diagnosis, Differential; Follow-Up Studies; Humans; Inflammatory Bowel Diseases; Intestine, Small; Male; Predictive Value of Tests; Sensitivity and Specificity; Severity of Illness Index; Treatment Outcome

X-ray fluorescence elemental mapping and microscopy to follow hepatic disposition of a Gd-based magnetic resonance imaging contrast agent. - Delfino, Riccarda; Altissimo, Matteo; Menk, Ralf Hendrik; Alberti, Roberto; Klatka, Tomasz; Frizzi, Tommaso; Longoni, Antonio; Salomè, Murielle; Tromba, Giuliana; Arfelli, Fulvia; Clai, Milan; Vaccari, Lisa; et al. (Clin Exp Pharmacol Physiol, 2011)
1. Spatially resolved X-ray fluorescence (XRF) spectroscopy with synchrotron radiation is a technique that allows imaging and quantification of chemical elements in biological specimens with high sensitivity. In the present study, we applied XRF techniques at a macro and micro level to carry out drug distribution studies on ex vivo models to confirm the hepatobiliary disposition of the Gd-based magnetic resonance imaging contrast agent B22956/1. 2. Gd presence was selectively quantified allowing the determination of the time dependent disappearance of the drug from blood and its hepatic accumulation in mice after administration. Elemental mapping highlighted the drug distribution differences between healthy and diseased livers. XRF microanalyses showed that in CCl(4) -induced hepatitis, B22956/1 has greatly reduced hepatic accumulation, shown as a 20-fold reduction of Gd presence. Furthermore, a significant increase of Fe presence was found in steatotic compared with healthy livers, in line with the disease features. 3. The present results show that XRF might be useful in preclinical pharmacological studies with drugs containing exogenous elements. Furthermore, quantitative and high-sensitivity elemental mapping allows simultaneous detection of chemical variation, showing pathological conditions. This approach was useful in suggesting reduced B22956/1 accumulation in steatotic livers, thus opening possible new diagnostic perspectives for this drug.
Keywords: Animals; Contrast Media; Fatty Liver; Female; Gadolinium; Hepatitis; Iron; Liver; Magnetic Resonance Imaging; Mice; Mice, Inbred CBA; Organometallic Compounds; Spectrometry, X-Ray Emission

An alternative role of C1q in cell migration and tissue remodeling: contribution to trophoblast invasion and placental development. - Agostinis, Chiara; Bulla, Roberta; Tripodo, Claudio; Gismondi, Angela; Stabile, Helena; Bossi, Fleur; Guarnotta, Carla; Garlanda, Cecilia; De Seta, Francesco; Spessotto, Paola; Santoni, Angela; Ghebrehiwet, Berhane; et al. (J Immunol, 2010)
Fetal trophoblast cells invading the decidua in the early phase of pregnancy establish complex interaction with the maternal extracellular matrix. We discovered that C1q was widely distributed in human decidual stroma in the absence of C4 and C3 and was actively synthesized by migrating extravillous trophoblasts. The cells expressed the messages for the three chains of C1q and secreted this complement component that interacted with the proteins of the decidual extracellular matrix. Solid phase-bound C1q promoted trophoblast adhesion and migration, and cell binding to C1q resulted in activation of ERK1/2 MAPKs. Ab inhibition experiments showed that the receptors for the globular head of C1q/p33 and α(4)β(1) integrin were both involved in this process and were colocalized on the cell surface following binding of C1q to trophoblasts. We also found that C1q(-/-) mice manifested increased frequency of fetal resorption, reduced fetal weight, and smaller litter sizes compared with wild-type mice. C1q deficiency was associated with impaired labyrinth development and decidual vessel remodeling. Collectively, these data suggest that C1q plays an important role in promoting trophoblast invasion of decidua and that defective local production of C1q may be involved in pregnancy disorders, such as pre-eclampsia, characterized by poor trophoblast invasion.
Keywords: Animals; Cell Adhesion; Chemotaxis, Leukocyte; Complement C1q; Female; Humans; Immunoblotting; Immunohistochemistry; Immunoprecipitation; Mice; Mice, Inbred C57BL; Microscopy, Confocal; Placentation; Pre-Eclampsia; Pregnancy; Reverse Transcriptase Polymerase Chain Reaction; Trophoblasts

Analysis of DEFB1 regulatory SNPs in cystic fibrosis patients from North-Eastern Italy. - Segat, L; Morgutti, M; Athanasakis, E; Trevisiol, C; Amaddeo, A; Poli, F; Crovella, S (Int J Immunogenet, 2010)
Cystic fibrosis (CF) transmembrane regulator protein (CFTR) gene is undoubtedly the main genetic factor involved in the modulation of CF phenotype. However, other factors such as human defensins and the genes encoding for these antimicrobial peptides have been hypothesized as possible modifiers influencing airways infection in CF patients, but their role in the pathogenesis of lung disease is still debated. Since DEFB1 gene encoding for human beta-defensin 1 displays features such as antimicrobial or chemotactic activity playing a role in inflammation, it has been considered as a possible candidate CF modifier gene. We analysed three single nucleotide polymorphisms (SNPs) in the 5'-untranslated region of the DEFB1 gene (namely g-52G>A, g-44C>G and g-20G>A) in a group of 62 CF patients from North Eastern Italy, and in 130 healthy controls, with the aim of verifying the possible association of these functional SNPs with the pulmonary phenotype of CF patients. DEFB1 SNPs have been genotyped by using Taqman allele-specific fluorescent probes and a real-time PCR platform. No significant differences were found for allele, genotype and haplotype frequencies of DEFB1 g-52G>A, g-44C>G and g-20G>A SNPs in CF patients stratified for Pseudomonas aeruginosa infection, as well as in patients with a severe and mild clinical phenotype or in patients stratified for CFTR genotypes. DEFB1 allele, genotype and haplotype frequencies of CF patients globally considered were similar to those of healthy controls. Our findings are discordant with respect to another recent study performed on CF patients coming from Southern Italy, probably due to different ethnicity of the patients.
Keywords: 5' Untranslated Regions; Adolescent; Alleles; beta-Defensins; Case-Control Studies; Child; Child, Preschool; Chronic Disease; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Gene Frequency; Genotype; Haplotypes; Humans; Immunity, Innate; Infant; Infant, Newborn; Italy; Male; Polymorphism, Single Nucleotide; Pseudomonas Infections

Anti transglutaminase antibodies cause ataxia in mice. - Boscolo, Sabrina; Lorenzon, Andrea; Sblattero, Daniele; Florian, Fiorella; Stebel, Marco; Marzari, Roberto; Not, Tarcisio; Aeschlimann, Daniel; Ventura, Alessandro; Hadjivassiliou, Marios; Tongiorgi, Enrico (PLoS One, 2010)
BACKGROUND: Celiac disease (CD) is an autoimmune gastrointestinal disorder characterized by the presence of anti-transglutaminase 2 (TG2) and anti-gliadin antibodies. Amongst the neurological dysfunctions associated with CD, ataxia represents the most common one. METHODS: We analyzed by immunohistochemistry, the anti-neural reactivity of the serum from 20 CD patients. To determine the role of anti-TG2 antibodies in ataxia, two anti-TG2 single chain variable fragments (scFv), isolated from a phage-display IgA antibody library, were characterized by immunohistochemistry and ELISA, and injected in mice to study their effects on motor coordination. We found that 75% of the CD patient population without evidence of neurological involvement, has circulating anti-neural IgA and/or IgG antibodies. Two anti-TG2 scFvs, cloned from one CD patient, stained blood vessels but only one reacted with neurons. This anti-TG2 antibody showed cross reactivity with the transglutaminase isozymes TG3 and TG6. Intraventricular injection of the anti-TG2 or the anti-TG2/3/6 cross-reactive scFv provoked transient, equally intensive ataxia in mice. CONCLUSION: The serum from CD patients contains anti-TG2, TG3 and TG6 antibodies that may potentially cause ataxia.
Keywords: Adult; Animals; Antibodies; Ataxia; Autoimmune Diseases; Brain; Celiac Disease; Female; Gliadin; Humans; Isoenzymes; Male; Mice; Mice, Inbred C57BL; Middle Aged; Motor Skills; Rats; Rats, Sprague-Dawley; Transglutaminases

Beta defensin-1 gene (DEFB1) polymorphisms are not associated with atopic dermatitis in children and adolescents from northeast Brazil (Recife, Pernambuco). - Segat, Ludovica; Guimarães, Rafael L; Brandão, Lucas A C; Rocha, Cintia R C; Zanin, Valentina; Trevisiol, Chiara; de Lima Filho, José Luiz; Crovella, Sergio (Int J Dermatol, 2010)
BACKGROUND: Atopic dermatitis (AD) is a common inflammatory skin disease resulting from the interplay between environmental, immunological and genetic factors. In our study, we investigated the role of three single nucleotide polymorphisms (SNPs) at 5'-UTR of DEFB1 gene, encoding for the human beta defensin-1, on the susceptibility to develop AD in a group of Brazilian children and adolescents. METHODS: Three SNPs, -20 G/A (rs11362), -44 C/G (rs1800972), and -52 G/A (rs1799946) at 5'-UTR of DEFB1 gene were genotyped in two groups of children and adolescents, one affected by AD (96 subjects), the other healthy (191 individuals), from northeast Brazil. RESULTS: -44 C/G frequencies were comparable between the two groups. The -20 GG genotype was more frequent in AD subjects than in healthy controls; the -52 GG, conversely, was more frequent in healthy controls than in AD. However, both these differences did not reach statistical significance. Also, association between SNPs and AD severity has been shown. The analysis of DEFB1 haplotypes did not highlight any association of the three SNPs with AD development or disease severity. CONCLUSIONS: Our results seem to exclude a role for the -44 C/G DEFB1 SNPs on the pathogenesis and severity of AD, while for the -20 C/G and -52 G/A, even if not statistically significant, we evidenced a slight trend for susceptibility (-20 GG) and protection (-52 GG) for the development of AD. However, as controversial findings have been reported in the literature, the role of DEFB1 in the development of AD and in the severity of the phenotype deserves further investigation.
Keywords: Adolescent; beta-Defensins; Brazil; Child; Child, Preschool; Dermatitis, Atopic; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Infant; Male; Polymorphism, Single Nucleotide; Risk Factors

Circulating levels of frizzled-related protein (FRZB) are increased in patients with early rheumatoid arthritis and decrease in response to disease-modifying antirheumatic drugs. - Corallini, Federica; Secchiero, Paola; Castellino, Gabriella; Montecucco, Maurizio; Trotta, Francesco; Zauli, Giorgio (Ann Rheum Dis, 2010)
Keywords: Antirheumatic Agents; Arthritis, Rheumatoid; Biological Markers; Glycoproteins; Humans

Declining HCV seroprevalence in pregnant women with HIV. - Floridia, M; Tamburrini, E; Anzidei, G; Tibaldi, C; Muggiasca, M L; Guaraldi, G; Fiscon, M; Vimercati, A; Martinelli, P; Donisi, A; Dalzero, S; Ravizza, M (Epidemiol Infect, 2010)
We assessed recent trends in hepatitis C virus (HCV) prevalence in pregnant women with HIV using data from a large national study. Based on 1240 pregnancies, we observed a 3.4-fold decline in HCV seroprevalence in pregnant women with HIV between 2001 (29.3%) and 2008 (8.6%). This decline was the net result of two components: a progressively declining HCV seroprevalence in non-African women (from 35.7% in 2001 to 16.7% in 2008), sustained by a parallel reduction in history of injecting drug use (IDU) in this population, and a significantly growing presence (from 21.2% in 2001 to 48.6% in 2008) of women of African origin, at very low risk of being HCV-infected [average HCV prevalence 1%, adjusted odds ratio (aOR) for HCV 0.09, 95% CI 0.03-0.29]. Previous IDU was the stronger determinant of HCV co-infection in pregnant women with HIV (aOR 30.9, 95% CI 18.8-51.1). The observed trend is expected to translate into a reduced number of cases of vertical HCV transmission.
Keywords: Chi-Square Distribution; Female; Hepatitis C; HIV Infections; Humans; Italy; Logistic Models; Pregnancy; Risk Factors; Seroepidemiologic Studies

Decreased cholesterol levels reflect a consumption of anti-inflammatory isoprenoids associated with an impaired control of inflammation in a mouse model of mevalonate kinase deficiency. - Marcuzzi, Annalisa; Decorti, Giuliana; Pontillo, Alessandra; Ventura, Alessandro; Tommasini, Alberto (Inflamm Res, 2010)
OBJECTIVE: The aim of this study was to evaluate, in a mouse model of mevalonate kinase deficiency (MKD), the possible link between inflammatory symptoms and serum cholesterol levels. MATERIALS AND METHODS: Balb/c mice were treated with alendronate and bacterial muramyl dipeptide. Body temperature, interleukin-1 beta (IL-1 beta) secretion and serum cholesterol levels were measured. RESULTS: An increased production of the pro-inflammatory cytokine IL-1 beta (p < 0.05) and a rise in body temperature (p < 0.05) was observed, while, in parallel, serum cholesterol concentration significantly decreased (p < 0.05). These effects were completely reversed when animals were treated with exogenous isoprenoids. CONCLUSIONS: In the mouse model of MKD, the inflammatory response is associated with a reduction in cholesterol levels, and hence this parameter could be used as an indicator of isoprenoid consumption. In addition, plant derived isoprenoids could represent candidate treatments for this disease.
Keywords: Animals; Anti-Inflammatory Agents; Cholesterol; Disease Models, Animal; Inflammation; Interleukin-1beta; Male; Mevalonate Kinase Deficiency; Mice; Mice, Inbred BALB C; Random Allocation; Terpenes

Defective FOXP3 expression in patients with acute Kawasaki disease and restoration by intravenous immunoglobulin therapy. - Olivito, Biagio; Taddio, Andrea; Simonini, Gabriele; Massai, Cristina; Ciullini, Sara; Gambineri, Eleonora; de Martino, Maurizio; Azzari, Chiara; Cimaz, Rolando (Clin Exp Rheumatol, 2010)
OBJECTIVES: The aims of this study were: 1) to investigate forkhead box P3 (FOXP3) expression in patients with Kawasaki disease (KD), exploring possible differences during the acute phase and after defervescence; 2) to evaluate a possible association of the FOXP3 single nucleotide polymorphism (SNP) 543 (SNP ID: rs2232367) with KD. METHODS: FOXP3 expression was evaluated on 8 children with KD and 15 healthy children by flow cytometry and Real-Time polymerase chain reaction (RT-PCR). FOXP3 SNP 543 was genotyped by denaturing high-performance liquid chromatography (DHPLC) and sequencing on DNA samples from 58 additional children with KD and 114 healthy donors. RESULTS: The frequencies of CD4+CD25 +FOXP3+ regulatory T cells were significantly (p=0.0002) lower during the acute phase of KD than in sex- and age-matched healthy donors (median % + SD: 4.8+/-1.3 vs. 7.7+/-1.7) and a similar tendency was revealed for FOXP3 mRNA transcripts (p<0.0001). FOXP3 expression increased significantly, at both protein and mRNA levels, after intravenous immunoglobulin (IVIG) therapy treatment and achieving complete remission of disease (at least 48 hrs; median 9.5 days, range 2-30). Of the 58 patients screened, only one female subject (1.7%) carried the presence of 543 SNP in heterozygosis (C>T; for a total of 1 allele out of 88), with no difference between KD patients and controls (0.0%, 0/203 alleles). CONCLUSIONS: Our data reinforce the notion of an impaired immunoregulation in KD, suggesting also a role of IVIG treatment in modifying the Treg compartment. FOXP3 SNP 543 does not seem to be involved in susceptibility to KD in Italian children.
Keywords: Acute Disease; Child; Child, Preschool; Female; Flow Cytometry; Forkhead Transcription Factors; Genotype; Humans; Immunoglobulins, Intravenous; Infant; Italy; Male; Mucocutaneous Lymph Node Syndrome; Polymorphism, Single Nucleotide; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; T-Lymphocytes, Regulatory

EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part I: Overall methodology and clinical characterisation. - Ruperto, Nicolino; Ozen, Seza; Pistorio, Angela; Dolezalova, Pavla; Brogan, Paul; Cabral, David A; Cuttica, Ruben; Khubchandani, Raju; Lovell, Daniel J; O'Neil, Kathleen M; Quartier, Pierre; Ravelli, Angelo; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To report methodology and overall clinical, laboratory and radiographic characteristics for Henoch-Schönlein purpura (HSP), childhood polyarteritis nodosa (c-PAN), c-Wegener granulomatosis (c-WG) and c-Takayasu arteritis (c-TA) classification criteria. METHODS: The preliminary Vienna 2005 consensus conference, which proposed preliminary criteria for paediatric vasculitides, was followed by a EULAR/PRINTO/PRES - supported validation project divided into three main steps. Step 1: retrospective/prospective web-data collection for HSP, c-PAN, c-WG and c-TA, with age at diagnosis <or=18 years. Step 2: blinded classification by consensus panel of a subgroup of 280 cases (128 difficult cases, 152 randomly selected) enabling expert diagnostic verification. Step 3: Ankara 2008 Consensus Conference and statistical evaluation (sensitivity, specificity, area under the curve, kappa-agreement) using as 'gold standard' the final consensus classification or original treating physician diagnosis. RESULTS: A total of 1183/1398 (85%) samples collected were available for analysis: 827 HSP, 150 c-PAN, 60 c-WG, 87 c-TA and 59 c-other. Prevalence, signs/symptoms, laboratory, biopsy and imaging reports were consistent with the clinical picture of the four c-vasculitides. A representative subgroup of 280 patients was blinded to the treating physician diagnosis and classified by a consensus panel, with a kappa-agreement of 0.96 for HSP (95% CI 0.84 to 1), 0.88 for c-WG (95% CI 0.76 to 0.99), 0.84 for c-TA (95% CI 0.73 to 0.96) and 0.73 for c-PAN (95% CI 0.62 to 0.84), with an overall kappa of 0.79 (95% CI 0.73 to 0.84). CONCLUSION: EULAR/PRINTO/PRES propose validated classification criteria for HSP, c-PAN, c-WG and c-TA, with substantial/almost perfect agreement with the final consensus classification or original treating physician diagnosis.
Keywords: Adolescent; Biopsy; Child; Delphi Technique; Granulomatosis with Polyangiitis; Humans; International Cooperation; Internet; Polyarteritis Nodosa; Purpura, Schoenlein-Henoch; Reproducibility of Results; Takayasu Arteritis

Five new OTOF gene mutations and auditory neuropathy. - Zadro, Cristina; Ciorba, Andrea; Fabris, Annalisa; Morgutti, Marcello; Trevisi, Patrizia; Gasparini, Paolo; Martini, Alessandro (Int J Pediatr Otorhinolaryngol, 2010)
OBJECTIVE: Purpose of this paper is to analyse OTOF gene in a series of subjects affected by auditory neuropathy. METHODS: Four children showing mild to profound prelingual deafness, confirmed by the absence of a clear and detectable responses at auditory brainstem responses (ABR), associated with the presence of bilateral OAE, were enrolled in the study. RESULTS AND CONCLUSIONS: Genetic analysis identified five new mutations (a nonsense, a small and a large deletion and two splicing site mutations), and one missense mutation (F1795C) previously described. These results further confirm the role of OTOF gene in auditory neuropathy. In the absence of a context of neurological syndrome, the combination of absent ABR and positive OAE responses should lead to an auditory neuropathy diagnosis and to a mutational screening in OTOF.
Keywords: Auditory Diseases, Central; Deafness; Evoked Potentials, Auditory, Brain Stem; Female; Humans; Male; Membrane Proteins; Mutation; Otoacoustic Emissions, Spontaneous; Polymerase Chain Reaction

Follow-up and quality of life of patients with cryopyrin-associated periodic syndromes treated with Anakinra. - Lepore, Loredana; Paloni, Giulia; Caorsi, Roberta; Alessio, Maria; Rigante, Donato; Ruperto, Nicola; Cattalini, Marco; Tommasini, Alberto; Zulian, Francesco; Ventura, Alessando; Martini, Alberto; Gattorno, Marco (J Pediatr, 2010)
OBJECTIVE: To evaluate the quality of life and long-term follow-up of patients enrolled in the Italian registry of cryopyrin-associated periodic syndromes (CAPS). STUDY DESIGN: Since 2004, 20 patients with CAPS were enrolled in a common registry from different Italian Centers of Pediatric Rheumatology; 14 patients were treated with Anakinra in an open fashion. Both treated and untreated patients were routinely followed according to standard of care. The Child Health Questionnaire (CHQ-PF 50) was used to assess the health-related quality of life. RESULTS: The mean duration of follow-up was 37.5 months. In all treated patients, a complete and persistent control of the inflammatory manifestations was observed with no further progression of the disease. At enrollment in the registry, patients showed a poorer health-related quality of life than healthy children in both physical and the psychosocial summary scores. Treatment was associated with a dramatic and sustained amelioration of a variety of measures of poor quality of life, particularly in those concerning the global health perception, bodily pain-discomfort, and other physical domains. CONCLUSIONS: Long-term IL-1 blockade produces a significant and persistent improvement in the clinical manifestations associated with the disease and on the overall quality of life.
Keywords: Adolescent; Adult; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Follow-Up Studies; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-1; Male; Phenotype; Quality of Health Care; Quality of Life; Questionnaires; Syndrome; Treatment Outcome

Histatins in non-human primates: gene variations and functional effects. - Padovan, Lara; Segat, Ludovica; Pontillo, Alessandra; Antcheva, Nikolinka; Tossi, Alessandro; Crovella, Sergio (Protein Pept Lett, 2010)
Human histatins are histidine-rich, low molecular weight salivary proteins that contribute to the immune system of the oral cavity. In this work, nucleotide sequences of the HIS1 (coding for histatin 1) and HIS2 (coding for histatin 3) genes, homologous to the human ones, have been sequenced and analysed in five primates species including Great Ape, Hylobatidae and Cercopithecidae. In HIS1, the region corresponding to the putative mature peptide shows a premature stop codon in Macaca and Cercopithecus, while HIS2 a six codon insertion in the Cercopithecidae. Histatin 5, a 24-residue peptide derived from histatin 3, is the most antimicrobially active among human histatins, thus macaque and nomascus orthologues of histatin 5 were selected for chemical synthesis and functional characterization, in comparison to the human peptide. All synthesized histatins are predicted to be poorly amphipathic, depending on the charged state of His residues and assume partially a-helical conformations only in lipophilic conditions. Antimicrobial assays against Candida and Criptococcus spp. indicate somewhat different spectra of in vitro activity against the tested fungi. We have described HIS1 and HIS2 gene variations in primates and have analysed their functional effects on selected Hst5 orthologues. The human antimicrobial peptide has been proposed to represent an important lead for new generation of antimicrobial compounds for the treatment of oral mycoses, thus the information from the non-human primates histatins studied may aid strategies for drugs design.
Keywords: Amino Acid Sequence; Animals; Anti-Infective Agents; Base Sequence; Candida; Catarrhini; Cell Proliferation; Computational Biology; Cryptococcus; Genetic Variation; Histatins; Humans; Molecular Sequence Data; Phylogeny; Sequence Alignment; Sequence Analysis, DNA

Individual differences in prefrontal cortex activity during perception of bitter taste using fNIRS methodology. - Bembich, Stefano; Lanzara, Carmela; Clarici, Andrea; Demarini, Sergio; Tepper, Beverly J; Gasparini, Paolo; Grasso, Domenico L (Chem Senses, 2010)
Although bitter taste has a crucial role in nutrition by preventing the ingestion of toxic foods, there are few studies on bitter taste neuroimaging. To identify cortical areas involved in bitter taste perception and to determine if individual differences in taste sensitivity to 6-n-propylthiouracil (PROP) are represented in the brain by different cortical activation patterns, we examined 48 healthy volunteers using functional near-infrared spectroscopy. Participants rated the perceived intensity of filter paper disks impregnated with PROP and NaCl during the imaging procedure and were then classified as PROP tasters and nontasters. We monitored cortical activity in both the anterior and posterior regions of the dorsolateral prefrontal cortex (DLPFC) and in the ventrolateral prefrontal cortex (VLPFC). No activity was detected in the anterior DLPFC in any of the participants. However, during the administration of PROP, significant cortical activation was detected in the more posterior regions of the left DLPFC and in the left and right VLPFC but only in PROP tasters. PROP nontasters showed no cortical activity in these areas. These data suggest that the prefrontal cortex is involved in the conscious perception of the bitter taste of PROP and that the pattern of activity is consistent with individual differences in the ability to taste this compound. Thus, the PROP phenotype is associated with fundamental differences in cortical taste processing.
Keywords: Adult; Eating; Female; Food Preferences; Humans; Individuality; Male; Perception; Phenotype; Prefrontal Cortex; Propylthiouracil; Sodium Chloride; Spectroscopy, Near-Infrared; Taste; Taste Threshold; Young Adult

Mannose-binding lectin is produced by vaginal epithelial cells and its level in the vaginal fluid is influenced by progesterone. - Bulla, R; De Seta, F; Radillo, O; Agostinis, C; Durigutto, P; Pellis, V; De Santo, D; Crovella, S; Tedesco, F (Mol Immunol, 2010)
Mannose-binding lectin (MBL) is a recognition molecule of the complement (C) system and binds to carbohydrate ligands present on a wide range of pathogenic bacteria, viruses, fungi, and parasites. MBL has been detected in the cervico-vaginal cavity where it can provide a first-line defence against infectious agents colonizing the lower tract of the reproductive system. Analysis of the cervico-vaginal lavage (CVL) obtained from 11 normal cycling women at different phases of the menstrual cycle revealed increased levels of MBL in the secretive phase. Part of this MBL derives from the circulation as indicated by the presence of transferrin in CVL tested as a marker of vascular and tissue permeability. The local synthesis of MBL is suggested by the finding that its level is substantially higher than that of transferrin in the secretive phase. The contribution of endometrium is negligible since the MBL level did not change before and after hysterectomy. RT-PCR and in situ RT-PCR analysis showed that the vaginal tissue, and in particular the basal layer of the epithelium, is a source of MBL which binds to the basal membrane and to cells of the outer layers of the epithelium. In conclusion, we have shown that MBL detected in CVL derives both from plasma as result of transudation and from local synthesis and its level is progesterone dependent increasing in the secretive phase of the menstrual cycle.
Keywords: Adolescent; Adult; Body Fluids; Enzyme-Linked Immunosorbent Assay; Epithelial Cells; Female; Humans; Immunohistochemistry; Mannose-Binding Lectin; Menstrual Cycle; Progesterone; Reverse Transcriptase Polymerase Chain Reaction; Vagina; Young Adult

Methotrexate withdrawal at 6 vs 12 months in juvenile idiopathic arthritis in remission: a randomized clinical trial. - Foell, Dirk; Wulffraat, Nico; Wedderburn, Lucy R; Wittkowski, Helmut; Frosch, Michael; Gerss, Joachim; Stanevicha, Valda; Mihaylova, Dimitrina; Ferriani, Virginia; Tsakalidou, Florence Kanakoudi; Foeldvari, Ivan; Cuttica, Ruben; et al. (JAMA, 2010)
CONTEXT: Novel therapies have improved the remission rate in chronic inflammatory disorders including juvenile idiopathic arthritis (JIA). Therefore, strategies of tapering therapy and reliable parameters for detecting subclinical inflammation have now become challenging questions. OBJECTIVES: To analyze whether longer methotrexate treatment during remission of JIA prevents flares after withdrawal of medication and whether specific biomarkers identify patients at risk for flares. DESIGN, SETTING, AND PATIENTS: Prospective, open, multicenter, medication-withdrawal randomized clinical trial including 364 patients (median age, 11.0 years) with JIA recruited in 61 centers from 29 countries between February 2005 and June 2006. Patients were included at first confirmation of clinical remission while continuing medication. At the time of therapy withdrawal, levels of the phagocyte activation marker myeloid-related proteins 8 and 14 heterocomplex (MRP8/14) were determined. INTERVENTION: Patients were randomly assigned to continue with methotrexate therapy for either 6 months (group 1 [n = 183]) or 12 months (group 2 [n = 181]) after induction of disease remission. MAIN OUTCOME MEASURES: Primary outcome was relapse rate in the 2 treatment groups; secondary outcome was time to relapse. In a prespecified cohort analysis, the prognostic accuracy of MRP8/14 concentrations for the risk of flares was assessed. RESULTS: Intention-to-treat analysis of the primary outcome revealed relapse within 24 months after the inclusion into the study in 98 of 183 patients (relapse rate, 56.7%) in group 1 and 94 of 181 (55.6%) in group 2. The odds ratio for group 1 vs group 2 was 1.02 (95% CI, 0.82-1.27; P = .86). The median relapse-free interval after inclusion was 21.0 months in group 1 and 23.0 months in group 2. The hazard ratio for group 1 vs group 2 was 1.07 (95% CI, 0.82-1.41; P = .61). Median follow-up duration after inclusion was 34.2 and 34.3 months in groups 1 and 2, respectively. Levels of MRP8/14 during remission were significantly higher in patients who subsequently developed flares (median, 715 [IQR, 320-1 110] ng/mL) compared with patients maintaining stable remission (400 [IQR, 220-800] ng/mL; P = .003). Low MRP8/14 levels indicated a low risk of flares within the next 3 months following the biomarker test (area under the receiver operating characteristic curve, 0.76; 95% CI, 0.62-0.90). CONCLUSIONS: In patients with JIA in remission, a 12-month vs 6-month withdrawal of methotrexate did not reduce the relapse rate. Higher MRP8/14 concentrations were associated with risk of relapse after discontinuing methotrexate. TRIAL REGISTRATION: isrctn.org Identifier: ISRCTN18186313.
Keywords: Adolescent; Antirheumatic Agents; Arthritis, Juvenile; ATP-Binding Cassette Transporters; Calgranulin B; Child; Child, Preschool; Female; Humans; Infant; Male; Methotrexate; Predictive Value of Tests; Prospective Studies; Recurrence; Remission Induction

Mode of delivery in HIV-infected pregnant women and prevention of mother-to-child transmission: changing practices in Western Europe. - Boer, K; England, K; Godfried, M H; Thorne, C (HIV Med, 2010)
OBJECTIVES: The aim of the study was to examine temporal and geographical patterns of mode of delivery in the European Collaborative Study (ECS), identify factors associated with elective caesarean section (CS) delivery in the highly active antiretroviral therapy (HAART) era and explore associations between mode of delivery and mother-to-child transmission (MTCT). METHODS: The ECS is a cohort study in which HIV-infected pregnant women are enrolled and their infants prospectively followed. Data on 5238 mother-child pairs (MCPs) enrolled in Western European ECS sites between 1985 and 2007 were analysed. RESULTS: The elective CS rate increased from 16% in 1985-1993 to 67% in 1999-2001, declining to 51% by 2005-2007. In 2002-2004, 10% of infants were delivered vaginally, increasing to 34% by 2005-2007. During the HAART era, women in Belgium, the United Kingdom and the Netherlands were less likely to deliver by elective CS than those in Italy and Spain [adjusted odds ratio (AOR) 0.07; 95% confidence interval (CI) 0.04-0.12]. The MTCT rate in 2005-2007 was 1%. Among MCPs with maternal HIV RNA<400 HIV-1 RNA copies/mL (n=960), elective CS was associated with 80% decreased MTCT risk (AOR 0.20; 95% CI 0.05-0.65) adjusting for HAART and prematurity. Two infants born to 559 women with viral loads <50 copies/mL were infected, one of whom was delivered by elective CS (MTCT rate 0.4%; 95% CI 0.04-1.29). CONCLUSIONS: Our findings suggest that elective CS prevents MTCT even at low maternal viral loads, but the study was insufficiently powered to enable a conclusion to be drawn as to whether this applies for viral loads <50 copies/mL. Diverging mode of delivery patterns in Europe reflect uncertainties regarding the risk-benefit balance of elective CS for women on successful HAART.
Keywords: Adult; Antiretroviral Therapy, Highly Active; Cesarean Section; Delivery, Obstetric; Epidemiologic Methods; Europe; Female; HIV Infections; Humans; Infant; Infant, Newborn; Infectious Disease Transmission, Vertical; Pregnancy; Pregnancy Complications, Infectious; Premature Birth; Prenatal Care; Reverse Transcriptase Inhibitors; Substance Abuse, Intravenous; Viral Load; Young Adult; Zidovudine

Molecular surveillance of pandemic influenza A(H1N1) viruses circulating in Italy from May 2009 to February 2010: association between haemagglutinin mutations and clinical outcome. - Puzelli, S; Facchini, M; De Marco, M A; Palmieri, A; Spagnolo, D; Boros, S; Corcioli, F; Trotta, D; Bagnarelli, P; Azzi, A; Cassone, A; Rezza, G; et al. (Euro Surveill, 2010)
Haemagglutinin sequences of pandemic influenza A(H1N1) viruses circulating in Italy were examined, focusing on amino acid changes at position 222 because of its suggested pathogenic relevance. Among 169 patients, the D222G substitution was detected in three of 52 (5.8%) severe cases and in one of 117 (0.9%) mild cases, whereas the D222E mutation was more frequent and evenly distributed in mild (31.6%) and severe cases (38.4%). A cluster of D222E viruses among school children confirms reported human-to-human transmission of viruses mutated at amino acid position 222.
Keywords: Adolescent; Adult; Age Distribution; Aged; Amino Acid Substitution; Child; Child, Preschool; Female; Hemagglutinins; Humans; Infant; Influenza A Virus, H1N1 Subtype; Influenza, Human; Italy; Male; Middle Aged; Mutation; Pandemics; Population Surveillance; Reverse Transcriptase Polymerase Chain Reaction; Severity of Illness Index; Sex Distribution; Young Adult

Natural isoprenoids inhibit LPS-induced-production of cytokines and nitric oxide in aminobisphosphonate-treated monocytes. - Marcuzzi, Annalisa; Tommasini, Alberto; Crovella, Sergio; Pontillo, Alessandra (Int Immunopharmacol, 2010)
The inhibition of mevalonate pathway through genetic defects (mevalonate kinase deficiency, MKD) or pharmacologic drugs (aminobisphosphonates) causes a shortage of intermediate compounds and, in particular, of geranylgeranyl-pyrophosphate (GGPP) associated to the activation of caspase-1 and IL-1beta release. Geraniol (GOH), farnesol (FOH), geranylgeraniol (GGOH) and menthol (MOH), due to their isoprenoid structure, are supposed to enter the mevalonate pathway and to by-pass the biochemical block, reconstituting the pathway. Considering the already known side effects of aminobisphosphonates, and the lack of a specific treatment for MKD, we evaluated the impact of these natural isoprenoids compounds in a RAW cell lines chemically treated with the aminobisphosphonate alendronate, and in monocytes isolated from 2 patients affected by MKD. GOH, FOH, GGOH and MOH were all capable to diminish inflammatory marker levels induced by LPS. These natural isoprenoids could be proposed as novel therapeutic approach for the still orphan drug MKD, but also considered for the evaluation of possible inflammatory side effects of aminobisphosphonates.
Keywords: Animals; Cell Line; Cells, Cultured; Child; Child, Preschool; Cytokines; Diphosphonates; Humans; Inflammation; Interleukin-1beta; Lipopolysaccharides; Male; Mevalonate Kinase Deficiency; Mice; Monocytes; Nitric Oxide; Terpenes

Oxidative stress-based cytotoxicity of delphinidin and cyanidin in colon cancer cells. - Cvorovic, Jovana; Tramer, Federica; Granzotto, Marilena; Candussio, Luigi; Decorti, Giuliana; Passamonti, Sabina (Arch Biochem Biophys, 2010)
Colorectal cancer is the second most frequent cause of cancer death in the western world. Although the prognosis has improved after the introduction of newer anticancer drugs, the treatment of metastatic colorectal cancer still remains a challenge due to a high percentage of drug-resistant tumor forms. We aimed at testing whether anthocyanidins exerted cytotoxicity in primary (Caco-2) and metastatic (LoVo and LoVo/ADR) colorectal cancer cell lines. Both cyanidin and delphinidin, though neither pelargonidin nor malvidin, were cytotoxic in metastatic cells only. The cell line most sensitive to anthocyanidins was the drug-resistant LoVo/ADR. There, cellular ROS accumulation, inhibition of glutathione reductase, and depletion of glutathione could be observed. This suggests that anthocyanidins may be used as sensitizing agents in metastatic colorectal cancer therapy.
Keywords: Anthocyanins; Antioxidants; Apoptosis; Caco-2 Cells; Camptothecin; Cell Line, Tumor; Colonic Neoplasms; Drug Resistance, Neoplasm; Glutathione; Glutathione Reductase; Humans; Oxidants; Oxidative Stress

Progress towards the achievement of MDG4 in the Commonwealth of Independent States: uncertain data, clear priorities. - Cattaneo, Adriano; Gafurov, Ilkhom; Bomestar, Tamara; Bacci, Marianna; Kumar, Sanjiv; Popovic, Dragoslav; Tamburlini, Giorgio (Health Res Policy Syst, 2010)
Data on under five mortality in the twelve countries of the Commonwealth of Independent States show important fluctuations over time due to variations in quality of data, definitions of neonatal deaths and methods of mortality estimation. Despite the uncertainties regarding mortality trends, the analysis of health and social information from different sources offers clues to identify priority areas and key strategic directions for accelerating the achievement of the 4th Millennium Development Goal. Neonatal deaths represent from 40% to over 50% of under five deaths in all these countries. Maternal mortality was above 50 per 100,000 in 2005, despite the good coverage with antenatal care and births assisted by skilled birth attendants. The scanty information on quality of perinatal care indicates widespread substandard care at all levels. Stunting in children under five is above 10% in ten out of twelve countries and coexists with emerging overweight. Exclusivity and duration of breastfeeding fall short of what is recommended. There are important inequalities in child and maternal mortality, malnutrition and access and use of health services within countries. Taken as a whole, the available information clearly indicates that priority should be given to improvement of the health of women in reproductive age and of the quality of perinatal care, including the establishment of reliable data collection systems. To achieve this, action will need to focus on strengthening the capacity of the health system to improve the technical content of service provision, and on improving access and appropriate use of services by the most disadvantaged groups. The involvement of other sectors will be necessary to improve reproductive health and nutrition at community level and to tackle inequity. Comparisons between countries with similar socioeconomic background but different health policies seem to indicate that gradual progression towards universal coverage with essential health care through a national health insurance system is associated with larger reduction of child mortality than troubled transition towards a privatized and unregulated health system.

Rotavirus vaccine efficacy in African and Asian countries. - Tamburlini, Giorgio; Cattaneo, Adriano; Monasta, Lorenzo (Lancet, 2010)
Keywords: Africa; Child; Dysentery; Gastroenteritis; Humans; Rotavirus Infections; Rotavirus Vaccines; Treatment Outcome

Storage of human milk: accepting certain uncertainties. - Davanzo, Riccardo; Travan, Laura; Demarini, Sergio (J Hum Lact, 2010)
Keywords: Food Handling; Humans; Milk, Human; Refrigeration

Structural aspects of plant antimicrobial peptides. - Padovan, Lara; Scocchi, Marco; Tossi, Alessandro (Curr Protein Pept Sci, 2010)
Antimicrobial peptides exert an important role in plant defence and their structure/activity relationship against pathogens is widely described. Although the most striking feature of these antimicrobial peptides is their molecular diversity, they share some common features, such as a relatively low molecular weight, and the presence of a variable number of cysteines residues that contribute to stabilize conserved scaffolds through disulphide bond formation, and can be assigned to different structural classes. Peptides from different classes in some cases act synergistically against pathogens when produced by the same tissue, and contribute to extending defence to a wider range of microbes. In this review we briefly describe the structure of some of the main plant antimicrobial peptide classes: thionins, defensins, lipid transfer proteins, cyclotides and snakins, and how they are reported to contribute to the plant protection. In many cases these antimicrobial peptides show a wider activity spectrum than that suggested by their name, exerting an action also against predatory insects and revealing useful antiviral activities. This extends their interest from defense of important food crops also to the design of novel anti-infective compounds for both pharmaceutical and agricultural applications.
Keywords: Amino Acid Sequence; Antimicrobial Cationic Peptides; Molecular Sequence Data; Plant Proteins; Plants; Sequence Alignment

Targeting farnesyl-transferase as a novel therapeutic strategy for mevalonate kinase deficiency: in vitro and in vivo approaches. - De Leo, Luigina; Marcuzzi, Annalisa; Decorti, Giuliana; Tommasini, Alberto; Crovella, Sergio; Pontillo, Alessandra (Pharmacol Res, 2010)
Mevalonate kinase deficiency (MKD) is a rare inborn auto-inflammatory disease due to the impairment of the pathway for the biosynthesis of cholesterol and non-sterol isoprenoids. The shortage of isoprenoids compounds and in particular of geranylgeranylpyrophosphate (GGPP) was recently associated to the MKD characteristic inflammatory attacks. The aim of this study is to demonstrate that the normalization of the mevalonate pathway intermediates levels and in particular of GGPP, through the specific inhibition of farnesyl-transferase (FT) with Manumycin A could ameliorate the inflammatory phenotype of MKD patients. The effect of Manumycin A was first evaluated in MKD mouse and cellular models, chemically obtained using the aminobisphosphonate alendronate (ALD), and then in monocytes isolated from 2 MKD patients. Our findings were compared to those obtained by using natural exogenous isoprenoids (NEIs). Manumycin A was able to significantly reduce the inflammatory marker serum amyloid A in ALD-treated Balb/c mice, as well as IL-1 beta secretion in ALD-monocytes and in MKD patients. These results clearly showed that, through the inhibition of FT, an increased number of mevalonate pathway intermediates could be redirected towards the synthesis of GGPP diminishing the inflammatory response. The importance in limiting the shortage of GGPP was emphasized by the anti-inflammatory effect of NEIs that, due to their biochemical structure, can enter the MKD pathway. In conclusion, manumycin A, as well as NEIs, showed anti-inflammatory effect in MKD models and especially in MKD-monocytes, suggesting novel approaches in the treatment of MKD, an orphan disease without any efficacious treatment currently available.
Keywords: Adult; Animals; Anti-Inflammatory Agents; Cells, Cultured; Child, Preschool; Enzyme Inhibitors; Farnesyltranstransferase; Female; Humans; Male; Mevalonate Kinase Deficiency; Mevalonic Acid; Mice; Mice, Inbred BALB C; Monocytes; Polyenes; Polyisoprenyl Phosphates; Polyunsaturated Alkamides; Young Adult

Therapeutic strategy in p47-phox deficient chronic granulomatous disease presenting as inflammatory bowel disease. - Freudenberg, Folke; Wintergerst, Uwe; Roesen-Wolff, Angela; Albert, Michael H; Prell, Christine; Strahm, Brigitte; Koletzko, Sibylle; Ehl, Stephan; Roos, Dirk; Tommasini, Alberto; Ventura, Alessandro; Belohradsky, Bernd H; et al. (J Allergy Clin Immunol, 2010)
Keywords: Age of Onset; Anti-Bacterial Agents; Antibodies, Monoclonal; Child; Drug Therapy, Combination; Gene Deletion; Granulomatous Disease, Chronic; Humans; Inflammatory Bowel Diseases; Male; NADPH Oxidase; Steroids; Treatment Outcome; Vidarabine

Thirty new loci for age at menarche identified by a meta-analysis of genome-wide association studies. - Elks, Cathy E; Perry, John R B; Sulem, Patrick; Chasman, Daniel I; Franceschini, Nora; He, Chunyan; Lunetta, Kathryn L; Visser, Jenny A; Byrne, Enda M; Cousminer, Diana L; Gudbjartsson, Daniel F; Esko, Tõnu; et al. (Nat Genet, 2010)
To identify loci for age at menarche, we performed a meta-analysis of 32 genome-wide association studies in 87,802 women of European descent, with replication in up to 14,731 women. In addition to the known loci at LIN28B (P = 5.4 × 10⁻⁶⁰) and 9q31.2 (P = 2.2 × 10⁻³³), we identified 30 new menarche loci (all P < 5 × 10⁻⁸) and found suggestive evidence for a further 10 loci (P < 1.9 × 10⁻⁶). The new loci included four previously associated with body mass index (in or near FTO, SEC16B, TRA2B and TMEM18), three in or near other genes implicated in energy homeostasis (BSX, CRTC1 and MCHR2) and three in or near genes implicated in hormonal regulation (INHBA, PCSK2 and RXRG). Ingenuity and gene-set enrichment pathway analyses identified coenzyme A and fatty acid biosynthesis as biological processes related to menarche timing.
Keywords: Adolescent; Aging; Body Height; Body Size; Child; DNA Copy Number Variations; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inheritance Patterns; Menarche; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Time Factors

Transmission of hemagglutinin D222G mutant strain of pandemic (H1N1) 2009 virus. - Puzelli, Simona; Facchini, Marzia; Spagnolo, Domenico; De Marco, Maria A; Calzoletti, Laura; Zanetti, Alessandro; Fumagalli, Roberto; Tanzi, Maria L; Cassone, Antonio; Rezza, Giovanni; Donatelli, Isabella (Emerg Infect Dis, 2010)
A pandemic (H1N1) 2009 virus strain carrying the D222G mutation was identified in a severely ill man and was transmitted to a household contact. Only mild illness developed in the contact, despite his obesity and diabetes. The isolated virus reacted fully with an antiserum against the pandemic vaccine strain.
Keywords: Adult; Amino Acid Substitution; Disease Outbreaks; Hemagglutinin Glycoproteins, Influenza Virus; Humans; Influenza A Virus, H1N1 Subtype; Influenza, Human; Male; Middle Aged; Mutation, Missense; Phylogeny; Retrospective Studies; RNA, Viral; Sequence Analysis, RNA; Severity of Illness Index

Treatment with recombinant tumor necrosis factor-related apoptosis-inducing ligand alleviates the severity of streptozotocin-induced diabetes. - Zauli, Giorgio; Toffoli, Barbara; di Iasio, Maria Grazia; Celeghini, Claudio; Fabris, Bruno; Secchiero, Paola (Diabetes, 2010)
OBJECTIVE: To evaluate the potential therapeutic effect of recombinant human tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) treatment in a model of type 1 diabetes. RESEARCH DESIGN AND METHODS: Recombinant TRAIL was added in vitro to primary human and mouse peripheral blood mononuclear cells (PBMCs) and isolated human islets to evaluate the expression of the immunoregulatory gene SOCS1. Diabetes was induced by five consecutive daily injections of low-concentration (50 mg/kg) streptozotocin (STZ) in C57 black mice (n = 24). A group of these mice (n = 12) was co-injected with recombinant TRAIL (20 microg/day) for 5 days, and the diabetic status (glycemia and body weight) was followed over time. After 6 weeks, circulating levels of insulin, TNF-alpha, and osteoprotegerin (OPG) were measured, and animals were killed to perform the histological analysis of the pancreas. RESULTS: The in vitro exposure of both PBMCs and human islets to recombinant TRAIL significantly upregulated the expression of SOCS1. With respect to STZ-treated animals, mice co-injected with STZ+TRAIL were characterized by 1) lower levels of hyperglycemia, 2) higher levels of body weight and insulinemia, 3) a partial preservation of pancreatic islets with normal morphology, and 4) a lower expression of both systemic (TNF-alpha and OPG) and pancreatic (vascular cell adhesion molecule [VCAM]-1) inflammatory markers. CONCLUSIONS: Overall, these data demonstrate that the administration of recombinant TRAIL ameliorates the severity of STZ-induced type 1 diabetes, and this effect was accompanied by the upregulation of SOCS1 expression.
Keywords: Animals; Cells, Cultured; Diabetes Mellitus, Experimental; Gene Expression; Humans; Islets of Langerhans; Leukocytes, Mononuclear; Mice; Recombinant Proteins; Suppressor of Cytokine Signaling Proteins; TNF-Related Apoptosis-Inducing Ligand

The universe of immune deficiencies in Crohn's disease: a new viewpoint for an old disease? - Tommasini, Alberto; Pirrone, Angela; Palla, Gabriella; Taddio, Andrea; Martelossi, Stefano; Crovella, Sergio; Ventura, Alessandro (Scand J Gastroenterol, 2010)
Crohn's disease (CD) is generally considered a multifactorial disorder, since different genetic and environmental factors are thought to play a role in its pathogenesis. Recently, genome wide linkage studies allowed to identify the association of several loci with the increased risk of CD, although it is still unclear how they interact with environmental factors in causing the disease. The fact that many CD-risk-related genes are involved in the function of phagocytes seems in agreement with the well known role of these cells in CD histopathology. Functional defects in cytokine production or in clearance of bacteria in CD patients have recently been reported. Growing evidence that CD could arise from primary phagocyte immunodeficiency is also coming from the study of cases with early onset in infancy. We review such evidences starting from selected cases and discuss the clinical implications of these findings.
Keywords: Biological Markers; Crohn Disease; Cytokines; Evidence-Based Medicine; Granulomatous Disease, Chronic; Hematopoietic Stem Cell Transplantation; Humans; Immunosuppressive Agents; Phagocytes; Treatment Outcome; Wiskott-Aldrich Syndrome

Use of ketamine continuous infusion for pediatric sedation in septic shock. - Barbi, Egidio; Rizzello, Elisa; Taddio, Andrea (Pediatr Emerg Care, 2010)
Keywords: Anesthetics, Dissociative; Child; Conscious Sedation; Humans; Infusions, Intravenous; Ketamine; Male; Shock, Septic

Formate assay in body fluids: application in methanol poisoning. - Makar, A B; McMartin, K E; Palese, M; Tephly, T R (Biochem Med, 1975)
Keywords: Aldehyde Oxidoreductases; Animals; Body Fluids; Carbon Dioxide; Formates; Haplorhini; Humans; Hydrogen-Ion Concentration; Kinetics; Methanol; Methods; Pseudomonas